The Legal Appraisal of the Nature of Liability of Land Transport Operators in Cases of Accidents in Cameroon - Kombo, Kutiefe Umaro (International Multilingual Journal of Science and Technology, 2026)
Land transport operators in Cameroon can be criminally and civilly liable as a result of an accident resulting from their actions. This is provided for in section 289(1) of the penal code1. The criminal liability can be either in tort law, like in negligence, vicarious liability and strict liability, as well as under contract law. The criminal liability can be for an imprisonment term, the payment of a fine, or loss of life or destruction of property. However, the nature of liability in cases of accidents is faced with problems in Cameroon, as the cases suffer from continuous delay before the courts, weak sanctions provided in the penal code and more. This paper sets out to examine the efficiency of the nature of liability of transport operators in cases of accidents in Cameroon. A doctrinal research method has been adopted where the researcher has analyzed both primary and secondary sources of information. The primary sources are the laws and cases decided by courts, while the secondary sources are other write up which the researcher consulted to complete the research paper. Our findings reveal that the laxity of the courts and weak sanctions provided by the Penal code affects the effectiveness of the liability regime for transport operators in cases of accidents. We recommend that the penal code be revised and a more stringent criminal sanction be put in place. Also, a separate court system should be set up for disputes related to accidents to solve the problem of continuous delay before the courts.
Keywords: Accidents; Land Transport Operators; Nature of Liability; Responsabilité; Transport par route; Transporteur

The ordinary life of exceptional justice : procedural law in transition - Muñoz, Anamaria (Institut d'études politiques de Paris - Sciences Po, 2026)
This dissertation interrogates the extraordinary character of transitional justice as a legal project. My central claim is that treating procedure as dispensable in pursuit of expansive transformative goals is a disservice to the project itself. The prevailing assumption among scholars and practitioners has been that the existential battles of a transition are fought and won at the macro level: in the text of peace agreements, in constitutional amendments, or in grand normative commitments to truth, justice, and reparation. I show that some of the most consequential distributions of power take place elsewhere: in the granular procedural rules that govern how tribunals operate in practice. Procedural analysis serves here as both method and argument, disaggregating legal rules to reveal who bears costs and who captures benefits, and exposing how procedural opacity creates space for alternative sources of law to emerge. I contend that the exception in exceptional justice should not extend to procedural rigor, and that holding transitional tribunals to the same standards as any other apex court is not a limitation on what transitional justice can achieve, but the condition under which its achievements can be considered legitimate. Taken together, these moves advance a broader theoretical claim: that transitional justice sustains and reinforces the very same distributive arrangements as ordinary justice, rather than disrupting them. I develop these arguments by examining transitional justice in the Colombian 2016 peace process - one of the few ongoing transitional justice processes in the world, and therefore an important site for observing the legal project of transition in motion rather than in retrospect. I engage with Colombia as a matter of epistemic justice: my political commitment is that Latin America is not merely a recipient of international legal frameworks developed elsewhere but an important site in their production. I do not take Colombia as my object because it is exceptional. I take it because the claim that it is, and what that claim conceals, is precisely what this dissertation contests. Cette thèse interroge le caractère extraordinaire de la justice transitionnelle en tant que projet juridique. Mon argument central est que traiter la procédure comme accessoire, au nom d'objectifs transformateurs ambitieux, dessert le projet lui-même. L'hypothèse dominante a été que les batailles décisives d'une transition se gagnent au niveau macro : dans les accords de paix, les réformes constitutionnelles, les grands engagements normatifs en faveur de la vérité et de la réparation. Je montre que certaines des distributions de pouvoir les plus importantes se jouent ailleurs : dans les règles procédurales qui gouvernent le fonctionnement concret des tribunaux. L'analyse procédurale est ici à la fois méthode et argument : elle désagrège les règles juridiques pour révéler qui supporte les coûts et qui capte les bénéfices, et met en évidence comment l'opacité procédurale crée un espace pour l'émergence de sources alternatives du droit. Je soutiens que l'exception dans la justice exceptionnelle ne devrait pas s'étendre à la rigueur procédurale, et que soumettre les tribunaux transitionnels aux mêmes exigences que tout autre tribunal de rang supérieur n'est pas une limite à ce que la justice transitionnelle peut accomplir, mais la condition sous laquelle ses accomplissements peuvent être considérés comme légitimes. Ces arguments avancent une thèse théorique plus large : la justice transitionnelle maintient et renforce les mêmes distributions que la justice ordinaire, plutôt que de les remettre en cause. Je les développe en examinant le processus de paix colombien de 2016 - terrain privilégié pour observer la transition en train de se faire. J'aborde la Colombie comme une question de justice épistémique : l'Amérique latine n'est pas simplement destinataire de cadres juridiques élaborés ailleurs, mais un lieu important de leur production.
Issue: 2026IEPP0015
Keywords: Courts; Criminal law; Droit procédural; Droit pénal; Justice transitionnelle; Procedural law; Transitional justice; Tribunaux

Quels sont les effets des recettes pétrolières sur le capital humain en zone CEMAC ? - Fompehou, Amadou (MPRA Paper, 2026)
This article examines the effects of oil revenues on human capital in CEMAC countries over the period 1995–2020. The study is based on a dynamic panel of five countries (Cameroon, Congo, Gabon, Equatorial Guinea and Chad). The data are sourced from the IMF, the World Bank (WDI), the UNDP and the Worldwide Governance Indicators (WGI). The author employs the Blundell and Bond (1998) GMM system estimator to address the endogeneity and persistence of human capital, supplemented by interaction term models and robustness tests (stationarity, cross-sectional dependence). The analyses reveal a negative or non-significant effect of oil revenues on human capital indicators (school enrolment, life expectancy, HDI-education). Institutional quality acts as a powerful positive moderator, whilst revenue volatility has a detrimental effect. These results highlight the need for better governance, stabilisation funds and a more efficient allocation of oil revenues towards education and health.
Number: 129352
Keywords: Human capital; Institution; Oil revenue

Access to social rights for temporary labour migrant women in the EU : an intersectional perspective on seasonal and posted workers in France and Spain - Deverson, Audrey (Université de Strasbourg, 2026)
Temporary labour migration constitutes both a historical phenomenon and an enduring central issue within the European Union. This thesis adopts a socio-legal approach to analyse the cases of France and Spain, focusing on seasonal work and posting of workers in the agricultural sector. It examines the experiences of temporary migrant women workers at the intersection of migration law and labour and social security law, in particular with regard to social security. Drawing on an intersectional perspective articulated around the concept of vulnerability, this research highlights the structuring role of law in these women’s experiences. This thesis demonstrates that the applicable legal framework contributes to reinforcing their vulnerability by establishing a system of exclusion and invisibilisation based on migration status, employment status and a gendered and racialised labour division, thereby limiting these women’s effective access to rights linked to their participation in the labour market, such as unemployment benefits, as well as to those relating to their reproductive lives. La migration temporaire de travail constitue à la fois un phénomène historique et un enjeu toujours central au sein de l’Union européenne. Cette thèse analyse, dans une perspective sociojuridique, les cas de la France et de l’Espagne, en se concentrant sur le travail saisonnier et le travail détaché dans le secteur agricole. Elle examine l’expérience des travailleuses migrantes temporaires à l’intersection du droit des migrations et du droit social, notamment en matière de sécurité sociale. Mobilisant une perspective intersectionnelle articulée au concept de vulnérabilité, cette recherche met en lumière le rôle structurant du droit dans l’expérience de ces femmes. La thèse démontre que le cadre juridique applicable contribue à renforcer leur situation de vulnérabilité en instaurant un système d’exclusion et d’invisibilisation fondé sur le statut migratoire, le statut d’emploi, et une division du travail genrée et racialisée, limitant ainsi l’accès effectif de ces femmes aux droits liés à leur participation au marché du travail, tels que le droit au chômage, ainsi qu’à ceux relatifs à leur vie reproductive.
Keywords: Agriculture; Approches sociojuridiques; Droit au chômage; Droit de l’UE; Droits économiques et sociaux; Espagne; European Union law; France; Intersectionality; Intersectionnalité; Justice reproductive; Migration temporaire de travail; Pays de l'Union européenne; Posting of workers; Protection sociale; Reproductive justice; Seasonal work; Social protection; Socio-Legal studies; Spain; Statut juridique; Temporary labour migration; Travail détché; Travail saisonnier; Travailleuses étrangères; Unemployment benefits; Vulnerability; Vulnérabilité; Émigration et immigration

The Role of the Institutions Put in Place to Protect and Promote Land Acquisition in Cameroon: A Critical Analysis - Bate, Racheal Arrah Oben (International Multilingual Journal of Science and Technology, 2026)
The protection and promotion of land acquisition in Cameroon is ensured through a number of legal and administrative institutions established by the State to regulate land ownership, guarantee security of tenure and ensure land transactions are conducted in accordance with the law. These institutions operate within the framework established by the 1974 Land Ordinances, which reorganized the Land tenure system and create mechanisms for the management and allocation of land. Key institutions such as the Ministry of State Property, Surveys and Land Tenure, Land Consultative Boards, local administrative authorities and the courts play significant roles in supervising land registration, resolving disputes and ensuring that the procedures for acquiring both private and public land are respected. Despite the important, the effectiveness of these institutions is sometimes challenged by administrative delays and corruption. Nevertheless, their existence remains fundamental in promoting secure land tenure, facilitating lawful land transactions and strengthening confidence in the administration system in Cameroon. This article is based on the hypothetical premise that the role the institutions put in place to protect and promote land acquisition in Cameroon is ineffective. It seeks to examine the effectiveness of the role of the institutions in protecting and promoting land acquisition. Adopting the Doctrinal research method, the paper concludes that with improved coordination, institutional reforms, greater transparency and stronger enforcement of land laws, these bodies can more effectively fulfil their mandate of ensuring secure land tenure, reducing land disputes and encouraging sustainable land development and investment in Cameroon.
Keywords: Cameroon; Institutions; Land Acquisition; Promotion; Protection

Arbitration and state sovereignty in commercial disputes resolution within ohada laws - Buma, Roland Sigala; Biya, Fabilou (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Long ago before the creation of the state courts, men had resorted to arbitration for the resolution of diputes. Today, based on the principle of monopoly of the state to render justice, the power to judge is given only to the state. Rendering of justice is one of the areas where the state exeercises its sovereign powers. This has made us to ask the question : is arbitration a violation of the sovereignty of the state in the domain of dispute resolution ? Arbitration is not a violation of the sovereign powers of the state because, it is not all disputes that are resolved via arbitration (for example, crimnal, tax disputes etc can not be settled via arbitration) and the state courts intervene in arbitratin when ever it is necessary. The sate courts intervene in arbitration to grant exequatur, order interim mesaures etc. Nonetheless, since OHADA legislator has not given a complete list of all disputes that can not be resolve via arbitration, we recomend that OHADA should provide a list of all disputes whcih can be settle via arbitration as it is the case with the Arbitration Act of Zimbabw. This article aims at identifying those cases that can not be settled by way of arbitration and those instances in which the state courts intervene in arbitration. Avant la création des tribunaux étatiques, les hommes ont eu recours à l'arbitrage pour la résolution des litiges. Aujourd'hui, sur la base du principe du monopole de l'État à rendre la justice, le pouvoir de juger n'est conféré qu'à l'État. Le fait de rendre la justice est l'un des domaines dans lesquels l'État exerce ses pouvoirs souverains. Cela nous a amenés à poser la question : l'arbitrage constitue-t-il une violation de la souveraineté de l'État dans le domaine du règlement des différends ? L'arbitrage n'est pas une violation des pouvoirs souverains de l'État car, d'une part, tous les litiges ne sont pas résolus par voie d'arbitrage (par exemple, les litiges pénaux, fiscaux, etc. ne peuvent pas être réglés par arbitrage) et, d'autre part, les tribunaux étatiques interviennent dans l'arbitrage chaque fois que cela est nécessaire. Les tribunaux étatiques interviennent dans l'arbitrage pour accorder l'exequatur, ordonner des mesures provisoires, etc. Néanmoins, étant donné que le législateur de l'OHADA n'a pas établi une liste exhaustive de tous les litiges qui ne peuvent pas être résolus par arbitrage, nous recommandons que l'OHADA fournisse une liste de tous les litiges qui peuvent être réglés par voie d'arbitrage, comme c'est le cas dans la loi sur l'arbitrage du Zimbabwe. Cet article vise à identifier les litiges qui ne peuvent pas être réglés par voie d'arbitrage ainsi que les situations dans lesquelles les tribunaux étatiques interviennent dans l'arbitrage.
Keywords: Arbitrage; Arbitrage commerciale; Arbitragem; Arbitraje; Arbitration; Commercial disputes; Droit OHADA; Litiges commerciaux; OHADA law; Souveraineté; Sovereignty

A legal appraisal of the minimum wage policy in the private formal sector and sustainable livelihood in urban centres in Cameroon: the case of Buea - Akamin Asonga, Patrick (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
This paper analyses the minimum wage as an instrument to provide a sustainable livelihood for employees and their families. In addressing this topic, the paper questions whether the present- day minimum wage of the country can actually enhance a sustainable livelihood for workers and their families in urban centres in general, and in the Buea municipality in particular. The paper further examines the relevant international and domestic instruments, such as the ILO Minimum Wage Fixing Convention No. 131 and the 1992 Labour Code of Cameroon. Findings reveal that the current minimum wage, which stands at 43,969 FRS, is grossly inadequate and does not match the prices of basic commodities needed for survival in the country as a whole and in Buea specifically. This, therefore, necessitates an increase in the current minimum wage. Given this situation, workers struggle to attain a sustainable livelihood. A new minimum wage policy considering Cameroon’s current economic situation could alleviate the suffering of these workers. Cet article analyse le salaire minimum en tant qu’instrument permettant d’assurer des moyens de substance durable aux travailleurs et leurs familles. Abordant cette problématique, l’étude s’interroge sur la capacité du salaire minimum actuellement en vigueur dans le pays à garantir effectivement un niveau de vie durable aux travailleurs et à leurs familles dans les centres urbains en général, et dans la municipalité de Buea en particulier. L’article examine en outre les instruments internationaux et nationaux pertinents, tel que la Convention (n° 131) de l’OIT sur la fixation des salaires minima et le Code du travail camerounais de 1992. Les résulta révèlent que le salaire minimum actuel, fixé à 43,969 FCFA est largement insuffisant, et ne correspond pas au coût des produits de première nécessité indispensables à la survie, tant a l’échelle nationale qu’à Buea en particulier. Cette situation rend donc nécessaire une revalorisation du salaire minimum en vigueur. Dans ces conditions, les travailleurs éprouvent de sérieuses difficultés à atteindre des moyens de subsistance durables. L’adoption une nouvelle politique de salaires minimum, tenant compte de la situation économique actuelle du Cameroun, pourrait contribuer à atténuer les souffrances de ces travailleurs.
Keywords: Appréciation juridique; Cameroon; Cameroun; Legal Appraisal; Minimum Wage Policy; Moyens de Substance durables; Politique du salaire minimum; Private Formal Sector; Secteur formels privés; Sustainable Livelihood

Artificial Intelligence of Everything (AIoE) in energy sectors : cybersecurity, data protection, and data localization - Mohaghegh Montazeri, Leila (Université de Montréal, 2026)
L'Internet est devenu une partie essentielle de la vie moderne. Un développement important est «l'Internet des objets» (IoT), qui connecte des dispositifs physiques à Internet. Plus récemment, un concept plus large est apparu: «l'Internet de tout» (IoE), intégrant quatre composantes, les personnes, les processus, les données et les objets. L'ajout de l'intelligence artificielle (IA) à l'IoE a donné naissance à «l'Intelligence Artificielle de Tout» (IAdT). Cette combinaison offre des avantages significatifs pour le secteur de l'énergie en optimisant la production, la distribution et la consommation d'énergie. Cependant, elle soulève également des défis critiques en matière de protection des données, de cybersécurité et de localisation des données. Dans cette thèse, j'explore comment les gouvernements et les entreprises énergétiques peuvent collaborer pour répondre aux risques liés à la confidentialité et à la cybersécurité des technologies IAdT. J'analyse également les exigences de localisation des données et j'examine les cadres réglementaires pertinents, en particulier au sein de l'Union européenne (avec un accent sur l'Irlande) et au Canada (y compris la province de l'Ontario). The Internet has become an essential part of modern life. One significant development is the “Internet of Things” (IoT), which connects physical devices to the Internet. More recently, a broader concept has emerged: the “Internet of Everything” (IoE), which integrates four key components: people, processes, data, and things. The addition of artificial intelligence (AI) to IoE has given rise to the "Artificial Intelligence of Everything" (AIoE). This combination offers significant benefits to the energy sector by optimizing energy production, distribution, and consumption. However, it also introduces critical challenges related to data protection, cybersecurity, and data localization. In this thesis, I explore how governments and energy companies can collaborate to address privacy and cybersecurity risks associated with AIoE technologies. I also analyze data localization requirements and review relevant regulatory frameworks, particularly within the European Union (with a focus on Ireland) and Canada (including the province of Ontario).
Intelligence Artificielle du Tout (AIoE) dans les secteurs de l’énergie : Cybersécurité, protection des données et localisation des données
Keywords: Artificial Intelligence; Artificial Internet of Everything (AIoE); Cybersecurity; Cybersécurité; Data Localization; Data Protection; Energy Industry; Intelligence artificielle; Internet artificiel de tout; Internet des objets; Internet of Things (IoT); Localisation des données; Protection des données; Secteur de l’énergie

Combating trafficking in persons in Africa: efforts and enforcement challenges - Tamfuh, Wilson N.; Awa Njoworia, Valerie Adamu (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Recently, human trafficking has been on a rise with African states fighting to put an end to the crime by protecting victims, prosecuting culprits and collaborating with other partners. As a giant step towards fighting this crime, many African states ratified the Palermo Protocol, Ouagadougou Action Plan, domesticated trafficking laws and put in place institutions. Despite these efforts, trafficking in persons remain a persistent crime due to conflicts, poverty, unemployment and corruption, which increase the vulnerability of persons within and from Africa. Adopting a doctrinal research method, this paper questions the effectiveness of African States’ efforts to protect, prosecute and prevent this crime in and from Africa. It concludes that, while African states must be applauded for their efforts to protect, prosecute and collaborate with other states and organizations to combat this crime, much still remains to be done. This is due to the existence of factors like poverty, unemployment that create vulnerabilities and enforcement challenges like corruption, victim identification, delays in cross-border collaboration and weak legal frameworks. African states should therefore address underlying socio-economic factors, strengthen their domestic legal frameworks and enhance international cooperation to fully combat this crime. Récemment, la traite des êtres humains a connu une recrudescence, et les États Africains s'efforcent d'y mettre fin en protégeant les victimes, en poursuivant les auteurs et en collaborant avec d'autres partenaires. Dans le cadre de cette lutte, de nombreux États Africains ont ratifié le Protocole de Palerme et le Plan d'action de Ouagadougou, intégré des lois nationales relatives à la traite et mis en place des institutions spécialisées. Malgré ces efforts, la traite des personnes demeure un crime persistant en raison des conflits, de la pauvreté, du chômage et de la corruption, qui accroissent la vulnérabilité des personnes en Afrique et en provenance d'Afrique. Adoptant une méthode de recherche doctrinale, cet article examine l'efficacité des efforts déployés par les États Africains pour protéger, poursuivre et prévenir ce crime sur leur territoire et à partir de leur territoire. Il conclut que, alors que les États Africains doivent être salués pour leurs efforts de protection, de poursuite et de collaboration avec d'autres États et organisations pour combattre ce crime, il reste encore beaucoup à faire. Ceci s'explique par l'existence de facteurs tels que la pauvreté et le chômage, qui créent des vulnérabilités, et par des difficultés d'application de la loi comme la corruption, l'identification des victimes, les retards dans la collaboration transfrontalière et la faiblesse des cadres juridiques. Les États africains devraient donc s'attaquer aux facteurs socio économiques sous-jacents, renforcer leurs cadres juridiques nationaux et intensifier la coopération internationale afin de lutter pleinement contre ce crime.
Keywords: African States; Corruption; Palermo protocol; Pauvreté; Poverty; Protocole de Palerme; Trafficking in persons; Traite des personnes; États Africains

Artifical intelligence and international arbitration law: revolution or evolution - Łągiewska, Magdalena (Taylor & Francis, 2026)
The book asks whether the use of Artificial Intelligence (AI) and Generative AI (GenAI) in international arbitration represents a revolution or an evolution of the international dispute resolution landscape. Critically engaging with the transformative impact of the Fourth Industrial Revolution (4IR), this book focuses on the integration of AI and GenAI into international commercial arbitration. Set against the backdrop of rapid technological advancement, it explores how arbitral tribunals and stakeholders are cautiously yet progressively adopting these innovations in a manner that respects and preserves the foundational principles of arbitration. Through an interdisciplinary and practice-oriented approach, the book examines the evolving role of AI in arbitration. It analyzes how AI is perceived and applied by parties, arbitral institutions, and arbitrators, as well as assesses the legal frameworks in place to govern it. Offering a balanced analysis of both the opportunities and legal and ethical dilemmas posed by emerging technologies, the book asks if a duty of disclosure is relevant in relation to AI use, and what challenges this might entail. It also covers the status of AI-generated arbitral awards under international law, as well as copyright law. This book will be of interest to researchers in the field of international arbitration and commercial law
Keywords: Arbitrage; Artificial Intelligence; Convention on the Recognition and Enforcement of Foreign Arbitral Awards (1958); Intelligence artificielle; International commercial arbitration; UNCITRAL Model Law on International Commercial Arbitration (1985)

Social media and structural injustice : a critical analysis of EU platform regulation - Griffin, Rachel (Institut d'études politiques de Paris - Sciences Po, 2025)
Cette thèse examine le traitement par la régulation européenne de la problématique des injustices structurelles sociales liées aux grands réseaux sociaux. Pour ce faire, elle opère une synthèse de nombreuses recherches empiriques qui mettent en évidence les inégalités dans la gouvernance des contenus, et s'appuie sur des perspectives théoriques tirées de la philosophie politique, de la théorie juridique féministe, et des recherches en droit et économie politique. Elle présente trois lignes d'argumentation principales. Premièrement, le droit européen n'empêche pas les injustices telles que la discrimination dans la modération, les violences en ligne, ou la visibilité inégale des différents groupes sociaux, parce qu'il conceptualise ces inégalités d'une manière individualiste et formaliste, visant à protéger les droits d'individus particuliers et à assurer l'application des règles prédéfinies, tout en ignorant la nature systémique des inégalitésDeuxièmement, le droit contribue souvent activement aux injustices : par exemple, en permettant aux agences policières de demander la suppression des contenus pour des raisons politiques. Troisièmement, les aspects du cadre réglementaire qui sont perçus comme les plus à même de combattre les inégalités systémiques, à savoir les obligations autour de la gestion des risques et les principes des droits de l'homme, se révèlent en réalité peu capables d'empêcher les injustices structurelles. Ces deux éléments restent en effet inscrits dans un paradigme de régulation technocratique, dépolitisée, et favorable au marché, et excluent toute contestation réelle du pouvoir ou des pratiques commerciales des plateformes de « big tech ». This thesis analyses EU regulation of social media content governance, focusing on how the law addresses the impacts of the largest platforms on structural social injustice. To do so, it draws on theoretical perspectives from political philosophy, feminist and queer legal theory, and law and political economy, and synthesises a wide range of empirical scholarship that illuminates the unjust impacts of social media platforms' content governance. It makes three main arguments.First, EU law cannot effectively address unjust impacts - such as discriminatory content moderation, online violence, or the unequal visibility of different social groups - because it regulates them in a highly individualistic and formalistic way, focused on protecting individual rights and consistently applying predefined rules, which overlooks systemic inequalities and their connections to underlying political-economic structures. Second, moreover, the law often actively contributes to injustice: for example, by excluding minority perspectives from platform governance, or by making it easier for state institutions to target politically disfavoured content for removal. Third, the two aspects of the legal framework which are widely seen by experts as the most promising levers to address systemic inequalities and power disparities - risk management obligations, and human rights principles - are also incapable of counteracting these problems. They remain limited by a technocratic, depoliticised and marketised regulatory paradigm, which excludes genuine political contestation of the power of 'big tech' platforms to organise online content in line with their own commercial interests.
Issue: 2025IEPP0034
Keywords: Digital law; Droit des technologies de l'information et de la communication; Droit européen; Droit numérique; Eu law; Feminism; Féminisme; Platform regulation; Régulation des plateformes; Réseaux sociaux

An evaluation of China’s securitization regulatory system - Cao, Lei (Université de Montréal, 2025)
Since its innovation as a modern financial product in the 1970s, securitization has swept the global financial market. In 2000s, in order to ease China’s concentrated debt risks in the banking system and to improve the country’s imbalanced financial system, the Chinese government started to promote a trial program of securitization. An associated regulatory system was then created to facilitate the development of the Chinese securitization markets. Unlike regulations drafted and applied in North America, where an ex-ante regulatory analysis procedure and an ex-post evaluation system are installed, the current Chinese securitization regulation system is built mainly upon a basis of trial and interim rules. In other words, Chinese regulations regarding securitization were not comprehensively assessed before their adoption and there has been no systemic ex-post evaluation of the current securitization regulatory system in the past 20 years. This raises the question of whether the Chinese securitization regulation system facilitates the achievement of its regulatory objectives. The author purports to answer this question using three tools: The theory of regulation, legal historical analysis of law, and comparative law. To begin the analysis, the author designs an analytical framework based on the theory of regulation to evaluate Chinese regulations on securitization. In this evaluative framework, perspectives and criteria are stipulated to guide and draw the boundary of the evaluation. While applying the analytical framework, the author reviews the development of the Chinese securitization regulatory system over the past 20 years. The author studies the historical context of regulations established and regulatory modifications adopted in order to assess whether the logic embedded in the current Chinese securitization regulatory system is still valid. To better evaluate the Chinese securitization regulatory system, the author also applies a micro comparison of certain Chinese securitization regulations with their counterparts in North America. The purpose of this comparison is also to understand whether the Chinese characteristics in Chinese securitization regulations facilitate the achievement of its regulatory objectives. At the end of this assessment, the author provides a report to find the merits and disadvantages of Chinese securitization regulatory system. Due to the evaluative nature of this research, no demonstrated solutions are proposed in this report. Depuis sa création dans les années 1970, la titrisation s’est répandue à travers le marché financier mondial. Dans les années 2000, le gouvernement chinois a commencé à promouvoir le programme de titrisation afin d'atténuer les risques liés à la concentration de la dette dans le système bancaire et d'améliorer un système financier déséquilibré. La règlementation associée a été mise en place pour faciliter le développement du marché chinois de la titrisation. Contrairement aux régles créées et appliquées en Amérique du Nord, qui suivent une analyse ex ante —c’est-à-dire avant leur adoption — et une évaluation ex post — soit après leur application pendant une certaine période, le système de réglementation de la titrisation actuellement en vigueur en Chine a été élaboré sur la base d’essais et de mesures provisoires. Autrement dit, la Chine ne s’est pas fondée sur une analyse ex ante approfondie, et n’a mené aucune évaluation systémique ex post de ses réglementations de la titrisation au cours des vingt dernières années. Ce système chinois de réglementation de la titrisation facilite-t-il ou non la réalisation de ses objectifs réglementaires ? L'auteur tente de répondre à cette question à partir de trois outils : la théorie de la réglementation, l’analyse historique du droit et le droit comparé. Pour commencer, l’auteur conçoit un cadre analytique basé sur la théorie de la réglementation pour évaluer les dispositions chinoises en matière de titrisation. Dans ce cadre d’évaluation, des perspectives et des critères sont proposés pour guider et délimiter l’évaluation. À la lumière de ce cadre analytique, l’auteur replace la réglementation chinoise de la titrisation dans son contexte historique et retrace les modifications apportées au cours de deux dernières décennies. Il s’agit ainsi d’évaluer si la logique qui a présidé à l’adoption de ces règles reste valide dans le contexte actuel. Mais pour mieux saisir les caractéristiques de la réglementation chinoise de la titrisation, l’auteur ajoute à cette analyse historique interne à la Chine des micro-comparaisons de la titrisation chinoise et de ses règles avec leurs homologues nord-américains dans différentes sections de cette thèse. C’est ainsi qu’il sera possible de voir si les caractéristiques chinoises de la réglementation en matière de titrisation facilitent ou non la réalisation de ses objectifs. Au terme de cette recherche évaluative, l’on proposera un rapport qui mettra en lumière les avantages et les inconvénients du système chinois. En raison de sa nature évaluative, cette thèse ne proposera aucune solution aux inconvénients repérés.
Keywords: China; Chine; Evaluation of Chinese; Financial Regulation; Marchés chinois; Réglementation financière; Securitization; Securitization Markets; Securitization Regulation; Titrisation; Titrisation (réglementation)

Predictive Artificial Intelligence Tools in the U.S. Criminal Trial : Reflections on Technology and Justice - Ilhan, Mina Ayşe (Université Côte d'Azur, 2025)
Under the aegis of efficiency and neutrality, algorithmic risk-assessment tools have been rapidly inserted into the realm of pretrial justice, promising scientific and objective prediction where presumption of innocence and scarce resources are pitted against each other. Their sprawl has been uneven and confined to looser pretrial rules than would govern similar proof at trial. These systems translate miscellaneous data into scores of “risk,” inviting courts to act on what might happen rather than on what has been proven, within a process already plagued by plea bargaining, racial disparity, and institutional asymmetry. This thesis argues that such tools do not merely constitute information about the defendant; they reorder what counts as usable knowledge and who is treated as a credible knower at the weakest stage of a criminal process. The thesis lays out how scores interact with judicial decision-making; how ostensibly neutral inputs (criminal history, prior contacts, residence, employment) can re-encode social disadvantage; and how opacity and trade-secret claims frustrate fundamental rights such as due process. The doctrinal analysis clarifies the boundary between regulation and punishment under United States v. Salerno, the demands of proportionality, and the significance of the presumption of innocence when decisions are predictive. A brief technical account explains why claims of “explainability” often exceed what such models can reliably demonstrate for legal purposes, but the core argument is juridical: claims of legitimacy must be substantiated by enforceable safeguards; falling short of that, systems described as ‘explainable' or ‘fair' remain as fancy adjectives. The thesis contends that the safeguards that govern the trial must be applied earlier in the criminal process, where liberty is already fragile. Accordingly, the thesis argues for invoking evidentiary rules early on: demonstrating reliability of the tools; reasoned judicial decisions that explain how any score was weighed against case-specific facts; meaningful opportunities for defence challenge; and, where appropriate, access to independent expertise to translate model outputs without displacing judicial authorship. The researcher is of the opinion that these emphases are necessary so that pretrial decisions remain individualised and proportionate and detention retains its status as an exceptional, non-punitive measure. Finally, it defends doubt as a juridical virtue, a disciplined moment of pause that reins in the allure of algorithmic certainty and reasserts judicial responsibility, so that the presumption of innocence and liberty remains the rule even in a predictive age. Sous l'égide de l'efficacité et de la neutralité, les outils algorithmiques d'évaluation du risque ont été rapidement introduits dans le domaine de la justice pré-procès, promettant une prédiction scientifique et objective là où la présomption d'innocence et la rareté des ressources se trouvent mises en tension. Leur déploiement a été inégal et s'est inscrit dans des règles pré-procès plus souples que celles qui régiraient des éléments de preuve similaires au stade du procès. Ces systèmes traduisent des données hétérogènes en scores de « risque », invitant les juridictions à agir en fonction de ce qui pourrait advenir plutôt que de ce qui a été prouvé, au sein d'un processus déjà marqué par le plaider-coupable, les disparités raciales et les asymétries institutionnelles. La présente thèse soutient que de tels outils ne constituent pas seulement une information relative au prévenu ; ils réorganisent ce qui compte comme connaissance mobilisable et déterminent qui est traité comme un sujet crédible de savoir au stade le plus fragile de la procédure pénale. Elle expose la manière dont les scores interagissent avec la prise de décision judiciaire ; comment des variables présentées comme neutres (antécédents judiciaires, contacts antérieurs avec la police, résidence, emploi) peuvent réencoder des désavantages sociaux ; et comment l'opacité ainsi que les revendications de secret commercial entravent des droits fondamentaux tels que le droit à une procédure régulière. L'analyse doctrinale précise la frontière entre régulation et punition au regard de l'arrêt United States v. Salerno, les exigences de proportionnalité et la portée de la présomption d'innocence lorsque les décisions sont de nature prédictive. Un bref exposé technique explique pourquoi les prétentions à « l'explicabilité » excèdent souvent ce que ces modèles peuvent démontrer de manière fiable à des fins juridiques, mais l'argument central demeure juridique : les revendications de légitimité doivent être étayées par des garanties effectives ; à défaut, les systèmes qualifiés d'« explicables » ou d'« équitables » ne demeurent que des adjectifs séduisants. La thèse soutient que les garanties gouvernant le procès doivent être appliquées plus en amont dans le processus pénal, là où la liberté est déjà fragile. En conséquence, elle plaide pour une mobilisation précoce des règles de preuve : démonstration de la fiabilité des outils ; décisions judiciaires motivées expliquant la manière dont tout score a été mis en balance avec les faits propres à l'affaire ; possibilités effectives de contestation par la défense ; et, le cas échéant, accès à une expertise indépendante permettant de traduire les résultats des modèles sans se substituer à l'autorité judiciaire. La chercheuse estime que ces exigences sont nécessaires afin que les décisions pré-procès demeurent individualisées et proportionnées, et que la détention conserve son caractère exceptionnel et non punitif. Enfin, la thèse défend le doute comme une vertu juridique, moment discipliné de suspension qui tempère l'attrait de la certitude algorithmique et réaffirme la responsabilité judiciaire, afin que la présomption d'innocence et la liberté demeurent la règle, y compris à l'ère prédictive.
Issue: 2025COAZ0023
Keywords: Algorithmes; Algorithmes predictifs; Algorithms; Criminal Justice; Intelligence artificielle en droit; Justice criminelle; Justice prédictive; Procès; Risk assessment tools; États-Unis

A framework for bank resolution in Namibia - Eiseb, Bryan Karl Gunther (University of Pretoria, 2025)
Banks are regarded as special financial institutions because, apart from the various critical intermediary and other functions they fulfil in a financial system, the hallmark of their business models is receiving deposits from the public and using such deposits for extending loans against interest from which they make profit. Unlike other companies, banks are however vulnerable to loss of public confidence and remain exposed to various risks and failure. Banks are thus critically important actors in domestic and global financial systems, - thus their safety is critical to the maintenance of financial stability. As a result, banks are subject to stringent regulation and supervision to ensure their safety. Despite prudential regulation, the failure of banks remains a reality. If the risk of bank failure is not adequately addressed through appropriate regulation and supervision, , it may result in a financial crisis like the 2008 Global Financial Crisis (2008 GFC). Because banks play a special role in an economy and their failure may have an adverse impact on financial stability and depositors, this thesis aligns with the view expressed by academics and international organisations that there is a need for a special regime (lex specialis) to deal with the failure of banks since normal insolvency procedures are not suitable for this purpose. f. This is because bank failures require swift, timely intervention by a supervisor to resolve failing banks in an orderly and optimal manner to ensure the maintenance of financial stability, depositor protection and relegating bailouts with taxpayers’ money as a last resort. A very notable lesson that emanated from the 2008 GFC is the criticality of special resolution frameworks for banks; the need to balance the interests of shareholders, creditors, and depositors, while promoting financial stability objectives. As a result, the need for special resolution frameworks for banks which empowers Resolution Authorities with adequate resolution tools and powers to resolve a failing bank timeous and orderly , has become a legislative imperative in contemporary financial systems. To deal with bank failures in Namibia, the Banking Institutions Act, 2 of 1998 (the BIA 1998) contained provisions that allowed for the assumption of control and liquidation of a failed bank. However, the newly enacted Banking Institution Act 13 of 2023 (the BIA 2023 which repealed the BIA 1998) has changed that position and introduced a single provision in section 70 that provides for bank resolution. Until now, prior to the introduction of this very new statutory provision, all bank failures in Namibia were dealt with under the limited supervisory tools of the BIA 1998. This study seeks to determine whether section 70 of the BIA 2023, is sufficiently aligned with international best practice as captured in the Financial Stability Board’s Key Attributes of Effective Resolution Regimes for Financial Institutions (FSB KAs), issued in 2011, as updated in 2014 and 2024. Alternatively, if the regime introduced by the BIA 2023 does not adequately align with the FSB KAs it is then considered whether the new Namibian bank resolution framework requires to be strengthened further to better align it with the FSB KAs. To consider possible further reforms to the new Namibian bank resolution regime, this thesis considers the resolution frameworks in Germany and Nigeria by way of comparative studies to observe best practices.
Keywords: Bank; Financial stability; Key Attributes; Namibia; Resolution

The Interpretation of UNCITRAL Law in Australian Courts: A Roadmap for Elevating the UN Sales Convention’s Status to That of Arbitration Law - Hayward, Benjamin (Sydney Law Review, 2025)
Despite being part of Australian law for more than 30 years, the United Nations Convention on Contracts for the International Sale of Goods (‘CISG’) has not secured the internationally minded interpretation that CISG art 7(1) requires. Australia’s international commercial arbitration (‘ICA’) laws, however, are routinely approached by Australian courts with an internationalist perspective, as their own interpretative rules require. It is tempting to conclude that Australia’s approach to interpreting its ICA laws is transferable to the CISG context. In this article I address a previously unexplored nuance affecting that conclusion. Australian courts routinely accept Singaporean, Hong Kong and New Zealand interpretative influence concerning ICA laws. In the CISG context, however, significantly less influence from those jurisdictions exists. That being so, I explore how Australia’s courts might better apply the CISG in an internationalist manner. First, I recommend that Australia’s courts emphasise to practitioners the need to consider the CISG’s application and its internationalist interpretation requirements. Second, I recommend that Australian courts use the amicus curiae procedure to solicit third party submissions addressing the CISG’s interpretation. Both techniques are applied by foreign courts in the ICA context and would assist Australian courts in discharging their CISG art 7(1) obligations.
Keywords: Asia-Pacific; Australia; CISG; Harmonisation; International commercial arbitration; Model Law; New York Convention; Sales law; Statutory interpretation

The role of ADR and judicial agreements: legal analysis and behavioral economics insights - Solano Mantilla, Valeria (LUISS Guido Carli, 2025)
From rationality to reality. The evolution of law and economics through the behavioral lens. Understanding how we choose: foundations of behavioral economics. Rethinking law through the lens of behavioral economics. Why law needs behavioral economics. The challenge of integrating behavioral economics into private law: freedom vs regulation. The double-edged sword of behavioral economics: protecting consumers from psychological manipulation. Balancing innovation and consumer rights: a global view on consumer protection in the EU, Italy and Colombia. Alternative dispute resolution and the judicial agreements. The justice system seen though behavioral economics. Judicial agreements: procedural autonomy and enhancing judicial cooperation. Alternative dispute resolution (ADR) and mediation: legal frameworks, party autonomy and behavioral economic. A brief comparative analysis on mediation: EU, Italy and Colombia. Applying behavioral economics in the ADR (mediation).
Keywords: ADR; Alternative dispute resolution; Economic behaviour; Mediation; Médiation

Impact of Blockchain Adoption, Regulatory Environment, and Institutional Investor Participation on FinTech Innovation - Almestarehi, Ahmad Abdel Rahim; Al-Ababneh, Hassan Ali; Malkaw, Eyad Mohammad (Theoretical and Practical Research in Economic Fields, 2025)
This study investigates how blockchain integration, regulatory policies, and the participation of institutional investors impact fintech innovation in Jordanian fintech companies. A descriptive analytical approach was used to evaluate and summarize the effects of these factors on innovation in the sector. An electronic survey was conducted among 125 administrative personnel working in Jordan's fintech industry. The results indicate a strong presence of blockchain adoption, involvement of institutional investors, and overall fintech innovation in these companies. However, the regulatory landscape in Jordan's fintech sector was found to be moderate. Furthermore, the analysis reveals that both blockchain integration and the regulatory framework significantly influence fintech innovation, with a significance level of 0.05. In light of these findings, the study suggests the creation of strategies to promote blockchain adoption, aiming to enhance efficiency and innovation in the industry.
Number: 2

Tax Reform and Investment Decision Effects in an Emerging Economy: Insights from Ghana - Yeboah, Michael; Danquah, Benjamin Adjei; Bawuah, Jonas; Nkwantabisa, Agyeiwaa Owusu (Theoretical and Practical Research in Economic Fields, 2025)
This study focuses on both domestic and foreign investment as indicators of economic growth in an emerging market context, examining the effects of tax reforms on investment decisions in Ghana from 1985 to 2020. The research employs a time-series analysis to integrate control variables like inflation, gross capital formation, and base rate, revealing their significant influence on investment activity in tandem with tax policy changes. Unlike previous research that mostly uses gross fixed capital formation as a proxy for investment, this study includes a wider range of investment types, giving a more complete picture of how the economy works. We did unit root and co-integration tests, which showed that the variables were first-order co-integrated. We performed the model estimate using a Vector Error Correction Model (VECM) and Granger causality tests. Results reveal that tax reforms have a measurable impact on investment patterns, underscoring the importance of adaptive tax policies in promoting sustainable economic development. The findings contribute to the broader literature on investment and fiscal policy in emerging economies, offering insights for policy-makers on optimizing tax strategies to encourage investment and drive economic growth.

Transparency in Investor-State Arbitration Under USMCA - Petrova Georgieva, Virdzhiniya (Jurídica Ibero. Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)
The provisions of USMCA and their interpretation and application in the developing case law of international arbitral tribunals constituted under its investment chapter show a progressive move towards a higher transparency standard in the resolution of inves-tor-State disputes. The incorporation of most of the UNCITRAL Rules on Transparen-cy in USMCA Annex 14-D expanded the scope of NAFTA’s transparency rules. The entry into force of USMCA and the recent end of NAFTA’s “legacy claims” is to bring normative uniformity across the case law of arbitral tribunals on issues of procedural transparency. In addition, better access to arbitral orders and awards under USMCA will promote the quality of the decisions, as tribunals and parties will be able to lean on the experience of their predecessors. Las disposiciones del T-MEC y su aplicación en la jurisprudencia arbitral internacional muestran un avance hacia mayores estándares de transparencia en disputas inversionista-Estado. Al incorporar la mayoría de las Reglas de Transparencia de la CNUDMI en su Anexo 14-D, el T-MEC amplió el marco del TLCAN. La entrada en vigor del T-MEC y el fin de las “reclamaciones heredadas” del TLCAN promueven una mayor uniformidad normativa en torno a la transparencia procesal. Esta coherencia fortalecerá la aceptación del capítulo de inversión del T-MEC y aumentará la legitimidad del arbitraje de inversiones a nivel global.
Keywords: Arbitraje internacional de inversiones; Arbitrajes entre Inversionistas y Estados; CNUDMI; International Investment Arbitration; NAFTA; Procedural transparency; T-MEC; TLCAN; Transparencia procedimental; UNCITRAL Rules on Transparency; USMCA

Organizational Identity for Cross-border Digital Trade: Achieving Technical and Legal Interoperability Within the Model Law on the Use and Cross-border Recognition of Identity Management and Trust Services (MLIT) Using the vLEI - Marin, Ivan; Castellani, Luca G. (United Nations Commission on International Trade, 2025)
Identity management is a cornerstone of digital trade and a core component of trust services, starting with electronic signatures. However, there is limited awareness of its legal and technical implications. The United Nations Commission on International Trade Law (UNCITRAL) has prepared a Model Law on the Use and Cross-border Recognition of Identity Management and Trust Services to provide uniform guidance on how to establish an enabling legal environment for identity management and trust services. The Global Legal Entity Identifier Foundation (GLEIF) has developed the Legal Entity Identifier (LEI) and its digital counterpart the verifiable LEI (vLEI) as universal solutions for a secure and cost-effective persistent business identifier. This paper illustrates how the MLIT and the vLEI may interact to provide legal and operational certainty to identification needs, thus fostering global economic growth.
Keywords: Digital cross-border trade; Digital trade; GLEIF; LEI; Legal entity digital identity; MLTR compliance; Trade facilitation; vLEI verifiable credential

An Assessment of Concurrent Jurisdiction and Claim of Ownership of Trademarks under OAPI Legislation - Dashaco Akuriah, Nelson (International Multilingual Journal of Science and Technology, 2025)
Trademarks are economic tools that aid businesses to communicate with their customers and capture a vast section of the population. Trademarks are only useful when used efficiently in the course of trade, meaning the higher the reputation of the mark, the more consumers want to associate themselves to the products or services the mark is affixed upon. This study examines the criteria to own a trademark and how ownership claims are handled between the African Organisation of Intellectual property as known by its French acronym OAPI and the competent domestic courts found at the level of Member States which has become a breathing ground for confusion in the resolution of disputes. Due to both bodies having concurrent jurisdiction in dispute resolution, the cost has become unbearable on trademark owners or beneficiaries of an exclusive license of exploitation, coupled with inconsistency in judgements from the two structures. The article highlights some key improvements expanding trademark subject matter and provides information on how the two institutions cited above handle matters of jurisdiction based on case law. The article also brings to the limelight how the OAPI administrative litigation bodies can collaborate with the competent domestic courts to arrive at clear and concise decisions. In conclusion the paper provides some recommendations on bridging the gap between both jurisdictions in order to attain the objectives of all parties involved.
Keywords: Concurrent Jurisdiction; Intellectual property; Litigation; Ownership; Registration; Trademarks; Use

A comparative statutory analysis of the causes of bank failures in Zimbabwe - Tsaura, Oscar (North-West University, 2025)
Zimbabwean financial sector has experienced significant periods of financial distress as depicted by numerous bank failures since 1980. Bank failure occurs when a financial institution experiences significant financial distress, rendering it incapable of fulfilling its obligations to depositors, shareholders and other stakeholders. In other words, bank failure is when a financial institution undergoes substantial financial distress rendering it unable to meet its obligations as they become due. In this thesis, the researcher adopted the definition of bank failure which refers to a situation where a bank is in financial distress and is recapitalised either by the central bank or a strategic investor, acquired by another institution, surrenders its license or the license is suspended, or it closes its operations altogether. This thesis reveals that in Zimbabwe bank failures can be attributed to various factors including the failure of regulatory and supervisory systems to detect irregularities in the operations of banking institutions. In addition, poor corporate governance practices such as inadequate oversight, inexperienced management, undue influence by dominant shareholders, nonperforming loans, excessive risk-taking, abusive related party transactions and noncompliance with laws are commonly cited as causes of bank failures in Zimbabwe. Bank failures often pose negative implications to the banking sector and banking stakeholders such as depositors and investors. This owes to the fact that banks serve as intermediaries that facilitate the avenues for deposits and extend credit services to individuals and the production sector of the economy. It is submitted that the proper functioning of banks requires effective and adequate regulatory supervision. Failure to provide robust and effective regulation of banks could lead to bank failures. This thesis presents a comparative analysis of the banking statutory framework of Zimbabwe and those of the UK and South Africa to determine if the banking laws in Zimbabwe are robust enough to prevent bank failures. The thesis reveals that the banking statutory framework in Zimbabwe is not robust enough to curb bank failures in times of stress because it lacks effective regulatory oversight. This thesis further reveals that poor banking regulation, inconsistent enforcement, weak regulatory insolvency procedures, and inadequate supervision framework are some of the weaknesses in the current banking statutory framework which needs to be rectified in order to combat bank failures effectively in Zimbabwe. The Banking Act does not fully incorporate the international best standards on bank supervision to prevent bank failures. Consequently, the banking statutory framework in Zimbabwe does not comprehensively and effectively provide for the prevention of bank failures like those of the UK and South Africa. The robustness of the banking statutory framework is in providing adequate and effective regulatory provisions and enforcement mechanisms that curb bank failures in Zimbabwe. The researcher proposes the adoption of a new model, the Zimbabwean twin peaks model, comprising the Zimbabwean Prudential Regulatory Authority and the Zimbabwean Financial Sector Conduct Authority. It is argued that if the adoption of the twin peaks model is considered and robustly implemented, it can prevent the causes of bank failures in Zimbabwe.
Keywords: Bank failure; Banking legislation; Banking statutory framework; Banks; Curatorship; Financial regulations; Financial stability; Fraud; Money laundering; Political instability; Zimbabwe

From trustworthy AI to technical standards : The distinctive European approach to artificial intelligence regulation - Gornet, Mélanie (Institut polytechnique de Paris, 2025)
L'Europe a été à l'avant-garde de l'éthique de l'intelligence artificielle (IA), en élaborant des chartes et des principes non contraignants sur l'IA « digne de confiance ». Le terme « digne de confiance » est utilisé par l'Europe pour désigner les systèmes d'IA qui sont « éthiques », « légaux » et « techniquement robustes ». L'Europe a complété ces principes non contraignants par un texte de loi sur l'IA, connu sous le nom de règlement sur l'IA, ou AI Act. Le règlement sur l'IA est l'un des premiers cadres légaux au monde à réglementer les systèmes d'IA dans différents secteurs et cas d'utilisation, en mettant l'accent sur la sécurité et la protection des droits fondamentaux. Pour les questions opérationnelles, le règlement sur l'IA s'appuie principalement sur des normes techniques en cours d'élaboration. L'approche européenne combine donc trois niveaux d'instruments réglementaires : les chartes éthiques de l'IA, le règlement sur l'IA et les normes techniques.L'approche par la normalisation est traditionnelle dans le domaine de la sécurité des produits, mais dans le règlement sur l'IA, les normes sont également censées répondre aux préoccupations en matière de droits fondamentaux. Pour éviter de faire des choix normatifs difficiles, les organismes de normalisation jouent la carte de la sécurité en élaborant des normes qui restent à un niveau élevé. De plus, dans le cadre du règlement sur l'IA, la responsabilité de l'élaboration des normes techniques est déléguée à des organismes de normalisation privés, où les grandes entreprises multinationales sont surreprésentées et exercent une influence considérable. Ces normes sont également généralement payantes, bien que la situation puisse évoluer dans les années à venir après une récente jurisprudence de la Cour de justice de l'Union européenne. Les experts en normalisation sont donc sous pression pour fournir des normes à temps et de bonne qualité. Europe has been at the forefront of Artificial Intelligence (AI) ethics, developing non-binding charters and principles on "trustworthy'' AI. The term "trustworthiness'' is used by Europe to designate AI systems that are "ethical'', "legal'' and "technically robust''. Europe has supplemented these non-binding principles with a binding regulation on AI, known as the AI Act. The AI Act is one of the world's first comprehensive frameworks for regulating AI systems across different industries and use cases, focusing on safety and protection of fundamental rights. The AI Act relies, for operational questions, mostly on technical standards that are in the course of development. The European approach thus combines three layers of regulatory instruments: AI ethics charters, the AI Act and technical standards.The standardisation approach is traditional in product safety, but under the AI Act, standards are also expected to address fundamental rights concerns. To avoid making hard normative choices, standardisation organisations are playing it safe, developing standards which remain at a high-level. Moreover, under the AI Act, the responsibility for developing technical standards is delegated to private standardisation bodies, where large multinational companies are over-represented and hold significant influence. These standards are also often locked behind paywalls, although the situation may evolve in the coming years after a recent case law from the Court of Justice of the European Union. Standardisation experts therefore face pressures to deliver standards on time and of good quality.
Keywords: AI Act; Apprentissage machine; Artificial Intelligence; Ethics; Inteligência artificial; Intelligence Artificielle; Intelligence artificielle; Machine learning; Normes techniques; Regulation; Règlement IA; Régulation; Technical standards; Éthique

Promoting Treaties in Nigeria and Operationalising the Singapore Convention on Mediation - Okoli, Pontian (African Journal of Legal Studies, 2025)
In Nigeria, the United Nations Convention on International Settlement Agreements Resulting from Mediation (2018) has entered into force. This Convention was incorporated or domesticated by referring to it in the Arbitration and Mediation Act (2023), but statutes are often dedicated to the domestication of treaties. There is no consensus on the most pragmatic way(s) to facilitate Nigerian treaty engagement. This article examines the Nigerian legal regime on treaties and explores the extent to which the regime can be maximised considering the Vienna Convention on the Law of Treaties (1969). A case is made for a principled basis to underpin the domestication of treaties that facilitate international business, including dispute resolution treaties. This analytical basis should enable legislative flexibility already woven into the overarching legal regime. The article articulates how such flexibility can be used to promote the operationalisation of relevant treaties using the Arbitration and Mediation Act as a paradigm.
Keywords: Good faith; International commercial mediation; Legislative flexibility; Singapore Convention; Treaties; Vienna Convention

International Arbitration: Impact on Global Economy - Jahan, Bushrat (International Journal of Innovation and Applied Studies, 2025)
The significant increase in the development of world economy over the last few decades have been experienced a considerable increase in the number of commercial disputes. When there is any business and dealings with contracts the question of dispute must be happened. But all of the parties actually want to run their business well and smoothly. In recent world a massive part of global economy depends on the trans-border business. But disputes in such business dealings sometimes can be the reasons to become risk the inter-relation of those parties. Which can affect the global economy as a whole. Comparing to the disputes inside domestic entities the trans-border or international business disputes can arise as bigger problem because of different jurisdictions, diverse legal systems and tradition. International Court of Justice (ICJ) already has the jurisdiction to try all the international civil suits but Alternative Dispute Resolution (ADR) mechanism also considered as a viable alternative to resolve the dispute over the court. The international arbitration arises as a way of alternative dispute resolution mechanism which upraise benefits both of the parties and maintain the confidentiality. In this paper details of international arbitration and the broader impact of this mechanism in the global business economy will be focused. The legal status and the implementation process of international arbitration also be the discussing point of this paper.
Keywords: Business economy; Enforcement of awards; Globalization; International Arbitration

The Protection of E-Banking Services Against Cybercrimes in Cameroon: Prospects and Challenges - Ghaseh, Nkambeh Allen (International Multilingual Journal of Science and Technology, 2025)
This article seeks to examine the extent to which users of e-banking services are protected in Cameroon. Over the past decades financial transactions have gradually emerged from traditional methods to modern forms of banking. The Information and Communication Technology (ICT) has transformed the banking system into a digital arena. With e-banking, customers can access their bank accounts, transfer funds, pay bills, and check their accounts balances. Banks serve as the backbone of every modern economy and should be protected. The development of e-banking in the 1980s with the aid of ICT has rendered banks and their customers vulnerable to cybercrimes. As an effort to combat cybercrimes and ensure cyber security in Cameroon, the 2010 Cyber Law provides both substantive and procedural rules. It is rather unfortunate that, the measures put in place to ensure cyber security and protect bank customers against cybercrimes are to a greater extent ineffective. The main objective of this article is to determine the protection accorded to banks and their customers against cybercrimes. The method adopted in the course of this work is doctrinal wherein, both primary and secondary sources of data were collected. The findings reveal among others that, the measures put in place to combat cybercrimes within the banking sphere in Cameroon are not effective. There is lack of explicit definitions for cyber offences. Most of the offences provided by the 2010 Cyber Law are vague and ambiguous. We therefore recommend that, the 2010 Cyber Law should be amended to address the current issues of ICT. This amendment should include explicit definitions for the different forms of cybercrimes with severe sanctions. Banks are advised to put in place effective monitoring machineries to mitigate cybercrimes.

The regulation of crypto-assets in South Africa with particular regard to crypto-asset market manipulation - Mgijima, Lwandiso (University of Pretoria, 2025)
Market manipulation is one of the dishonest means used by unscrupulous investors to make unjustified profits. It is conduct which unlawfully interferes with the normal operations of the markets in order to create false appearances with respect to the trading activity or the price of a financial asset. Market abuse is one of the various challenges plaguing the crypto-assets market, and is one of the financial regulators’ priority concerns. This study examines and discusses the problem of market manipulation in crypto-assets, and the need for the enactment of an effective regulatory framework in order to combat this problem and to promote investor protection and safeguard the integrity of the markets. The study finds that South Africa and other countries need to introduce rules in crypto-assets market which aim at regulating the activities of crypto-asset service providers. Currently South Africa has not enacted a comprehensive regulatory framework to address the various illegal uses of crypto-assets. The general approach adopted by South Africa to regulate crypto-assets activities involves subjecting crypto-asset service providers and their activities under the various financial sector laws established to regulate the traditional financial markets. This approach has been criticised as being inefficient in light of the unique risks presented by crypto-assets. The study discusses some of these arguments in detail and concludes by highlighting the need for the adoption of innovative regulations, in the long term, which comprehensively and effectively addressed the various risks presented by crypto-assets which also include market manipulation.
Keywords: Crypto-asset; Crypto-assets; Framework; Manipulation; Markets; Misconduct; Regulation; Service provider

The UNCITRAL Model Law: "Follow you follow me" or "I do it my way" - Wilske, Stephan (Contemporary Asia arbitration Journal, 2025)
Keywords: Arbitral Awards; Arbitral procedure; Arbitration agreements; Arbitration friendliness; Domestic arbitration law; Germany; Harmonization; Harmonization of law; International Commercial Arbitration; International standards; Modernization; Recognition and enforcement; Statutory frameworks; Taiwan; UNCITRAL Model Law

Essays on banking and society - Heyert, Axelle (Université de Strasbourg, 2025)
This dissertation examines the relationship between banking and society. It contributes to a better understanding of how banking affects society and, in turn on how society shapes banking practices. The first chapter studies the impact of inflation on trust in banks. Chapter two deals with the effect of trust in banks on financial inclusion. The third chapter investigates whether financial inclusion influences life satisfaction. Chapter four delves into how female bank leadership affects firm credit. The final chapter focuses on the influence of bank leaders’ age on sustainable lending. Overall, this dissertation highlights the important role of banks in societal development and the major influence of society in shaping banking practices.
Keywords: ACCESS TO CREDIT; Accès au crédit; Banking; Banks; Banques; Bonheur; Confiance; Financial inclusion; Gender; Genre; Inclusion financière; Inflation; Life satisfaction; Prêts durables; Sustainable lending; Trust in banks

The Middle Eastern and African Arbitration Review 2025 : Telecoms disputes in the Middle East and Africa - Mouzoula, Natalia; Kamau, Alice (Anjarwalla Collins & Haidermota, 2025)

Financial regulation and risk management: addressing risk challenges in a changing financial environment - Ojo, Marianne (Munich Personal RePEc Archive, 2025)
Will the April 2nd Announcement generate its intended objectives? It’s still early days – however, it appears increasingly likely that negotiation outcomes – particularly between those significantly impacted by the Announcement, will be a major determinant in deciding whether the tariff hikes resulting from the April 2nd Announcement, will be short or long term. As of the 11th April, 2025, President Trump’s universal tariffs on China had amounted to 145% whilst China announced tariffs of 125% on U.S imports. Amongst other things, this paper aims to address complexities and challenges faced by regulators in identifying and assessing risk, problems arising from different perceptions of risk, and solutions aimed at countering problems of risk regulation. It will approach these issues through an assessment of explanations put forward to justify the growing importance of risks, well known risk theories such as cultural theory, risk society theory and governmentality theory. In addressing the problems posed as a result of the difficulty in quantifying risks, it will consider a means whereby risks can be quantified reasonably without the consequential effects which result from the dual nature of risk that is, risks emanating from the management of institutional risks.
Keywords: Financial Forecasting and Simulation; General Financial Markets; International Financial Markets; Regulation and Business Law

How the Liberation Day Announcement is Shaping the Global Trade Order: From Free Trade to Fair Trade Agreements - Ojo, Marianne (Journal of Finance Research Letters, 2025)
It may be assumed that all of the United States’ trading partners were impacted by the recent “Liberation Day” announcement – an announcement which constitutes “two distinct tariff actions” – as will be highlighted in this paper. However, despite previous concerns of being targeted by their free trade agreement (FTA) partner, Canada and Mexico – as would have been or should be expected, have been exempted from the tariff imposition. As well as addressing factors which have contributed to the shift from free trade to increasingly and predominantly protectionist stances and most likely, fair trade practices, this paper is aimed at highlighting and explaining the rationales behind the recent historical developments – as well as highlighting those factors that have triggered the build up to the Liberation Day Announcement of the 2nd April 2025. It is remarked that “Trump’s reciprocal tariff doctrine, holds foreign countries accountable”. Against this backdrop of discontent with World Trade Organisation’s dispute resolution mechanisms, which will be further elaborated on, in the paper, the immediate and possible long term impacts of the Announcement, will be considered. As well as exploring the reasons for recent developments – by way of reference to historical developments and data, the paper also considers the underlying frameworks governing the calculations of recent tariff rates and hikes. Whilst there are arguments regarding the validity of such calculations, or whether the current scenario justifies the basis for implementing “national emergency measures”, what can be regarded as an emergency response can be determined through a consideration of underlying and contributory factors. If negotiations, and more specifically, bilateral negotiations, take place as hoped, between those countries impacted by the Liberation Day Announcement, financial stability across global markets is expected to be restored. However, if retaliatory measures follow – with an escalation of trade wars, possible repercussions should be cause for concern. The global trading system is still recovering from the recent crisis which was largely uncontrollable – hence, it is more likely (and hoped) that the recent market turbulence and volatilities will be short term.
Keywords: Deregulation; Dispute resolution mechanisms; Financial stability; Free trade agreements; Manufacturing; Monetary policy; Protectionism; World Trade Organisation

Legal remedies for breach of E-commerce contracts and related offences in Cameroon: a critical analysis - Saidou, Dan Lamy Nouhou (International Multilingual Journal of Science and Technology, 2025)
Avec de plus en plus de transactions commerciales effectuées par voie électronique, les litiges résultant d'intérêts conflictuels ou de malveillance deviennent inévitables, car Internet est devenu un terreau fertile pour divers abus. Ces abus vont de la rupture de contrat et des actes délictuels aux actes criminels. Il en résulte que l'utilisation d'Internet a donné une dimension différente à ces litiges. Cependant, comme le dit la célèbre maxime Ubi Jus Ubi Remedium, là où il y a un droit, il y a un remède. Le Cameroun, suivant cette tendance, a adopté un cadre juridique qui offre une panoplie de recours disponibles pour les victimes de violations du commerce électronique et d'infractions connexes, dans l'intention de rapprocher la partie lésée le plus possible de la position qu'elle aurait occupée s'il n'y avait pas eu d'abus. Le but de cet article est d'évaluer l'efficacité du cadre actuel pour remédier aux victimes de violations du commerce électronique et d'infractions connexes. L'article examine donc les bases des responsabilités en commerce électronique et les recours disponibles pour les victimes, mettant en évidence les difficultés qui rendent ces recours moins efficaces à cet égard. Plusieurs recommandations ont été proposées par cet article pour améliorer le statu quo. With more and more business being conducted through electronic means, disputes stemming from conflicting interests or malice become inevitable, as the internet has become a breeding ground for diverse abuses. These abuses range from contractual breaches and tortious acts to criminal acts. It follows that the use of the internet has given a different dimension to these disputes. However, as the famous maxim Ubi Jus, Ubi Remedium states, where there is a right, there is a remedy. Cameroon, following this trend, adopted a legal framework that provided a panoply of remedies available to victims of breaches of e-commerce contracts and related offenses to bring the aggrieved party as close as possible to the position he would have been in if there had been no abuse. The purpose of this article is to assess the efficiency of the present framework for remedying victims of e-commerce breaches and related offenses. The article thus examines the basis for liabilities in e-commerce and the remedies available to victims, bringing out the difficulties which render these remedies less efficient for the purpose. Several recommendations have been proffer by this article to improve the status quo.
Keywords: Commerce électronique; E-commerce; Electronic transactions; Recours; Remedies; Transactions électroniques

A trans-border African crypto asset licence to promote economic growth and deepen financial inclusion - Van der Lith, Johann Daniel (University of Pretoria, 2025)
Financial technology (Fintech) is a rapidly growing industry, both locally and globally. In various ways, Fintech is undeniably transforming financial services and products in every possible part of the financial sector by changing how people access and use financial services. By using innovative technologies, such as distributed ledger technology and cloud technology, and combining large data sets, including alternative data sets, better products can be provided that can be hyper-personalised for market segments and improve access and participation in respect of financial services. Fintech is solving issues that touch the consumer, through a bottom-up approach, considering the retail consumer as a starting point, in contrast to the common traditional finance evolution from the institutional investors to the retail consumer in a top-to-bottom approach. What is exciting about what Fintech can do for Africa, is that it can move inefficiencies in services and product life cycles to become efficiencies and move the frontiers for already efficient products and services. Fintech, therefore, provides an opportunity to improve the archaic and pave the way for the future. This study focuses mainly on crypto assets to limit its scope. It first examines the Fintech landscape in Africa, more specifically, the activity level in each selected comparative country, namely Mauritius, Kenya, Zambia, Namibia and South Africa, and how the activity benefits or can potentially benefit the economy in the host country and lead to the deepening of financial inclusion. It further examines the regulatory frameworks in those countries. The study examines the regulatory approach taken and the local activity, exploring some of the risks identified in each country, and considers the requirements that regulators chose to implement to mitigate these risks, as well as the current state of regulatory frameworks. Consideration is given as to whether similarities in both the risks and the mitigation requirements exist and how this can be aligned across jurisdictions. Recently, international standard-setting bodies have increased their focus on ensuring the alignment and cooperation of regulatory approaches globally. In light of the call for alignment and increased collaboration through policy recommendations and guidance, and or regulators to provide comprehensive and effective regulatory approaches without stifling innovation, this study considers the theoretical possibility of allowing certain Fintech companies, specifically crypto asset service providers (subject to specified conditions) to operate across jurisdictions with a trans-border licence. This study examines Europe’s Markets in Crypto Assets Regulation, as it was the first of its kind continental-wide framework for crypto assets, offering numerous lessons to be learned from this framework. The Commonwealth Model Law on Virtual Assets is also considered, as it is intended to assist member countries in implementing Virtual Asset and Virtual Asset Service Provider regimes in their respective jurisdictions, as they deem appropriate. Lastly, the study will explore what a theoretical trans-border regulatory framework containing prudential and market conduct requirements could look like and what embedded supervision tools, for instance, through forensic nodes or zero-knowledge proofs, could be utilised to ensure that all the regulators participating as part of a licencing panel receive real-time data and have a full view of the level of compliance with the requirements imposed by the joint framework and can proactively and intrusively act, when needed. The proposed trans-border regulatory framework aims to support crypto asset service providers with multi-jurisdictional strategies in Africa in scaling their operations, with a focus on building Africa as a global Fintech hub. The proposed framework aims to achieve this through a harmonised regulatory framework that simplifies compliance, increases efficiencies, enhances innovation, allows for scalability, and better risk management. In addition to the goal of positioning Africa as a globally recognised Fintech hub, the harmonised framework aims to realise the purported benefits of the technologies utilised by crypto asset service providers, thereby deepening financial inclusion and promoting inclusive economic growth through increased access and participation, as well as lower costs.
Keywords: Crypto assets; Embedded supervision; Financial inclusion; Financial technology; Regulatory frameworks

An Organizational Theory of Corporate Law - Aguirre, Emilie; Yen, Julie; Battilana, Julie (The Journal of Corporation Law, 2025)
Corporate law is in a moment of vibrant and contentious discussions about potential reforms. As firms exit Delaware, passive investment predominates, private equity expands, and public markets decline, corporate law faces a growing set of challenges that threaten its stability and efficacy. At the same time, the world faces pressing crises, including climate change, social and economic inequalities, and threats to democracy, though corporate law scholars typically consider these crises to be outside corporate law’s remit. In this Article, we argue that to understand and address the multidimensional crises that face both corporate law and society, we must address shortcomings in corporate law doctrine. We show how modern corporate law, shaped by neoclassical economic theories, provides an incomplete picture of the firm, and we propose an expanded theoretical perspective that draws from organization theory, a field long dedicated to understanding the complexities of the firm. This updated perspective demonstrates how firms actually consist of multiple constituents, including workers, the environment, and shareholders, who invest different forms of capital in the firm: labor capital, natural capital, and financial capital. It further shows that modern corporate law entrenches problematic power imbalances, privileging boards and insider shareholders over workers, the environment, and minority shareholders. Moreover, building on organization theory, we explain how corporate law fundamentally shapes and constrains firm behavior, leading these entrenched power imbalances to generate far-reaching negative consequences. To address these shortcomings, we propose redesigning board representation, fiduciary duties, and executive compensation to empower workers, the environment, and minority shareholders in relation to boards and insider shareholders. Integrating the organizational and economic perspectives can help address problematic power imbalances and ultimately provide a more effective corporate law framework to govern firms and serve society.

Artificial Intelligence in Accounting: Revolutionizing Financial Management in the Digital Landscape - Alnaimat, Mohammad Ahmad; Korsun, Inna; Lutsenko, Kostiantyn; Khodorkovskyi, Oleksandr; Artemchuk, Mykyta (Theoretical and Practical Research in Economic Fields, 2025)
The use of artificial intelligence (AI) builds up the accounting system efficiency, increases data entry accuracy and simplifying the accounting process. The aim of the study is to prove the effectiveness of modern AI-based information technologies (IT) in accounting and the possibilities of AI application for process optimization. The effectiveness and efficiency were proven using comparison methods, statistical analysis, graphical cause-and-effect analysis, modelling using the linear regression method. The assessment was carried out using quantitative and qualitative indicators of labour productivity and process optimization. The results of the study showed that 18 accounting department employees on average are needed to perform standard transactions in the companies studied without AI. With AI, 1 person can handle such a volume of work. Accordingly, with the implementation of AI, the average reduction in Transaction Processing Time per Week is 696.26 hours. Regression analysis confirmed that the implementation of AI increases the companies’ productivity in terms of Transaction Processing Time. Reducing the Data Processing Complexity by one unit leads to a reduction in transaction processing time by 592.69 seconds. Each percent increase in Data Entry Accuracy contributes to a reduction in processing time by 5135.51 seconds. The prospects for implementing AI in accounting include further improving algorithms to increase the accuracy and speed of transaction processing, optimizing material and time consumed.
Keywords: Accounting; Artificial Intelligence; Automation; Data analytics; Digital environment; Financial management; Inteligência artificial; Intelligence Artificielle; Machine learning

Fairness, Digital Markets and Competition Law – Reconciling Fairness Norms in Digital Markets Act, Data Act and AI Act with Competition Law - Kianzad, Behrang (Journal of Law, Market & Innovation, 2025)
The present article explores the implication of fairness as a regulatory and competition law concept applied to digital and Artificial Intelligence markets, in light of recent law and policy developments targeting the interaction between data, market power and competition law. Much of the policy discussions, legislative proposals as well some emerging case law elevate the matter of “fairness” in the context of digital markets and AI, creating both a novel regulatory framework as well as encouraging competition law to curb “unfairness” of said markets and related “unfair practices”. The interface between intellectual property rights and competition law is of utmost importance in this context, where we might find similar analogous insights as we can find regarding the matter of fairness within traditional EU competition law. Further, the question remains whether the “fairness norm” expressed in regulatory acts such Digital Markets Act, EU AI Act and the EU Data Act are akin to the “fairness” norms found in Union competition law, mainly under Article 102 Treaty on the Functioning of the European Union (TFEU).

South Africa judicial review of trade remedies in South Africa - Brink, Gustav Francois (Global Trade and Customs Journal, 2025)
No abstract available.
Keywords: Judicial review; South Africa; Trade remedies

Who can become a Member of a Company under OHADA Law: A Critical Appraisal - Eposi, Gladys Nku Tiku (International Journal of Science and Research, 2025)
OHADA Law plays a crucial role in fostering economic growth and regional integration by harmonizing business regulations in the era of globalization and trade liberalization. This study examines the legal framework surrounding company membership under OHADA Law. While certain individuals such as legally incapacitated persons or those facing legal prohibitions cannot become company members, the law provides alternative solutions. The study explores the distinction between members and shareholders and clarifies the eligibility criteria for company membership. Using an analytical approach, this research finds that any natural or corporate entity, unless restricted by legal incapacity, prohibition, or incompatibility, can be a company member under OHADA Uniform Act. Furthermore, the law offers flexibility for incapacitated individuals by allowing legal representatives to act on their behalf.
Keywords: Business law; Company membership; Corporate governance; OHADA Law; Shareholder rights

The future of a prohibition on indirect unfair discrimination as part of South African anti-discrimination employment law : a comparative reflection - Huysamen, Elsabe (Stellenbosch University, 2025)
ENGLISH ABSTRACT: The Constitution of the Republic of South Africa, 1996 (“Constitution”) enshrines the right to equality, emphasising “the full and equal enjoyment of all rights and freedoms”. This commitment embodies the principle of substantive equality, which extends beyond mere formal equality by addressing systemic inequities and striving for transformative change. The pursuit of transformative equality is underpinned by two constitutionally mandated mechanisms: affirmative action and the prohibition of unfair discrimination, both direct and indirect. Within this framework, the prohibition of unfair discrimination serves a dual purpose: It establishes a foundation for defending formal equality while simultaneously acting as a transformative tool, particularly in safeguarding against indirect discrimination. In a transformative context, the concept of protection against indirect discrimination specifically is significant as it acknowledges that equal treatment can still perpetuate inequality. The concept has the unique ability to identify hidden barriers and protect against more subtle forms of unfair discrimination, rendering it instrumental in advancing substantive equality and promoting long-term, systemic change. Yet, despite its transformative potential, the application of protection against indirect unfair discrimination in South African employment jurisprudence remains underdeveloped. And even in jurisdictions where the concept has received greater attention (for purposes of this study, the United States of America, Canada and the United Kingdom), it has not significantly advanced substantive workplace transformation. The reasons for this limited success are partly shared across these jurisdictions and partly unique to South Africa. Given the above, the primary objectives of this study are threefold: (i) to explore the protection against indirect discrimination in advancing transformative equality within the South African constitutional framework; (ii) to investigate the reasons for the limited development and application of this concept in South African employment law; and (iii) to assess whether the prohibition of indirect discrimination should be upheld as a distinct legal concept in employment law. These objectives were anchored by the fundamental question guiding the study: what role does the concept stand to play in employment law in SA in future and, if any, to what extent and in what form? The study begins by examining the broader concept of equality – a notion that is both complex and continually evolving. Key questions that are addressed include: What does equality mean? What are the objectives inherent to equality? What values underpin the concept? Following this exploration, the focus shifts to the role of equality within the South African Constitution, specifically the content of the right to equality as provided for in section 9 of the Constitution. This includes an overview of the constitutionally mandated mechanisms for enforcing equality, namely affirmative action and the prohibition of unfair discrimination, with particular attention to protection against indirect forms of unfair discrimination. The study thereafter narrows its focus to the application of the latter concept within South African employment law. It highlights the challenges that have hindered the effective development of the concept, which can be broadly categorised as conceptual and practical obstacles. The South African experience is compared to the development and application of the concept in the United States, Canada, and the United Kingdom, offering a comparative perspective on the concept’s evolution in the aforesaid jurisdictions. The study concludes by presenting suggestions and recommendations on the future role of indirect discrimination within South African anti-discrimination employment law. It also recommends strategies for more effective implementation of the concept.
Keywords: Affirmative action programs; Discrimination in employment; Employment; Labor laws and legislation; Law reform; South Africa; Unfair labor practices

Money Laundering: New Technologies and Control Challenges (Cryptocurrencies, Blockchain) - Kontogeorgis, Georgios (International Multilingual Journal of Science and Technology, 2025)
Tackling corruption is a global issue and tackling it effectively requires determination, cooperation and specialised technological knowledge. A significant proportion of global GDP is the sum of the money associated with corruption and fraud. The main objective of this article is to assess how new technologies such as cryptocurrencies and blockchain can combat corruption. The methodology of this article is a literature review. Specifically, scientific articles from databases and international organizations with expertise in new technologies are studied. This article deals with the new ways of corruption and money laundering. New technologies and the knowledge of them are a very important element in order to deal effectively with corruption. Perpetrators of financial crimes are usually ahead of the auditing authorities in terms of techniques and therefore knowledge of the new technology and the possibilities it offers is essential to effectively combat corruption and fraud globally. Cryptocurrencies and blockchain can combat corruption primarily due to their key characteristics of transparency, security, and decentralization. A key prerequisite for the transparency of cryptocurrencies is the application of supervision rules by the responsible authorities and the implementation of blockchain technology. In practice this is often not the case and cryptocurrencies are used as a money laundering tool.
Keywords: Corruption; Cryptocurrencies; Fraud; Money laundering; New technologies

Social justice at the Commission for Conciliation Mediation and Arbitration (CCMA) and the critical role of the commissioner - Letlonkane, Katlego (Stellenbosch University, 2025)
ENGLISH ABSTRACT: This study provides exploratory insight into the social justice mandate of the Commission for Conciliation Mediation and Arbitration (“CCMA”) in the context of labour relations in South Africa. As a vehicle for the advancement of social justice through the efficient resolution of labour disputes, the CCMA is a compelling actor in the pursuit of social justice in South Africa’s labour environment. Social justice as a legislative and policy imperative requires an investment in understanding its conceptual ideals and demands in order to empower those acting in its pursuit with the knowledge they need to fulfil its demands. The CCMA’s most critical functionary, its commissioner, holds the key to unlocking labour justice for many members of the public. One wonders, given the criticality of advancing social justice in labour relations, whether social justice is appropriately understood in order to enable the kind of decision-making that efficiently and consistently addresses the workings of power and inequality as they manifest in employment relationships. This study’s main provocation is to transform the pursuit of social justice (in the South African labour context, at least) from an elusive endeavour to a more tangible, realistic one. It attempts to offer a way of thinking about and applying social justice in the practice of labour dispute resolution in South Africa and the CCMA context. It critically explores the interwoven mechanisms of power, prejudice, and injustice and how these mechanisms work to sustain unequal labour relations. The commissioner’s role is thus a critical one, that involves a deliberate pursuit to recognise, understand and interrupt these movements of power and mitigate the effect of inequality. Any movement towards social justice that does not pay close attention to this matrix of power and prejudice threatens to dilute the transformative potency of social justice. This study identifies and discusses the decisions of commissioners that fall short of the kind of conscientious decision-making required by a mandate of social justice. Discussions in this study also point out significant achievements in centralising social justice principles in decision-making processes at the CCMA, where arbitrators, in reducing injustice and advancing justice in labour relations, show a conscientious consideration and appreciation of historical contexts, power, privilege and disadvantage. Living up to the constitutional imperative to transform society in the way of equality, commissioners ought to develop their agency and be empowered by the Constitution of the Republic of South Africa, 1996, to disrupt inequality. This study contributes to the understanding and clarification of social justice and its implications for the South African labour environment. It also posits ubuntu as an important consideration in the balancing exercise required to achieve justice.
Keywords: Arbitration; CCMA; Commission for Conciliation; Mediation; and Arbitration; Dispute resolution (Law); Mediation; Mediation and conciliation; Industrial; Officials and employees; Social justice

Party autonomy and the applicable law to the merits in intellectual property arbitration - Rivoire, Maxence (Arbitration International, 2025)
The freedom of the parties to choose the applicable law to the merits is often presented as an important benefit of arbitrating disputes involving intellectual property (IP). Yet, the reality is more uncertain and controversial than is commonly assumed. Is party autonomy really permitted in IP arbitration? Should it be? This article answers these questions with regard to patents, trademarks, and copyrights, using recent examples drawn from arbitral practice. It first examines the situation where the parties only made a choice of contract law, and considers in this regard whether that law can and/or should be extended to infringement claims and/or the remedies to infringement, either directly or through the technique of characterization. After discussing the impact of overriding mandatory rules in contractual IP cases, the article then examines the situation where the parties chose a law to govern IP questions, including by way of a broad choice-of-law agreement covering non-contractual problems. It seeks to provide as much guidance as possible to arbitral tribunals, using mainly the distinction among infringement, ownership, and validity issues, and by distinguishing among different scenarios in which party autonomy is more or less acceptable.
Keywords: Arbitrage; Arbitragem; Arbitration; Intellectual property; Party autonomy

Examining the Impact of Remote Work on Employees, Employers, and the State in Nigeria - Adeyinka, Mutiu Abiodun; Gbajumo-sherrif, Mariam A.; Elegbede, S. Tunde (African Journal of Economic and Business Research, 2025)
Abstract The rise of remote work, accelerated by the COVID-19 pandemic, has created significant challenges for employees, employers, and the government, complicating the management of remote teams while striving to maintain productivity and organizational cohesion. The central problem addressed in this study is the deteriorating state of employment relations marked by downsizing and layoffs, particularly in the private sector in Nigeria. This study aims to analyze the impact of remote work on these stakeholders through a systematic and thematic review based on PRISMA guidelines. Twenty four publications from 2013 to 2023 were reviewed, sourced from Google Scholar, DOAJ, Scopus, and Web of Science. The findings indicate that while organizations are beginning to adopt tools for remote work and virtual communication, these resources are primarily accessible to larger companies due to associated costs. Additionally, the study highlights the pressing need for enhanced infrastructure and structural improvements to support remote work at a societal and economic level. In conclusion, the study recommends that the government enhance infrastructural development and that organizations implement better strategies for remote work. Furthermore, individuals should pursue advancements in technology to adapt to the changing landscape. These recommendations aim to promote sustainable employment relations and economic development in Nigeria in light of the evolving digital economy.
Keywords: Employees; Employment Relations; Government; Remote Work

Effects of Dynamic Capabilities and Multichannel Integration Quality on Bank Performance; A Moderated Role of Environmental Dynamism : A Moderated Mediation Model Analysis - Geleta, Negash; Amentie, Chalchissa; Getahun, Misganu (African Journal of Economic and Business Research, 2025)
This study investigates the effects of dynamic capabilities (DCs) and multichannel integration quality (MCIQ) on the performance of banks (BP). It also explores the moderating role of environmental dynamism in the banking industry, using a moderated mediation model. Quantitative analyses were employed to examine data collected from multiple banks. Structural equation modeling (SEM) was used to test the relationships between variables, while moderation and mediation effects were analyzed using SEM-AMOS. The findings reveal that dynamic capabilities and MCIQ significantly enhance bank performance. Furthermore, environmental dynamism (ED) moderates the relationship between these variables, intensifying their effects on performance under high levels of dynamism. The mediation analysis shows that MCIQ partially mediates the impact of dynamic capabilities on bank performance. The study is limited by its cross-sectional design, which restricts causal inferences. Additionally, the findings may not be generalizable to non-banking industries or regions with distinct regulatory frameworks. The results provide actionable insights for bank managers, emphasizing the importance of fostering DCs and enhancing MCIQ to sustain performance in rapidly changing environments. The findings highlight significant social benefits, as improved dynamic capabilities (DCs) and critical information quality (MCIQ) enhance bank performance, fostering economic stability, financial inclusion, and customer trust. By enabling resilience and innovation in dynamic environments, banks contribute to broader societal goals, including sustainable development and socio-economic growth. This research contributes to the literature by integrating DCs and MCIQ in a moderated mediation framework, offering a novel perspective on their interplay with environmental dynamism in the banking sector.
Keywords: Dynamic Capabilities; Environmental Dynamism; Moderated Mediation Model; Multichannel integration quality

Whistleblowers and their role in the fight against corruption. Problems in protecting whistleblowers and suggestions for improvement - Kontogeorgis, Georgios (International Multilingual Journal of Science and Technology, 2025)
Whistleblower protection is necessary to reduce mismanagement in private and public organisations worldwide. The protection of whistleblowers is a complex and particularly challenging task that it is up to national authorities. The research methodology is the literature review. In this context, reputable scientific journals, reports from international organisations and websites dealing with the research field of whistleblowers are studied. The main conclusions are that there is an institutional framework for the functioning and protection of whistleblowers, but best practices are not fully implemented. Furthermore, the effectiveness of the use of whistleblowers is extremely high in detecting fraud and high public risks compared to other audit techniques. For this reason, the protection and framework of the whistleblower process is increasingly being legislated for by more and more countries as their importance is recognised. Finally, monitoring the use of whistleblowers and applying best practices and criteria for their effectiveness will make their use more effective.
Keywords: Corruption; Criminal activities; Financial Crime; Fraud; Whistleblower

An analysis of the challenges in combatting money laundering within Bureaux de Change establishments in Botswana - Mokone, Philadelphia Pontsho (Journal of Money Laundering Control, 2025)
PURPOSE : Financial institutions such as Bureaux de Change are susceptible to money laundering, posing a significant risk to a nation’s financial stability and security if not properly regulated and supervised. Botswana is a member of the Financial Action Task Force (FATF), a global organisation that sets standards, promotes policies to prevent money laundering, terrorist financing and arms proliferation, all to safeguard the global financial system. Efforts have been made to incorporate FATF recommendations on money laundering into the fiscal laws of Botswana. However, some deficiencies still remain. Although there are no recorded cases of money laundering in Botswana, Bureaux de Change entities are susceptible to it as their business involves cash transactions and rapid money transactions. This paper aims to analyse the challenges faced by Bureaux de Change entities in combating money laundering in Botswana. This will be done by assessing the effectiveness of the current regulatory framework and role of the regulatory authorities in combating money laundering within Bureaux de Change entities. DESIGN/METHODOLOGY/APPROACH : This paper provides a comprehensive examination of the obstacles faced by Bureaux de Change entities in Botswana when it comes to combating money laundering. A qualitative research method and doctrinal research method are both used in this context. FINDINGS : It is hoped that policymakers and other relevant persons will adopt the recommendations provided in the paper to enhance the curbing of money laundering in Botswana. RESEARCH LIMITATIONS/IMPLICATIONS : This paper is only limited to the regulation of money laundering within the Bureaux de Change entities in Botswana and does not provide empirical research. PRACTICAL IMPLICATIONS : This paper is useful to policymakers, lawyers, law students and regulatory bodies especially in Botswana. SOCIAL IMPLICATIONS : This paper suggests changes to the Bank of Botswana (Bureaux de Change) Regulations of 2004 to improve their effectiveness, robustness and competitiveness in combating money laundering. ORIGINALITY/VALUE : This paper is original research on the challenges of combating money laundering within Bureaux de Change entities in Botswana.
Emerald Publishing Limited
Keywords: Botswana; Bureaux de Change; Cash transactions; Financial security; Financial stability; Money laundering; Risk; Supervision

Implementation of safeguard measures in digital trade to protect African domestic industries and platforms - Rotich, Nelly Chepngetich (University of Pretoria, 2025)
As technology continues to advance, more trade is moving online. The increase in digital trade brings with it both opportunities and challenges in the international trade field. The increase in digital trade could for instance result in a spike in digital trade imports which may subsequently cause or threaten to cause serious injury to domestic industries and platforms dealing in like or directly substitutable digital data/content and services. This would necessitate the application of safeguard measures to avert any such serious injury or threat to serious injury caused to the domestic industries and platforms. The procedure for applying safeguard measures to digital trade currently is unclear. The current legal framework on safeguard measures does not apply to digital trade despite increased digital trade over the years. Thus, this study explores the prospects and practical challenges relating to safeguard measures’ application to digital trade with a specific focus on African domestic industries and platforms. While domestic industries and platforms in any part of the world could be affected by surges in digital trade imports, Africa is in a precarious position. Intra-Africa digital trade volumes could be increased and disadvantages of African domestic industries and platforms by surges in digital trade imports could be prevented through regulation and judicious use of safeguard measures. This study established the need to regulate to tap into the potential of digital trade and prevent African industries and platforms from falling behind and from the disadvantage of market dominance by big techs from outside Africa. In conclusion, the study noted legal and institutional gaps in the application of safeguard measures to digital trade. The study has recommended that specific institutions at the global, continental and national levels take necessary actions to build a clear and robust framework for safeguard measures in digital trade.
Keywords: Digital trade; International Trade

The Limits of Shareholder Ratification - Anabtawi, Iman (The Journal of Corporation Law, 2025)
In this Article, I analyze the expanding common law doctrine of shareholder ratification, whereby shareholder approval can, for all practical purposes, absolve directors of fiduciary liability for their conflicted business decisions. Delaware law now allows a shareholder vote to perform substantially more work than ever before. Under prevailing doctrine, in transactions between a company and any party other than a controlling shareholder, shareholder ratification reinstates the business judgment rule and makes it irrebuttable, other than for waste. Substantive judicial review is effectively avoided for such transactions. Despite its extraordinary importance in corporate governance, the shareholder ratification doctrine’s foundations are feeble and its limits uncertain. Theoretically, there is no well-established basis for equating shareholder approval with either the informed, disinterested, and good-faith decision of a board or judicial review. Doctrinally, shareholder ratification’s expansion beyond its traditional context of self-dealing has been a judicial innovation, rather than an elaboration of precedent. And historically, the shareholder ratification doctrine, which originated in early 20th-century state interesteddirector statutes, was motivated by fairness principles that were lost in translation into the common law. This Article recovers the fairness genealogy of the shareholder ratification doctrine and, in doing so, provides useful guidance for the doctrine’s development, limits, and future application.

The effects of Basel III on the intermediation and market activities of WAEMU banks - Kouakou, Thiédjé Gaudens-Omer (University Library of Munich, Germany, 2025)
This paper analyzes the effect of Basel III adapted to WAEMU on the behavior of banks in the zone (intermediation and market activities). After having developed a model for optimizing the return on bank equity, under various constraints (balance sheet constraints, Basel III regulatory constraints), we resort to linear programming via the Danzig simplex algorithm and to a structure of reasonable rates to obtain the optimal values of the various bank balance sheet items. The results, obtained by comparing these theoretical values with the values observed before Basel III (before January 1, 2018), show an increase in the supply of loans, obtained not only from deposits and bank refinancing but also via resources from the financial markets. We can also observe the intuitive result of an increase of bank reserves in line with the constraint that Basel III imposes on banks to increase their liquidity. In short, Basel III tends to strengthen bank financing in the zone, while improving the soundness of banks through the constitution of larger reserves.
Keywords: Calibration; Credit supply; Linear programming; Prudential regulation

The Effectiveness of the Legal Frameworks in the establishment of Liability of Land Transport Operators in cases of Accidents in Cameroon: A Critical Appraisal - Kombo, Kutiefe Umaro (International Multilingual Journal of Science and Technology, 2025)
The liability of land transport operators in Cameroon is guaranteed by a good number of laws including; the constitution of Cameroon, the penal code, the 2001 law governing the Profession of Road Transport Operators, the 2023 law governing the rail sector in Cameroon and more. Such liability can be under the Tort of negligence, vicarious liability, or strict liability as provided for under section 289(1) of the Cameroonian penal code on Unintentional killing. However, the laxity of the courts in handling accident-related disputes, the contradictory and vague nature of the laws on the liability regime and even the lenient nature of the sanctions provided for by these laws do not meet up with the rate of accidents today in Cameroon. This article therefore has as its objective to examine the effectiveness of the legal frameworks in the establishment of liability of land transport operators in cases of accidents in Cameroon. Arguably, the author holds that the legal frameworks establishing the liability of land transport operators in cases of an accident in Cameroon are ineffective. A doctrinal research method has been adopted where both primary and secondary sources of information have been consulted. Our finding reveals that; the ineffectiveness of legal frameworks in the establishment of the liability of land transport operators in cases of accidents is a result of the laxity of the courts in implementing the laws and, the vague and contradictor nature of the law. We, therefore, recommend that; separate court hearings should be set for accident-related disputes and judges trained only on that, the laws should be revised, the sanctions in cases of accidents should be increased and all mitigating circumstances in cases of accidents should not be taken into consideration like a first-time offender, the plea of guilt etc.
Keywords: Accidents; Cameroun; Land Transport Operators; Liability; Opérateurs de transport terrestre; Responsabilité; Transport terrestre

The Artificial Intelligence (AI) framework and the benefits of its use in internal audit - Kontogeorgis, Georgios (International Multilingual Journal of Science and Technology, 2025)
AI is well known today as a valuable tool that can improve our daily lives. In addition, it can improve the efficiency and productivity of many professions, such as the internal auditor. The research methodology is literature review. The primary objectives of the article are twofold: Firstly, to provide a comprehensive description of the institutional framework for the operation of AI internationally, and secondly, to examine the benefits that arise from the use of AI in internal audit units and organisations in general. The significance of the research lies in its examination of artificial intelligence (AI) as a valuable instrument in the arsenal of internal auditors. The findings suggest that AI has the potential to enhance the efficacy of internal audits, reduce the time required for their execution, reduce the frequency of internal audits, and, in general, optimise the operations of companies and organisations.
Keywords: AI; Artificial Intelligence; Corruption; Fraud; Inteligência artificial; Intelligence Artificielle; Internal audit; Management

International investment regime reform : integrating sustainable development into Uganda’s bilateral investment treaty system – a new model bit - Asiimwe, Esther Muchwa (University of Pretoria, 2025)
This thesis critically analyses Uganda’s bilateral investment treaty (BIT) system to determine its compatibility with sustainable development imperatives and proposes a new model BIT that aligns with Uganda’s evolving development priorities. Recognising the country’s reliance on foreign direct investment (FDI) for economic growth, this study interrogates the extent to which Uganda’s current BITs—many of which were concluded during earlier policymaking eras—expose the country to legal, economic, and regulatory risks. These include susceptibility to investor–state dispute settlement (ISDS) claims, constraints on the host state’s right to regulate, and a lack of provisions promoting environmental, social, and developmental objectives. Through doctrinal and comparative legal analysis, the study traces the historical evolution of international investment law (IIL), critiques the limitations of Uganda’s domestic and treaty-based FDI frameworks, and identifies substantive and structural weaknesses in Uganda’s in-force and model BITs. The analysis also considers international reform efforts and best practices from new-generation investment agreements, including the AfCFTA Protocol on Investment, the Investment Facilitation for Development (IFD) Agreement, and the SADC and EAC Model BITs. Particular attention is paid to the South African BIT reform experience as a comparator for Uganda’s reform journey. The study finds that Uganda’s BIT system is outdated, overly protective of investors, and poorly aligned with its sustainable development goals (SDGs). It recommends terminating unratified and problematic BITs, renegotiating existing ones, and adopting a new model BIT that balances investor protection with Uganda’s regulatory autonomy and sustainable development objectives. To this end, a draft model BIT is proposed as an annex to guide future treaty negotiations and reform Uganda’s investment regime in line with contemporary global standards and regional aspirations.
Keywords: Bilateral Investment Treaties (BITs); ISDS; Investissements; Investment law reform; Investments; Investor-State Dispute Settlement; Uganda

Climate justice and litigation in the context of South Africa - Chihombe, Denmark (North-West University, 2025)
This study interrogates the intersection of climate justice and litigation in the South African context. It addresses the urgent need for legal methods to address the disproportionate impact of climate change on marginalised communities. As climate change has become one of the greatest global challenges, marginalised communities most keenly feel its impacts, particularly those historically disadvantaged by socioeconomic inequalities rooted in apartheid. What follows is a critical examination of the most important international climate frameworks, in particular the United Nations Framework Convention on Climate Change (hereinafter UNFCCC) and the Paris Agreement, which have shaped the global discourse on climate change. The increasing recognition of the rights of historically marginalised and vulnerable communities underscores the potential role of climate litigation in achieving climate justice for all by holding both government and corporations accountable for their actions and lack thereof in mitigating climate change. The study examines the South African legal framework and recognises its progressive constitution that guarantees environmental rights. On the other hand, the study highlights significant barriers to effective climate action, particularly for the country’s most vulnerable, poor and marginalised populations, who often lack access to legal resources and skills needed for climate action. Using decided climate cases such as Earthlife Africa v. Minister of Environment, the study highlights the problems that plaintiffs often face when it comes to proving causation and the need for expert evidence in such litigation. Finally, the study concludes that while climate litigation offer opportunities for climate justice, the challenges identified need to be addressed to ensure the effectiveness of climate processes in achieving climate justice. The study therefore makes recommendations for strengthening legal aid, promoting public climate litigation and improving community capacity. By implementing these recommendations, climate justice will be achieved so that South Africa can effectively utilise climate litigation to demand climate justice for both current and future generations.
Keywords: Climate change; Global challenges; Justice; Litigation; Marginalised communities

A path to paperless trade: analysing the legal gaps and economic benefit of adopting or maintaining a legal framework that takes into account the UNCITRAL Model Law on Electronic Transferable Records (MLETR) - Committee on Trade and Investment (CTI) (Asia-Pacific Economic Cooperation, 2025)
Keywords: Asia and the Pacific; DIGITAL TECHNOLOGY; ELECTRONIC COMMERCE; UN Convention on the Use of Electronic Communications in International Contracts (2005); UNCITRAL Model Law on Electronic Commerce (1996); UNCITRAL Model Law on Electronic Transferable Records (2017)

Internationality overreach in the interpretation of uniform private law conventions: the Contra Proferentem rule and the CISG - Kryla-Cudna, Katarzyna (International and comparative law quarterly, 2025)
This article argues that the rule of contra proferentem is not applicable to international sales contracts governed by the United Nations Convention on Contracts for the International Sale of Goods (CISG). It further argues that the common recognition of the rule of contra proferentem under the CISG is an instance of a broader phenomenon which it calls ‘internationality overreach’. ‘Internationality overreach’ is the tendency to project onto the provisions of a uniform private law instrument doctrines and concepts which are inaccurately presumed to constitute universally recognised principles of private law or the ‘common core’ of various legal systems. This article demonstrates that internationality overreach disrupts the goals underpinning the harmonisation of commercial law in two ways: first, it undermines uniformity in the application of international conventions; and, second, it leads to outcomes that fall short of the agreement reached by the Contracting States during the drafting process. While this article focuses on the CISG, the argument developed in this article is of equal relevance to other uniform private law conventions which follow the principle of autonomous interpretation.
Keywords: INTERNATIONAL SALE OF GOODS; INTERNATIONAL TRADE LAW; UN Convention on Contracts for the International Sale of Goods (1980)

Corporate purpose and governance in Africa: French-influenced OHADA law, local norms, and heterodox pluralism - Minzoto, Bonheur (Journal of Corporate Law Studies, 2025)
This article examines corporate governance in Africa and its significance for corporate repurposing. It relies on the framework of the Organisation for the Harmonisation of Business Law in Africa (OHADA), which unites seventeen African states under one corporate law jurisdiction while exploring how the interpretation and practice of this legal system can be integrated with or influenced by national sectoral laws and cultural norms. The workings of these different legal sources denote the case for heterodox pluralism of corporate purpose, whereby corporate membership is not tethered to shareholding only, but the workforce and neighbouring too and corporate legitimacy is not merely a function of legal arrangements but equally derives from broader society. The governance of corporations in Africa must correspond to such imperatives to ensure that the prevailing shareholder primacy norm does not continue its unencumbered de facto reign and reduce African stakeholderism to comparative impotence and mere scholarly exercise.
Keywords: CSR; Corporate governance; Corporate purpose; DRC mining legislation; Directors’ liability; Directors’ sustainability duties; Local cultures

A legal analysis of the application of the FATF grey-listing standards on South Africa - Mthembu, Zanele (North-West University, 2025)
The Financial Action Task Force (FATF) is a watchdog established to counter the abuse of the financial system by criminals for money laundering, the financing acts of terrorists and proliferation financing. For the FATF to achieve its mandate, it came up with a set of global standards in the form of Recommendations. The Recommendations seek to mitigate the risks of money laundering and terrorist financing and to assess whether FATF member countries are taking effective action to combat money laundering and terrorist financing. South Africa is a member of the FATF and therefore, is obliged to comply with the standards set to combat money laundering and terrorist financing and proliferation. The FATF uses assessments done through peer mutual evaluations. In other words, FATF members assess one another’s anti-money laundering and counter-terrorism financing (AML/CTF) regulatory frameworks for compliance with FATF’s standards. Following the FATF's assessment in the years 2003, 2009 and 2018, South Africa’s AML/CTF regulatory framework was found to be weak leading to greylisting in 2023. The greylisting of South Africa follows the findings of strategic deficiencies in the country’s implementation of the FATF AML/CFT standards. Greylisting by the FATF carries various economic and reputational implications for South Africa such as increased scrutiny from international partners resulting in increased compliance costs for financial institutions, an estimated reduction in South Africa’s gross domestic product (GDP) and a decrease in foreign direct investment (FDI). Since the greylisting, South Africa has embarked on a legislative and regulatory journey to address the shortcomings with a view to be taken off the greylist. This dissertation provides a detailed analysis of the FATF standards, evaluates South Africa's legislative and institutional responses in the form of the Prevention of Organised Crime Act 121 of 1998, Financial Intelligence Centre Act 38 of 2001 and the Protection of Constitutional Democracy Against Terrorist and Related Activities Act 33 of 2004, and assess their effectiveness in addressing the identified deficiencies. Recommendations are suggested to assist in fortifying South Africa’s AML/CTF regulatory framework.
Keywords: Accountable institutions; GAFI; Greylist; Money laundering; Mutual evaluation; Recommendations; Terrorism financing

The interpretation of social relations in the environmental, social and governance framework - Nxumalo, Nyiko (North-West University, 2025)
Environmental, social and governance (ESG) issues have gained prominence in recent years. Companies have come to understand their role in the global economy and that their decisions cannot be based solely on profits. They are now required to have regard for the environment in which they operate, to be mindful of the social factors that affect their employees, customers and the community at large, and to ensure that their corporate governance complies with the standards set out in the Companies Act 71 of 2008 and the various King Reports. While ESG has become a buzz word in the corporate world, there is still much uncertainty among stakeholders about what they are required to do and what the reporting requirements, if any, are. Its implementation in South Africa is still in its infancy and there is much uncertainty about what ESG monitoring and compliance truly entail. A perfect illustration of this is the fact that the Johannesburg Stock Exchange (JSE) only published ESG disclosure guidelines for the first time in 2022. This means that until the guidelines were published, hundreds of companies in South Africa had been wondering aimlessly in the dark when it comes to ESG issues. To make matters worse, while environmental issues and corporate governance issues have received significant attention from scholars and legislators in South Africa alike, the "S" in ESG has received little attention. It is often treated as the undesirable stepchild that everyone conveniently forgets is part of the ESG family. The purpose of this study is to highlight the gaps in the existing ESG regulatory framework, which leads to gaps in the understanding and monitoring of the implementation of the social indicators of ESG. The study aims to firstly determine whether companies in South Africa have a proper understanding of the social framework of ESG and whether the current legal and/or regulatory framework in South Africa offers sufficient guidance to n organisations to ensure that they comply with and fully implement the social guidelines of the ESG framework.
Keywords: ESG; ESG Framework; Governance factors; King IV report; Section 29 of Companies Act; Social factors; Social indicators

Transforming arbitration: exploring the impact of AI, blockchain, metaverse and Web3 - Piers, Maud; McCarthy, Sean (Radboud University Press, 2025)
In an era where technology is rapidly transforming the legal landscape, Transforming Arbitration explores how innovations like AI, blockchain, the Metaverse, and Web3 are reshaping arbitration as a key form of dispute resolution. The book features insights from leading academics, practitioners, and policymakers, offering a comprehensive look at how these advancements are influencing our conceptual, substantive and procedural understandings of many parts of this field. Each chapter examines the challenges and opportunities presented by these technologies, raising important questions about the compatibility of traditional arbitration processes with digital innovations. As the legal field adapts to developments like cryptocurrencies, NFTs, and 'virtual' disputes, this book provides valuable guidance on the future implications for arbitration. By questioning established norms and advocating for fresh approaches, Transforming Arbitration is a vital resource for legal professionals and scholars committed to evolving with the times. Combining theoretical exploration with practical recommendations, this collaborative volume equips the legal community with the tools to navigate the complexities of our digital age with confidence and foresight.
Keywords: AI; Arbitrage; Arbitragem; Arbitration; Artificial Intelligence; Blockchain; Convention on the Recognition and Enforcement of Foreign Arbitral Awards (1958); Electronic Commerce; Inteligência artificial; Intelligence Artificielle; International commercial arbitration; MARD; Mediación; Mediation; Mediação; Médiation; UNCITRAL Arbitration Rules; UNCITRAL Model Law on International Commercial Arbitration (1985)

Impact of the basel accords on small indigenous banks in developing countries : the case of Zambia - Rolls II, Douglas Walter (University of Pretoria, 2025)
The purpose of this thesis is to evaluate the impact of the Basel Accords on small indigenous banks in developing countries, with particular concentration on small Zambian banks. The problem statement intends to investigate whether implementing the three Basel Accords is conducive to the growth of small banks in Zambia. The study further aims to determine whether the present approach to legal regulation of small banks in Zambia is appropriate. The methodology is based on desk-bound research and examination of both primary sources and secondary sources of material such as books, journals, and relevant articles. The study is impacted by the dearth of secondary research work and the difficulty of getting information from sources like the Zambian central bank and other information centres. While Basel I and II seem to have stabilised the Zambian financial sector, the Basel III Accord appears to have impacted negatively on many small banks to the extent that they have been forced into merger and acquisition arrangements with larger foreign banks to fund their undercapitalised positions to survive. It also emerges that the Zambian financial system is strongly linked to the international global economy; regionalisation with organisations like SADC and COMESA being the first stages in the process. This situation is likely to introduce increased instability in the Zambian financial sector by making banks more vulnerable to the vagaries of the international financial markets. It is thus recommended that the Zambian central bank should be more proactive in lobbying for better conditions for small banks from the Basel Committee for Banking Supervision and other international financial regulatory bodies; it should also avoid “cutting and pasting” rules from other jurisdictions to avoid possible distortions in the banking sector. It should also encourage further development of primary and secondary markets in low-cost paper and provide small banks with long-term, low-interest loans to support their growth. The Bank of Zambia, the Zambian central bank, should consider establishing a separate Act financial services Act for small banks to better regulate them. The central bank should also seek out non-Basel Accord solutions for small banks including re-examining the positive aspects of the infant-industry argument. Lastly, it should introduce a formal system for classifying banks in Zambia. At the international level, it is suggested that the global standard-setting bodies should undergo radical reforms to ensure that they are in tandem with the problems that banks in developing countries face as well as allow them to have a say in global standard setting. It is recommended that global standard-setting bodies apply simpler rules for smaller banks. The impact of the Basel Accords on small indigenous banks in developing countries and Zambia, in particular, is important because of the role that small banks play in developing economies in growing small and medium-sized businesses that are often ignored by large foreign banks. It is also important that small banks are allowed to grow into large and medium-sized banks to effectively compete against foreign multinational banks. Institutions based on neoliberal ideals appear to only serve Western businesses’ interests despite their call for all countries to create a level playing field. Due to the dearth of empirical research, there are several gaps in the work that may provide opportunities for further research in this important area of the law.
Keywords: Banking supervision; Basel accords; Basel committee; Developing countries; Financial regulatory framework; Small banks

Expedited procedures in the Multilateral Investment Court: efficiency and consistency - Shouzab, Ali (Uppsala universitet, 2025)
The ongoing ISDS reform, under UNCITRAL Working Group III with a substantial input from the EU, has recently proposed for the establishment of a Multilateral Investment Court (MIC) with an appellate mechanism. Simultaneously, expedited arbitration procedures have gathered significant academic interest in the recent decades. While extensive literature exists on both the MIC development and expedited procedures, their intersection remains relatively unexplored. This dissertation bridges this research gap by analyzing how the best practices from different expedited procedures and EU treaties could be used to establish expedited MIC procedures. Adopting a doctrinal methodology, the research identifies the prominent models and trends in different expedited procedures, accesses their compatibility with the objectives of MIC, and finally proposes a suitable model to attain (cost and time) efficiency and consistency both for the first-tier and appellate proceedings in MIC. By doing so, the study contributes some recommendations for the development of expedited MIC procedures.
Keywords: Appellate Proceedings; Consistency; Efficiency; Expedited MIC Procedures; Expedited Procedures; First-Tier Proceedings; ISDS Reform; Multilateral Investment Court (MIC); UNCITRAL Working Group III

Editorial: Special Edition on Banking, Competition & Corporate Law: Confronting Contemporary Challenges of Banking, Competition & Corporate Law to Enhance Consumer Protection - Chitimira, Howard (Potchefstroom Electronic Law Journal, 2024)
Although Zimbabwe has established several institutions to combat money laundering and related crimes, there is a perception that inadequate measures are taken to apprehend offenders responsible for financial crimes. Institutions such as the Financial Intelligence Unit (FIU), the Zimbabwe Anti-Corruption Commission (ZACC), the Zimbabwe Republic Police (ZRP), the National Prosecuting Authority (NPA) and the Reserve Bank of Zimbabwe (RBZ) have done little to prove that the government of Zimbabwe is resolute in combatting money laundering. On the contrary, it increasingly appears that these institutions are poorly equipped and lack the necessary capacity to enforce and uphold anti-money laundering (AML) measures in Zimbabwe. Further, there appears to be a selective application of the law, with one set of rules for individuals or institutions that are perceived as political adversaries of the incumbent establishment and a different set of rules for the political elite. Consequently, the selective application of the law projects Zimbabwe as a jurisdiction that is somehow tolerant to money laundering, corruption and related financial crimes, thereby lowering and tarnishing the standing of the country in the global economic community of nations. This paper provides a regulatory analysis of the AML role-players in Zimbabwe in order to assess their functions in combatting financial crimes. It also analyses whether these role-players are effective and substantively executing their responsibilities therein. The authors argue that while Zimbabwe is well able to effectively combat money laundering through the even application of the law to all persons regardless of their political or economic standing, it is imperative that its AML institutions operate without fear, favour or prejudice. This is crucial in combatting money laundering and instilling confidence in the general public's perception of AML institutions in Zimbabwe.
Keywords: Banking; Competition; Financial crimes; Financial markets; Securities

Impact of the Revision of the OHADA Accounting System on the Decision to Grant Bank Credit to Cameroonian Companies: An Interview with Credit Analysts - Sekadjie, Dedy Christelle; Mbohwa, Charles (Journal of Accounting and Finance in Emerging Economies, 2024)
Purpose: The objective of this study is to evaluate the impact of accounting data produced after the revision of the OHADA accounting system on the decision to grant bank credit to Cameroonian companies. Methodology: qualitative approach was used in this study. We conducted semi-structured interviews with eight credit analysts in eight banks based in Cameroon. We used the Nvivo 10 software to carry out the content analysis. Findings: It emerges from the analysis of the content of the speeches collected that the most used ratios by credit analysts are: activity ratios, debt ratios, operating ratios, financial structure and autonomy ratios, debt ratios and net cash. In addition, the information provided by the new accounting system is increasingly fluid, detailed, and precise and facilitates decision-making. However, when it comes to the completeness and sincerity of the information provided, analysts remain wary because, companies always provide information subjectively based on their interests Implication: This study reveals that despite the revision of the accounting system, users still remain wary face of informations provided because of its subjective nature. It is therefore recommended that Member States promote unified information for all stakeholders.
Keywords: Accounting system; Bank credit; Decision-making; Revision

From Divergent Paths to the Same Trap: The Legitimacy Crisis of the Investor-State Dispute Settlement System - Sönmez, Esma Yağmur (Middle East Technical University, 2024)
This thesis critically examines a much-debated issue in international law: the legitimacy of the Investor-State Dispute Settlement system (ISDS). The system was initially conceived to provide an alternate dispute resolution mechanism for the protection and promotion of foreign investment. In time, this objective has incited a discussion on the legitimacy of the system as the developed world has started to experience the role of host states. Since then, they have taken the lead in the reform process to achieve a balance between host state's and foreign investors' rights. To this effect, both the European Union (EU) and the Third Way Approaches to International Law (TWAIL) are for centralization of the system arguing its current problems emanate from its ad hoc and decentralized nature. Although both are aimed at system centralization, the paths they take to achieve it clearly differ. The EU seeks a permanent investment court by which ad hoc arbitration would give way to a more centralized framework. However, TWAIL advocates for a return to the pre-ISDS era, where national courts resolve investment disputes between foreign investors and states. The effectiveness of these two reform ideas in addressing the purported legitimacy concerns of the ISDS is critically examined in this thesis using Martti Koskenniemi's legal approach. Ultimately, it asserts that neither proposal is adequate to resolve the legitimacy issue of the system, as legitimacy can only be achieved by strengthening the principle of justice, which is feasible alone through a more decentralized structure.
Keywords: ADR; Alternative dispute resolution; Foreign investment; Foreign investors; ISDS; Investment Dispute; Investments; Investor-State Dispute Settlement

New Public Management Reforms and the Performance of Public Enterprises: An Assessment of Privatization in Nigeria's Telecommunications Sector - Adejuwon, David; Amodu, Akeem; Majekodunmi, Aderonke (African Journal of Politics and Administrative Studies, 2024)
The implementation of New Public Management (NPM) reforms, particularly privatization, has been a significant strategy adopted by governments worldwide to enhance the performance of public enterprises. This article focuses on the telecommunications sector in Nigeria, where privatization was introduced as part of broader economic reforms in the early 2000s. The objective is to assess the influence of privatization on the performance of public enterprises within this sector. The article is anchored on public choice theory. It is qualitative in nature, relying on secondary sources of data, such as, journals, textbooks, official publications and internet materials. It observes that privatization of public enterprises in the telecommunication sector in Nigeria has led to improvements in operational efficiency, increased investment inflows, and expanded service coverage. However, challenges such as regulatory effectiveness, equity in service provision, and the socio-economic impact on marginalized populations remain significant concerns. It contributes to the broader discourse on NPM reforms by providing empirical insights into the complexities and outcomes of privatization within Nigeria's telecommunications sector. It concludes with policy recommendations aimed at optimizing the benefits of privatization while addressing its associated challenges to ensure sustainable and inclusive growth in the sector.
Keywords: New Public Management; Operational Efficiency; Privatisation; Public Enterprises; Public Sector Performance; Service Delivery

The Challenges of Adoption of Eco Single Currency among ECOWAS Member-States - Anele, Livinus; Anuga, Joseph (African Journal of Politics and Administrative Studies, 2024)
The Economic Community of West African States, ECOWAS, had an agreement to adopt the Eco as its single currency for the fifteen member-states of the West African Sub-regional organization. This major objective has failed to materialize after a long period of time. This paper, therefore seeks to highlight the major challenges confronting the Eco currency project. Data were collected from secondary sources, using content analysis. The paper of discusses the challenges facing the proposed Eco single currency in West Africa, discusses the theoretical framework of monetary integration using Mundell’s factors of Mobility Theory and Mundell’s Optimum Currency Area Theory applied. Based on the findings, Some of the challenges facing the proposed Eco currency in ECOWAS include lack of political will, influence of France on its former territories in West Africa, membership of multiple regional blocs by member states of ECOWAS and fear of domination of the smaller states in the bigger ones. Other challenges include; security and political challenges, inadequate legal instruments to enforce treaty obligations, inadequate modern infrastructure among others. To make this proposed Eco currency a success, the paper suggests that West Africa Monetary Zone member states must take concrete action by showing political will towards the creation of Eco currency area in West Africa. There should be clearly spelt out benefits and costs accruing to each member state in the proposed Eco community currency area. All member states of ECOWAS must be treated as equal partners.
Keywords: Adoption; Anglophone-Francophone; Development; ECOWAS; Eco single currency

Nigeria-United States Economic Relations and the Development of the Oil Sector - Okorie, Ikechukwu; Iwuozor, Obialor; Itumo, Anthony (African Journal of Politics and Administrative Studies, 2024)
This study examines Nigeria – United States economic relations from 1999-2018. It was noted that since the Nigeria’s economic relation with United States, the development stride which Nigeria state so desired in the oil sector did not yield any tangible result within the period under study viz opening of new refineries and effective turn around maintenance of the refineries. The specific objectives of this study are: 1. To examine whether Nigeria-United States economic relations has led to opening of new indigenous refineries in Nigeria 2.To determine whether Nigeria–United States economic relations improved the maintenance of refineries in Nigeria within the periods under study 3.To ascertain if Nigeria and United States economic relations had advanced technological transfer in the oil sector industry in Nigeria. The data employed for the study were collected from documentary sources while content analysis was implored for data analysis. The theoretical framework that anchored this study is the Rentier State Theory (RST). After a critical analysis, the following findings were made: 1. it was discovered that Nigeria United States economic relations did not lead to opening of new indigenous refinery 2. The crude oil export to the United States did not improve the maintenance of oil refinery in Nigeria 3. The Nigeria-United States economic relations had not advanced technological transfer in the oil sector industry in Nigeria. In line with the findings the researcher made the following recommendations: 1.That Nigeria government should make a policy that will bring a paradigm shift from net import to net export 2. Nigerian government should make it policy easier as to accommodate and encourage private sector participation in the refining of petroleum products 3. Nigeria government should partner with other countries of the world outside United States that are willing to develop her indigenous technological skills.
Keywords: Crude oil; Development; Economic Relations; Oil sector; Petroleum

Corporate social responsibility performance of property-development firms in Nigerian south-western urban cities - Oyesomo, Oyewole; Oyedeji, Oyewale; Saheed, Omobolaji; Anifowose, Titilayo (Acta Structilia, 2024)
Previous studies on corporate social responsibility (CSR) in the construction and property-development domain have mainly focused on countries in the Global North with very few studies in the Global South. These prior studies have defined the pyramid elements (economic, legal, ethical, and philanthropic) that make up overall CSR, but none of them have assessed how well corporations performed in relation to each pyramid element, particularly in the property-development industry. Consequently, reflecting on the limited CSR studies in the Global South, this study examines the performance of property-development companies regarding the CSR pyramid elements. The study also assesses the barriers and strategic drivers of CSR among property-development companies. The study employed a descriptive survey research, and questionnaires were administered to 43 property-development companies. Descriptive data analysis was done to rank the relative importance of items from the questionnaire. Results showed that, although companies performed ‘well’ in their legal CSR, and ‘average’ in their economic and ethical CSR, companies performed ‘poorly’ in the area of philanthropic CSR. Lack of support by top management, corruption/lack of transparency, lack of knowledge and awareness by professionals, and lack of regulatory framework were identified as significant barriers to CSR implementation among property-development companies. Vision of founders/support by top management, regulatory framework, stakeholder activism, and good relationship-building are potential key strategic drivers of CSR implementation programmes among property-development companies. Given the findings, it is recommended that property-development companies should integrate CSR principles into their vision and mission statement and consider it to be a business function. This can be done by mitigating the barriers identified through the adoption of strategic drivers as postulated by this study.
Keywords: CSR; RSE

SME contractors’ management practices to achieve sustainable business performance in the Eastern Cape province, South Africa - Sogaxa, Athenkosi (Acta Structilia, 2024)
The construction industry in the Eastern Cape province of South Africa plays a crucial role in the region’s economy, yet small and medium enterprise (SME) construction companies face significant challenges in achieving long-term business sustainability. This article aims to provide practical guidelines for SMEs, by investigating the most critical construction management practices adopted by SME contractors. Utilising a quantitative approach, data were collected from 59 purposefully selected participants, including directors, construction managers, quantity surveyors, site agents, and technicians, all registered under the Construction Industry Development Board (CIDB) Grades 1-4 in General Building (GB). The management practices of SME contractors were analysed using the relative importance index (RII) and factor analysis to rank these practices according to their significance. Findings indicate that SME contractors prioritise health and safety strategies, effective resource utilisation, integrated project management systems, competent recruitment, strong leadership skills, and robust health and safety management as essential practices. The principal component analysis identified six key management factors to enhance competitiveness while contributing to the region’s sustainable development goals. These factors include shared knowledge among management, effective project scope planning, comprehensive health and safety management, ownership of construction business knowledge, scope control on projects, and clearly defined goals for management teams. This study is original in its focus on the specific management practices that can strengthen the sustainability of SME contractors within a developing region, providing a valuable framework for enhancing their operational effectiveness.

Intra-Africa trade and the need to rethink the neo-liberal approach - Ngwu, Franklin; Ojah, Kalu (Transnational Corporations Review, 2024)
Notwithstanding past trade reforms, trade in Africa and particularly intra-Africa trade, remain dismal. Africa has even created economic communities, fitted with monetary, fiscal, and socio-political anchors, by way of various Regional Economic Communities (RECs) – now reflected by the African Continental Free Trade Area (AfCFTA). Whilst these have yielded marginal benefits, the persistence of low intra-Africa trade calls into question their suitability. Focused on the realities of institutions targeted by these reforms and Africa's context – i.e., weak linkages between institutions, high informality, and low social capital – we posit that reforms have not elicited the hoped-for high intra-Africa trade because of their near total reliance on the neo-liberal approach, which neglects Africa's context. Drawing on Africa's sociology and new institutional economics, we use a conceptual institutional analysis to evolve a political economy based framework that suggests potential solutions: Linking the formal sector that currently underpins economic/trade policies to the informal institutions that are reflective of Africa's norms, values, cultures and expectations (the informal sector), and scaling up production; via the cooperatives production model, strategic procurement mandates, and effectuation of continental transportation infrastructure network, are our recommended pathways to reversing the current dismal intra-continental trade.
Keywords: Africa; Africa's sociology; Growth and trade policies; Institutional economics; Intra-Africa trade

Diaspora as a Generator of Foreign Direct Investment - Dizdarević, Emina (IUS LAW Journal, 2024)
Focusing on Bosnia and Herzegovina, this study examines how diasporas contribute to the creation of foreign direct investment (FDI) in developing countries. It defines FDI as the acquirement over assets in a foreign nation and highlights how diaspora populations support investment flows. It also examines diaspora investment strategies, such as diaspora portfolio investment (DPI) and diaspora direct investment (DDI), and offers a historical overview of diaspora FDI patterns and how Bosnia and Herzegovina's policies are changing to engage its diaspora more.One case study illustrates the impact of diaspora-led FDI by highlighting the success of Senad Šantić, a Bosnian entrepreneur who returned to his home country to start a tech company. While these investments support development and economic growth, there are still issues, like the possibility of putting one's own interests ahead of the interests of the economy as a whole. Particularly in Bosnia and Herzegovina, where diaspora participation has historically been low, the implementation of effective policies and procedures is crucial, especially from a regulation perspective.The study also looks at the future of FDI, emphasizing the part that digital technology and new investment patterns will play. Opportunities for developing nations can be found in digital FDI, especially in industries like fintech and e-commerce, yet obstacles still exist in luring these investments. According to all the findings, developing nations can improve their chances for economic success by creating an atmosphere that encourages diaspora investment which will shift those nations into the global investment scene. Ultimately, FDI regulations and government programs are needed in order to fully utilize diaspora-led FDI for sustained growth.
Keywords: Bosnia and Herzegovina; Diaspora Engagement; Diaspora Investment; Economic Development; FDI; Foreign direct investment

The Blockchain Data Gatekeepers Limited Liability for Violations of the GDPR - Jusić, Asim (IUS LAW Journal, 2024)
Data gatekeepers (data controllers and processors) that use blockchain for data transfer effectively enjoy limited liability for violations of the GDPR. This is due to the fact that applying the GDPR’s data gatekeeper system of liability to a decentralized technology such as blockchain is difficult for three reasons. Firstly, identifying data gatekeepers on the blockchain can only be done by either assigning data gatekeeper roles to actors on the blockchain, or structuring the blockchain as private or permissioned one, so as to fit with GDPR requirements. Neither of these approaches provides a universally applicable and satisfactory method for privacy protection. Secondly, because of their knowledge and investment in infrastructure, large data gatekeepers such as IBM, Amazon and Microsoft have an informational advantage over data protection authorities (DPAs) and an additional protective layer against liability, as their blockchain infrastructure is used by other businesses and corporations that are primarily liable for data processing. Finally, administrative fines and reputational damages for non-compliance with the GDPR are insufficient deterrents for large data gatekeepers, whereas damages awarded to individual data subjects for data gatekeepers’ violations of GDPR are extremely low and too costly to obtain.
Keywords: Blockchain; Compliance; Data gatekeepers; GDPR; Liability

Business Environment and its Impact on Attracting Foreign Direct Investment - Tanrıverdi, Elif Tanrıverdi (IUS LAW Journal, 2024)
This study provides an in-depth look at the complex relationship between business environments and foreign direct investment. The study examines this critical issue by focusing on emerging economies, such as Kosovo. In this research, analytical and empirical research methods have used to highlight the importance of FDI in promoting economic growth. FDI not only increases production capacity but also supports economic growth by increasing purchasing power and creating employment opportunities, especially in countries in transition. This analysis distinguishes between endogenous and exogenous variables to classify the various elements of the business environment. It is important to emphasize how a supportive business environment plays a vital role in attracting investment. The main factors affecting FDI include infrastructure quality, political stability, workforce skills, market potential and tax incentives. These initiatives are critical to creating a more favorable investment climate.As a result of the variables the study concludes by emphasizing the need for continuous reforms to strengthen the business environment. Such strategic efforts are crucial to optimize FDI flows and advance sustainable economic development. By strengthening regulatory frameworks and improving infrastructure, developing countries can be in better position itself to attract foreign investors. Furthermore, creating a strong business environment can also support the development of local entrepreneurs, increasing economic diversification. As a result, it not only facilitates the flow of capital, but also contributes to the long-term stability and growth of the national economy. Therefore, policymakers and governments need to prioritize these initiatives and develop comprehensive and sustainable strategies to improve the business environment.
Keywords: Business Environment; Economic growth; Foreign direct investment; Investment Incentives; Investments; Political Stability

The role and mandate of the motor industry ombudsman of South Africa : addressing prospects and challenges to enhance consumer protection - Tshabalala, Thapelo; Magau, Phemelo (PER / PELJ, 2024)
The Motor Industry Ombudsman of South Africa (MIOSA) is an industry ombud recognised under the Consumer Protection Act 68 of 2008 (CPA). The MIOSA regulates the interaction and provides for alternative dispute resolution in the automotive and related industries in South Africa. Moreover, the MIOSA is an impartial organisation that focusses on the resolution of disputes where a deadlock has been reached between the automotive and related industries and their customers, as well as relationships among participants in the automotive and related industries to the benefit of the parties. The role of the MIOSA is to make recommendations in cases referred to it where parties cannot reach common ground and are unable to arrive at mutually acceptable agreements following a dispute. This analysis explores and proffers possible solutions to address the challenges that impede the MIOSA from discharging its role and mandate under the CPA effectively in resolving consumer disputes in the South African automotive industry.
Keywords: Automotive industry; Consumer protection; Dispute resolution; MIOSA; Ombuds

Legal Certainty in the Resolution Process of Business Disputes due to Default on Payment with Bank Guarantee through Arbitration - Wijaya, Didit Wijayanto (International Journal of Science and Research, 2024)
Corporations have been established and recognized in Indonesia as entities engaged in business activities since 1602. In these business activities, disputes can occur regarding the non-disbursement of Bank Guarantees through the Indonesian National Arbitration Board (BANI). Therefore, this research uses the Normative Juridical method through a literature review. The research questions considered are (1) What is the guarantee of legal certainty in the process of resolving business disputes regarding Bank Guarantee payments through the Arbitration Board? (20) What can the Supreme Court Decision provide legal certainty for resolving business disputes through arbitration in Indonesia? The process of resolving business disputes in default on Bank Guarantee payments through the Arbitration Court has fulfilled the legal certainty principle. The results showed that the rules were available through different Arbitration and Alternative Dispute Resolution Laws, as well as other laws applied consistently in the BANI Surabaya Decision Number 59/ARB/BANI-SBY/XI/2021. The Supreme Court Decision Number 918 B/Pdt.Sus-Arbt/2023 tried the appeal case and rejected the application for annulment of the arbitration decision from the Applicant. In addition, legal certainty is created for corporate legal efforts to take the arbitration route.
Keywords: Arbitrage; Arbitragem; Arbitration; Business Disputes; Default; Legal Certainty

Digital Vulnerability and the Formulation of Harmonised Rules for Algorithmic Contracts: A Two-Sided Interplay - Rodriguez, Teresa de Las Heras Ballell (The New Shapes of Digital Vulnerability in European Private Law, 2024)
This book provides an analysis on whether and how the current European legal framework adequately deals with personal conditions in which digital...

Perspectives of post-commencement financiers regarding their voting rights on a business rescue plan - Van Niekerk, Larisa (University of Pretoria, 2024)
Post-commencement financiers provide a lifeline to companies under business rescue and these financiers have their best interest in the survival of these companies. Should it be that the business rescue plan is unsuccessful, the chances are that the post commencement financiers will be the largest creditors. In Wescoal Mining (Pty) Ltd v Mkhombo NO, a dispute arose regarding the appropriate adoption of a business rescue plan during the meeting. One critical legal issue was whether the Companies Act bestows voting rights exclusively to the company's creditors who existed at the initiation of business rescue, or if creditors accruing after the commencement may also partake in voting on the plan. Following an assessment by Judge Wilson, it was established that only creditors with claims predating the commencement were eligible to participate in the voting process. Subsequently, Judge Wilson believed that section 135 of the Companies Act places post-commencement financiers as creditors in a different class and provides for their protection and interests in a different way. Against this background, the dissertation evaluates the position of post-commencement creditors when it comes to voting on a business rescue plan.
Keywords: Business rescue; Company law; Creditors; Insolvency; Insolvency law; Life-line; Post-commencement creditors; Post-commencement finance

An Exploration of Selected Anti-Money Laundering Role-Players in Zimbabwe - Chitimira, Howard; Torerai, Elfas; Jana, Vimbai (Potchefstroom Electronic Law Journal, 2024)
Although Zimbabwe has established several institutions to combat money laundering and related crimes, there is a perception that inadequate measures are taken to apprehend offenders responsible for financial crimes. Institutions such as the Financial Intelligence Unit (FIU), the Zimbabwe Anti-Corruption Commission (ZACC), the Zimbabwe Republic Police (ZRP), the National Prosecuting Authority (NPA) and the Reserve Bank of Zimbabwe (RBZ) have done little to prove that the government of Zimbabwe is resolute in combatting money laundering. On the contrary, it increasingly appears that these institutions are poorly equipped and lack the necessary capacity to enforce and uphold anti-money laundering (AML) measures in Zimbabwe. Further, there appears to be a selective application of the law, with one set of rules for individuals or institutions that are perceived as political adversaries of the incumbent establishment and a different set of rules for the political elite. Consequently, the selective application of the law projects Zimbabwe as a jurisdiction that is somehow tolerant to money laundering, corruption and related financial crimes, thereby lowering and tarnishing the standing of the country in the global economic community of nations. This paper provides a regulatory analysis of the AML role-players in Zimbabwe in order to assess their functions in combatting financial crimes. It also analyses whether these role-players are effective and substantively executing their responsibilities therein. The authors argue that while Zimbabwe is well able to effectively combat money laundering through the even application of the law to all persons regardless of their political or economic standing, it is imperative that its AML institutions operate without fear, favour or prejudice. This is crucial in combatting money laundering and instilling confidence in the general public's perception of AML institutions in Zimbabwe.
Keywords: Anti-money laundering; Corruption; Financial crimes; Money laundering; Role-players

Essays on Corporate Finance and Corporate Governance - Ding, Zijun (McMaster University, 2024)
This thesis includes three essays that examine the effects of firm policies on labor costs, corporate culture, and stock markets. The first essay studies the impact of major customers on supplier firms’ performance, and I find that supplier firms are willing to collaborate with their major customers while keeping low financial leverages. The cooperation with major customers results in higher productivity and strategic alliance, which could explain the reduction in the labor share of supplier firms. In my study, labor share is defined as the ratio of labor costs to total revenue. Compared to firms without major customers, supplier firms with at least one major customer would reduce labor shares on average by 33% in absolute terms. The findings contribute to the growing literature on the global trend of labor share reduction. The second essay examines the effect of market competition on corporate openness, which is a particular aspect of corporate culture. Corporate openness reflects how open firms are when facing new ideas and experiences, and measures firms’ willingness to innovate and cooperate. I conclude that market competition improves firms’ corporate openness through good corporate governance. Furthermore, corporate social responsibility activities are seen as a positive social outcome of corporate openness. As to economic consequences, less open firms would experience stock return reductions when the market competition is high. The third essay studies the firms listed on Chinese stock exchanges that established an internal whistleblowing mechanism. The results show that the employee whistleblowing system prevents firms from misconducting and leads to reduced stock price crash risk. Furthermore, a cooperative corporate culture helps the internal whistleblowing system decrease crash risk, while an unfair organizational climate exerts the opposite influence. Overall, this study contributes to the emerging literature on the governance role of whistleblowing.

Climate change and international investment law : lessons from Africa's investment treaty practice - Mogashoa, Lebogang Paul (University of Pretoria, 2024)
This dissertation critically analyses new generation continental, regional and bilateral investment treaties in Africa with the aim to explore enhancements that could be made thereto in order to enable African citizens to hold investors accountable for investment-related climate change issues in Africa. The main research question answered in the dissertation is: to what extent does African investment treaty practice incorporate climate change-related provisions and investor accountability for climate change. The dissertation analysed traditional investment treaties, particularly noting their silence on climate change and investor accountability, and their partiality to investor protection. Using the AfCFTA Investment Protocol as an anchor alongside other new generation continental, regional and bilateral investment treaties in Africa, it discusses a fundamental contemporary shift in African investment treaty practice towards ensuring sustainable investments and greater investor accountability for sustainability in Africa. It also explores the various limitations in these new generation investment treaties that still make investor accountability. In the end it proposes reforms to the Investor-State Dispute Settlement provisions of these investment treaties to recognise citizen-led arbitral claims against investors, utilising the Hague Rules on Business and Human Rights as the procedural infrastructure for handling arbitration of such claims.
Keywords: AfCFTA; African Continental Free Trade Area; Climate change; ISDS; Investment treaties; Investments; Investor-State Dispute Settlement

The relationship between the business rescue practitioner and the directors of the company - Mokoka, Neo (University of Pretoria, 2024)
This dissertation on the relationship between the business rescue practitioner and the directors of the company under business rescue. In essence, this dissertation investigates whether a conflict arises between the duties, roles and powers of the business rescue practitioner and those of directors of the financially distressed company. The aim of this dissertation is to study what are the limitation on duties, roles and powers of directors of the company as a result of the appointment of the business rescue practitioner and the extent thereof. In achieving the above objective, this dissertation commences with setting out the background of business rescue proceedings in South Africa by analysing provisions of Chapter 6 of the Companies Act 71 of 2008 which has introduced “a new corporate rescue procedure” in South Africa, being business rescue. The focus is on provisions dealing with duties, roles and powers of directors in the ordinary course as set out in section 66, 75 to 77 of the Act. The focus then shifts to the provisions dealing with the commencement of business rescue proceedings, the appointment of the business rescue practitioner and his duties, roles and powers. In order to establish whether a conflict truly exists between the duties, roles and powers, various sources dealing with this issue are considered. In order to assess whether there are solutions in dealing with the conflict and/or limitation that arises, this dissertation includes a comparative study on selected foreign jurisdictions dealing with the interaction between the board of directors and business rescue practitioner are considered. In particular, this dissertation considers corporate rescue mechanisms in the Commonwealth of Australia, the United Kingdom and the United States of America. The purpose of the comparative study is to determine which lessons can be learned from the practices in the aforementioned jurisdictions. The overall objective of this study is to determine how the South African legal framework pertaining to the interaction between directors and business rescue practitioners can be enhanced.
Keywords: Business rescue; Business rescue practitioner; Companies Act 71 of 2008; Comparative study; Duties of directors; Limitations on powers; Powers of directors; Roles of directors; US bankruptcy code

Theories on the nature and purpose of the company and their implications for corporate governance - Ramalho, Anna Francina (University of Pretoria, 2024)
Despite the emergence of corporate governance as a formal discipline more than thirty years ago, the proliferation internationally of scholarly work on the topic and its formal regulation over this period, the scope, definition and direction of corporate governance remain contested. Company theories could potentially assist in this regard but have been inconsistent in their explanations of the both the means and ends of corporate governance. This has led to scepticism about the efficacy of theories to illuminate the phenomena associated with companies and company law. Notwithstanding, theory is critical as it makes explicit what is implicit in policymaking by regulators, as well as in the behaviour and decision-making by corporate actors, so that regulation and decisions are transparent for analysis and evaluation. The study, therefore, set out to provide a synthesis and doctrinal analysis of the main theories on the nature and general purpose of corporations in historical context. It was found that objections can be raised against all of these theories to a greater or lesser extent for inaccurate portrayal of the law, limited explanatory power and detachment from the real word. This study shows that corporate theories are a product of the settings in which they have developed and consequently none of these theories represents a universal or absolute truth, nor are they an inevitability due to widespread adoption and use. This leaves room for new formulations of the corporate form and its purpose fit for today’s context with its political, social and environmental challenges. This dissertation also includes further directions for theoretical exploration.
Keywords: Contractarianism; Corporate governance; Entity theories; Shareholder primacy; Stakeholder theories

The Middle Eastern and African Arbitration Review 2024 : CRCICA and new CRCICA Arbitration Rules - Selim, Ismail; Hafez, Mohamed (The Cairo Regional Centre for International Commercial Arbitration, 2024)

Selected problem areas pertaining to the removal of directors from office - Shange, Thandokuhle Wandile (University of Pretoria, 2024)
This paper constitutes a composite analysis of the legal framework and procedures for removing directors and the key challenges presented by the framework. It achieves this by looking at four legal questions: Firstly, it looks into what is the legal framework for director removal in South Africa, secondly, it delves into the challenges and/or uncertainties presented by this process, and further explores if there are any possible learnings South Africa can learn from foreign jurisdiction.
Keywords: Companies Act 2008; Comparative company law; Director removal; Director’s right; Judicial review; Section 71

Proposed legal reforms to protect South Africa's informal social security - Zeelie, Robin Erin (University of Pretoria, 2024)
Informal social security is a non-governmental form of social security between kin and/or community members and is a prevalent practice in South Africa. The question this dissertation analyses is whether the South African government fails in its constitutional duty to protect and advance informal social security. The dissertation limits itself to analysing cash transfers through social grants, and social insurance in the Unemployment Insurance Act and the Compensation for Occupational Injuries and Diseases Act. This dissertation delineates its definition of informal social security, historically contextualises its practice, and explains the contemporary formal social security framework. This dissertation finds five prominent shortcomings in the formal framework, and that these shortcomings have a profoundly negative, weakening effect on informal social security, as the more people who rely on informal mechanisms, the less it can respond to needs arising from life contingencies, shocks, and risks. The dissertation concludes by analysing three legal reform proposals the state can implement: extending existing social insurance frameworks to those in the informal sector, promoting cooperatives as a formal platform for the informal, and the basic income grant.
Keywords: Basic income grant; Cooperatives; Duty; History; Informal social security; Republic of South Africa; Social assistance; Social security

Attachment Proceedings for Goods Onboard an Aircraft: A Closer Look at the OHADA Law on Simplified Recovery Procedures and Measures of Execution - Atemlefac, Atemnkeng Micheal (Scholars International Journal of Law Crime and Justice, 2024)
The practical application of international conventions like the Montreal Convention of 1999 and the OHADA Uniform Act of 2023 in the context of attaching goods onboard aircraft presents significant challenges. These frameworks do not explicitly address the attachment of such goods, focusing instead on liability and recovery procedures. The OHADA Uniform Act aims to simplify recovery processes but may struggle with conflicting national regulations and regional legal practices. The absence of specific legislation for attaching goods in-flight creates a critical gap, leading to uncertainty and inefficiency in enforcement. Addressing this gap in this paper requires developing targeted legal solutions that align with international standards while addressing the unique demand of air transport.
OpenAlex: https://openalex.org/W4403880779
Keywords: Aircraft; Goods; Measures of Execution; Simplified Recovery Procedures

Lawyers and Non-Lawyers in International Arbitration: Discovering Diminishing Diversity - Nottage, Luke; Teramura, Nobumichi; Tanna, James (Loyola of Los Angeles International and Comparative Law Review, 2024)

Termination of the Mandate of an Agent: An Examination under OHADA Uniform Act on General Commercial Law - Ndekwena Noh, Alison (Scholars International Journal of Law Crime and Justice, 2024)
When an agency relationship is created, it confers on the parties obligations which must be fulfilled by the parties. These obligations do not remain forever as they can come to an end. This can be done under normal circumstances by the act of the parties or by operation of the law and when the conduct of the agent is in contradiction to the mandate agreement as may be the case if the agent is liable for serious misconduct as provided by the OHADA Uniform Act on General Commercial Law. The provisions of the act regarding termination on grounds of serious misconduct is worrisome, as the act talks about termination in such manner only for commercial agents and is silent about the other two types of agents: the broker and the commission agent. The act also, does not tell us what this serious misconduct it mentions by the commercial agent is, nor gives us insights on what constitutes such conduct to warrant termination of the mandate of the agent by the principal. When termination of the agency is done under conditions as such, it has grave consequences on the agent who might not be entitled to certain benefits associated with termination of the contract such as loss of the right to compensatory allowance or indemnity and more importantly may give room to arbitrary or wrongful termination of the mandate of the agent. Through analytical and comparative studies, this paper focuses on termination of the mandate of an agent under the OHADA Uniform Act on General Commercial Law, wherein, the different modes of termination of the mandate of an agent have been discussed, and more specifically makes an attempt in looking at what serious misconduct is and what could amount to such conduct so as to avoid arbitrary or wrongful termination. It is therefore suggested that, statutory guidelines found in other statutes in relation to the subject matter can serve as a lamp light in our context.
OpenAlex: https://openalex.org/W4403198358
Keywords: Mandate

Editorial on Doing business in Africa: Navigating opportunities and challenges in Africa's emerging markets - Adomako, Samuel; Shenkar, Oded; Liu, Xiaohui; Amankwah-Amoah, Joseph; Ahsan, Mujtaba (Journal of International Management, 2024)
This editorial delves into the evolving context of doing business in Africa, tracing its journey from being dubbed the “hopeless continent” to becoming a beacon of hope and opportunity. Drawing on a wealth of scholarly research, it highlights Africa's increasing attractiveness for global investments, underscored by rising FDI inflows and the emergence of a vibrant middle class. Despite these promising trends, the editorial also sheds light on the persistent challenges, including institutional fragility and political instability, coupled with limited representation in the existing international business discourse. We advance a more nuanced understanding of Africa's business environment, emphasizing the need for responsible growth, improved governance, and sustainable development. Thus, the Special Issue offers insights into the complexities and challenges of doing business in Africa, as well as the paradoxes and potential for fostering competitiveness and inclusive growth on the global stage.
Keywords: Africa; Doing business; International business; MNEs

'Banking' on artificial intelligence to enhance bank risk management - Chiba, Mayuree (University of Pretoria, 2024)
This dissertation investigates the impact of digital transformation on risk management within the banking sector, emphasizing the integration of artificial intelligence (AI) in enhancing operational risk management. It examines key research questions about how digitisation reshapes risk management practices, the extent to which South African banks align with international standards, and the role of AI in advancing these frameworks. The study finds that AI holds substantial potential to improve risk management, particularly in managing operational risks, while underscoring the indispensable role of human oversight. Ultimately, this shift toward a more AI-driven, adaptive approach marks a pivotal evolution in the financial sector, suggesting that the future of risk management can indeed rely on AI's transformative capabilities.
Keywords: Artificial Intelligence; Bank; Inteligência artificial; Intelligence Artificielle; Operational risk; Risk management

Product liability in an age of development risks : should South Africa reconsider adopting a development risk defence? - Tennant, Sarah-lynn; Van Heerden, C. M. (Corlia) (Journal of African Law, 2024)
To provide protection against harm caused by defective, unsafe products and to promote product safety, the law of product liability has developed as a specialized area of the law of delict (tort). The vexing question is, who should bear such liability? This contribution interrogates the notorious EU development risk defence, which exonerates manufacturers that meet certain stringent requirements for undiscoverable development risks in products that consequently inflict harm on consumers. In particular, it considers the election by South Africa, which recently adopted a “strict” product liability regime with the introduction of the Consumer Protection Act 2008, not to adopt such a defence. The purpose of this contribution is to consider the nature and scope of the development risk defence as contained in article 7(e) of the European Union (EU) Product Liability Directive and to determine whether it was prudent for South Africa to steer clear of incorporating a similar defence in its new statutory product liability regime.
Keywords: Defective product; Developmental risk; Hybrid regime; Product liability; Strict liability

Product Liability in a More Circular Economy : A Study of Liability for Alternative Methods of Distributing and Producing Consumer Goods - Van Gool, Elias (Université de Lille, 2024)
Specific, more strict theories of product liability, which have now largely been maximally harmonised in the EU, have developed on the basis of a linear economic model. By using doctrinal and economic legal research, this thesis examines the state of EU product liability law and how it is tested by alternative, circular economic methods of distributing and producing consumer goods, like product reuse, repurposing, resales and other retransfers, repairs, refurbishments and remanufacturing. Besides direct relevance to circular economy in the consumer goods sector, this study of so-far overlooked questions offers new theoretical insights about product liability with broader academic and practical relevance. After a general introduction to the domains of product liability and circular economy, a normative framework is developed that blends distributive justice in terms of economic efficiency with corrective justice. Subsequently, it is argued that also in a more circular economic setting a more strict product liability rule like the EU harmonisation is preferable in light of this normative framework, while the added value of product liability increases compared to its main regulatory alternatives. The thesis then studies the application to the aforementioned circular strategies of current EU product liability law based on the 1985 Directive and its almost finally adopted 2024 successor. Overall, EU product liability law turns out to be quite versatile and its relevance in a more circular consumption sector is improved by several of the new proposed rules. Nevertheless, some limitations remain and also some interpretative issues are identified in the proposed new Directive, for which amendments are proposed. Les théories spécifiques et plus strictes de la responsabilité du fait des produits, qui ont maintenant été largement harmonisées au maximum dans l'UE, se sont développées sur la base d'un modèle économique linéaire. En utilisant la recherche doctrinale et économique en droit, cette thèse examine l'état du droit européen en matière de responsabilité du fait des produits et comment il est mis à l'épreuve par des méthodes économiques alternatives et circulaires de distribution et de production de biens de consommation, comme la réutilisation des produits, le réemploi, la revente et autres retransferts, les réparations, les reconditionnements et la refabrication. Outre une pertinence directe pour l'économie circulaire dans le secteur des biens de consommation, cette étude des questions jusqu'à présent négligées offre de nouvelles perspectives théoriques sur la responsabilité du fait des produits avec une pertinence académique et pratique plus large. Après une introduction générale aux domaines de la responsabilité du fait des produits et de l'économie circulaire, un cadre normatif est développé qui mélange la justice distributive en termes d'efficacité économique avec la justice corrective. Ensuite, il est soutenu que, même dans un cadre économique plus circulaire, une règle de responsabilité du fait des produits plus stricte comme l'harmonisation de l'UE est préférable à la lumière de ce cadre normatif, tandis que la valeur ajoutée de la responsabilité du fait des produits augmente par rapport à ses principales alternatives réglementaires. La thèse étudie ensuite l'application aux stratégies circulaires susmentionnées du droit actuel de l'UE en matière de responsabilité du fait des produits basé sur la Directive de 1985 et son successeur de 2024 presque adopté. Dans l'ensemble, le droit européen en matière de responsabilité du fait des produits se révèle assez polyvalent et sa pertinence dans un secteur de consommation plus circulaire est améliorée par plusieurs des nouvelles règles proposées. Néanmoins, certaines limitations subsistent et des questions d'interprétation sont également identifiées dans la nouvelle directive proposée, pour lesquelles des amendements sont proposés.
Keywords: Accidents; Accidents de biens de consommation; Biens d'occasion; Biens de consommation; Circular economy; Commerce d'occasion; Consommateur (protection); Consumer product accidents; Product liability; Produits d'occasion; Repair; Responsabilité (droit); Responsabilité du fait des produits; Responsabilité du fait des produits (droit européen); Responsabilité du fait des services; Reuse; Réparation; Réutilisation; Second-Hand; Économie circulaire

Beyond free trade in raw materials: Reconciling international trade rules with planetary boundaries - Kuppuswamy, Chamundeeswari; Boklan, Daria (The Extractive Industries and Society, 2024)
International trade rules enshrined in agreements like the General Agreement on Tariffs and Trade (GATT) promote free trade, with exceptions for environmental protection. This paper explores the tension between these rules and Earth Systems Science's concept of planetary boundaries, which define environmental tipping points beyond which humanity faces irreversible harm. We analyse GATT's provisions, particularly Article XI's prohibition on trade restrictions and Article XX's exceptions, through the lens of planetary boundaries. Our analysis argues that current interpretations of these articles are inadequate to address the environmental impact of raw material trade. We further examine the concept of permanent sovereignty over natural resources, which grants states autonomy over resource exploitation and trade. We posit that planetary boundaries are not a restriction on sovereignty but a call for modifying state trading behaviour and consequently how international trade rules is structured and interpreted. This analysis demonstrates the complexity of transforming the legal landscape necessary for a global just energy transition, a response to climate change that requires aligning international trade with environmental sustainability.
Keywords: Climate change; GATT Art. XX; No-harm principle; PSNR; Planetary boundaries; WTO trade rules

Product Liability in a More Circular Economy : A Study of Liability for Alternative Methods of Distributing and Producing Consumer Goods - Gool, Elias van (Université de Lille ; Katholieke Universiteit Leuven, 2024)
Specific, more strict theories of product liability, which have now largely been maximally harmonised in the EU, have developed on the basis of a linear economic model. By using doctrinal and economic legal research, this thesis examines the state of EU product liability law and how it is tested by alternative, circular economic methods of distributing and producing consumer goods, like product reuse, repurposing, resales and other retransfers, repairs, refurbishments and remanufacturing. Besides direct relevance to circular economy in the consumer goods sector, this study of so-far overlooked questions offers new theoretical insights about product liability with broader academic and practical relevance. After a general introduction to the domains of product liability and circular economy, a normative framework is developed that blends distributive justice in terms of economic efficiency with corrective justice. Subsequently, it is argued that also in a more circular economic setting a more strict product liability rule like the EU harmonisation is preferable in light of this normative framework, while the added value of product liability increases compared to its main regulatory alternatives. The thesis then studies the application to the aforementioned circular strategies of current EU product liability law based on the 1985 Directive and its almost finally adopted 2024 successor. Overall, EU product liability law turns out to be quite versatile and its relevance in a more circular consumption sector is improved by several of the new proposed rules. Nevertheless, some limitations remain and also some interpretative issues are identified in the proposed new Directive, for which amendments are proposed. Les théories spécifiques et plus strictes de la responsabilité du fait des produits, qui ont maintenant été largement harmonisées au maximum dans l'UE, se sont développées sur la base d'un modèle économique linéaire. En utilisant la recherche doctrinale et économique en droit, cette thèse examine l'état du droit européen en matière de responsabilité du fait des produits et comment il est mis à l'épreuve par des méthodes économiques alternatives et circulaires de distribution et de production de biens de consommation, comme la réutilisation des produits, le réemploi, la revente et autres retransferts, les réparations, les reconditionnements et la refabrication. Outre une pertinence directe pour l'économie circulaire dans le secteur des biens de consommation, cette étude des questions jusqu'à présent négligées offre de nouvelles perspectives théoriques sur la responsabilité du fait des produits avec une pertinence académique et pratique plus large. Après une introduction générale aux domaines de la responsabilité du fait des produits et de l'économie circulaire, un cadre normatif est développé qui mélange la justice distributive en termes d'efficacité économique avec la justice corrective. Ensuite, il est soutenu que, même dans un cadre économique plus circulaire, une règle de responsabilité du fait des produits plus stricte comme l'harmonisation de l'UE est préférable à la lumière de ce cadre normatif, tandis que la valeur ajoutée de la responsabilité du fait des produits augmente par rapport à ses principales alternatives réglementaires. La thèse étudie ensuite l'application aux stratégies circulaires susmentionnées du droit actuel de l'UE en matière de responsabilité du fait des produits basé sur la Directive de 1985 et son successeur de 2024 presque adopté. Dans l'ensemble, le droit européen en matière de responsabilité du fait des produits se révèle assez polyvalent et sa pertinence dans un secteur de consommation plus circulaire est améliorée par plusieurs des nouvelles règles proposées. Néanmoins, certaines limitations subsistent et des questions d'interprétation sont également identifiées dans la nouvelle directive proposée, pour lesquelles des amendements sont proposés.
Issue: 2024ULILD015
Keywords: Accidents de biens de consommation; Biens d'occasion; Circular economy; Consumer product accidents; Product liability; Repair; Responsabilité du fait des produits et du fait des services; Reuse; Réparation; Réutilisation; Second-Hand; Économie circulaire

The role and liability of internet service providers in South Africa : a critical and comparative appraisal - Nameka, Celeste Zara (University of South Africa, 2024)
This research uses a comparative approach to explore the role and liability of internet service providers in South Africa. The research aims to analyse and compare the role and liability of internet service providers for crimes and civil infractions committed by content providers and/or internet users. Against this aim, the researcher argues that internet service providers, as intermediaries, are ideally placed to monitor and control illicit content provision and/or internet use by the end user. The research focuses on South Africa, China, Ireland, and Nigeria. The research interrogated legislative control and queried the fitness for purpose of these mechanisms for internet service providers and the lacunae created by a rapidly expanding digital world comparatively. The research points out recurrent controversial and problematic concerns that affect both the internet service provider and the consumer. The researcher further explores challenges in applying legal imperatives to internet service providers that affect their end users. The comparative analysis assists in indicating how internet service providers operate in practice and their control (or lack thereof) by various legal frameworks. The researcher makes recommendations and offers solutions to assist with the future role and development of internet service providers and their impact on the end-user and criminal justice system.

Anticipation of ratings during crises and investor behaviour: The case of MENA countries - Mahouachi, Noura; Henchiri, Jamel Eddine (African Journal of Economic and Business Research, 2024)
The study explores the reaction of stock markets to anticipated or unexpected rating announcements by the market in a crisis context by conducting an empirical study on the MENA (Middle East and North Africa) stock market over the period from December 2010 to August 2022. The results show that the crisis context support the anticipation of bad ratings and neutral ratings as opposed to good ratings. These results validate the asymmetry in investor reaction to announcements of anticipated rating downgrades compared with announcements of upgrades in times of crisis. This reaction highlights the irrational behave of investors in times of crisis. In fact, when investors detect a risk concerning the financial situation of a stock, they anticipate a downgrade and react quickly, even before the official announcement of the downgrade, by selling their shares on masse. This action will cause the share price to fall. Similarly, the market’s weak reaction to early good announcements is explained by the fact that this type of announcement does not provide them with any unknown information to guide their financial decisions.
Keywords: Abnormal returns; Anticipation; Event study; Expected rating; Stock markets; Unexpected rating

The Impact of Financial Technology (Fin Tech) on Economic Growth: Evidence from Tanzania - Ngeze, Raphael Michael; Seif, Muba (African Journal of Economic and Business Research, 2024)
This research is driven by the rapid spread of fintech, and its contributions to Tanzania’s economic growth. This study uses quantitative quarterly time series data from Tanzania from 2008 to 2022. The Augmented Dicky Fuler (ADF) is used for the stationarity test, Johansen Cointegrations for the hypothesis and Cointegrations test, VAR and VECM for testing both short-run and long-run causality relationships, and Granger Causality for testing variable causality. The Ordinary Least Squares (OLS) regression model is used for parameter estimation, modelling and significance testing. The results show that the model is statistically significant and the independent variables in the regression accounted for around 89% of the overall variation in GDP. Fintech variable subscriptions have a positive impact on Tanzania’s economic growth. Thus, unemployment in Tanzania may be alleviated by the growing sector of financial technology. Fintech has involved many people from all over the world, including Tanzania, and has had a positive impact on both the national economy and per capita growth. Since TTCL and ZANTEL have witnessed a sharp decline in subscriptions, the government, as a fixed-wired broadband service provider, must take the necessary steps to increase the subscriptions.
Keywords: Economic growth; Financial Technology; M-Pesa; OLS; VAR; VECM

Effect of Taxpayer’s Attitudes on Tax Evasion among SMEs in Tanzania: A Case of Singida Tax Region - Chindengwike, James (African Journal of Economic and Business Research, 2024)
Paying taxes is essential to attaining sustainable economic growth and national economic independence, hence tax evasion is a concern for the economies of both wealthy and developing countries. This study examined how tax payer attitudes, particularly in the Singida Tax Region, affect tax evasion in Tanzanian Small and Medium-Sized Enterprises (SMEs). This study employed a survey method in which data collection comprised both qualitative and quantitative research approaches. A multiple regression model was employed in combination with a descriptive study approach to ascertain the outcomes. 145 SMEs taxpayers made up the study's as a sample size. The findings demonstrate that, among SMEs in the Singida Region, peer influence, tax awareness, tax morale, and tax evasion have statistically significant relationships with the taxpayer's attitude. This association is supported by statistics. Consequently, the United Republic of Tanzanian government needs to consider how taxpayer attitudes including peer pressure, tax knowledge, and morale affect tax evasion. This will contribute to the goal of reducing tax avoidance by all taxpayers, including SMEs Taxpayers.
Keywords: SMEs Taxpayers; Tanzania; Tax evasion; Taxpayer’s Attitudes

Facilitating Trade through Rules of Origin: A Consideration of the African Continental Free Trade Area - Okoroma, Blessing Ijeoma (University of Calgary, 2024)
Rules of origin play a pivotal role in free trade agreements. Apart from serving as a tool to distinguish goods by determining the nationality of a product, rules of origin have the capacity to increase trade relations or deter it. Of course, it is the hope of any viable state to increase profitable trading relations, and if rules of origin can help with that, it becomes expedient to fully understand how these rules of origin operate. In Africa, we see rules of origin being implemented amongst the Regional Economic Communities (RECs), but this has come with many struggles. In fact, low intra-African trade can be narrowed down to complex rules of origin regimes deployed in regional agreements in Africa. As of date, the major RECs have each implemented different rules of origin, leading to the co-existence of conflicting rules of origin across Africa. This non-uniformity in the rules of origin regimes in Africa has resulted in low continental trade in Africa. As such, these RECs have not yielded the expected increase in intra-African trade. With the creation of the African Continental Free Trade Area (AfCFTA), which currently doubles as the latest and largest FTA in Africa, it is expected that better rules of origin will be deployed to mitigate the existing intra-African trade deficits. This thesis thus deploys a doctrinal approach in determining whether AfCFTA’s rules of origin are positioned to achieve greater intra-African trade. Consequently, this thesis uncovers some lapses in AfCFTA’s rules of origin and calls for harmonization of all the rules of origin in Africa and recommends a possible amendment to Article 19 of the Agreement establishing AfCFTA to accommodate the intended harmonization.
Keywords: African Continental Free Trade Area; Free Trade Area; Rules of Origin

Selected legal aspects of money-laundering control in trade-finance instruments - Makuyana, Tsanangurai (University of South Africa, 2024)
The traditional perception that trade-finance instruments are less susceptible to the risk of money laundering has changed due to the increasing threat of trade-based money laundering (TBML). In the process of facilitating trade-finance transactions, financial institutions may be entrapped in the dangers of TBML and be abused for criminal gains. In this regard, the institutions play a significant role in ensuring that only legitimate trade is facilitated through trade finance without being tainted by TBML. Despite that, vulnerabilities for the vice have been discovered in the trade-finance sector. This study employs a macro-comparative approach in examining how selected jurisdictions respond to the problem of TBML in trade-finance instruments. It analyses the vulnerabilities of documentary credits, documentary collections, demand guarantees and standby letters of credit to the potential risk of TBML. The thesis compares the response of the South African AML regime with that of the English, the US and Singapore AML regimes to the threat of TBML in the selected trade-finance instruments. The study reveals, inter alia, that there is not much difference between the South African AML regime and the AML regimes of the comparative jurisdictions in terms of the legislative response to the challenge of TBML in trade-finance transactions. However, the difference is apparent when it comes to the varied institutional responses to the problem within the jurisdictions considered in this thesis. While South African AML authorities have not made any official pronouncement against TBML in trade finance, those from other comparative jurisdictions have done so. The latter have also gone a step further to produce best practice reports on TBML for banks and other financial institutions involved in trade-finance transactions to enable the institutions to prepare for the challenge. However, similar to the South African position, there has not been any legislative change in the comparative jurisdictions to provide for TBML in specific terms. This means that these jurisdictions also deal with TBML using current AML legislation, which was designed originally for cash-based money-laundering operations. Therefore, the institutions and laws under the South African AML regime are relevant in the combatting of TBML. However, they may require some modifications to appropriately counter the challenge. The study makes various policy and best practice recommendations to strengthen the South African AML regime against TBML in trade-finance transactions.
Keywords: AML Regime; Bankers Association for Finance and Trade; Black Market Peso Exchange; Customer Due Diligence; Demand Guarantees; Documentary Collections; Documentary Credits; English AML Regime; FinCEN; Financial Action Task Force; Financial Intelligence Centre Act 38 of 2001; Financial Intelligence Unit; International Best Practices; International Chamber of Commerce; International Trade; Money Laundering; Money-Laundering Control; Prevention of Organised Crime Act 121 of 1998; RBA; Red-Flag Indicators; SAMLIT; Singapore AML Regime; South African AML Regime; Standby-Letters of Credits; TBML; Trade Finance; Trade-Based Money Laundering; Trade-Finance Instruments; Trade-Finance Principles; Trade-Finance Transactions; US AML Regime; World Customs Organisation; the Wolfsberg Group

African Continental Free Trade Area and Regional Trade in ICT and Digital Technologies - Adams, Kweku; Attah-Boakye, Rexford; Yu, Honglan; Chu, Irene; Mali, Dafydd (Journal of International Management, 2024)
This study examines the impact of the African Continental Free Trade Area (AfCFTA) on regional trade in the Information and Communication Technology (ICT) and Digital Technologies (DT) sector across 43 African countries from 2014 to 2021. Employing the augmented gravity model and confidence-level estimations, it highlights AfCFTA's mediating role in enabling ICT&DT trade on the continent. Using hierarchical regression analysis of a panel dataset comprising 5,160 observations, the findings imply that trade openness and productive capacities not only facilitate trade in the ICT&DT sector but also result in positive spillover effects across various economic sectors. This study contributes to the international business literature by refining the application of the gravity model to capture the need for sector-specific analyses to unpack institutional dynamics and dis-enablers of trade. It identifies AfCFTA as a pivotal yet underexplored element in the global trade landscape, highlighting its potential as Africa seeks a more prominent role on the global stage. The research stresses the significance of digital empowerment and policy reforms to maximise the benefits of regional integration under AfCFTA.
Keywords: AfCFTA; ICT and digital technologies; Regional trade; Trade enablers; Trading bloc

Joint and several liability at the interface of national and international law and the FIDIC conditions of contract - Mahasneh, Nisreen (Uniform Law Review, 2024)
The international terms of the 2017 FIDIC Red Book (reprinted and amended in 2022) state that, when the contractor is a joint venture (JV), all members are jointly and severally liable to the employer. These terms also establish certain procedural rules—the most important ones being the submission to the employer of the JV undertaking and the appointment of a leader. However, these international terms do not provide for substantive rules pertaining to the plurality of the JV members. These require reference to the applicable law that governs the construction contract. The applicable law can be domestic law, such as Qatari law, or an international soft law, such as the Unidroit Principles. Comparing these two possibly applicable laws, it becomes evident that there are no significant differences between the two regarding the substantive rules concerning a plurality of obligors. Furthermore, it is argued that the majority of these substantive legal rules, whether national or international, are inoperative in a construction contract incorporating the international terms of the FIDIC Red Book.

From red tape to red carpet: the Unidroit Cape Town Convention and MAC Protocol’s Adventure in Africa - Otabor-Olubor, Iyare (Uniform Law Review, 2024)
This article examines the implementation of the Mining, Agricultural and Construction (MAC) Equipment Protocol under the Cape Town Convention in Africa, focusing on enhancing economic growth and sustainable development through improved access to financing for high-value mobile equipment. Africa’s economic development is significantly hindered by inadequate infrastructure, which escalates transaction costs and limits access to international markets. Investment in modern infrastructure, particularly in the mining, agricultural, and construction sectors, is typically expensive for many businesses in the African region. The MAC Protocol aims to address these challenges by providing a uniform legal framework that supports the financing of MAC equipment. The Convention and the MAC Protocol facilitate access to affordable capital and reduce risks for financiers who take international interests in MAC equipment, promoting economic activities in Africa. The article highlights the legal protections offered by the MAC Protocol, ensuring rights against third-party claims and enhancing the enforceability of international interests. The adoption of the MAC Protocol by African States could significantly impact their ability to meet the United Nations Sustainable Development Goals by making modern, cost-efficient equipment more accessible, thus boosting productivity and economic diversification. The article advocates for adopting the MAC Protocol, emphasizing its potential to enhance foreign investment in the mining, agriculture, and construction sectors, stimulating economic development in Africa. This strategic move will propel African countries towards greater economic resilience and integration into the global economy. The article also critically analyses and illustrates the several declaration mechanisms available to countries adopting the MAC Protocol, accompanied by a guidance note to sensitize lawmakers when signing and/or ratifying or acceding to the Cape Town Convention and the MAC Protocol.

Compliance with decent work standards by multinational enterprises - Maluleke, Tirhani Foster (University of Pretoria, 2024)
In contemporary times, the issue of human and labour rights violations has gained significant momentum, rendering it imperative for international organisations, states, and businesses to address this critical concern. It is widely acknowledged that while multinational enterprises can aid in achieving economic growth by investing directly overseas and raising the standard of living for the residents of host nations, their business operations may also result in abuse of human and labour rights. The United Nations (UN) Charter was drafted to set forth obligations for individual states, yet businesses do not bear international legal obligations. The Universal Declaration on Human Rights was adopted to implement the substantive contents of human rights referred to in the UN Charter in the general way. The preamble of the Universal Declaration refers to all organs of society, but, at the time of its adoption, businesses were not considered among such organs. It was inconceivable that business organisations would become so economically powerful within a few decades that they would pose a significant risk to human and labour rights, which would not be easily regulated under the national law of their host nations. It is the hypothesis of this study that numerous multinational enterprises (MNEs) violate core human and core labour rights, and that the existing regulatory framework does not adequately regulate them. To prove this hypothesis, this thesis will adopt a two phased approach. Firstly, a careful case law and literature review will reveal the inadequate regulation of MNEs. Evidence suggests that MNEs are guilty of flagrant labour standards and human rights violations. As a result of globalisation, MNEs have gained stronger international influence, and they are able to move their businesses to countries with low cost of labour and less regulations. This phenomenon weakens the governments of host nations as they are keen to promote foreign direct investment in order to reduce unemployment and to ensure economic growth. As a result, the host nations are encouraged to set laws that will attract MNEs at the expense of human and core labour rights. As result, MNEs are not held accountable in respect of their violation of human and labour rights. Secondly, this thesis will assess the efficacy of the regulatory instruments developed by the international community in response to the mentioned problem. This aspect is covered in Chapter 3 to 7 of this thesis. The strategies include the public and private hard law and soft law mechanisms developed at international level as well as campaigns by Non-Governmental Organisations (NGOs). Based on evidence, this thesis will conclude that a soft law approach is not fully effective. As such, Chapter 8 of this thesis proposes the introduction of some hard law measures to improve the existing soft law instruments to augment the existing legislative frameworks of the host countries. In particular, the thesis recommends regulatory reforms, which will empower the International Labour Organisation to intervene to prevent the labour rights violations by MNEs and where such violations occur, to at least provide effective remedies to vulnerable employees. This thesis constitutes a theoretical study, which attempts to provide suggestions regarding the implementation of realistic measures, which if implemented, may contribute to the attainment of decent work for all men and women who are engaged in work for MNEs.
Keywords: Codes of conduct; Decent work; Hard law; Human rights; Human rights due diligence; ILO MNE declaration; International Labour Organisation; International framework agreements; Labour rights; Multinational enterprises; OECD guidelines; Regional free trade agreements; Soft law

Cross-border banking and bank stability: evidence from Sub-Saharan Africa - Gondwe, Sopani; Gwatidzo, Tendai; Mahonye, Nyasha (Journal of Banking Regulation, 2024)
Based on bank-level data from 29 Sub-Saharan African countries between 2005 and 2019, we apply panel fixed effects (FE) and two-step system GMM estimators to investigate whether increased cross-border banking affects domestic banking sector stability. We find significant evidence that the stability of banks in host countries declines with an increased presence of foreign banks—and the impact is more pronounced on banks that are small and less efficient. The stability impact of foreign banks is also found to depend on the quality of governance institutional factors in the host country. The findings shed some important insights on the downside of financial liberalisation policy in developing countries and the need for increased cross-border collaboration between home and host supervisory authorities in the SSA region—especially in jurisdictions where the foreign bank affiliates are systemically important. The domestic supervisory authorities thus need to effectively manage the inherent trade-off between reaping the benefits from international financial integration while effectively safeguarding domestic banking systems against cross-border contagion and fragility.
Keywords: Bank stability; Consolidated supervision; Cross-border banks; Home-host countries; Systemically important

A Proposal for Reforming the Calculation of Damages in Investment Treaty Arbitration = Proposition pour le calcul des dommages-intérêts dans l’arbitrage au titre des traités d’investissement = Propuesta para Reformar el Cálculo de Daños en el Arbitraje de Los Tratados de Inversión - Jarrett, Martin (Investment Treaty News, 2024)

Characterization (and Registration) of a “BRI Dispute” - Kirkwood, Jamieson (Asian Journal of International Law, 2024)
This article explores the terms “BRI dispute” and “BRI jurisprudence”. It undertakes a practical and theoretical analysis that considers whether “BRI disputes” have distinct and visible characteristics and are capable of being identified in a legal sense. This is important since practitioners – arbitration centres and law firms – use the term broadly and without specific criteria. By exploring the customary usage and the approach of legal scholars to the term, presenting examples of “BRI disputes” and examining their unique features, and constructing a theoretical approach (utilizing the concepts of ratione materiae, ratione loci, ratione temporis, and ratione personae; and considering the jurisprudence of the ICSID), this article moves from a broad to a narrow analysis to develop both a definition and a system of registration of “BRI disputes” for use by academics, practitioners, and policymakers.
Keywords: BRI; Belt and Road; China; Dispute Settlement; ICSID

An overview of the extent of the powers of South African competition authorities in the regulation of price discrimination under the Competition Act 89 of 1998 in the context of digital transformation - Magau, Phemelo (PER / PELJ, 2024)
The purpose of the Competition Act 89 of 1998 as amended (the Competition Act) is, among others, to promote the efficiency, adaptability and development of the economy as well as to provide consumers with competitive prices and product choices. In line with this purpose, the Competition Act provides that a dominant firm is prohibited from engaging in price discrimination if such conduct will likely substantially prevent or lessen competition, which would be to the detriment of consumers. Notably, the Competition Act has established various bodies to regulate competition and act against any conduct prohibited by this Act in South Africa. These bodies include the Competition Commission, the Competition Tribunal, and the Competition Appeal Court. Notwithstanding the prohibition of price discrimination, the Competition Act does not expressly provide adequate enforcement tools for competition authorities to combat uncompetitive practices in the digital era. Moreover, the Competition Act does not expressly grant these statutory bodies clear roles and mandates on providing consumers with adequate and suitable redress when they have been victims of algorithmic price discrimination. With recent technological developments, electronic commerce (e-commerce), and digital transformation, consumers have become vulnerable to various challenges such as excessive pricing, data breaches and algorithmic pricing. The online and digital markets are characterised by complex transactions, innovative technologies and business practices which expose all consumers, including vulnerable consumers, to different risks. As such, the role of the competition authorities needs to be recalibrated to enhance consumer protection on the pricing of goods and services. To this end this paper seeks to investigate the role and ambit of the powers of these competition authorities in the regulation of price discrimination in the context of digital transformation and the digital economy. This is done to assess whether the competition authorities have the necessary tools of enforcement to ensure that markets are competitive and to combat uncompetitive conduct in the digital economy and online markets.
Keywords: Algorithmic pricing; Competition authorities; Consumer protection; Digital transformation; Price discrimination

Corporate Social Responsibility Practices in the Nigerian Public Sector - Mohammed, Abbas (University of Plymouth, 2024)
This study examines Corporate Social Responsibility (CSR) practices in Nigerian public sector organisations using a comprehensive mixed-methods approach. The data collection process involved analysing 185 organisation-year observations from annual reports spanning 2011–2020, as well as questionnaires distributed to key stakeholders and interviews with senior executives from various organisations.The analysis utilised a multi-pronged strategy, including quantitative techniques such as regression analysis to explore the relationship between CSR practices and corporate governance mechanisms and qualitative methods such as narrative analysis and thematic coding to gain insights from survey responses and interviews.The findings indicate that CSR practices in the Nigerian public sector are moving in a positive direction. Organisations demonstrated commitment to CSR activities, including community development, education, environmental conservation, and philanthropy. Survey results showed that 83% of organisations engaged in CSR, driven by community acceptance and moral obligation. Additionally, 84% of organisations complied with regulatory frameworks, and 79% aligned their CSR policies with national or international standards. The analysis also found a significant positive relationship between CSR practices and factors such as larger board sizes, greater board independence, the presence of women on the board, and CEOs with longer tenures, higher educational qualifications, and international exposure.By triangulating these findings, it is clear that organisations have a strong commitment to giving back through various CSR initiatives, such as humanitarian assistance, youth empowerment, and educational programmes. Despite challenges such as budgetary constraints and weak accountability frameworks, organisations recognise the perceived benefits of CSR, including increased public confidence, improved stakeholder perceptions, enhanced organisational reputation, trust-building, community engagement, and empowering marginalised communities through education.The insights gained from this study conducted in an emerging economy namely, Nigeria, provide a new understanding of CSR practices in public-sector organisations. They also highlight the proactive approach of public sector organisations towards responsible practices. Consequently, the implications of this research extend beyond national boundaries, encouraging diverse and dedicated leadership to enhance CSR efforts and create lasting social impact. Future studies could explore comparative analysis between the public and private sectors or different countries, as well as sector-specific impact assessments.
Keywords: CSR; Corporate Social Responsibility; ESG; Sustainability

The use of blockchain for collecting value-added tax on online cross-border trade in digital goods - Kabwe, Ruddy Kapasula (University of Pretoria, 2024)
The collection of value-added tax from the cross-border supply of digital goods remains a challenge for tax authorities around the world. South Africa is no different. The traditional methods of collecting VAT from the supply of digital goods relies on the honesty of the consumer and on the supplier to account for and remit VAT to the tax authorities in the jurisdiction where the goods are consumed. The traditional collection models are often unreliable, inefficient, burdensome, and expensive for the consumers and the suppliers. The adoption of blockchain technology as a model to collect VAT on the cross-border supply of digital goods has the potential to alleviate the compliance burden on consumers and suppliers of digital goods, improve the efficiency of tax administration, and reduce VAT fraud. Importantly, blockchain technology can create trust between tax authorities, suppliers of digital goods, and consumers. This thesis critically discusses the advantages and disadvantages of implementing blockchain technology for the collection of VAT on the cross-border supply of digital goods in South Africa. This thesis unpacks the consideration factors for policymakers in the implementation of blockchain technology for the collection of VAT on cross-border trade in digital goods. The thesis makes recommendations for the South African VAT Act to be amended to make provision for the collection of VAT by utilising blockchain technology.
URI: https://repository.up.ac.za/handle/2263/97005
Keywords: Anonymisation; Blockchain technology; Decentralisation; Digital goods; Private blockchain; Smart contracts; Taxpayer privacy; Value-added tax

Multilateralism and Bilateralism in International Trade - Aro, Gilbert; Nwosu, Chiedozie; Ngene, Innocent; Nnadi, Samuel (African Journal of Politics and Administrative Studies, 2024)
The contemporary international system is dominated by international trade. Therefore, it is the fundamental and critical aspect of international economic relations. The study investigated the how African states participate in common bilateral and multilateral trade relations. Its core objective is to study whether trade barriers have been made less cumbersome among the participating countries in African continental region. Common trade and international trade justify the essence of globalization. The wave of globalization has necessitated the flux of multilateralism and bilateralism among the participating nations in the international trade. Methodologically, the study adopted comparative theory of international trade. Its method of data collection is documentary method and analyzed through interpretive studies. As the international trade continues to take the centre stage in the international economic relations; States continue to engage in multilateral and bilateral trade relations. The operations of Transnational Corporations (TNCs) and Multi-national Corporations (MNCs) as non-state actors also engage in multilateral and bilateral agreements with the host states. Several agreements led to the establishment of General Agreement on Tariff and Trade (GATT) and World Trade Organization (WTO) remains conspicuous products of multilateralism and bilateralism in the international trade in the recent time. African Continental Free Trade Area (AFCFTA) is a multilateral agreement enacted by fifty-four members of the African Union (AU) in 2019 to boost trade relations among them. Its core benefit is to facilitate free trade and removal of trade barriers in the region Therefore, this study is set to examine the advantages and impacts of AFCFTA and other multilateral and bilateral agreements in Africa and the world at large.
Keywords: AfCFTA; Bilateralism; International Trade; Multilateralism; Trade agreements; WTO

Termination of Commercial Sale Contracts under the OHADA Uniform Act Relating to General Commercial Law - Ataíde, Rui; Boura, Marta (Centro de Investigação de Direito Privado (CIDP) Research Paper, 2024)
The Uniform Act relating to General Commercial Law of the Organisation for Harmonisation of Business Law in Africa (hereinafter referred to as the OHADA Uniform Act) establishes a commercial sale regime applicable to any trader (natural or legal person), including any commercial companies whose place of business or registered office is located in the territory of a party to the Treaty on the Harmonisation of Business Law in Africa. In this study we propose to analyse the non-performance of commercial sale agreements, focused on its termination regime, by reflecting on the right of termination, the termination by judicial means, its grounds, exemption from liability and the effects of termination. The economic and legal relevance of the commercial sale contract justifies the opportunity to reflect on how legal standardisation process has been achieved overall, particularly with regard to termination regimes. Both OHADA Uniform Act and the Vienna Convention on Contracts for the International Sale of Goods of 1980 (CISG) were conceived as unification mechanisms to circumvent the constraints and legal uncertainty associated with cross-border trade. Therefore, this analysis aims to assess how OHADA rules embody the long process of evolution in French law, as well as the influence of the CISG.
Keywords: CISG; Commercial sale contracts; Comparative law; French law; International Organisations; Legal standardisation; OHADA; Portuguese law; Termination regime; Uniform Act relating to General Commercial Law for Harmonisation of Business Law in Africa

Employee’s Pilferage and Security in Beverage Manufacturing Companies in Lagos State, Nigeria - Attah, Edwin; Abdullahi, Liman; Yusuf, Usman (African Journal of Politics and Administrative Studies, 2024)
The purpose of this paper is to examine the relationship between employee pilferage of pilferage and security in beverage manufacturing companies in Lagos State. The study is anchored on the rational choice theory in order to understand the connection between pilferage and security in beverage manufacturing companies in Lagos State. The researcher adopted a mixed research method involving survey research and historical research designs. The population of this study is 8,595 staff. This comprises all employees of Promasidor Nigeria Ltd, Nigeria Bottling Company (Coca Cola), Cadbury Nigeria Plc, and Guiness Nigeria Plc. The sample size of the study was 400 determined using Rakesh Sample size formula. Data were collected from primary and secondary sources. Primary data were collected using questionnaires, while secondary data were collected from related works on pilferage and security in beverage manufacturing companies. Data collected from questionnaire were analyzed using absolute frequencies and simple percentages, while data from secondary sources were analyzed using relational-content analysis. Among other things, it was found that the higher the level of pilferage, the lower the level of security of employees in beverage manufacturing companies in Lagos State. Among other things, it was recommended that given that there is relationship between pilferage and security in beverage manufacturing companies in Lagos State, beverage manufacturing companies in the state should ensure that stealing is drastically reduced in their various organizations through employment, training and proper motivation of staff who must be full-time staff. This would largely make the employees committed to work and shun pilferage.
Keywords: Pilferage; companies; employee; manufacturing; security

Evaluation of Revenue Effect from Tax Components and Economic Growth in Nigeria - Atuma, Emeka; David, Amarachi; Nwibo, Nneamaka; Nkwagu, Chibuike; Udenta, Blessing; Njim, Sunday; Uwaeke, Uchechukwu (African Journal of Politics and Administrative Studies, 2024)
This research empirically examined the relationship between tax revenue and economic growth in Nigeria for the period 1994-2021. Ex-post facto research design was adopted in the investigation. Multiple regression analysis was employed, in which Auto-Regressive Distributed Lag (ARDL) model as the method of analysis was utilized in the research. The ARDL model evaluates long-run and short-run interactions among the specified variables. The unit root tests conducted using Augmented Dickey-Fuller (ADF) revealed that the time series variables used were stationary at level and the first difference, but none of the variables was stationary at the second difference. The ARDL – Bound test analysis revealed the existence of long-run equilibrium relationship between tax revenue and economic growth in Nigeria within the period of the study. The coefficient of error correction mechanism was statistically significant and also negatively signed. The results equally showed that both company income tax and value added tax were statistically significant and positively related to economic growth in Nigeria in both shot-run and long-run periods; whereas personal income tax was statistically insignificant and positively related to economic growth in Nigeria in both short-run and long-run. Based on the findings, the study therefore recommended tax authorities responsible for tax administration should upgrade the tax database to capture all potential tax-payers in order to broaden tax income.
Keywords: Autoregressive Distributed Lag Mode; Economic growth; Nigeria; Tax Revenue

Re-Evaluation of the Effectiveness of Exchange Rate Depreciation on Import Demand in Nigeria - Atuma, Emeka; Ebuka, Bright; Nwibo, Fidelia; Nkwagu, Christain; Nancy, Udenta; Njim, Robert; Ogbonna, Nkemdirim; Uwaeke, Uchechukwu (African Journal of Politics and Administrative Studies, 2024)
The study investigated the impact of exchange rate depreciation on import demand in Nigeria from 1986 to 2021. The data used was sourced from Central Bank of Nigeria. Ex-post facto research design was adopted in the investigation. Multiple regression analysis was employed, in which Auto-Regressive Distributed Lag (ARDL) model as the method of analysis was utilized in the research. The ARDL model evaluates short-run and long-run interactions among the specified variables. The unit root tests conducted using Augmented Dickey-Fuller (ADF) revealed that the time series variables used were stationary at level and the first difference, but none of the variables was stationary at the second difference. The ARDL – Bound test analysis revealed the existence of long-run equilibrium relationship between exchange rate depreciation and import demand in Nigeria within the period of the study. The coefficient of error correction mechanism was statistically significant and also negatively signed. The results equally found that exchange rate depreciation is statistically not significant and negatively impacted on import demand in Nigeria in the short-run. However, in the long-run, exchange rate depreciation is negatively impacted to import demand and statistically significant. Causal relationship does exist between exchange rate depreciation and import demand in Nigeria with causation running from import demand to exchange rate depreciation. On the basis of the findings, the researcher made the following recommendations among others: Government should consider inward looking to strengthen the imports substitution policies that ensure massive production of goods and services.
Keywords: Autoregressive Distributed Lag; Exchange Rate Depreciation; Import Demand; Mode; Nigeria

Nigeria-China Relations and Economic Development - Chiedozie, Nwosu; Aloh, Ngwuta; Ibiam, Okechukwu; Nwankwo, Felix; Ikpolo, Gabriel; Iwuala, Harrison (African Journal of Politics and Administrative Studies, 2024)
This work explored the dynamics of Nigeria-China relations from the political and economic points of view between 1999-2023. The primary concern of this paper is to discern the extent Nigeria-China relations is mutually beneficial and how Nigeria can stand to gain more if the relationship is properly aligned to Nigeria’s national interest. The central argument of this work is that Nigeria stands to gain more from China than from the West bearing in mind the fact that over one hundred years of Africa’s relationship with the West has been largely exploitative and disadvantageous. In this regard, the research employed both primary and secondary sources of data collection. The primary sources relied on first-hand information gathered from the Chinese Embassy as well as key actors within the Nigeria External Affairs Ministry and Key Informant Interviews on experts in Nigeria-China relations. The secondary sources relied on already existing information from libraries, text books, journals and the internet. The theoretical framework employed is the Complex Interdependence Theory. The conclusion drawn from this work is that Nigeria-China relations have not fully developed to the extent of being more beneficial to Nigeria economically and politically. What currently subsists is that China is gaining economically more in terms of trade to Nigeria’s disadvantage. However, politically and socio-culturally, the two countries are mutually benefiting due to various diplomatic protocols and cultural exchanges. The study recommended among others that Nigeria must strive to develop her techno-industrial export-oriented base to ensure more symmetric beneficial relationship with China.
Keywords: Bi-Lateral Relations; China; Development; Economic Development; Nigeria

The impact of ISDS arbitration claims and adjudication on cross-border direct investment - Du, Julan; Zhang, Yifei (Transnational Corporations Review, 2024)
This study investigates the impact of the arbitration cases under the Investor-State Dispute Settlement (ISDS) scheme on cross-border direct investment in the form of merger and acquisition deals. The initiation of ISDS claims has significant and negative effects on direct investment from the claimant home country to the developing or weak-institution responding country. Indirect expropriation claims often have stronger effects than direct expropriation claims. The investor-win arbitration cases produce a significant substantiation effect by reducing merger flows, while the state-win cases produce an acquittal effect that encourages the subsequent capital inflow to the respondent state. Both effects are more striking in weak-institution or less developed target countries. We also detect some spillover effects of ISDS arbitration.
Keywords: Arbitration decisions; Cross-border merger deals; Direct and indirect expropriations; ISDS claims

Digitalization and Tax Administration in the Gambia - Ogbeta, Oghenekevwe; Ayeni, Oluwadare (African Journal of Politics and Administrative Studies, 2024)
This study extensively explored the potential of digitalization in The Gambia Revenue Authority's tax administration, amidst concerns over the practical application of digital tools and their underutilization, which have hindered the realization of improved revenue mobilization and efficient tax processes in The Gambia. The research, adopting a mixed method design, aimed to understand the intricate relationship between digitalization and tax administration in The Gambia. With specific objectives, including identifying driving factors, examining effects, and evaluating the correlation with GRA's performance, the study adopted quantitative and qualitative analyses. Similarly, the study population is two thousand, one hundred and eighty-eight (2188). Using Krejcie and Morgan (1970) formula, out of 2188 population of the study, three hundred and twenty seven (327) were selected as the sample size. This encompassed individuals drawn from the Ministry of Finance and Economic Affairs, GRA staff, and corporate taxpayers using a stratified and proportionate-to-size sampling approach. Hypotheses analysis revealed a statistically significant and positive effect of digitalization on tax administration, indicating improved efficiency and GRA effectiveness. Also, Spearman's rank-order correlation affirmed a positive relationship between digitalization and tax administration. Furthermore, qualitative insights from stakeholder interviews highlighted drivers such as international financial body stipulations, modernization imperatives, trust-building, accurate record-keeping, and alignment with global standards. Recommendations include training programs for GRA staff, public awareness campaigns, and enhancing user experiences for e-payment systems, among others.
Keywords: Digitalization; Tax Administration; Tax Compliance; Tax Evasion; Taxation

Sustainable development clauses in international contracts through the lens of the Unidroit principles - Pannebakker, Ekaterina (Uniform Law Review, 2024)
Most transactions that leave an imprint on the environment and communities are organized by commercial contracts. However, little is known about the way in which parties reflect sustainable development in contractual clauses. How can parties to international contracts commit to respect sustainable development goals? What are the possible degrees of commitment? Which contractual mechanisms can apply to the monitoring of compliance? How does one establish a link between the failure to meet sustainable development goals and the contractual liability or termination of contract? This article identifies contractual clauses relating to sustainable development and analyses these clauses through the lens of the 2016 International Institute for the Unification of Private Law (Unidroit) Principles of International Commercial Contracts (PICC). Drawing inspiration from open access contracts, the analysis will demonstrate that Article 1.8 of the PICC, precluding inconsistent behaviour, and Articles 5.1.4 and 5.1.5, on the duty of best efforts and the obligation to achieve a specific result, as well as the provisions on liability, can assist contract drafters, judges, and arbitrators in drafting and interpreting such clauses.

The efficient enforcement challenge of secured transactions law reforms in civil law systems: self-help repossession, strict foreclosure, and other methods for the acceleration of enforcement of security interests - Tajti (Thaythy), Tibor (Uniform Law Review, 2024)
Although the forging of an efficient system for enforcement of security interest is one of the central expectations of secured transaction law reforms in civil law systems, the results hardly give reason for satisfaction. As the reforms tend to be supported and influenced by various international organizations’ projects (especially the World Bank, the European Bank for Reconstruction and Development, the International Institute for the Unification of Private Law, and the United Nations Commission on International Trade Law), most out-of-court methods of enforcement of security interests have played a central role. Yet due to civil law’s general hostility towards self-help as such, either the introduction of the concept has been rejected or the local limited-reach kin have been merely ‘paper tigers’. Similarly, although security interests on several types of collateral (accounts, investment property) or on the workhorse of the English financial system—the floating charge—have also been enforced extrajudicially (save the exceptions), little attention has been attributed to these enforcement modalities. The same applies to strict foreclosure in civil law systems still being prohibited, or restricted, and thus rarely resorted to, due to the inherited hostility towards the doctrine of lex commissoria. Rethinking local laws on preliminary and temporary court orders to match them with such globally known ex parte preliminary measures as the English Mareva Injunction or the French Saisie Conservatoire, which allow creditors to swiftly freeze debtors’ assets and thus substitute self-help repossession, has also been given short shrift. The enforcement segment, consequently, remains the Achilles’ heel of secured transaction law reforms in civil law systems. This article desires to contribute to reform literature by addressing these deficiencies and by offering tested, fully or partially fitting, functional equivalents of self-help repossession.

The Enforcement of Settlement Agreements Under the Ohada Uniform Act on Mediation - Nshom, Kelese George (IUS LAW Journal, 2024)
On 23 November 2017, OHADA member states adopted the Uniform Act on Mediation. The Act lays down rules relating to mediation of disputes which, if successful, ends in a settlement agreement. Settlement agreements that are not freely respected by the parties will have no effect unless they are forcefully executed. Forceful execution is made with the help of a court or notably public who are empowered to insert an executory formula on the agreement after verification of its regularity. These local authorities involved in the enforcement process rely on domestic laws of member states which vary from state to state. This has the effect of tainting the harmonization process intended by the OHADA lawmaker and may be inimical to investors. This raises the problem of the suitability of the Act to dispute settlement as regards enforcement of settlement agreements. With the help of qualitative and comparative analysis, this article brings to limelight the intricacies of the enforcement of settlement agreements underOHADA. It concludes that enforcement of settlement agreements is rendered simple and rapid but faces serious drawbacks which could be alleviated by setting up OHADA mediation institution to oversee the entire mediation process, besides other recommendations.
Keywords: Agreement; Enforcement; Exequatur; MARD; Mediación; Mediation; Mediação; Médiation

Taxpayer Confidentiality : implications of the tax secrecy provisions regarding illegal miners - Kgobe, Kgothatso (University of Pretoria, 2024)
Taxpayer confidentiality and its implications (if any), on illegal miners

"Non erit innocens malus". Looking for Justice over maritime Crimes of International Concern. A tale of dichotomies - Guizzardi Righetti, Giampaolo (Université Côte d'Azur ; Università degli studi di Milano, 2024)
This dissertation is about dualities or dichotomies. In particular it investigates the interrelationships between two couple of dichotomies, the dichotomy between international and transnational crimes and the duality of land and sea as geographical and jurisdictional spaces in the attempt to answer the question of who does or should exercise its jus puniendi in case of maritime crimes of international concern. This dissertation is about dualities or dichotomies. In particular it investigates the interrelationships between two couple of dichotomies, the dichotomy between international and transnational crimes and the duality of land and sea as geographical and jurisdictional spaces in the attempt to answer the question of who does or should exercise its jus puniendi in case of maritime crimes of international concern.
Keywords: Compétence; Droit de l'homme; Droit de la mer; Justice maritime; Responsabilité (droit international); Violation des droits de l'homme; État

The Relevance of IFRS Accounting Information: Evidence from a Pure IFRS Environment - Abu Alia, Muiz; Amarneh, Khairieh; Abdeljawad, Islam (An-Najah University Journal for Research - B (Humanities), 2024)
The International Financial Reporting Standards (IFRS) are supposed to raise the value relevance of accounting information and thus ensure its usefulness for users. Most of the studies on the relevance of IFRS-based accounting information were conducted in countries that had previous accounting standards before the adoption of IFRS. However, the relevance of accounting information is influenced by the accounting traditions inherited from previous practices. This study provides distinctive evidence on the relevance of IFRS accounting information by examining the association between accounting information prepared by Palestinian companies and share prices. Palestine represents a pure IFRS environment since IFRS is its first financial reporting framework. The study estimates the impact of accounting information, including book value of equity per share, earnings per share, and operating cash flow per share, on the market value of the share. Totally, the results show that the accounting numbers prepared by Palestinian companies are relevant. Precisely, earnings per share and book value of equity per share are the important variables in determining the share market value. Notwithstanding, no significant impact of operating cash flow per share has been observed. Moreover, evidence supporting the existence of conformity and predictive relevance is obtained, but the overall predictive relevance is higher. To enhance the relevance of IFRS information, this paper recommends local regulators and policymakers to work on improving the readiness of the Palestinian environment to fully benefit from the adoption of IFRS. On the other hand, the International Accounting Standards Board should adequately consider the circumstances prevailing in underdeveloped countries when issuing its standards. For future research, larger samples from several countries with different prevailing factors should provide insights into the mechanisms of the relationship between book and market values.
Keywords: Conformity Value; IFRS; Predictive Value; The Palestine Exchange; Value Relevance

States and Regional International Organizations - Zouapet, Apollin Koagne (International Organizations Law Review, 2024)
Beyond the thorny, even insoluble question of the definition of a region and the definition of the criteria that should make it possible to apprehend the polymorphism of rio s, the raison d’être of these organizations, their mode of operation and their activities are at the heart of the debate on “international governance”. For many authors, the advent of RIO s has often been seen as a challenge to the state monopoly in the international legal order and a redefinition of the relationship between these particular organizations and states. It is this relational dynamic between the States and the RIO s that this contribution aims to describe and analyse. The aim is to examine the originality and specificity of the relationship between the RIO s and the States, compared to the latter’s relationship with the ‘classic/universal’ ios, which would reveal something about the very nature of regional organizations.
PDF: https://brill.com/downloadpdf/view/journals/iolr/21/1/article-p147_008.pdf
Keywords: Cooperation; Instrumentalism; Integration; Regionalism; Supranationalism; Universalism

Mobile money and financial inclusion in Africa: Emerging themes, challenges and policy implications - Osabutey, Ellis L. C.; Jackson, Terence (Technological Forecasting and Social Change, 2024)
Mobile money is purported to promote financial inclusion. The growing number of studies have largely focused on transactions and related benefits with limited attention to emerging challenges, policies and initiatives that address the relative needs of different stakeholders. Consequently, little has been done to probe the ‘bottom-of-the-pyramid’ paradigm that underpins these assumptions. There has been inadequate endeavour to examine ways that empirical research could shed more light on these challenges and how to overcome them. To address these gaps, this study reviews the emerging literature on mobile money that explores both benefits and challenges. From our study three main themes emerge that suggest areas where challenges to the efficacy of the mobile money-financial inclusion link still appears not to have been adequately addressed by policymakers: ensuring integrity, privacy and security; addressing resource and infrastructure constraints; and integrating stakeholder benefits. Yet we suggest merely addressing these challenges does not go far enough in safeguarding the needs of local communities, as major stakeholders. Evidence from our study suggests little direct benefit to the poorer sections of local communities, only to the strata above and to elites and external stakeholders. This has implications for development and social change through technology adoption.
Keywords: Africa; Bottom-of-the-pyramid; Financial inclusion; Fintech; Mobile money

Lessons for insolvency law from the emoluments attachment order experience - Grobler, Frederik (University of Pretoria, 2024)
Section 23(5) of the Insolvency Act poses an interesting challenge, namely vesting a portion of an insolvent’s post-sequestration income in the trustee of the insolvent estate without infringing on the insolvent’s constitutional rights. The income earned by the insolvent during sequestration is in general excluded from his estate and does not vest in the trustee, unless the Master determines that a portion of the insolvent’s income will not be required to maintain the insolvent and his dependents. In such a case, only the portion deemed to be surplus to requirements will be included in the insolvent estate and will vest in the trustee. The question of what role the insolvent’s income should play during the sequestration process, and therefore how section 23(5) should be interpreted and applied, has vexed the courts and numerous practical and constitutional issues arise. This study examines the application and shortcomings of section 23(5) during the administration phase of the sequestration process. It then explores the lessons learned during the recent constitutional scrutiny and subsequent amendment of the emoluments attachment process. Lastly, recommendations are made for possible law reform of section 23(5).

A comparative appraisal of creditor protection mechanisms under South African company law - Sibanda, Mandhlaenkosi (University of South Africa, 2024)
The study comparatively scrutinised creditor protection mechanisms entrenched in South African Corporate law to determine their effectiveness in advancing creditor interests in company affairs. The enquiry was triggered by the need for corporate laws to adapt to and align with the pace of global economic changes in open and democratic societies. The 2004 DTI Policy document on South African Corporate Law Reform (SACLR) proposed a shift from the traditional shareholder-centric view, which espouses shareholder importance in corporate governance, to a model that retains the supremacy of shareholder interests while simultaneously catering to the interests of other stakeholders (the enlightened shareholder value approach). In light of the DTI policy proposal, the parliament, in enacting the South African Companies Act 71 of 2008 (the Companies Act), reflected on the need to provide appropriate redress to investors' and third parties (creditors`) rights in the preamble to this piece of legislation. It was based on the forgoing expositions that this research work sought to establish whether the South African Corporate law had been adequately modelled to protect creditors and to look beyond the traditional company’s goal of profit maximisation for the shareholder at the expense of other stakeholders, such as the creditors, who equally have stakes in the success and continuation of the company. Thus, a comparative doctrinal and critical analysis of creditor protection laws from selected cognate jurisdictions was undertaken to determine the efficacy of the protection mechanisms accorded to creditors under the South African corporate jurisprudence. It is thus the researcher's findings that the South African provisions on mechanisms to protect creditors are set in motion and are, therefore, effective to a greater extent, subject to legislature dealing with some discrepancies as per lessons drawn from comparator jurisdictions and recommendations. Conclusively, the Companies Act should clearly include the creditor’s interests in those of the company and thus give a secondary duty to directors to ensure creditor interests, among other non-member stakeholders, are assertively safeguarded.
Keywords: Company controllers; Company law; Corporate entity; Corporate law; Corporate veil; Credit systems; Creditor interests; Creditor protection mechanisms; Creditors; Directors; Employees; Investors; Shareholders; Stakeholder constituencies; Stakeholder interests; Stakeholders; Third parties

The development of explicit deposit insurance schemes in selected countries in Southern Africa - Moloi, Mbakiso Ndumiso (University of Pretoria, 2024)
This dissertation explores the evolution of explicit deposit insurance schemes (EDIS) in Southern African countries. It emphasises the important role of banks in the economy and their vulnerability to failures despite prudential requirements and supervision. Financial safety nets are essential for failing banks, and deposit insurance is the primary mechanism to protect depositors and maintain financial system stability in the event of a bank's failure. Originating in 1933 with the establishment of the Federal Deposit Insurance Corporation in the United States of America during the Great Depression, EDIS has become a global standard. Southern Africa, with its developing financial sector, faces many challenges including bank failures, causing depositors to lose funds. The region's high interconnectedness increases the threat of contagion if parent banks fail. The absence of deposit insurance raises the likelihood of fiscal authorities succumbing to political pressure to bailout failing banks during crises as seen during the 2007-09 Global Financial Crisis (GFC). The GFC prompted the International Association of Deposit Insurers and the Basel Committee on Banking Supervision to establish the Core Principles for Effective Deposit Insurance Systems. Issued in June 2009, these principles are used by jurisdictions as a benchmark for assessing the quality of their deposit insurance systems and identifying gaps in their deposit insurance practices. This research aims to evaluate international best practice standards for EDIS and extract lessons from the establishment of EDIS in the USA to address gaps in the implementation of deposit insurance schemes in Southern African countries. Examining ten Southern African countries, this research investigates varied progress in EDIS adoption. Case studies, particularly Zimbabwe as a pioneer of EDIS in the region and Namibia as a recent entrant, help to identify gaps and opportunities for enhancing deposit insurance frameworks in the region.

Transformative impact of blockchain technology and smart contracts on dispute resolution: legal challenges and other implications. - Christie, David; Mante, Joseph; Mak, Charles Ho Wang (Artificial intelligence: its applications, academic and practical legal implications, 2024)
This paper comprehensively analyses the potential of blockchain technology and smart contracts to revolutionise dispute resolution. As dispute resolution methods evolve, blockchain and smart contracts, which offer efficiency, transparency, and fairness, are becoming more critical. That is especially the case in mediation and construction adjudication, which are less traditionally formal and tend to be carried through much more quickly than other forms of dispute resolution. The opportunity of blockchain comes from its ability to demonstrate a tamper-proof, clear record, reducing risks of misunderstanding and bias. This facilitates the transfer and verification of evidence both in the carrying out of projects and during dispute resolution processes. Smart–digital contracts with terms coded indirectly- allow for automated contract enforcement. They execute automatically upon meeting specific conditions. This automation brings a new efficiency level, cutting the time and costs of conventional dispute resolution. Nonetheless, integrating blockchain and smart contracts in dispute resolution faces several challenges. The current limited understanding and acceptance of these technologies in the legal sector is an imminent issue. Legislative changes are necessary to provide a solid legal framework for these technologies in legal processes and to address potential inconsistencies of approach. Such reform requires strong cooperation among lawmakers, technologists, and legal experts to ensure implementation that adheres to legal and ethical norms and ensures that the technologies can be applied with confidence by the stakeholders within the process. This collective effort is crucial for seamlessly integrating blockchain and smart contracts into legal frameworks.
Publisher: Kuwait International Law School ISSN 2410-2237 https://rgu-repository.worktribe.com/output/2343788/transformative-impact-of-blockchain-technology-and-smart-contracts-on-dispute-resolution-legal-challenges-and-other-implications
Keywords: Blockchain technology; Dispute resolution methods; English law; Smart contracts

Rethinking Environmental Obligations in Corporate Insolvencies: What New Role for Lenders? - Ebegbodi, Daniel Onyeje (University of Calgary, 2024)
Environmental reclamation obligations are statutory mechanisms designed to regulate environmental protection by corporate entities. Bankruptcy laws on the other hand are meant to offer insolvent corporations an opportunity to reorganize their affairs, satisfy creditors claims and make a fresh start. In practice, the application of bankruptcy laws can undermine key environmental reclamation objectives, leading many to ask whether a corporation undergoing restructuring with significant outstanding environmental reclamation obligations should be able to commence bankruptcy proceedings to satisfy creditors’ claims? By employing the doctrinal and comparative research methodologies, this research interrogates that inquiry. It argues that, despite the importance of bankruptcy protection for corporations undergoing financial distress, environmental protection should be paramount. Although sustainable finance (SF) instruments have been deployed by banks to enable creditors to mitigate environmental concerns in their investments, the persistent recurrence of environmental reclamation issues in the oil and gas sector particularly during insolvencies, underscores the need for financial investors to strengthen their investment policies to reflect best practices providing the desired protection for the environment. The research finds that, although SF and environmental, social and governance (ESG) approaches, are commendable, they are insufficient in instilling adequate regulatory impact on the environment compared to judicial control offered by the courts. The thesis concludes that whilst judicial control mechanism is not without concerns, with government’s deliberate financial policy and judicial control to complement SF and ESG efforts, ESG and SF mechanisms can be strengthened to compel greater significant influence on best practices in lending.

Current Issues of the Utilization of Online Dispute Resolution as a Method for International Trade Dispute Settlement - Rohmah, Nuzul Quraniati (Ipso Jure, 2024)
The transformation of international trade from conventional to digital impacts several things, including resolving international trade disputes. In order to realize an efficient and effective dispute resolution process, many countries have implemented ODR to settle international trade disputes. This study aims to analyze the implementation of ODR in various countries and examine issues with unclear guidelines based on international law. This research observes the development of ODR in Indonesia and the urgency for its implementation in Indonesia. The research is normative juridical, with a statutory and comparative approach. The results obtained in this study are model law arrangements relating to the standardization of ODR Providers aimed to protect the personal data of the parties, unification of ODR dispute resolution clauses, and formulation of national legal instruments to create legal certainty regarding ODR, including ODR proceedings, permits, and monitoring, as well as recognition and execution process of electronic ODR decisions.
Keywords: International Trade; ODR; Online Dispute Resolution; Regulation

Transborder flow of personal data (TDF) in Africa: Stocktaking the ills and gains of a divergently regulated business mechanism - Babalola, Olumide (Computer Law & Security Review, 2024)
Technology-based transactions are inseparable from the routine exchange of data. These exchanges may not pose privacy problems until the movement takes extra-territorial turns thereby facing multiple levels of cross-border regulations. In the 80 s, the frequency of transfer of personal data beyond geographical boundaries in Europe precipitated the regulation of transborder data flows (TDF) beginning with the enactment of the Organization for OECD Guidelines. In Africa, the concept of TDF is more complex than usually viewed by the stakeholders and this is partly because neither the African Union nor other regional bodies have introduced legislation on TDF. Like many concepts in data protection, TDF is bereft of a generally accepted meaning. Regardless of the uncertainty, this paper approaches TDF as the transmission of personal data from one country to another country or international entity for the purpose of processing. The paper discusses some definitions of TDF as understood under African regional and national data protection legislation. In a comparative and normative approach, the paper analyses the barriers to TDF in Africa vis a vis the European experience and then concludes with recommendations for workable TDF within and outside the continent from an African perspective beginning with the harmonization of existing regional framework.
Keywords: Africa; Data Protection; ECOWAS; GDPR; Privacy; Transborder data transfer

The African Continental Free Trade Area (AfCFTA): Taking stock and looking ahead for international business research - Debrah, Yaw A.; Olabode, Oluwaseun E.; Olan, Femi; Nyuur, Richard B. (Journal of International Management, 2024)
The establishment of the African Continental Free Trade Area (AfCFTA) has opened new avenues of research interest in International Business and International Management. However, scholarly work in this fledgling area of research has been disparate and often lacking in the assessment of core international business implications of the emergence of the AfCFTA on member states as well as non-member states. This is because, as yet, no systematic attempt has been made to explore the AfCFTA in the context of IB research, or project future IB research directions. Hence, in this paper, using the PRISMA method we have systematically identified the current published research and scholarly work on the AfCFTA and provided a robust picture of the current state of knowledge and available literature on the AfCFTA while at the same time outlining potential areas for future international business research.
Keywords: AfCFTA; African Continental Free Trade Area; Informal cross-border trade; International business; Regional economic communities (RECs); Systematic literature review

Overview of the role of selected consumer protection bodies in the regulation of prices and access to redress under the Consumer Protection Act 68 of 2008 - Magau, Phemelo; Chitimira, Howard (Acta Universitatis Danubius. Juridica, 2024)
The Consumer Protection Act 68 of 2008 (CPA) seeks to promote the achievement and maintenance of a fair, accessible, efficient, sustainable and responsible market place for consumer products and services in South Africa. Moreover, the CPA seeks to provide an accessible, consistent, harmonised, effective and efficient system of redress for consumers. Notably, the CPA provides that the supplier should not supply or enter into an agreement to supply any goods or services at a price that is unfair, unreasonable, or unjust. This is generally aimed at combating any problems that are suffered by consumers when accessing goods and services in South Africa. Accordingly, various regulatory bodies and related role-players were established to enforce consumer rights and provide redress mechanisms to vulnerable and affected consumers. These consumer protection bodies and related roleplayers include the National Consumer Commission (NCC), the National Consumer Tribunal (NCT), provincial consumer courts, ordinary courts and other alternative dispute resolution agencies. These bodies and role-players are statutorily obliged to resolve consumer disputes in South Africa. However, there are some uncertainty challenges regarding the jurisdiction of ordinary courts and consumer protection regulatory bodies in relation to disputes that relate to the consumers’ right to fair, just and reasonable prices, terms and conditions of goods and services. This article discusses the role of the NCC, the NCT, provincial consumer courts, ordinary courts and other alternative dispute resolution agencies in the regulation of prices for goods, services and access to redress for affected consumers under the CPA. This is done to provide some recommendations that could resolve jurisdictional and regulatory challenges in relation to the price and access to goods and services under the CPA.
Keywords: Consumer Protection Act 68 of 2008 (CPA); Consumer protection; Consumer rights; Prices; Regulatory bodies; Vulnerable consumers

Evaluating bank technical efficiency in SADC region - Abel, Sanderson; Mukarati, Julius; Manenge, Robson; Le Roux, Pierre (Heliyon, 2024)
Efficiency is generally defined as the capacity to deliver desirable results with little effort or input. A bank cannot afford to allocate limited resources at random in a competitive market. Only once the efficiency factors have been identified can resources be allocated in a conscious and effective manner. The study investigates the determinants of technical efficiency of banks in the SADC region. The study is significant in the SADC region as the block is trying to create a robust and stable banking system. This is driven by the desire to stay away from the current global financial system volatility and the region is working to develop an integrated banking system. The results show that the banks are relatively inefficient with the level of inefficiency around 40 percent. The efficiency of the banks is determined by the level of capitalisation, size of the bank, research costs and automation of the banks. The results of the study imply that that there is great scope for the banks in the SADC region to increase their efficiency. Improved efficiency will ensure banks provide services at a lower cost to clients. The study recommends adequately capitalizing banks, increasing the asset base of the banks, investing in research and the automation of the banking systems.
Keywords: Banks; Capitalisation; Data envelopment analysis; Technical efficiency; Tobit

Influence of remuneration on organizational performance in co-operative banks in Kiambu, Kenya - Brian, Kasale; Abuga, Isaac Mokono (African Journal of Social Issues, 2024)
This study investigates the influence of remuneration on organizational performance in cooperative banks in Kiambu County, Kenya. Employing a mixed-methods approach, the research explores how compensation packages, salary reviews, and employee recognition impact performance. The study utilizes a descriptive research design with structured questionnaires to gather data from 94 participants. Findings indicate a significant correlation between competitive remuneration and enhanced organizational performance. The majority ofemployees are satisfied with salary increments and recognize the positive effects of frequent salary reviews on their motivation and job satisfaction. The study also highlights the importance of recognition and praise in boosting employee morale and engagement, contributing to overall organizational success. This research is grounded in Equity Theory, which posits that fair treatment in compensation leads to higher motivation and productivity. The conclusions drawn suggest that cooperative banks should implement equitable and competitive remuneration strategies, along with regular salary reviews and robust recognition programs, to enhance performance. The study provides valuable insights for policymakers andbank managers aiming to improve organizational effectiveness through strategic human resource practices.
Keywords: Co-operative Banks; Employee Motivation; Equity Theory; Organizational Performance; Remuneration

Corporate Income Tax (CIT) and Capital - Agossadou, Stanislas Théodule Médard Dèwanou Comlan (International Journal of Accounting, Finance, Auditing, Management and Economics, 2024)
This research consists of verifying whether CIT has an effect on capital given the financing risk incurred. A review of several capital theories has shown that CIT is one of the main determinants of a firm's capital structure. The inclusion of CIT in capital structure models continues to divide the world of corporate finance. Debt interest deduction in computing CIT reinforces the controversy over the question of the capital structure that optimizes the tax savings provided by this deduction. The consequence is the existence of two opposing groups on the optimum capital structure: on the one hand, the group of those who believe that there is one and only one optimal capital structure, and on the other, the group of those who reject out of hand any possibility of an optimal capital structure. The sample starts with a case study of two hypothetical identical firms, one indebted and the other non-indebted, with the same profitable investment project over a period of time, and ends with 101 pairs of identical firms belonging to different classes of financing risk. The hypothesis of non-gratuity of cost and income is used, and capital markets are assumed to be pure and perfect. The results confirm that CIT has no effect on the structure, value, cost and return of capital for a given financing risk, and reveal the existence of a third source of financing called "public capital", whose cost is the corporate capital tax rate (CCTR). There is no longer any question of thinking about the optimum capital structure, which is a pure financial illusion. This paper is one of the first to show that CIT does not affect capital, and to propose a model that explains capital structure behavior in the presence of CIT. Paper type: Empirical Research Stanislas Théodule Médard Dèwanou Comlan AGOSSADOU, (Researcher) Laboratory for Research on Performance and Development of Organizations (LARPEDO) Faculty of Economics and Management (FASEG) University of Abomey-Calavi (UAC) - Benin,
Keywords: Capital structure; Financial integration of corporate tax; Firm value; Return on investment; Weighted average cost of capital (WACC)

A comparative legal analysis of the accommodation of neurodiversity in the workplace : towards a universal right to reasonable accommodation - Conradie, Riana (Stellenbosch University, 2024)
Workforces are made up of individuals with differences in personal characteristics, differences that may be traced back to unique personality types and traits and – sometimes – neurodivergence. Due to the inherent subjectivity of the interpersonal relationships that form the foundation of a work environment, these differences in personal characteristics inevitably lead to tension. In addition, as part of managing a work environment employers frequently take decisions that may be influenced by views and perceptions regarding employees’ personal characteristics. This study starts with a descriptive examination of the meaning of personality and the influence that personality traits and types may have on employment. This is followed by a descriptive examination of neurodivergence, the various forms of neurodivergence, and the impact of these conditions on the work environment. Building on these descriptive and conceptual underpinnings, the legal implications of neurodiversity in the workplace are investigated by identifying which principles of the existing South African employment law framework may be utilised to provide protection and promote respect for neurodiversity and the neurodiverse differences between employees. This encompasses a discussion of the South African employment law rules relating to recruitment and selection of employees, some of the rules applicable to the day-to-day management of employees, and the rules relating to termination of employment that may be (in)directly influenced by considerations of neurodiversity. The focus thereafter shifts to consider the legal principles of employment discrimination law, where it is found that the listed ground of disability and an unlisted arbitrary ground may potentially be used as the applicable grounds of discrimination by employees if they are prejudiced due to their neurodiverse characteristics. In addition, the possibility that the rules on reasonable accommodation may be utilised as primary mechanism to properly regulate neurodiversity in the work environment and protect against prejudicial treatment of employees due to their inherent personal neurodiverse characteristics is also considered. The South African position and potential employment law rules that may apply to the management of neurodiversity in the work environment is compared to the position in the United Kingdom by focusing on the meaning of disability, the right to reasonable adjustments, and the right to request flexible working arrangements. Finally, the conclusions that may be drawn from this study are emphasised and are followed by some recommendations on how (reasonable) accommodation of neurodiversity in the work environment may appropriately be used as primary mechanism to provide employees with sufficient and appropriate protection of differences in neurodiverse characteristics. Even though this study focuses on neurodiversity and neurological differences between employees, the principles and recommendations from this study may be of value in relation to the appropriate management and regulation of all inherent differences between employees.
Keywords: Discrimination in employment; Diversity in the workplace; Employment; Labor laws and legislation; Neurodivergent people; Neurodiversity; People with disabilities

Aspects of substantial compliance and strict compliance as applied to demand guarantees - Sikobi, Nkanyiso (University of South Africa, 2024)
Demand guarantees are essential for purposes of commerce and are used to secure the performance of the contractor. South African courts have held that demand guarantees are akin to letters of credit. Despite the independent nature of demand guarantees to the underlying contract, in circumstances where the beneficiary has made a fraudulent claim, the guarantor may dishonour the demand or claim. South African courts have indicated that if the underlying contract is illegal, courts may intervene by granting an interdict to stop payment under the guarantee. The South African law recognises traditional guarantees (often called suretyship) where the beneficiary, when making a demand or claim, must demonstrate liability on the part of the contractor. There are instances where courts have held that guarantees were of a nature akin to suretyship. In South Africa, parties entering into a demand guarantee contract are subject to the common law of contract. The Uniform Rules for Demand Guarantees, adopted by the International Chamber of Commerce, are only applied by explicit reference in the demand guarantee failing which such rules do not apply. Non-implementation of these rules has resulted in rigorous litigation in the recent years on this subject-matter. A demand must be supported by documents and require strict conformity. However, strict compliance with the prerequisites of the demand guarantee has not been applied consistently in South Africa. South African courts have recently been applying substantial compliance, in certain circumstances finding that a term in a guarantee is just directory and not obligatory. Furthermore, on many occasions, courts have deviated from strict compliance holding that a term in a guarantee does not make commercial sense thus such term is not mandatory. In this way, courts apply the most business-sensible interpretation when interpreting demand guarantees.
Keywords: Autonomous; Beneficiary; Contractor; Demand guarantees; Demand or conditional guarantee; Documentary letters of credit; Employer; First written demand; Fraud and illegality exception; Guarantor; Independence; Performance guarantees; Security for performance; Strict compliance; Substantial compliance; Suretyship; Underlying contract; Uniform rules for demand guarantees

The Impact of the United Nations Human Rights Treaties on the Domestic Level: Twenty Years On - Heyns, Christof; Viljoen, Frans Jacobus; Murray, Rachel (Brill, 2024)
This collection of chapters tracks and explains the impact of the nine core United Nations human rights treaties in 20 selected countries, four from each of the five UN regions. Researchers based in each of these countries were responsible for the chapters, in which they assess the influence of the treaties and treaty body recommendations on legislation, policies, court decisions and practices. By covering the 20 years between July 1999 and June 2019, this book updates a study done 20 years ago.
PDF: https://brill.com/downloadpdf/edcollbook-oa/title/38945.pdf
Keywords: Comparative Social Sciences; Human Rights; Human Rights and Humanitarian Law; Humanitarian Law; International Law; International Law: Regional Perspectives

The Impact of the United Nations Human Rights Treaties on the Domestic Level in Senegal - Kane, Ibrahima (The Impact of the United Nations Human Rights Treaties on the Domestic Level: Twenty Years On, 2024)
"Chapter 16 The Impact of the United Nations Human Rights Treaties on the Domestic Level in Senegal" published on 09 Feb 2024 by Brill | Nijhoff.
Section: The Impact of the United Nations Human Rights Treaties on the Domestic Level: Twenty Years On
Keywords: Comparative Social Sciences; Human Rights; Human Rights and Humanitarian Law; Humanitarian Law; International Law; International Law: Regional Perspectives; Social Sciences

Islamic Law Aspect on in Valuation and Execution Intellectual Property (IP) Asset as Bank Collateral in Creative Economy - Margono, Suyud (International Journal of Social Science Research and Review, 2024)
One of the issues faced by many creative economy actors in this relatively newly established industry is the lack of supporting infrastructure, such as the limited access to financing and one of the prominent issues is banks’ reluctance to accept intellectual property (“IP”) as collateral to secure loans including problems concerning valuation of IP Asset as Collateral which has implications several regulation concerning Intellectual Property. In the spirit of furthering the creative economy, the Government has recently issued Government Regulation Number 24 of 2022 on Intellectual Property-Based Creative Economy Financing. This matters includes in relation with IP assets that are exposed and exploited their product (goods or services) on the basis of exclusivity in financing and loan contractual scheme as collateral. This article normative legal research in which intended for studies that are literary and practical works which is Intellectual Property (IR) system in relation with valuation and execution as bank collateral either Indonesia prevailing law and Islamic (Syariah) Law. The result of this research that IP owners often deal with complex contractual relationships that involve different forms of cooperation in research, production or commercialization. most important aspect concerning capacity and competency with comprehensive knowledge deal with IP Asset as Collateral before Banks, and others financial institution, execution of guarantees as applied to Islamic banking has adopted many syariah law, in the practice, there are still many problems the implementation of guarantees as applied to Islamic banking has adopted many Islamic laws. However, in the practice, there are still many problems that arise from the Islamic law scope the concept of justice and the philosophy of maslahah.
Keywords: Creative Economy Valuation and Execution Asse; Intellectual Property (IP) Collateral; Islamic (Syariah) Law

Corporate law, governance, and sustainability : the public turn in the global socio-ecological transition - Junqueira, Gabriela de Oliveira (Universidade de São Paulo, 2024)
The overlap of financial, economic, ecological, and political crises has pushed the consensus on the need to promote a socio-ecological transformation, or, in short, a green transition. The discontent with the corporate world for its contributions to those crises has taken a central stage, with calls for greater corporate responsibility being articulated under a sustainability imperative. In the context of a new round of debates on the purpose of companies, this thesis examines the turning of corporate law and governance into a site for advancing a new capitalism. More specifically, the research investigates institutional changes occurring under the label of the public turn in corporate law, addressing the following questions: what constitutes the so-called public turn? What are its drivers and the perspectives on it? Which structural features led to targeting corporate law and governance to push for responsible corporate conduct? How does the public turn in corporate law relates to the broader set of actors and norms that shape corporate governance? Guided by critical approaches to the green transition and by political theories of corporate governance, the thesis resorts to different scholarships to examine the current wave of public oriented corporate governance mechanisms from within and from without corporate law. On the one side, the thesis offers a taxonomy of corporate law strategies being employed as well as a rich account on the multiple dimensions assumed by the new tools, placed at the intersection of human rights and environmental protection, corporate social responsibility, and global value chains. On the other, the thesis embeds corporate laws public turn within the unfolding of global capitalism, as the field evolves from corporate law to corporate governance to sustainable corporate governance. The thesis argues that the public turn in corporate law, caught in between the global and the local, enables the investigation of changing roles of states, businesses, and civil society within the political and epistemic terrain of the transition to a more just and sustainable economy. A sobreposição de crises financeiras, econômicas, ecológicas e políticas impulsiona o consenso sobre a necessidade de uma transformação socioecológica, ou, em resumo, uma transição verde. O descontentamento com o mundo corporativo assume centralidade, motivando demandas por mais responsabilidade corporativa, articuladas em torno de um imperativo de sustentabilidade. No contexto de uma nova rodada de debates sobre o interesse social, esta tese examina a transformação do direito societário e da governança corporativa em um locus de promoção de um 'novo capitalismo'. Mais especificamente, a pesquisa investiga as mudanças institucionais ocorrendo sob "a virada pública no direito societário", abordando as seguintes perguntas: o que constitui a esta virada? Quais são seus impulsionadores e perspectivas? Quais características estruturais levaram a mirar o direito societário e a governança para promover conduta corporativa responsável? Como a virada pública no direito societário se relaciona com o conjunto mais amplo de atores e normas que moldam a governança corporativa? Guiada por abordagens críticas da transição verde e por teorias políticas da governança corporativa, a tese recorre a diferentes correntes acadêmicas para examinar a atual onda de mecanismos de governança corporativa orientados para o público, de dentro e de fora do direito corporativo. Por um lado, a tese oferece uma taxonomia das estratégias do direito societário utilizadas, bem como um relato abrangente sobre as múltiplas dimensões assumidas pelas novas ferramentas, na interseção de direitos humanos, proteção ambiental, responsabilidade social corporativa e cadeias de valor globais. Por outro lado, a tese contextualiza a virada pública do direito societário nos desdobramentos do capitalismo global, à medida que o campo evolui do direito societário para a governança corporativa para a governança corporativa sustentável. A tese argumenta que a virada pública no direito corporativo, situada entre o global e o local, permite a investigação das mudanças nos papéis dos estados, empresas e sociedade civil no terreno político e epistêmico da transição para uma economia mais justa e sustentável.
Keywords: Corporate governance; Corporate law; Corporate sustainability; Direito societário; Economia política; Governança corporativa; Political economy; Private regulation; Regulação privada; Sustentabilidade corporativa

The legal framework regulating the duties of insurance intermediaries - Sithole, Eugine (University of Pretoria, 2024)
In South Africa, before the Financial Advisory and Intermediaries Services Act (FAIS Act) and other insurance laws came into existence, intermediary services regarding the rendering of insurance products have always been regulated by the law of agency and mandate. This means that the Roman-Dutch principles provided for the standards to which the conduct of intermediaries was to comply with when rendering insurance services. The mandate of intermediaries in terms of the Roman-Dutch Principles also included the fact that they had to act with care, skill and in good faith. When the FAIS Act came into operation, it introduced several detailed rules and minimum standards for insurance intermediaries to comply with, and these minimum standards are not limited to qualifications, experiences and characteristics of honesty and integrity that an intermediary must comply with, but they also stipulated in detail what an intermediary must do when discharging insurance intermediary duties. The FAIS Act is the leading legislation when it comes to the regulation of intermediary services. The FAIS Act, under section 16, provides for a General Code of Conduct for Authorised Financial Services Providers and their Representative (GCC), which contains a set of rules that are applicable to all intermediaries. These rules under the GCC are aimed at ensuring that insurance customers are provided with material facts that will enable them to make a prior informed decision and that their reasonable financial needs concerning insurance products will be carefully considered so that they can be provided with a product that will be suitable to satisfy their needs. Furthermore, in terms of South African laws and practices, intermediaries play an essential role in the creation of legally binding insurance contracts. Insurance businesses are concluded through intermediaries. Considering that many insurance companies are juristic persons, and they can only conduct business by means of human agents, insurance laws make it compulsory for intermediaries to have skills, knowledge, and experience regarding insurance products that they are rendering to insurance customers. It is commonly believed that intermediaries with skills, knowledge and experience, they always act in the best interest of the client, and they ask relevant questions to assist the clients to disclose all material facts, and they always make sure that material facts are clearly communicated/disclosed to the insurer and insured to avoid future conflicts. The legal framework placed a duty on the intermediary to assist the insured to disclose all material facts and to explain all clauses contained in the insurance contract which may lead to the insurer repudiate its liability. Furthermore, an intermediary is at all material times expected to first consider the financial situation of the potential insured before determines a cover that will be best suitable for the insured’s needs. However, despite the best guidelines outlined by applicable insurance laws and regulations, mistakes are still being made by intermediaries, which lead to insurance customers to suffer the consequences of impractical intermediary services, and that has resulted in numerous complaints, legal disputes, debarments, and other regulatory actions. As a result of intermediaries’ continuous misconduct, insurers have been repudiating claims, and it has created a presumption that insurers conduct businesses to enrich themselves instead of protecting the interests of their customers as required by regulating legal framework. Therefore, so many people have lost confidence in the insurance industry due to unlimited court cases and complaints arising from misconduct or omissions of intermediaries, such as their failure to disclose material facts to the parties. Once it is found that material facts were not fully disclosed between the insurer and insured, both parties would have been deprived of their right to make an informed decision before consenting or signing a legally binding contract. Therefore, a need is created for intermediaries to be educated of their legal duties when rendering insurance services and that will help strengthen or restore the confidence of the public towards insurance industry.

The legitimacy of dismissals for off-duty misconduct in South African labour law - Phulu, Thandekile (University of Pretoria, 2024)
The main aim of this thesis is to solve the uncertainties brought about by dismissals for off-duty misconduct. First, it should be acknowledged that the world as we know it has changed and continues to evolve. Dismissals have been significantly impacted by the use of social media outside the workplace. The legalisation of the use of cannabis by an adult person has also brought uncertainties in the way dismissals are handled, especially in cases where an employee consumes cannabis off-duty. These two aspects have significantly influenced dismissals for off-duty misconduct in South Africa, with employees alleging that their rights to privacy, dignity and freedom of expression are infringed. The thesis reveals that regardless of these modern changes, off-duty misconduct dismissal is still governed by the generic provisions of the Labour Relations Act 1995 and its Code of Good Practice: Dismissal. The thesis underscores the lack of clarity regarding the regulation of dismissals for off-duty misconduct in South Africa. Furthermore, despite the judiciary’s establishment of tests (the nexus test and the breakdown of the employment relationship), challenges in adjudicating off-duty misconduct cases persist. This thesis analyses the South African legal framework governing dismissals for off-duty misconduct. The research investigates the evolution of South African dismissal law, tracing its development from the pre-democratic era to the post-democratic era. This investigation scrutinises the shifts in the legal landscape regarding dismissals for off-duty misconduct. The analysis encompasses a range of legal instruments pertinent to South Africa, including legislation, international law, common law, and judicial precedent. The current need for a Code of Good Practice for off-duty misconduct dismissal is highlighted. This rationale is prompted by a comparative examination of other countries where, despite the absence of specific codes addressing off-duty misconduct, a proactive stance has been adopted to safeguard employees’ off-duty rights by enacting relevant legislation. These chosen states have statutes regulating employees’ off-duty conduct and clarifying which conduct is protected and in which circumstances. Consequently, the thesis proposes a Code of Good Practice: Dismissal for Off-duty Misconduct. This Code would assist in the uniformity of application of relevant aspects in determining the fairness of dismissals for off-duty misconduct, thus alleviating labour suits concerning this type of dismissal. The Code would also provide employers with guidelines on how to draft off-duty misconduct policies without infringing employees’ constitutional rights.
URI: https://repository.up.ac.za/handle/2263/97021
Keywords: Cannabis use; Dismissal; Labour law; Misconduct; Off-duty; Social media; South Africa

How can the rule of law under the WTO framework ensure sustainable fishery governance through fishery subsidies? A study from the perspective of special and differential treatment - Bai, Jiayu; Wu, Yuting (Heliyon, 2024)
Background Considering the declining situation of sustainability in global marine fisheries, World Trade Organization (WTO) members successfully concluded the Agreement on Fisheries Subsidies(AFS) after 21 years of negotiations in 2022. As an the integral part of these negotiations, special and differential treatment (SDT) provisions provide developing countries with special rights and developed countries with the possibility to treat developing countries more favorably than other WTO members. Objective This study analyzed the role of SDT for fisheries subsidies in ensuring sustainable fishery governance by the rule of law, as well as the reflection of SDT under the AFS, to explore whether SDT can support sustainable fishery governance under the WTO framework. Methods This study is primarily based on official data and critical legal studies and used normative analysis and historical analysis to expose the essence of the SDT issue in the AFS as a political game in the legal form. Results The practical challenges in the implementation of SDT may affect the compliance willingness of member states. To overcome the obstacles, such as ambiguity and inefficiency, that impede the legalization process of sustainable global marine fishery governance, it is necessary to emphasize the value of SDT for the common interests of the WTO members in marine fisheries legislation. This will benefit the developing countries, especially the small island developing states, in the short term; and the common interests of developed and developing countries in the long term. Policy implications SDT facilitated the consensus between the developing and developed countries on issues such as illegal, unreported, and unregulated fishing subsidies and overfishing subsidies. However, current SDT practices have deviated from the original intention of the fairness and democratic approach of global marine fisheries governance, which should take into consideration the specific situation of developing countries.
Keywords: Agreement on fisheries subsidies; Overfishing; Rule of law; Special and differential treatment; Sustainable fishery governance; World Trade Organization

Articulation between Soft Law and Hard Law in the Award of Public-Private Partnership Contracts through Unsolicited Bids in Burundi: Towards Harmonization with International Practice - Amani, Jean Pierre (Open Journal of Social Sciences, 2024)
The awarding of public-private partnership (PPP) contracts through unsolicited bids is characterized by flexible domestic law, with the involvement of public and private players aiming to achieve the general interest objective of public infrastructure development and, by extension, national development. These players are helping to build the normative framework for PPP project activities by spontaneous offer, given their increasingly widespread use on the bangs of positive law, while their standards are classically deprived of the binding force attached to hard law. Marked by its normative guarantee, the flexible law of unsolicited bids is situated at the threshold of the mandatory, and is essential to PPP law. It produces legal effects by linking up with the hard law of PPP contracts, which is the law of the parties. This link between soft law and hard law has a major legal impact on the transformation of the law and legal certainty, for the benefit of investment confidence, especially international investment confidence. Faced with the limitations of positive law on the award of PPP contracts in unsolicited bids, and the difficulties of interpreting soft law and hard law standards, there is a need for harmonization with international practice. To this end, the instruments of the United Nations Commission on International Trade Law (UNCITRAL) on PPPs are being used to link up with Burundian hard law through a transposition mechanism. It is therefore possible that our positive approach to PPP contracting could be improved, highlighting the principle of competition and the exception of non-competition, while taking into account the win-win principle, risk sharing and performance. Finally, the article considers the adjustments to the hard law that would be necessary if Burundi were to decide to revisit the legal framework to make it more attractive to investment, and thus ensure the completion and financing of PPP contracts by spontaneous bidding.
Number: 1
Keywords: Articulation of Law; Competition Principles; Hard Law; Harmonization Principles; Legal Certainty; Mutation of Law; Soft law; Spontaneous Offer

A bibliometric review of IFRS adoption and compliance research in Africa - Effah, Nana Adwoa Anokye (Journal of Business and Socio-economic Development, 2024)
Purpose This article aims to identify and review existing studies on the adoption and compliance of Internat ional Financial Reporting Standards (IFRS) in Africa. Design/methodology/approach The methodology involves a sole focus on studies conducted with an African sample, using a bibliometric method and data from the Web of Science (WoS) database. Visualizations from VOSViewer and Biblioshiny software are employed to identify the dominant authors, journals and countries contributing to research in the region. Findings The findings reveal existing collaborations among authors in the field. However, the study emphasizes the need for additional research to enhance the intellectual structure of the research domain, as the majority of related documents are concentrated within twenty articles with at least one citation. Practical implications The practical implications underscore the importance of collaboration in practice, emphasizing the need for cooperation among corporations, experts and regulatory agencies involved in IFRS adoption and compliance in Africa. By fostering collaborative efforts and knowledge-sharing among corporations, experts and regulatory agencies, practitioners can enhance their understanding, streamline implementation processes and improve compliance methods. Originality/value This review is one of the few to explicitly conduct a bibliometric review of IFRS adoption and compliance studies in Africa, providing a foundation for future research to determine the current direction of IFRS studies in this region.
Keywords: Africa; IFRS adoption; IFRS compliance; Web of science database

Internationalisation patterns of African sharing economy companies: The role of gateway markets - Ochieng, Irene Achieng; Thornton, Heidi Coral; Owusu, Richard Afriyie (Journal of Business Research, 2024)
Sharing economy companies (sharecoms) have been internationalising rapidly, including entering African markets. Little research has been conducted on the strategies and behaviours of African sharecoms. Questions have been raised as to whether existing theories adequately explain the internationalisation of African firms. Thus, we analyse the internationalisation patterns of six African sharecoms, focusing on time, speed, and scope. The findings indicate that firms apply unique combinations of various internationalisation models. A novel pattern of internationalisation where the firms use “foreign gateway markets” as strategic “launchpads” before rapidly internationalising was also uncovered. Locational advantages, strategic networks, and relative technological advancement characterise the foreign gateway markets. We also propose the concept of “complex regional context” to define the context of emerging regions with many neighbouring countries with the potential for high levels of internationalisation but low levels of international business due to the lack of common enabling frameworks and institutions.
Keywords: Emerging African markets; Foreign gateway markets; Internationalisation; Patterns; Sharing economy

Tax Behavior and Financing Behavior of Corporate Managers: Case of Banks and Decentralized Financial Systems (DFSs) in Benin - Agossadou, Stanislas T. Médard D. C. (Journal of Economics, Finance and Management, 2024)
This paper aims to analyzing the influence of tax behavior on financing (financial leverage) behavior of corporate managers. The paper applies the generalized method of moments (GMM) to dynamic panel data. The sample used covers 21 firms, i.e. 11 banks for the period from 2011 to 2020 and 10 DFSs for the period from 2016 to 2021. It turns out that financial leverage behavior is influenced more positively by corporate income tax (CIT), then by dividends (DIVIDEND); and negatively by interest on debt (INTEREST), by cash flow (CASH_FLOW) and by past financial leverage (LEVERAGE(‑1)). This paper is one of the first to extend the literature by identifying the main determinants of financing behavior, notably the positive effect of corporate income tax (CIT).
Keywords: Corporate income tax behavior; Corporate income tax savings; Financial objectives; Leverage behavior; Tax objectives

The duty of bank confidentiality and the safeguarding of financial privacy - Ahmed, Kousar Bibi (University of KwaZulu-Natal, 2024)
Abstract available in PDF.
Keywords: Banks and privacy; Customer confidentiality; Duty of confidentiality; Protection of personal information

Part XV Chapter 2, Conciliation beyond the courts: aspirations and limits of mandated and voluntary court mediation programmes from a multi-jurisdictional perspective - Ali, Shahla (Comparative Procedural Law and Justice, 2024)
Keywords: Convention on the Recognition and Enforcement of Foreign Arbitral Awards (1958); International commercial arbitration; MARD; Mediación; Mediation; Mediação; Médiation; UNCITRAL Arbitration Rules; UNCITRAL Model Law on International Commercial Arbitration (1985)

Uniform Law: Legal Responses to Globalisation - Basedow, Jürgen; Max-Planck-Institut für Ausländisches und Internationales Privatrecht (Hamburg, Germany) (Mohr Siebeck, 2024)
International conference proceedings
Keywords: COMMERCIAL LAW; Economic Analysis; PRIVATE INTERNATIONAL LAW; Uniform law

Procedural Justice in Online Dispute Resolution: An Empirical Enquiry - Beretta, Rachele (University of Antwerp, 2024)
The surge in online interactions has led to a parallel rise in civil and commercial disputes that transcend geographical boundaries. As traditional dispute resolution mechanisms face challenges adapting to this evolving paradigm, conflicts increasingly migrate to online platforms. Within this proliferating landscape, it is crucial to recognize the scarcity of research devoted to Online Dispute Resolution (ODR) providers and the myriad types of services they currently offer to users worldwide. Despite the ongoing geographical expansion of ODR, the inquiry into how procedural justice principles manifest in these digital dispute resolution systems remains notably under-explored. A growing body of literature underscores that procedural justice is critical for building users’ trust, enhancing the legitimacy of organizations among communities, and fostering compliance with outcomes. The ability of ODR providers to meet users' expectations in terms of procedural justice can significantly shape users' perception of ODR institutions as trustworthy and dependable. This bears paramount implications for the ongoing development of ODR, whose acceptance varies widely across jurisdictions. This doctoral thesis delves into the intricate intersections of procedural justice within the realm of international civil and commercial ODR, examining the nuanced dynamics that emerge in virtual spaces. Ultimately, it seeks to understand how procedural justice principles, rooted in the notion of fairness, manifest and evolve in the context of ODR, exploring the impact of digital interventions on the perceived fairness of dispute resolution processes. Understanding procedural justice in ODR is not merely an academic pursuit; it holds profound implications for legal practitioners, policymakers, and society at large. This research aims to contribute valuable insights that can inform the design of fairer and more effective ODR systems.
Keywords: Dispute Settlement; Justice; ODR; Online Dispute Resolution; Procedure (Law); UNCITRAL Arbitration Rules

Evaluating the International Arbitration of Oil and Gas Investment Dispute Settlement in Nigeria - Bisina, Lucky N. (African Journal of International Energy & Environmental Law, 2024)
This paper examined international arbitration as a tool for resolving investment disputes in Nigeria’s oil and gas sector, a critical industry that contributes significantly to Nigeria’s Gross Domestic Product (GDP), foreign exchange earnings and government revenues. This sector is marked by high-risk investments and complexity and often faces disputes arising from regulatory changes, fluctuating global prices, environmental concerns and contractual breaches. Arbitration, particularly in cross-border investments, provides a neutral, efficient and flexible mechanism for resolving such disputes. Using a doctrinal research methodology, the study analysed statutes, case law, international treaties, and academic sources. Findings revealed that while arbitration offers benefits such as neutrality and enforceability, there are still some challenges that must be addressed as a matter of urgency. Issues include resistance to enforcement of arbitral awards by Nigerian courts on grounds of national interest, high arbitration costs and biases favouring foreign investors. Nigeria’s legal framework, including the Arbitration and Mediation Act 2023 and the Petroleum Industry Act 2021, supports arbitration but lacks procedural clarity, leading to delays and inefficiencies. The paper concluded that legal reforms are essential to strengthen arbitration processes, enhance enforcement mechanisms and align Nigeria’s framework with international standards. Such reforms would foster investment stability and improve Nigeria’s attractiveness as an investment destination by reducing legal uncertainties. The paper recommended legislative and judicial improvements in order to achieve these goals.
Keywords: Dispute Settlement; International Arbitration; Investment Dispute; Oil and Gas Investment

Climate Litigation and Justice in Africa - Bouwer, Kim; Etemire, Uzuazo; Field, Tracy-Lynn; Jegede, Ademola Oluborode (Bristol University Press, 2024)
This volume brings together an international team of contributors to provide a much-needed examination of climate litigation in Africa. The book outlines how climate litigation in Africa is distinct as well as pinpointing where it connects with the global conversation. Chapters engage with crucial themes such as human rights approaches to climate governance, corporate liability and the role of gender in climate litigation.
Keywords: Africa; Climate adjudication; Climate governance; Climate justice; Climate litigation

Arbitration in the era of e-commerce: A comprehensive overview - Buhuri, Kristi (World Journal of Advanced Research and Reviews, 2024)
Technology is continuously evolving and has changed human interaction. It is consequently changing the ways disputes are solved. International dispute resolution procedures, and international arbitration, more specifically, are considerably influenced by the rapid expansion of innovative technologies. Years after the dot-com boom, Online Dispute Resolution (ODR) emerged and evolved considerably. Due to the digitalization of ODR methods, remote arbitration (or e-arbitration) is expanding. Arbitration is of particular interest due to its formal and binding nature, from a theoretical perspective. E-arbitration, as other ODR methods have attractive features as well as drawbacks, which are addressed in this document. The purpose of this paper is three-fold: providing an overview of e-arbitration and the different considerations of this method, presenting the e-arbitration models of the European Union (EU), the United States (US), and the People’s Republic of China (PRC) and suggesting recommendations to improve international e-commerce arbitration, notably through a revision of the UNCITRAL Model Law on International Commercial Arbitration (UNCITRAL Model Law).
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Digitalization; Innovative Technologies; ODR; Online Dispute resolution; e-Arbitration

Arbitration rules: In force as from 15 January 2024 - Cairo Regional Centre for International Commercial Arbitration (CRCICA, 2024)

Corporate mergers: a comparative analysis of the Italian and American legal systems - Carboni, Ludovica (LUISS Guido Carli, 2024)
Mergers in the Italian and European legal system. The Italian legal landscape for mergers. Applicable regulations. Stages of the merger process. The first phase: the merger plan. The second phase: the merger resolution. The third phase: the merger deed. The protection of creditors. The invalidity of the merger. The FIAT-Chrysler merger. Evolution of the legal nature of mergers in the Italian legal system: legislative and jurisprudential perspectives. The extinguishing-successory orientation. The evolutionary–modifying orientation. Court of cassation ruling no. 2637 of 2006. Return to the extinguishing-successory orientation: judgement no. 21970/2021. Debate surrounding judgement 21970/2021: criticism and support. Mergers in the American legal system. The American legal landscape for mergers. The evolution of the US corporate law of mergers. Sources of corporate law. The merger process. Economic motives for mergers. Steps of the merger procedure. The merger plan. Merger between parent and subsidiary or between subsidiaries. Articles of merger. Effects of merger. Abandonment of a merger or share exchange. The ExxonMobil merger. Comparative analysis of the Italian and American legal systems. Historical and constitutional influences on Italian and American legal systems. Differences and similarities in the merger process. Comparison of FIAT Chrysler and ExxonMobil mergers.

The protection of executory contracts in restructuring proceedings - Dejoux-Pasdeloup, Lea Francoise Paulette (Mikolas Romeris University, 2024)
This thesis focuses on the relationship between contract law and corporate insolvency law as it investigates the idea and protection of executory contracts within restructuring proceedings. However, preserving these agreements frequently necessitates taking legal action against established contract law tenets like the freedom of contract and the duty to perform. The study looks at how difficult it can be to keep debtor and creditor interests in balance, especially when there are disruptions brought on by insolvency. The study suggests ways to improve the efficacy of restructuring proceedings by analysing the EU Directive on restructuring and insolvency, contrasting practices in various jurisdictions, and evaluating the impact on stakeholders. The goal of this study is to protect the rights of all parties involved in corporate restructuring while advancing the creation of legal frameworks that facilitate effective restructuring.
Keywords: Creditor; Cross-border Insolvency; Darbuotojai; Debtor; Employees; Insolvency; Kreditorius; Nemokumas; Restructuring proceedings; Restruktūrizavimo bylos; Skolininkas

(R)evolution of insolvency law under the impact of artificial intelligence (AI): transformative technologies - challenges and perspectives - Didea, Ionel; Ilie, Diana Maria (Legal and administrative studies, 2024)
Keywords: AI; Artificial Intelligence; Bankruptcy; Cross-border Insolvency; Insolvency; Inteligência artificial; Intelligence Artificielle; Technology; UNCITRAL Model Law on Cross-Border Insolvency (1997)

The Influence of Corporate Sustainability Laws on Multi-Stakeholder Initiatives to Eliminate Forced and Child Labour in Supply Chains - Fanou, Temisan (McMaster University, 2024)
An array of governance initiatives has emerged to address forced labour and labour exploitation in global value chains (GVCs). Drawing on the transnational business governance interactions theoretical framework, as well as Timothy Bartley’s place-conscious transnational governance model, this thesis examines the interaction between two of these hybrid forms of governance: multi-stakeholder initiatives and corporate sustainability laws. I conduct a case study of the cocoa sector, and specifically of the multinational company, Nestlé, using multiple qualitative research methods including legal analysis, key informant interviews, and documentary analysis. My research suggests that the layering of corporate sustainability laws, and particularly the French Duty of Vigilance Law, on top of CSR and MSIs in the cocoa sector, is not addressing the governance gap that permits corporations to evade accountability for human rights abuses in their supply chain. I find that the introduction of corporate sustainability laws may have contributed to a decrease in Nestlé's efforts to address labor violations in certain areas, while in others, it appears to have supported the continuation of existing practices. This raises implications for the continuous efforts in various jurisdictions to introduce these laws as a solution to the shortcomings of private, voluntary rule-making systems. Further research is required to explore how these governance mechanisms are interacting in other sectors, in companies of different sizes, and within various types of MSIs. This will help identify the factors that influence interactions and shed further light on the path forward for policymakers.

ISDS 2.0: Time for a Doctrine of Precedent? - Jarrett, Martin (Journal of international economic law, 2024)

The International Tax Regime Complex: Understanding Change in Global Tax Governance - Kuhn, Katharina; Cadzow, Lucinda; Heitmüller, Frederik; Hearson, Martin; Randriamanalina, Tovony (Institute of Development Studies, 2024)
Keywords: Global tax governance; International tax; Legitimacy; Low-income countries; Regime complex; UN Framework Convention on International Tax Cooperation

Antitrust policy and EU labour markets : lessons from the US and comparative prospects - Langlois D'estaintot, Isaure (European University Institute, 2024)
Recent empirical evidence suggests that labour markets are not as competitive as previously thought. In that context, mobilizing antitrust policy has been discussed as a possible solution. The proposition sounds counterintuitive, however. If workers are paid below the competitive level, doesn’t this promote consumers’ outcomes by reducing downstream prices? Given that antitrust policy promotes consumer welfare, why would antitrust authorities intervene against such a state of affairs? Besides, why would stepping up on antitrust enforcement improve workers’ outcomes? Their interests have traditionally been protected through their exclusion from the scope of antitrust enforcement, not by the enforcement of antitrust rules to their benefit. This thesis demonstrates that those spontaneous assumptions do not hold. Consumer welfare does not speak against the defence of workers’ interests. First, the focus on consumers is a by product of methods: it does not prevent consideration of other types of market participants. Moreover, consumers benefit from competitive labour markets. The welfare effects of monopsony power simultaneously worsen workers and consumers’ outcomes. As for the promotion of workers’ interests, it can be achieved through both positive and negative enforcement of antitrust. So far, the EU Commission has been less proactive than the American DOJ and FTC on the issue of antitrust enforcement in labour markets ( although the state of affairs is evolving). While this difference may stem from EU workers benefitting from higher levels of social protection than US workers, those higher levels of protection may not negate the usefulness of antitrust ’s intervention. The low levels of antitrust enforcement in EU labour markets may result from legal uncertainty and case law inconsistency more than an absence of harm. Just like the merger control apparatus, Article 101 and 102 TFEU can be used to scrutinize labour markets. While doing so involves some practical complexities, they can be overcome.
Accepted: 2024-04-08T07:03:10Z
Keywords: Antitrust law; European Union countries; Labor laws and legislation; Unfair competition

The Rotterdam Rules Convention: United Nations Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea 2008 - Laurijssen, Peter (CMI, 2024)
Keywords: MARITIME LAW; UN Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea (2008)

Property in goods and the CISG - Maier-Lohmann, Till (Fachmedien Recht und Wirtschaft, dfv Mediengruppe, 2024)
Keywords: CONTRACTS; INTERNATIONAL SALE OF GOODS; UN Convention on Contracts for the International Sale of Goods (1980)

Climate Change Litigation in Civil Law African Countries: An Assessment of Barriers and Potentialities in Cameroon - Mbarga, Daniel Armel Owona (Climate Litigation and Justice in Africa, 2024)
It seems like a long time ago that there were only a handful of climate lawsuits. Since the first climate lawsuits were filed in the United States in 1990,² a myriad of litigation has emerged at the national, regional and global levels. According to the Grantham Research Institute on Climate Change and the Environment, as of May 2021 the databases on climate litigation around the world contained 1,841 cases that were either in progress or had already been decided.³ This shows the exponential development of the phenomenon through which civil society organizations, public law legal entities and private individuals are
Keywords: Africa; Cameroun; Civil Law; Climate change; Litigation

Digitization and sustainability: Practical convergences of two leading discussions in business law - Mittwoch, Anne-Christin (Beiträge zum Transnationalen Wirtschaftsrecht, 2024)
Until now, digitization and sustainability have stood side by side in the discussion of business law. As leading discourses of the present-day business scene, both topics are leading to profound change in companies and are influencing each other in the process - a circumstance that can no longer be ignored by corporate management. The article shows the guiding ideas behind both discussions, as well as their convergences and interactions, and asks about the effects they have on management's duty to act.
Keywords: Corporate Digital Responsibility; Corporate Sustainability; Digitization; Directors' Duties; Sustainability

A comprehensive outline towards conciliation in the contemporary world of E-commerce - N, Vinod; Gupta, Poonam (World Journal of Advanced Research and Reviews, 2024)
Since the start of the millennial era, technical advancements have led to exponential growth in electronic commerce, or e-commerce. According to the United Nations Conference on Trade and Development (UNCTAD), e-commerce sales reached about US$25 trillion globally in 2021 [1] and are expected to grow at a compound annual growth rate of 9% through 2027, which is twice as fast as the 4% annual growth rate predicted for traditional in-person retail [2]. Online dispute resolution (ODR) techniques that aim to settle disagreements and lower the likelihood of expensive lawsuits are becoming more and more necessary as both individuals and corporations use online shopping platforms. Due of its legally binding nature, arbitration is the most formal method, as was briefly discussed [3]. Online arbitration is carried out using electronic methods, like email and digital tools designed to make the duties of arbitrators and parties to a dispute easier. It adheres to the same rules and processes as traditional arbitration. On the plus side of e-arbitration, advancements in technology allow for time and cost savings without sacrificing the ease of remote filing. The conclusion of e-arbitration agreements raises several negative issues, including privacy and data protection issues for the consumer signing the agreements and power imbalances between corporate entities and the consumer. The degree to which artificial intelligence (AI) is effectively and sufficiently analysing a dispute between parties is up for debate because it's unclear how new this adjudication process is.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Artificial Intelligence; Conciliation; E-Commerce; Inteligência artificial; Intelligence Artificielle; ODR; OECD

Squaring up with workplace bullying - Naidoo, Natashia (University of Pretoria, 2024)
Workplace bullying is not considered a form of harassment that is commonly acknowledged nor does it attract specific legislative protection. The aim of this mini-dissertation is to ascertain the degree to which victims of workplace bullying are protected by South African labour legislation and whether other measures are necessary to ensure that employees are adequately protected. A comparative analysis between South Africa and the United Kongdom's legislative frameworks that governs workplace violence and harassment and, by implication, bullying is a critical aspect of this mini-dissertation.

Summary survey on publishing contract in the OAPI space - Ngombé, Laurier Yvon (The Journal of World Intellectual Property, 2024)
The OAPI member states constitute a space for theharmonization of copyright in Africa. This harmonizationis yet to be completed, as attested by the conventionalrules relating to the publishing contract. In addition,investigating about the publishing contract in the OAPIspace requires an examination of both the text of theBangui Agreement and that of the national laws of the 17member states. Some differences must be pointed outkeeping in mind the question of possible conflict of laws.
Published by John Wiley & Sons Ltd.
Keywords: ARIPO; Conflict of laws; Contract; Copyright

Concurrent Investor-State Claims Before Domestic Courts and Investment Treaty Arbitration Tribunals: Philip Morris, Vattenfall and Beyond - Nottage, Luke; Stendel, Robert (Virginia journal of international law, 2024)
Keywords: Arbitrage; Arbitragem; Arbitration

Taxing the digital economy: Options available for African countries - Oluwatuyi, Oluwasikemi (University of Victoria, 2024)
Tax authorities have always assessed and enforced taxes based on the physical address of businesses over the years. Nevertheless, the idea of tax jurisdiction has taken on a new meaning with the development of information and communication technology, and its profound impact on every facet of human existence – including but not restricted to trade and business. This development has undoubtedly increased capital mobility, especially in corporate form, and exposed more the weaknesses in national tax laws by enabling the artificial relocation of important economic components and potential exemption from taxes. Since it is getting harder to separate the digital economy from the rest of the economy for taxation reasons, the process of digitalization has emerged as one of the primary growth drivers. This expansion, together with aggressive tax planning strategies used by multinational enterprises (MNEs) to move revenues to low-tax jurisdictions and the development of business models requiring less physical presence, has increased the workload for tax administrators; furthermore, it has reduced governments’ capacity to raise funds in the traditional manner. In this regard, I assess how “adequate” the selected African countries’ frameworks are vis-à-vis the ongoing OECD and UN negotiations. Beyond the consultations, I call for a more inclusive and Africanised approach and the need for African countries to improve their tax administration mechanisms.
https://hdl.handle.net/1828/20312
Keywords: Digital economy; International taxation; OECD; Tax

Global Common: The Rights and Responsibilities of the State and the Investor in Renewable Energy Foreign Investment - Pang, Hui (UNSW Sydney, 2024)
States poured millions of dollars to attract foreign renewable energy investments for climate change mitigation, however, when it becomes too hefty for some states, they have modified regulations to reduce the level of support. These regulation changes have led to dozens of investors filing arbitrations against the host states, alleging breaches of investment treaty obligations. This thesis examines whether the current investor-state dispute settlement (‘ISDS’) regime adequately addresses environmental concerns when adjudicating renewable energy investment cases. While renewable energy investments can help protect a global common (the atmosphere) and mitigate climate change, the regulation changes also seek to protect a domestic public good (financial stability of the host state). Therefore, when the protection of a global common conflicts with a domestic public interest in renewable energy ISDS cases, what are the rights and obligations of the host state and the investor? Are the existing approaches of the ISDS regime toward environmental concerns and other public interests fair and adequate, and if not, what interventions can be made? This thesis explores these questions by conducting doctrinal analysis on more than 60 renewable energy cases and the arbitral jurisprudence regarding international environmental obligations. It uses the constitutionalisation of international law to break the self-contained regime of international investment law and argues that common values should be regarded as equally important as investment protection goals in ISDS. This thesis finds that the ISDS regime considers international environmental obligations to be insignificant in supporting the host state’s defences in non-compliance of bilateral investment treaties or the investor’s claims for investment protection. This thesis shows that the current approach furthers discrepancies between climate change mitigation and international investment law. Not only does this approach fail to acknowledge the environmental connections of renewable energy investment, but it also creates opportunities for fossil fuel investors to seek compensation against environmental regulation changes using the same arguments. As an intervention against the current approach, this thesis proposes to reconstrue the concept of legitimate expectations to place common values on equal grounds with investment protection incentives. This thesis makes two significant contributions to knowledge. Firstly, it extends existing analyses of the conflicts and synergies between international investment law and environmental protection and contributes to the growing body of scholarship on this topic. Research on this topic has mainly focused on how the state safeguards environmental interests against investor protection claims. While this narrative comprises many cases, it does not capture the full picture and overlooks the possible contributions of private parties in protecting global commons. Instead, this thesis examines whether international environmental obligations can serve as a ‘shield’ for the state’s non-compliance in investment protection, or as a ‘sword’ for investors to compel the state to fulfil its international obligations. Secondly, this thesis makes an intervention to reconstrue ‘legitimate expectations’, where common values are reinforced and not only the interests of investors are protected but also the ‘legitimate expectations of a responsible investor’ from the state and local communities are taken into account.

The Individual in International Law: History and Theory - Sparks, Tom; Peters, Anne (Oxford University Press, 2024)
978-0-19-889891-7
Keywords: Humanisation; Individual; Individualisation; International law; Legal history; Legal theory

UNCITRAL Model Clause on Adjudication - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Confidentiality - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Highly Expedited Arbitration - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Technical Advisers - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

Measuring the Effects of Post-Convention Activities at the HCCH - Zhang, Ke (McGill University, 2024)
https://escholarship.mcgill.ca/concern/theses/cn69m944k
Keywords: HCCH; Hague Conference on Private International Law

Blockchain and smart contracts: a game changer in mediation? - Mak, Charles Ho Wang; Mante, Joseph (Asian journal on mediaton, 2023)
In light of accelerating technological innovation and shifts in dispute resolution paradigms, this article elucidates the transformative potential of blockchain technology and smart contracts in mediation. The paper posits that these advancements offer an innovative framework for dispute avoidance and a more efficient, transparent process for resolving conflicts, particularly in commercial settings. The article critically assesses the inherent challenges and argues that overcoming these obstacles necessitates a multi-stakeholder approach, encompassing legislative measures, educational initiatives, and technological enhancements. It ultimately contends that blockchain and smart contracts hold the capacity to significantly reshape the landscape of mediation.
https://rgu-repository.worktribe.com/output/2085489/blockchain-and-smart-contracts-a-game-changer-in-mediation https://rgu-repository.worktribe.com/output/2085489
Keywords: Blockchain technology; Dispute resolution; MARD; Mediación; Mediation; Mediação; Médiation; Smart contracts

Corporate Data Responsibility - Sarfaty, Galit A. (Big Data and Armed Conflict: Legal Issues Above and Below the Armed Conflict Threshold, 2023)
This is an accepted manuscript of a book chapter in the edited volume: Big Data and Armed Conflict: Legal Issues Above and Below the Armed Conflict Threshold
This file is under embargo and will become available on 2024-12-14

Chapter 1, Introduction to contract law and theory - DiMatteo, Larry A. (Principles of Contract Law and Theory, 2023)
This chapter provides background information on the evolution of the common law of contracts. It begins with a short history of the evolution of the common law in England including the roles played by the Roman Catholic Church, the development of a dual court system—one in law and the other in equity, the transition from absolute monarchy to a parliamentary form of government, the creation and restrictiveness of the English writ system, the common law’s reception in America, and the building of a general law of contract in the nineteenth century. It explains the historical differences between law and equity, along with the fusion of the two into a single court system. It also discusses the justifications given for contract law and its role in society. It describes the different perspectives of written or formal law, theory, and practice, and importantly, the difference between law in the books versus law in action. Finally, it explains the differences between rules, principles, and standards, and the boundaries of contract relative to other areas including tort and unjust enrichment.

Chapter 11, First principles in transportation law and policy - Levine, Jonathan; Shill, Gregory H. (A Research Agenda for US Land Use and Planning Law, 2023)
The main purpose of transportation is connecting people to destinations they value. This seemingly banal statement would, if taken seriously in policymaking, upend transportation and land use planning. Today, planning agencies rely on key performance indicators (KPIs) to measure outcomes. While ostensibly neutral and technical, these measurements in fact imply policy judgments and drive legal consequences. They operate both as a shield against litigation and as a sword to justify new projects. But the way KPIs are set up reflects confusion about basic purposes. They are used to plan and evaluate based not on the ability to reach anything but rather simply to accelerate the speed of traveling. We seek to anchor transportation policy discussion in first principles. The shift we propose is mode agnostic in that it is relevant to all means of transportation. Even so, shifting from a goal of speed to one of reachability would be a leap. We believe such a shift suggests important open questions regarding the barriers to reform and we engage a few of them.

Business climate and global value chains: Insights from Africa - Ajide, Folorunsho M. (Transnational Corporations Review, 2023)
This paper provides insights on how business climate affect global value chains (GVC) participation in the panel of African nations. The study explores country-level data spanning over a period of 2006–2018. Using the novel method of moments (MM)-Quantile regression, system generalized methods of moments (SYSGMM) and Panel spatial consistent correlation (PSCC) techniques, the study finds that all aspects of business environment have significant impacts on GVC participation in Africa. In specific, information and communication facilities, getting electricity, getting credit, trading across border, enforcing contract, protecting investors and business start-up registration have positive and significant impact on GVC. We also discover that tariff reduces GVC participation while strong political institutions enhance participation. The study concludes that business environment factors are fundamental to ensure high level of GVC participation. Political institutional framework needs to be strengthened to further encourage GVC participation in Africa.
Keywords: Africa; Business environment; Climate; GMM; Global value chains

Terms of trade, governance and household income in selected African countries - Edeme, Richardson Kojo; Mumuni, Sulemana (Sustainable Futures, 2023)
As African countries grapple with the challenges of terms of trade occasioned by economic uncertainty, there is a need for a study on the effect of terms of trade on household income in Africa. Also, as African countries continue to commit to the role of institutional quality in improving terms of trade, this study further reinforces the role of governance on household income in Africa. The study employs the Two-stage Least Squares (2SLS) fixed effects estimation technique based on data spanning 2002–2021 for 36 selected African countries. This study provides more robust evidence by employing household final consumption expenditure as a measure of household income. Findings suggest that improvement in the terms of trade stimulates household income. Similarly, the results indicate that governance plays a critical role in enhancing household income status in Africa. Specifically, government effectiveness, control of corruption, regulatory quality, rule of law, and political stability positively and statistically significantly influence household income levels in Africa. Furthermore, GDP per capita growth positively impacts household income, albeit the effect is statistically insignificant. On the contrary, higher inflation rates, exchange rate volatility, and foreign direct investment (net inflows) have a limiting effect on household income, although, the effect of currency depreciation is generally not statistically significant. Sequel to these findings, the study calls for strong institutional quality and export promotion strategies in Africa.
Keywords: 2SLS; Governance; Household income; Terms of trade

Nigeria’s Contribution to Africa’s Regional Integration: Assessment of its recent Performance - Garba, Dimas (African Journal of Politics and Administrative Studies, 2023)
This paper investigates the recent performance of Nigeria towards Africa’s regional integration as a major power in Africa. The main objective of the research is to determine the extent of Nigeria’s commitment to the realization of the African Union’s vision of becoming a fully integrated, prosperous and peaceful Africa; and a dynamic force at the global level. Since her independence in 1960, Nigeria has been widely acknowledged as a leading power in Africa (The Giant of Africa) by several studies because of its preponderant political, economic and militarily power; influence; and benevolent contributions regarding to the liberation and progress of Africa. However, there are hardly substantive assessments of its recent performance towards Africa’s integration. The study adopts the Hegemonic Stability Theory; and descriptive analysis method to analyze data obtained from secondary sources. Analysis of the 2016 and 2019 Regional Integration Index (ARII) reports covering the period from 2010-2019 reveals that Nigeria has performed poorly towards the continent’s integration among its peers, both at the continental and sub-regional levels. The paper concludes that Nigeria’s poor performance would significantly slow the acceleration of Africa’s integration; and the country risks losing its leadership position in Africa to its rivals, especially South Africa. It recommends that the Nigerian government should take deliberate steps in formulating and implementing policies that would improve its performance across the five dimensions of the regional integration; and it should strengthen its commitment to consolidate its leadership position in Africa, and motivate smaller countries to contribute their best.

The Challenges of Regional Integration and Effective Implementation of African Continental Free Trade Area (AfCFTA) Policy in Africa - Garba, Dimas; Wancelous, Avong (African Journal of Politics and Administrative Studies, 2023)
The paper is an investigation of the challenges of regional integration in Africa and their effects on the implementation of the African Continental Free Trade Area (AfCFTA) policy. The major objective of the paper is to proffer solutions to the challenges for the effective actualization of the policy. The assumptions of the neo-liberal theory were used to support the AfCFTA initiative to promote economic growth and development in Africa. The data used to advance the argument were obtained from secondary sources of data collection. The study finds that language barrier, multiple currencies, porosity of borders, foreign interference, political instability and insecurity, poor human development, over-lapping of membership of sub-regional organizations, poor state of infrastructure, and state-centric nature of integration initiatives are some of the core challenges hindering the effective execution of the AfCFTA policy. The study recommends that the African Union (AU) should intensify effort at realizing a single currency policy for Africa; design comprehensive regional security architecture to include high technological surveillance, joint air and ground border patrol among member states of Regional Economic Communities (RECs) to address trans-border crimes and insecurity. There should also be institutionalization of counterpart funding among AU member-states for infrastructural development; and encouragement of private and civil society participation in the integration initiative, among others. In concludes that if the challenges identified are not effectively addressed, it will be very difficult for the AU to successfully realize the objectives of the AfCFTA policy.
Keywords: AfCFTA Policy; Africa; Challenges; Implementation; Regional integration

Corruption and its Impact on Socio-Economic Development in Selected Countries of Africa - Muhammad, Ibrahim; Wasiu, Sanusi; Ahmad, Muddassir (African Journal of Politics and Administrative Studies, 2023)
Africa is indeed a continent blessed with an abundance of natural resources, ranging from valuable minerals like gold, diamonds, copper, and oil. These resources hold immense potential for fostering economic growth and development across the continent. However, Africa continues to grapple with extreme poverty and underdevelopment, with corruption being identified as a major impediment to progress. This paper focuses on the pervasive issue of corruption in Africa, with Nigeria, Uganda, and Zimbabwe as case studies. The research employs a descriptive and analytical method of historical research, grounded in the Prebendal Theory as its theoretical framework. The findings of this study reveal the staggering impact of corruption on Africa's development, with annual losses of approximately $60 to $100 billion due to illicit financial flows. These flows divert resources away from political and socio-economic advancement, exacerbating widespread impoverishment. In conclusion, the paper underscores the corrosive effect of corruption on Africa's development and offers several recommendations to address this issue. These include promoting merit-based leadership selection, enforcing stronger legal actions against corruption, empowering anti-corruption agencies, engaging citizens and civil society in the fight against corruption, and strengthening the rule of law and judicial independence. These recommendations aim to pave the way for a more transparent and accountable future in Africa.
Keywords: Corruption; Government; Infrastructure Africa; Socio-Economic Development

A comparative evaluation of the South African income tax regime for investments using trusts - Herbst, Hendri (Stellenbosch University, 2023)
This study evaluates the South African income tax regime for investments using trusts. It considers whether reforms are required, and if so, how can this be done to create a tax framework that will encourage investment, limit tax avoidance and curb capital outflows, while considering South Africa’s unique context and challenges.
Keywords: Income tax; Investments; Taxation; Trusts and trustees

Critical analysis of the institutional framework governing the agreement establishing the African Continental Free Trade Area - Lehlongwa, Thulane Charlo (Stellenbosch University, 2023)
The African Continental Free Trade Area as a flagship project of Agenda 2063 represents renewed attempts by the African Union to drive the continent closer to its economic integration ambitions, which can be formally traced back to the adoption of the African Declaration on Cooperation, Development, and Economic Independence, and later the Treaty Establishing the African Economic Community. Building on these frameworks, the AfCFTA seeks to, amongst others, advance intra-African trade by creating a single market for goods and services facilitated by the movement of persons, promoting sustainable and inclusive socio-economic growth, creating a liberalised market for goods and services, and promoting industrial development. Central to the attainment of the objectives of the AfCFTA is a well-functioning and effective institutional framework at a continental, regional, and national level all well-integrated to facilitate and oversee its implementation. The strengthening of regional and continental institutions to effectively lead and drive Africa’s transformation agenda has also been recognised by Agenda 2063 as a key enabler to this end. The demise of previous African integration efforts has mainly been attributed to the weakness of regional and continental organs to be able to effectively oversee and administer the implementation of continental programmes by the countries. This thesis appraises the institutional framework established to oversee the implementation, administration, facilitation, and monitoring of the AfCFTA, and this is considered against the broader African Union institutional framework and the regional economic communities. Although vastly different, the thesis further considers the experience and best practices from the European Union regional integration model to draw lessons and with a view to reforming and integrating African continental and regional bodies to be able to effectively oversee key initiatives including the AfCFTA. Finally, the thesis considers some of the work already initiated by the AU to review and reconfigure the extant continental bodies and then recommends some key interventions to reinforce and better integrate the institutional framework of the AfCFTA with the existing continental and regional frameworks.
Keywords: AfCFTA; African Continental Free Trade Area; Dispute resolution; Economic integration; Free Trade; International economic relations

Legal protection of the individual's image against unauthorised commercial exploitation in South Africa : a critical evaluation of existing law and suggestions for law reform - Van Gensen, Layckan Inge (Stellenbosch University, 2023)
URI: https://scholar.sun.ac.za/handle/10019.1/128896
Keywords: Commercial exploitation; Human rights; Image rights; Intangible property; Intellectual property; Personality; Right of privacy

The impacts of IFRS 16 on airlines - Ribeiro, José; Ribeiro, Francisco; Ribeiro, Fernando (Accounting and Management Review | Revista de Contabilidade e Gestão, 2023)
This study addresses the effects of the adoption of IFRS 16 on the passenger air transport sector. With practical effects for financial years beginning on or after 1 January 2019, IFRS 16 established the standardisation of a single accounting modelfor all leases, whether operating or financial. With this new adoption, IFRS 16 aims to increase the transparency and quality of the information that is presented in the financial statements for the most diverse stakeholders. This study aimed to assess the effects of adopting this new international standard in a specific sector and to identify whether the changes in some of the financial indicators are felt in the same way by all companies, this being the main focus of this study. Based on a sample of 12 airlines from various countries in Europe and South America, the financial indicators were interpreted by analysing the reports and accounts before and after the application of IFRS 16. The main conclusions obtained are: i) the adoption of IFRS 16 led to an increase in assets, liabilities and EBITDA, however in different proportions for each of these items; ii) companies with negative equity and, therefore, with greater risks of bankruptcy or greater information asymmetry, tend to resort more to leasing as a way of financing their assets; iii) the financial autonomy and solvency ratios showed significant variations for companies that resort more to operating leasing.
Keywords: Airline industry; Finance leases; IFRS 16; Information asymmetry.

An In-Depth Analysis of Choice of Law Rules in Consumer Contracts: A Focus on the African Continental Free Trade Area - Fiattor, Ethel (Journal of Law, Society and Development, 2023)
Choice of law is a perplexing concept due to the importance of party autonomy, the diversity of connecting factors, and the variety of different contractual issues. The problem of choosing a governing law is complicated in consumer contracts by industrialised mechanisms depriving consumers of negotiation rights. The core mandate of the African Continental Free Trade Area (AfCFTA) is to establish a single market for goods and services associated with the free movement of legal persons for economic integration. This objective requires a harmonised consumer protection policy to resolve the diverse consumer protection regimes applicable in state parties within AfCFTA member states. This policy should provide suitable consumer protection mechanisms generally and in the context of choice of law specifically. Implementing a draft competition policy bestows a legitimate mandate on the AfCFTA to negotiate a continental framework on consumer protection as both fields of law complement each other to safeguard consumer rights in cross-border trade. This article argues the dynamics of providing adequate choice of law rules on consumer contracts to inform suitable mechanisms on consumer interest within the AfCFTA. The article discusses the abuse of choice of law clauses in consumer contracts, affecting consumers’ rights in cross-border contracts within the AfCFTA. It suggests a harmonised consumer protection policy to regulate and mitigate these clauses. The article also examines trends in Global North jurisdictions like the European Union to inform a context-specific institutional framework for the AfCFTA’s choice of law rules.
Keywords: AfCFTA; Applicable law; Choice of law; Consumer protection; Economic integration; Harmonisation; International law; ZLECAf

South African controlled foreign companies' rules and the digital economy - Sengwane, Khodani (Potchefstroom Electronic Law Journal, 2023)
South Africa's controlled foreign company ("CFC") rules were enacted more than two decades ago before most of today's business models existed. These are anti-avoidance rules that ensure the South African taxation of profits diverted offshore by South African residents. In terms of the CFC rules, the profits of a non-resident company may also be subject to tax in South Africa at the hands of its South African resident shareholder if such non-resident company is considered to be a CFC. Advances in technology developments and the use of information communication and technology ("ICT") have given rise to what is referred to as the digital economy. The term refers to economic activities hinged on the use of ICT and the internet. Digitalisation has made it possible for a business to carry on economic activity without the need for a multitude of offices, staff, equipment, and other resources. As a result, new business models like Uber and Shien have emerged. This paper argues that the current South African CFC rules have not kept pace with these new business models and do not effectively regulate the new business models and the digital economy. This paper recommends that the CFC rules be updated to address the digital economy and new business models by amending the rules, incorporating the provisions of Electronic Communications and Transactions Act 25 of 2002 into the rules, using country-by-country reporting, and even considering implementing a regime alternative to CFC rules.
Keywords: Anti-avoidance; Controlled foreign company; Deemed source; Digital Economy; Digitalisation; Direct tax; Foreign business establishment exemption

The impact of exchange platforms on the security of European markets - D'Alessandro, Francesco (LUISS Guido Carli, 2023)
Exchange platforms listed on European markets: financial contamination? The Luna collapse: present-day exposé. Aògorithmic stablecoins. The Luna project and the Terra ecosystem. Legal framework of a billion-dollar scam. Class action lawsuits. National and European implications of such actions. Misleading advertising (binance's liability) and culpa in eligendo. Exchange platforms listed on European markets: financial contamination? Parallels between shares and cryptocurrency investments: lack of transparency giving rise to bubbles. InvestVoyager case study. FTX case study. Positive law and new horizons. DeFi self-regulation: AML compliance and exchange platforms. The proposal of MiCA regulation (markets in crypto-assets). Payment systems directive 2 (PSD2). Directive 2009/110/EC on e-money. Potential solutions (proposals). External audit of smart contracts: a comprehensive examination-technical and legal perspectives. Digital euro. Establishment of a national or European commission: risks for consumers and comparative research. Regulation of exchanges and enforcement of transparency obligations.

Developing a legal framework for determining forum choices in transnational intellectual property litigation - Ho, Vannessa May Ha (Macquarie University, 2023)
As communication technologies have assisted in the rapid transfer of information and goods across borders, there has been a commensurate rise in transnational intellectual property litigation. In particular, use of the Internet for trade and consumption of information has led to simultaneous infringement of parallel intellectual property rights in multiple States. The chosen forum to resolve such a dispute is perceived to have significant effect upon the outcome of litigation. There is a need to closely evaluate current jurisdiction rules and recent reform proposals to determine the extent to which they facilitate or prevent litigants from making forum choices that can promote efficiency and fairness in the dispute resolution process. However, there is currently no formal international treaty that regulates how litigants may make forum choices during transnational intellectual property litigation. As a result, the range of forum choices available to litigants are determined by divergent domestic rules, meaning that litigants must enforce their intellectual property rights in forums within every State where the rights exist and have been infringed upon. In such as context, a critical issue is to consider is whether an international regulatory framework could be developed to facilitate appropriate forum choices which advances and calibrates efficiency and fairness in transnational intellectual property litigation. As most conceptions of appropriate forums are from a doctrinal perspective, it is necessary to create a theoretical framework to determine what constitutes an appropriate forum choice during a transnational intellectual property dispute. This theoretical framework can then be used to evaluate the merits of current rules on jurisdiction and determine whether they define a suitable range of available forums that allow litigants to make appropriate choices. The forum non conveniens doctrine also needs to be evaluated as it has the most developed case law that considers appropriate forums for civil disputes. Finally, the risks and benefits of developing an international regulatory framework needs to be examined to assess which method would be the most suitable way to facilitate appropriate forum choices. It is hoped that this research will assist courts and legal practitioners when making decisions about complicated jurisdiction issues during transnational intellectual property disputes, as well as enable policy makers to promote reform that facilitates more efficient and fair forum choices.
Keywords: Forum choice; Forum non conveniens; Forum shopping; Intellectual property litigation; International regulatory framework; Kyoto Guidelines; Lucasfilm v Ainsworth; Private international law; Rational choice; Subject matter jurisdiction

Standing in international investment and trade disputes - Ossa, Ralph; Staiger, Robert W.; Sykes, Alan O. (Journal of International Economics, 2023)
International investment agreements employ dispute settlement procedures that differ markedly from their counterparts in trade agreements. A prominent and controversial difference arises with respect to the issue of “standing”: Who has the right to complain to adjudicators about a violation of the agreement? While trade agreements limit standing to the member governments (state-to-state dispute settlement), investment agreements routinely extend standing to private investors as well (investor-state dispute settlement). We develop parallel models of trade and investment agreements and employ them to study this difference. We find that the difference in standing between trade and investment agreements can be understood as deriving from the fundamentally different problems that these agreements are designed to solve. Our analysis also identifies some important qualifications to the case for including investor-state dispute settlement provisions in investment agreements, thereby offering a potential explanation for the strong political controversy associated with these provisions.
Keywords: Bilateral investment agreements; Investments; Investor-State Dispute Settlement; State-to-state dispute settlement; Trade agreements; Trade dispute

Legal Reconstruction of Dispute Settlement Between Importers and Exporters International Law Perspective - Pristha Utama, Wahyu; Tri, Lazarus; Setiyono, Joko (Journal of Xi'an Shiyou University, Natural Sciences Edition, 2023)
Reconstruction of dispute resolution law between importers and exporters from an international law perspective. The purpose of this study is to analyze: 1) How does the law of dispute resolution between importers and exporters perspective international law? 2) How is the implementation of the recommendations of the dispute resolution bodies of the World Trade Organization from an international law perspective? The research method used is normative juridical with a statutory approach, concept approach, and case studies. The results showed that: 1) Import export is a series of company activities that begin with an agreement. The agreement is the result of previous activities carried out by exporters and importers, namely in the form of supply and demand. The agreement is poured into a sales contract which is an agreement between exporters and importers to trade goods in accordance with mutually agreed conditions and each party binds itself to carry out all obligations incurred. 2) The series of processes undertaken in dispute settlement at the WTO consist of 4 processes, including: Mandatory Consultation between disputing parties to reach a settlement approved by the parties, Application for the establishment of a Panel, the Appellate Body, and the implementation and implementation of recommendations and provisions endorsed by the DSB.
Keywords: Dispute Resolution; Exporter; Importer; International Law; Reconstruction

Party autonomy and judicial participation in commercial arbitration: recalibrating the role of Nigerian courts. - Aduloju, Bamikole Martins (Robert Gordon University, 2023)
Courts and arbitration tribunals aim to resolve disputes and make enforceable decisions in their distinctive way. However, unlike courts, tribunals lack state enforcement power to function independently. Consequently, arbitrating parties have had to approach the courts for various supports. However, while supporting arbitration, the Nigerian courts have been criticised for overwhelmingly undermining party autonomy. Thus, the determination of the extent to which Nigerian courts should participate in arbitration remains topical. This research reviewed the current regime governing the scope and limits to the court's roles in arbitration in Nigeria, aiming to find out the problematic areas where the court's roles have been a leeway to undermine party autonomy. The research found that the current practice in Nigeria generally observes party autonomy as an affirmative stance by the Nigerian courts and laws. It further found the areas where the Nigerian system has, nevertheless, created some leeway for the courts to undermine party autonomy. These include (i) the narrow phrasing and interpretation of Section 34 of the Act and some specific provisions, and their failure to set out a definite limit to courts' roles in arbitration, (ii) the application of the concept of constitutional supremacy which has been interpreted to allow Nigerian courts to participate in all cases including arbitration and override parties' agreement, (iii) absence of Institutionalised tracking and periodic recalibration of the relationship between the courts and arbitration, and (iv) judicialisation of administrative roles of the courts in arbitration. To this end, a legal and analytical review of these problematic issues was conducted, particularly using some elements of the legal comparative approach to analyse the problems in the light of the related practices in some similar or advanced jurisdictions such as the United Kingdom, Ghana and Malaysia. Lessons were drawn from the analysis. Short- and long-term recommendations were, therefore, made for law reforms in Nigeria, particularly towards recalibrating the court's roles in arbitration such as to wedge the loopholes in the system without which recalcitrant parties and jurists could take advantage to undermine party autonomy.
Keywords: Arbitrage; Arbitragem; Arbitration; Autonomy; Court systems; Judiciary; Tribunals

Tacit Choice of Law in International Commercial Contracts. An Analysis of Future Instruments of Developmental Organisations - Bouwers, Garth J. (Potchefstroom Electronic Law Journal, 2023)
This article examines the various regional and supranational organisations of emerging countries that could benefit from a codification of private international law rules. They include the Organisation for the Harmonisation of Business Law in Africa (OHADA), the African Union (AU) and the Association of Southeast Asian Nations (ASEAN). In addition, the article analyses the envisaged instruments that may be especially relevant in the context of the abovementioned organisations. These include the Preliminary Draft Uniform Act on the Law of Obligations in the OHADA Region, the proposed African Principles on the Law Applicable to International Commercial Contracts and the Asian Principles of Private International Law. More specifically, the article focusses on the provisions regarding the determination of the law applicable, particularly those rules relating to a tacit choice of law in international commercial contracts.
Keywords: ASEAN; African Union; Asian Principles of Private International Law; Choice of Law; International Commercial Law; OHADA; Private International Law; Tacit choice of law

Infringement of Brand Rights on Different Products Is an Illegal ACT - Fahdia, Khamada Wafi; Roisah, Kholis (International Journal of Social Science Research and Review, 2023)
The study aims to find out how the provisions of the law are in violation of brand rights to nongender products and their protective forms, as well as how legal efforts should be made in violation of their laws. Legal protection for legitimate brands' owners is regulated within brand laws intended to give their owners exclusive rights. Legal measures that rights holders can make on broken brands can be made either by civil law or criminal law. Indonesia's brand registration system is a constituent system, and it is recommended that all efforts be quick to register a trademark or service brand for the creditor of intellectual property rights. The holding of a brand would be wise to appeal to the court immediately if there is any indication that a brand offense is committed by another and the cost is not greater.
Keywords: Brands Infringement; Products of No Kind; Unlawful Conduct

Vulnerability Theory as a Paradigm Shift in International Investment Law: Reimagining the Role of the State - Küçüksu, Aysel; Ünüvar, Günes (Business and Human Rights Journal, 2023)
This article argues for a fundamental raison d'être reconceptualization of international investment law (IIL) through Martha Fineman's 'vulnerability theory'. The theory helps identify the structural sources of IIL's shortcomings, whilst philosophically challenging the one-sided view that foreign investors are entitled to protections, but are free from obligations vis-à-vis the communities affected by their undertakings. Emphasizing the productive power of the state to take positive action that acknowledges ordinary citizens' embeddedness within, and dependence upon, surrounding structures, the vulnerability theory challenges the hegemonic perception of the state as a source of danger - a view which has hitherto undermined both the potency and the enforceability of investor obligations. Used as a heuristic device in studying both IIL's existing structures and the potential avenues for reimagining it, Fineman's theory not only shines a novel light on the foundational premises of IIL, but also grants theoretical traction to existing ideas about improving the system.

Prospects for an African continental model multilateral tax agreement for the co-ordination of cross-border corporate tax challenges - Fehun Aren, Marie-Louise (University of Pretoria, 2023)
This study explores the creation of an African Continental Model Multilateral Tax Agreement (MMTA) to address the limitations of current bilateral tax treaties and enhance existing African Regional Economic Community (REC) frameworks for more effective taxation of cross-border business profits. Focusing on critical international taxation framework issues such as taxing rights allocation, Permanent Establishment criteria, and tax dispute resolution, it compares African REC MMTA provisions with those in non-African agreements to identify key weaknesses and propose improvements. The proposed MMTA aims to ensure equitable taxing rights, update nexus rules to capture both physical and digital businesses, and provide robust dispute resolution mechanisms to foster investment. It advocates for harmonized tax policies and tax agreements across African RECs to minimize tax competition, promote intra-African trade, and support regional economic integration under the African Continental Free Trade Area (AfCFTA). By aligning with the Abuja Treaty’s objectives, the framework seeks to enhance revenue mobilization and sustainable economic development in Africa. This research provides a roadmap for creating a tailored multilateral tax treaty that balances diverse regional interests, addressing Africa’s development financing needs while promoting cross-border taxation efficiency.
Keywords: AfCFTA; African Continental Free Trade Area; Continental model; International taxation frameworks; Multilateral tax agreement; Revenue mobilisation; Tax treaties

An analysis of merger and amalgamation transactions under the Companies Act 71 of 2008 and the Income Tax Act 58 of 1962 - Meyer, Carolina (University of Pretoria, 2023)
In law it is common to encounter two separate pieces of legislation which govern a single matter or transaction, for example, the Companies Act 71 of 2008 (the Companies Act) and the Securities Transfer Act 25 of 2007 both of which address the sale of shares. Similarly, the Income Tax Act 58 of 1962 (the Income Tax Act) and the Companies Act both have regulations which govern, respectively, tax law and company law matters in South Africa. These two Acts overlap in various business and commercial fields as tax is frequently an important component of any business transaction undertaken by a company. Issues, however, arise when the regulations in these two Acts, are inconsistent. This can be observed if one compares the current South African Income Tax and Companies Act, specifically as regards the sections involving merger and amalgamation transactions. Section 44 of the Income Tax Act governs merger and amalgamation transactions from a tax perspective and provides for tax rollover relief if certain requirements are met. The regulations governing mergers and amalgamations under the Companies Act are contained in sections 113, 115 and 116 of the Act. Although these sections in both Acts address the same transaction – a merger or amalgamation between two or more companies – there are several discrepancies between the regulations in the two Acts which appear to operate entirely independently of one another. In practice, one often sees that other sections in the Companies Act and Income Tax Act are used to achieve a merger due, in the main, to the uncertainties in the application of the relevant merger sections in the two Acts and the limited interaction between them. This study identifies and assesses the impact of the discrepancies identified in these two Acts in relation to merger and amalgamation transactions. The study makes recommendations to address these discrepancies and to align the South African Companies Act and Income Tax Act as regards merger/amalgamation transactions.
URI: https://repository.up.ac.za/handle/2263/94064
Keywords: Amalgamation; Companies Act; Income Tax Act; Merger; Taxation

Earnings Management and Default Risk - Nguyen, Loan (Victoria University of Wellington, 2023)
This thesis comprehensively investigates the relationship between default risk (DR) and earnings management (EM) by addressing inconsistencies in prior research regarding the level and direction of EM in response to varying levels of DR. The thesis extends beyond severe financial distress to include firms with low and medium levels of distress. It examines the non-monotonic relationship between DR and EM, considering accrual earnings management (AEM), real earnings management (REM), and total earnings management (TEM). The thesis also examines the impact of DR on the relative use of REM versus AEM. The moderating effect of the global financial crisis (GFC) on the relationship between DR and EM is also explored.Using a sample of 29,228 firm-year observations from 4,514 US-listed firms during 2001-2019, the study employs both the traditional two-step and the more recent one-step approaches to identify EM. Sensitivity analysis is conducted, including and excluding mining firms.The findings reveal a non-monotonic relationship between DR and REM, with a concave pattern observed for all measures of REM. Initially, REM increases as DR rises, but it subsequently declines with further increases in DR. AEM, on the other hand, shows a convex or monotonically decreasing relationship with DR, although statistical significance is not consistently observed. The results for TEM align with those of REM, indicating the dominance of REM in TEM. These findings remain consistent when excluding mining industry observations and using different measures for EM and DR.The implications of these findings are significant for managers, firms, regulators, lenders, investors, and other stakeholders. The non-monotonic relationship between DR and REM offers insights for decision-making and determining appropriate levels of EM during varying levels of DR. Regulators can utilise this relationship to identify potential risk areas and develop effective regulations. Lenders can assess financial statements more vigilantly, and investors can make more accurate risk assessments and informed investment decisions. The robustness of the results and the inclusion of different EM measures provide valuable insights to auditors, analysts, and government professionals, enhancing their understanding of the complexities and risks associated with EM during varying levels of DR.The study also uncovers that the relative use of AEM and REM is complimentary, but the impact of DR dampens the increase in REM for a given increase in AEM. This result holds across primary and alternative measures of DR and is of significant interest to managers, firms, regulators, and other stakeholders. It provides insights into the interplay between AEM and REM, enabling informed decisions about EM strategies under different levels of DR. Regulators can leverage this information to identify potential risk areas and develop effective regulations to mitigate EM practices that could lead to financial instability. Lenders and investors benefit from understanding how DR affects the relative use of AEM and REM, enabling them to assess financial statements and manage investment risk more accurately. The study’s findings contribute to a deeper understanding of EM dynamics and have practical implications for various stakeholders in the financial ecosystem.Furthermore, the thesis investigates EM measures during the GFC and the moderating effect of the GFC on the relationship between DR and EM. The inclusion of REM and TEM, in addition to AEM, provides a comprehensive understanding of how firms managed their earnings during the GFC, offering insights into the effectiveness and implications of different EM strategies during a financial crisis. It confirms the decline of AEM during the GFC, reinforcing existing knowledge about the impact of the crisis on EM practices. Additionally, it identifies a negative impact of the GFC on REM and TEM, providing further evidence of the challenges and changes in EM strategies faced by firms during the economic crisis. The study also finds an insignificant moderating effect of the GFC on the relationship between DR and REM, as well as DR and TEM, shedding light on EM variation across different economic stages.Overall, this thesis contributes to the EM literature by examining the non-monotonic impact of DR on EM measures, comparing different approaches to identify EM, exploring the moderating effect of DR on the relative use of AEM and REM, and investigating EM measures during the GFC. The insights from this research assist managers in decision-making, firms in adapting financial management strategies, regulators in developing policies, lenders in risk assessment, and investors in understanding the complexities and risks associated with EM. The findings have practical implications for various stakeholders in the financial realm, guiding decision-making, regulatory efforts, risk assessment, and investment strategies.Keywords: earnings management, accruals earnings management, real earnings management, default risk, global financial crisis, one-step approach, two-step approach.

The Concise Encyclopedia of Business Ethics - MacDonald, Chris; Marcoux, Alexei (Toronto Metropolitan University, 2023)
The authors’ aim in writing The Concise Encyclopedia of Business Ethics (CEBE) was to provide readers with a useful, concise overview of key issues in business ethics. Our aim is not to be exhaustive, but to provide key definitions, main areas of controversy, and pointers for further reading. It is hoped that it will provide a useful reference guide for students, as well as a starting point for scholars in adjacent fields. Our commitment to sticking to what we consider to be essential topics inevitably means that some readers will find that we have left out what they take to be important topics. For the most part, we stand by our editorial choices. However, as a digital document, it is possible that the CEBE will change and grow slightly over the coming years. Readers are free to provide feedback and suggestions by emailing the authors jointly at editors@bejr.org

The impact of blockchain and smart contracts on dispute settlement: a case for mediation. - Mak, Charles Ho Wang; Mante, Joseph (Dispute settlement: the past, present and future dimensions, 2023)
The research is premised on two important developments, accelerating technological innovation and shifts in dispute resolution paradigms. These advancements offer an innovative framework for dispute avoidance and a more efficient, transparent process for resolving conflicts, particularly in commercial settings. To make this case, we use blockchain technology and smart contracts as technological exemplars, and mediation as an example of dispute resolution mechanism that can be positively impacted by the use of the relevant technology. The potential of these technologies to promote dispute avoidance and the emerging legal frameworks for resolving blockchain technology and smart contract disputes were also explored. We also examine how blockchain technology and smart contracts can be integrated into the mediation process, the advantages, challenges, and possible solutions.
https://rgu-repository.worktribe.com/output/2086138/the-impact-of-blockchain-and-smart-contracts-on-dispute-settlement-a-case-for-mediation
Keywords: Blockchain technology; Dispute resolutions; Disputes; Smart contacts; Technological innovation

Corporate Criminal Sanctions for Human Rights Abuses: A Legal Appraisal of This Liability Under Cameroonian Business Law - Nyiloh Bavoh, Frankline (International Multilingual Journal of Science and Technology, 2023)
Criminal responsibility for corporate related human rights violations is a challenging and complex question in today’s world, this is partly because of the individual or personal character of criminal responsibility. It is held as a general rule that only human beings can commit offences. The primary objective of this research is to critically examine the human rights aspects of corporate criminal responsibility of companies in Cameroon. The conducts of business by various corporations in Cameroon are recognized as an impetus to economic, social, cultural and political advancement. With the rise in corporate crimes in the world today, the question has been whether a corporate body can be held liable for corporate crimes or not. The paper answers in the affirmative that a corporate body can be subject to criminal prosecution and liability for crimes occurring within the corporation especially in the domain of human rights. Considering that a corporate body cannot be imprisoned, or punished like an individual, there are ways to punish a corporation. A corporate body may be fined, ban, closed placed under judicial supervision for a specified period of time. With this in mind, the paper analyses the concept of corporate criminal liability with specific regards to corporate capacity, the basis upon which such liability attaches to a corporation and sanctions with the aim of illustrating the weaknesses of the different aspects trundled-out above.
Keywords: Cameroun; Cooperate; Criminal; Human rights; Sanctions

Congolese Land Rights Put to the Test by the Private Real Estate Investment Revolution - Milenge, Christian Mwenyemali (Open Journal of Social Sciences, 2023)
Private investors’ land rights vary from country to country, depending on the legal system in place. The degree of openness of land laws determines the degree to which both domestic and foreign investors are attracted, as the latter aims to invest in countries with legal systems offering the most secure and sustainable interests. How can Congolese land laws be made more attractive to private investors in the real estate sector? Using exegetical and comparative methods, we will test our hypothesis that reform to increase the rights of private national and foreign investors to access land would be an asset. By comparing Congolese land law with other legal systems, and with current social and economic realities, we have concluded that accommodating land rights is a prerequisite for increasing both domestic and foreign private investment in real estate and an essential step towards boosting and modernizing real estate investment in the DRC.
Number: 9
Keywords: Agricultural Investment; Congolese Land Ownership Law; Investments; Land Rights; Private Investment; Real Estate Law

The Law of the Sea and Nigeria's Marine Policy: A Critical Evaluation - Tagowa, Wonotanzokan Nzeda (Ahmadu Bello University, 2023)
Keywords: Droit maritime; Marine policy; Nigeria; Sea

Corporate Finance, Governance, and Social Responsibility - Gherghina, Ştefan Cristian (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint covers 27 papers published in the Special Issue entitled Corporate Finance, Governance, and Social Responsibility, which examines several topics related to corporate finance, financial modeling, corporate governance, and corporate social responsibility. Corporate finance-related articles (Anton and Afloarei Nucu, 2021; Bae et al., 2023; Kedzior et al., 2020; Lts and Lukason, 2022; Miglo, 2020; Mihail et al., 2021; Mota and Moreira, 2023; Tsolas, 2021; Tudose et al., 2021; and Wen et al., 2021) focus on the drivers of the capital structure and firm performance, the effect of working capital management on profitability, and the link between derivative use and profitability. Regarding financial modeling, stock market volatility was explored during COVID-19 (Gherghina et al., 2021). Corporate governance studies (Aluchna and Kuszewski, 2020; Ararat et al., 2021; Ding and Chea, 2021; Kjrland et al., 2020; Loureno et al., 2021; Lukason and Camacho-Miano, 2020; Maier and Yurtoglu, 2022; Mihail and Dumitrescu, 2021; Mihail et al., 2022; Mihail and Micu, 2021; and Pourmansouri et al., 2022) examine the effect of corporate governance compliance practices, board attributes, or employee stock option plans on bankruptcy risk, performance, firm value, or earnings management. Regarding CSR (Bozos et al., 2022; Rossi et al., 2021; Saeed and Sroufe, 2021; Singh and Hong, 2023; and Tseng and Shih, 2022), the research focuses on how CSR affects financial performance, risk management, or analyst profits estimates.
Keywords: CSR; Corporate Finance; Financial performance

Transparency in international arbitration: balancing the need for openness with the need for confidentiality - Mak, Charles Ho Wang; Rohatgi, Akshita (ACICA review, 2023)
International arbitration is often presented as an efficient and appropriate alternative to domestic court systems for resolving conflicts. For international arbitration to be effective, it is essential that the procedure adopted be open and accountable. This article will discuss the significance of openness in international arbitration and how it may promote justice, foster trust, and avoid corruption and misbehaviour.
https://rgu-repository.worktribe.com/output/2255845/transparency-in-international-arbitration-balancing-the-need-for-openness-with-the-need-for-confidentiality
Keywords: Corruption; International Arbitration; Justice; Misbehavour; Transparency; Trust

Fishing for Rights ! The Protection of the Individual in Fisheries - Longo, Andrea (Università degli studi di Milano, 2023)
La pêche est une activité humaine ayant un impact considérable sur l'environnement. Une mauvaise gouvernance, des mécanismes d'application faibles ou inexistants et des subventions excessives et non réglementées ont entraîné la surexploitation des stocks de poissons dans le monde entier, en produisant des conséquences potentiellement désastreuses sur l'écosystème marin et la sécurité alimentaire. Cependant, les pratiques de pêche non durables sont également liées à des abus à bord des navires de pêche : les organisations internationales et non gouvernementales attirent progressivement l'attention sur les pratiques répandues de violations des droits de l'homme et de crimes en mer, en appelant à repenser le régime international pour la conservation et la gestion des pêches en vue de concilier la sécurité économique et environnementale avec la dimension sociale de la pêche durable.Dans ce contexte, la présente thèse de doctorat aborde les problèmes conceptuels et pratiques qui se rattachent à la protection des individus impliqués dans ou autrement affectés par l'activité de pêche, en se concentrant particulièrement sur les victimes à bord des navires de pêche. La thèse s'appuie sur les études relatives à l'interaction des régimes en vue de favoriser le dialogue entre le droit international des droits de l'homme et le droit de la mer, deux régimes relevant du système plus large du droit international public. Après avoir exploré la portée de la question de recherche et fourni le contexte théorique et factuel, le premier chapitre se penche sur le régime du droit des droits de l'homme et examine la notion de juridiction telle qu'elle s'applique aux violations des droits de l'homme en mer, en étudiant en particulier l'utilisation potentielle de la norme sur la juridiction de l'État du pavillon comme critère pour attirer une violation des droits de l'homme à bord de navires de pêche relevant de la juridiction de l'État du pavillon. Le chapitre explore également le contenu et la portée des obligations en matière de droits de l'homme, en se concentrant notamment sur un ensemble de six droits prétendument violés à bord des navires de pêche, à savoir le droit à la vie, l'interdiction de la torture et des traitements inhumains et dégradants, l'interdiction de l'esclavage et des formes modernes d'esclavage, l'interdiction de la privation arbitraire de liberté, le droit à un travail décent et le droit à la santé. Ensuite, le deuxième chapitre se concentre sur le droit de la mer, en retraçant spécifiquement le développement historique qui a conduit à la consolidation du régime actuel de la pêche et en explorant la portée de la notion de pêche illégale, non déclarée et non réglementée et du phénomène de la criminalité dans le domaine de la pêche. Enfin, le dernier chapitre traite de la notion de juridiction telle qu'elle est utilisée dans le droit de la mer, en étudiant spécifiquement son contenu en ce qui concerne tous les acteurs étatiques de ce régime, à savoir l'État côtier, l'État du pavillon, l'État du port et l'État du marché. En particulier, ce chapitre examine de plus près les obligations de chaque État en ce qui concerne la protection de la personne à bord des navires de pêche, en accordant une attention particulière aux pouvoirs d'exécution de l'État côtier et à l'exercice par l'État du pavillon du contrôle des ses navires. Enfin, et surtout, il apporte un éclairage sur la contribution potentielle que les États du port et les États du marché pourraient apporter à la protection des personnes à bord des navires de pêche.
Cotutelle : Université Côte d'Azur
Keywords: Droit de la mer; Droits de l'homme; Fisheries regime; Fisheries resources; Fishing vessels; Human Rights; Law of the Sea; Navires de pêche; Pêches; Ressources halieutiques; Régime de pêche

Attaining effective and speedy resolutions of unfair dismissal disputes in Lesotho: An explorarion of possible lessons from South Africa - Ntaitsane, Mamolefi Anacletta (National University of Lesotho, 2023)
National Manpower Development Secretariat
Keywords: Labour dispute; Lesotho; Resolution mechanisms; Unfair dismissal disputes

Confidentiality in International Commercial Arbitration: Is it an Accepted Principle, and if so, Should the Model Law Regulate it? - Kenny, Caroline Majella (Monash University, 2023)
This thesis examines two research questions: first, whether confidentiality in international commercial arbitration (‘ICA’) is an ‘accepted principle’, and second, if the answer to the first question is positive, whether confidentiality should be regulated by the United Nations Commission on International Trade Law (‘UNCITRAL’) Model Law on International Commercial Arbitration (1985), with amendments adopted in 2006 (‘Model Law’) and how such a provision would be framed. To place the questions in context, there is empirical evidence that confidentiality is expected by users of ICA but despite this expectation there appears to be no uniform approach on confidentiality in national laws and institutional rules.
Keywords: Arbitrage; Arbitragem; Arbitration; Confidentiality; UNCITRAL Arbitration Rules; UNCITRAL Model Law

Structural Change, Productivity Growth and Labour Market Turbulence in Sub-Saharan Africa - Mensah, Emmanuel; Owusu, Solomon; Foster-McGregor, Neil; Szirmai, Adam (Journal of African Economies, 2023)
This paper presents a shift-share decomposition of the role of structural change in driving labour productivity in sub-Saharan Africa (SSA). The paper further examines the effect that the observed structural change has had upon the dynamics of labour markets in SSA. The analysis is based on a newly constructed dataset, the Extended Africa Sector Database. This database updates and extends the Africa Sector Database of the Groningen Growth and Development Centre. It includes eighteen countries covering the period 1960–2015. Overall, the database shows that productivity growth has been slow, with large and persistent sectoral productivity gaps present. The extent of structural change has been higher than that observed in previous studies, however. But while the share of employment and value added in agriculture has declined, resources have been pulled into certain service sectors that have relatively low productivity, thus limiting aggregate productivity improvements. The general direction of structural change has not been towards the most productive sectors. Results of the labour market analysis complement this analysis, providing suggestive evidence of a role for labour market institutional arrangements in many SSA countries in affecting these outcomes.

Selection and Appointment in International Adjudication: Insights from Political Science - Larsson, Olof; Squatrito, Theresa; Stiansen, Øyvind; St John, Taylor (Journal of International Dispute Settlement, 2023)
This article summarizes insights from political science and empirical legal scholarship concerning selection and appointment of adjudicators to permanent international courts (ICs). This scholarship suggests that designers of ICs face challenging trade-offs in balancing judicial independence and accountability, as well as in promoting descriptive representation and necessary qualifications on the bench. The article considers different institutional design features related to appointment procedures: representation, reappointment, screening procedures and procedures for removing judges. Representation is discussed in a series of sections considering full or selective representation, voting rules and geographic and gender quotas and aspirational targets. Throughout, we draw on data on 24 ICs to illustrate the different appointment procedures and institutional features.

Corporate Social Responsibility and Green Marketing Adoption in Nigeria: A Panoramic View - Nkwede, Maria-Friday; Ogbulie, Angela (African Journal of Politics and Administrative Studies, 2023)
Corporate social responsibility (CSR) and green marketing adoption is a twin trend that is fast becoming a global tendency amongst world economies, irrespective of socio-economic outlook. This paper pedagogically links the two concepts in the Nigeria business climes and explores, through a panoramic view the rate of adoption of CSR and green marketing in Nigeria. This study adopted an exploratory research design vis-à-vis a qualitative research approach. Based on the findings, this paper posits that corporate social responsibility in the Nigerian context is highly “localized” to reflect realities in the Nigerian socio-cultural space. However, green marketing adoption is near impossible for the average Nigerian organization; this is due in part to the enormous funds necessary for implementation of green marketing strategies in their businesses. This study therefore recommends the setting up of trust fund for companies (especially, small scale business) by government; this would give the companies the opportunity to fully develop and adopt green marketing strategy
Keywords: CSR; Corporate Social Responsibility; Customers; Green marketing adoption; Nigeria; RSE

Artificial Intelligence: Challenges and Opportunities for the Accounting Profession in Nigeria - Nkwede, Maria; Aniuga, Chukwuma (African Journal of Politics and Administrative Studies, 2023)
Artificial intelligence with its fifth industrial revolution is fast griping the African continent. The emergence and adoption of artificial intelligence applications and systems is fast becoming a normal trend in emerging markets landscape across Africa. This paper is borne out of the need to identify challenges that professional grapple with in their quest to surmount the challenges posed by the realities of artificial intelligence applications in Africa. The study adopted the thematic style in presenting the challenges as well as the prospects of artificial intelligence applications for the accounting professional in emerging market. Some of the challenges of artificial intelligence application identified in this study include: complex algorithms, reduced investment, and software failure, lack of political will and limitations amongst others. On the other hand, opportunities of artificial intelligence in emerging market include transportation automation, technological cyborgs and robotic companions amongst others. From the findings, accounting professional are advised to strive harder in order to beat competition by delivering quality services to her clients through harnessing opportunities for rebranding, reengineering and radically improving the business and investment decisions which is the ultimate purpose of the profession. More so, they are encouraged to develop a novel set of proficiency revolving around data in the profession
Keywords: AI; Accounting Profession; Artificial Intelligence; Challenges; Fifth Industrial Revolution; Inteligência artificial; Intelligence Artificielle; Opportunities

The significance of a forum selection agreement as an indicator of the implied choice of law in international contracts: a global comparative perspective - Okoli, Chukwuma Samuel Adesina (Uniform Law Review, 2023)
Where the parties to an international contract fail to specify the choice of law, a forum selection agreement is one of the most, if not the most, significant factors to consider in implying the choice of law in many international, supranational, regional instruments, and national jurisdictions. However, it is an ill-defined, notoriously complex, and hotly debated issue as to the weight that should be attached to a forum selection agreement in implying the choice of law. Hence, this article is devoted to discussing this topic from a comparative perspective, in order to propose a guide to global uniform criteria. To achieve this, the article covers all relevant international, regional, and supranational instruments, and selected legal systems in Africa, Asia, Australasia, Europe, the Middle East, and North and South America. The legal systems compared include those from the global North and global South, including common law, civil law, and mixed legal systems. The article’s core proposal is that an exclusive forum selection agreement should be a key factor in implying the choice of law. However, except in such cases as where a forum is chosen on a neutral basis, there should be a general requirement of corroboration with at least one other factor of significance. The aim of the proposal is to contribute to greater uniformity, predictability, and certainty in the global community in this field of law.

Legal scope of the carrier's liability in the contract of carriage of goods by sea - Drici, Amina (Journal OF LEGAL STUDIES, 2023)
The area of responsibility of the sea freight carrier is to determine the scope of liability over time for damage to the goods and is reflected in the search for the beginning and end of its liability; as well as the determination of the damage which triggers the carrier's obligation to compensate for the losses, damage, delay and determine the persons responsible for the damages for which the recipient or beneficiary of the goods has the right to recourse.
Keywords: Liability; Material scope; Personal scope; Sea carrier; Time scope; Transportation of goods

Legal Framework on Protection of Environmental and Foreign Direct Investment Rights in Nigeria: A Reflection on the Oil and Gas Industry - Osaro, Ebiemere (African Journal of International Energy & Environmental Law, 2023)
It is trite that environmental challenges remain one of the major global concerns and no doubt of great impact on human existence and wellbeing. This impact is a result of human activities on the natural ecosystem. This article examines the legal framework by the Nigerian state in regulating the activities of the multinational investors in the oil and gas industry in the Niger Delta region of the country. It discusses the international, regional, and national legal framework in the protection of environment and environmental rights of the host community and foreign direct investment rights. The author demonstrates the imbalance in the protection of environmental and foreign direct investment rights from which suggestions are made towards correcting this injustice as caused by the existing legal framework.
Keywords: Community; Direct; Environment; Foreign investment; Niger Delta; Oil and Gas Industry; Protection; Rights

The efficacy of commercial arbitration, law and practice Lesotho - Thethe-Chitja, Makabelo (National University of Lesotho, 2023)
The success of commercial arbitration law and practice is achieved as a result of several factors. The purpose of the study was to investigate whether efficacy of commercial arbitration, law and practice in Lesotho is hindered by the legal framework which does not conform to the United Nations Commission Trade Law on International Commercial Arbitration, UNCITRAL Model Law. Examining such other factors as support of the courts and government, the study specifically investigated the impact of lack of education about commercial arbitration for the business community and unregulated arbitrators on the efficacy of the commercial arbitration, law and practice in Lesotho. With the use of the desk reviews and interviews as data collection methods for this study, the evidence obtained has revealed that efficacy of the commercial arbitration, law and practice in Lesotho is hampered by the law which is outdated and inconsistent with the UNCITRAL Model law. As such, support for the mechanism by the courts has been found to be at stake or adversely affected. Lack of support from the government and that of awareness campaigns about the mechanism for the business community have also been noted for constraining the efficacy of the commercial arbitration, law and practice in the country. Further noticeable from the findings include limited commitment from the legal profession and unregulated arbitrators, both of which could have significantly obstructed the mechanism. The study thus concludes that there is an urgent need for law reforms and concerted commitment from the relevant stakeholders to help towards achieving efficacy of the commercial arbitration, law and practice in Lesotho.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration; Lesotho

Saudi Banks Level of Compliance with Accounting Standards of Accounting and Auditing Organization for Islamic Financial Institutions - A. Al-Bogami, S. (Information Sciences Letters, 2023)

The Relation between Corporate Governance, Risk Management and Financial Performance: Theoretical and Analytics Framework - Ayoob Mohammed Hassan, Noora; Din, Badariah binti Haji; Senasi, Vally (Information Sciences Letters, 2023)
The paper aims to review the relation between Corporate Governance, Risk Management and Performance. We reviewed these variables and develop a Theoretical and Analytics framework. First introduction (study background, Problem Statement, Research Objectives and research questions). Second literature review (A) financial performance such as ROA, ROE, EPS and Tobin’s Q, (B) Corporate Governance as Board of Directors, Board Composition, CEO Duality and Board Size (C) Risk Management. Third, we discussed Underpinning Theories such as, Agency Theory and Institutional Theory. Fourth, we developed a Theoretical Framework where we illustrated (A) Corporate Governance and Financial Performance, (B) Risk Management and Financial Performance (C) Compliance with Accounting Standards and Financial Performance. Finally, we developed a comprehensive reviewing based on above variables.
Keywords: Corporate governance; Performance; Risk Management

Influence of Training, Experience, and Expertise on Quality of Financial Reporting in Dubai – Mediation of Adoption of International Public Sector Accounting Standards - IPSAS - El Haron, Esam O.; Haji Din, Badariah (Information Sciences Letters, 2023)

Accounting Choices During COVID 19 Pandemic: Does Corporate Strategy and Corporate Social Responsibility Matter? - T. Hassan, N. (Information Sciences Letters, 2023)
This study aims to understand the accounting effects of the Corona pandemic in more depth and clarity, where the study explores the accounting choices during the pandemic period and the impact of the firm's strategic orientation and its social responsibility performance on those choices. Using data from non-financial Saudi companies, the accounting choices divided into aggressive accounting strategy and conservative accounting strategy, and regression models used to examine the study hypotheses. The results of the study provide a clearer and in-depth vision about the nature of accounting practices during the pandemic and indicated that business strategy affects accounting choices, while corporate social responsibility does not affect. The results can imply useful information for the market regulators that help them in controlling and stabilizing the market, as well as for professional accounting organizations to help them issue guidelines for accounting work during crises.
Keywords: Accounting choices; CSR; Corporate Social Responsibility; Corporate strategy; Covid-19 pandemic; Saudi companies

Critical Reflection on the Rights of Creditors in Case of Insufficiency of Assets in OHADA Collective Procedures Law - Kontchop, Hilarion; Tsala, Edith Nadège Fopa (International Journal of Law and Society, 2023)
The procedure of liquidation of assets can be closed for the extinction of liabilities or for insufficient assets. The court may then, at the request of any interested person or ex officio, at any time during the proceedings and after a report by the official receiver, close the proceedings. In case of insufficiency of assets, the business disappears and, perhaps, the hope of any payment to creditors as well. For a long time, it was accepted that the closure for lack of assets allows creditors to resume individual proceedings against the debtor, especially if the latter returns to better circumstances. This traditional solution has been abandoned. According to OHADA Uniform Act on the organisation of collective procedures for the settlement of liabilities, revised on 10 December 2015, closure for insufficiency of assets no longer automatically gives creditors the right to take individual action. Thus, when a liquidation leads to a shortage of assets, the satisfaction of creditors remains uncertain. The objective of this study is to show that despite this reform, the protection of creditors’ rights has not changed significantly in the event of insufficient assets. Indeed, any possible recourse to the recovery of their claims remains paralysed by certain measures that infringe their rights. The infringements can be described as severe or moderate depending on the case.
OpenAlex: https://openalex.org/W4381057496
Keywords: Closure (psychology); Collective Proceedings; Creditors; Debtor; Insufficiency of Assets; Liquidation; Settlement (finance)

Addressing the Legitimacy Crisis of Investment Arbitration Through its Harmonization with World Trade Organization Law - Seifi, Seyed Jamal; Veis Karami, Mahdi (Public Law Researsh, 2023)
International investment law is facing a legitimacy crisis, in which to tackle, substantial efforts are being made in structural and procedural areas. The first step to overcoming this crisis is identifying the roots of it. The lack of a dynamic balance between public and private interests is one of the main factors creating this legitimacy crisis in this legal system.[1] This paper focuses on the changes in the investment arbitration jurisprudence to create this balance. The findings of this paper can explain one of the convergence points of international trade and investment law. Such a claim is based on the evolution of international trade law in facing a similar legitimacy issue and the structural-procedural approach of this legal system in balancing public and private interests as an ultimate solution to the crisis.[2] From this perspective, one of the major factors in creating a legitimacy crisis in both legal systems is the dominance of the paradigm for preference of private interests; and one of the convergence points of international trade and investment law has been to replace it by accepting the paradigm of creating a dynamic balance between competing goals.[3] This paper examines this convergence in arbitral jurisprudence.IntroductionIn recent years, the legitimacy crisis of the regime of international investment law and, as a result, the investor-state dispute settlement system has been one of the most important and controversial topics in the academic environment and the practice of states consequently, serious efforts in various fields to tackle this crisis have begun. According to this paper, choosing an arbitration mechanism modeled on international commercial arbitration to resolve disputes between host states and foreign investors can be evaluated as a wrong and hasty action that, regardless of its factors and contexts, has changed the nature and function of this system over time.[4] It should be noted that the main factor in such consequences is how this dispute resolution system is used which, contrary to the accepted model, always puts the host states in a "respondent" position in possible future disputes and, as a result, disrupts the balance expected in any international dispute settlement system. On this basis, the confrontation of the host state's sovereign competence in ensuring public interests with the foreign investors’ ability to challenge this competence is brought into the spotlight: currently, within the regime of international investment law, host states have only responsibilities and obligations in contrast to extensive and exclusive rights and privileges recognized for foreign investors, and this can be considered as the most important factor disturbing the said balance. The main issue in this field is to analyze the role of the investment arbitral tribunals in creating such a balance. In this regard, the authors, by focusing on the nature of investment treaties, and the relations between the parties in investment disputes and with emphasis on the general legal regime governing international investment, consider creating a dynamic balance between public and private interests to be the key to solving the crisis. They emphasize that; As long as the rights and obligations of the parties to the dispute are based on imbalanced grounds, the change in nature of the disputes and the function of the system -as the main roots of this legitimacy crisis - will remain. In this remark, it is very important to focus on the two-sided nature (public-private) of the relationships established in the framework of investment treaties. The relationship between the host state and the foreign investor is created within the framework of investment treaties and in light of fundamental differences from purely private relationships in international commercial arbitration.[5] Note that any dispute arising from this relationship is affected by its inherently public nature governed by public international law.[6] Thus, a purely private attitude towards these relations does not seem viable. As Ian Brownlie has stated in the case of SME v. the Czech Republic, it can lead to ignoring some of the basic elements of the relevant investment treaty.[7] In other words, the right and duty of the host state in protecting and promoting public interests is a fundamental part of this relationship, and any indulgence of it leads to a serious disruption of the mentioned balance through which the system's legitimacy will be the first victim.It is clear that the main task of any dispute resolution system is to create such a balance, and on this basis, and compared to the WTO dispute resolution system, the role of the investment tribunals in this process is discussed. This jurisprudential convergence is in line with the goal of strengthening the legitimacy of the international investment law system as a whole.Based on the above, the first part of this paper focuses on the process of establishing the ISDS in international investment law and its characteristics, the factors of the crisis of legitimacy are analyzed with an analytical approach, while also explaining the nature of investment treaties and explaining the general legal regime governing international investment. Furthermore, the lack of a dynamic balance between public and private interests is emphasized as the main cause of the crisis. In the second part, while comparing the two legal systems of international trade and investment with a similar crisis of legitimacy, we will examine the interaction of investment arbitration with the WTO's jurisprudence in facing this crisis through a case study of several investment arbitral awards. [1]. David Gaukrodger, “The Balance between Investor Protection and the Right to Regulate in Investment Treaties: A Scooping Paperˮ, OECD Working Paper on International Investment 2017/02, at 4.[2]. Nicholas DiMascio & Joost Pauwelyn, “Non-Discrimination in Trade and Investment Treaties: Worlds apart or Two Sides of the Same Coin?”, AJIL, Vol. 102, No.1, (2008), at 89.[3]. Jurgen Kurtz and Sungioon Cho, “Convergence and Divergence in International Economic Law and Politics”, EJIL, Vol. 20, No. 1, (2018), at 187.[4]. Benedict Kingsbury & Stephan W. Schill, “Public Law Concepts to Balance Investor's Rights with State Regulatory Actions in the Public Interest - The Concept of Proportionalityˮ, In Schill Stephan W., International Investment Law and Comparative Public Law (UK: Oxford University Press, 2010) at 76. [5]. Crina Baltag, “Reforming The ISDS System: In Search of a Balanced Approach?ˮ, Contemporary Asia Arbitration Journal, Vol. 22, No. 2, (2019), at 285.[6]. Ibid.[7]. Andreas Kulick, “Sneaking Through Backdoor – Reflections on Public Interest in International Investment Arbitrationˮ, Arbitration International, Vol. 29, No. 3, (2013), at 438.
Keywords: Crisis of Legitimacy; International Investment Law; Investor-State Dispute Settlement; WTO; World Trade Organization

Rights and Obligations of the Parties Against International Arbitration Awards in Indonesia - Puspita, Lona; Budiono, Abdul Rachmad; Kusumadara, Afifah; Widagdo, Setyo (International Journal of Social Science Research and Review, 2023)
The position of international arbitration awards which is different from national arbitration awards and district court decisions causes differences in the rights and obligations of the parties to arbitral awards, especially those relating to legal remedies against awards. The formulation of the problem in this study is how are the rights and obligations of the parties to international arbitral awards in Indonesia. The research method used in this article is legal research using primary and secondary legal materials. The results of the study state that the rights possessed by the parties to international arbitral awards in Indonesia are related to legal remedies against decisions, namely corrections to these international arbitral awards. The corrections to the decisions here are not only limited to administrative corrections but also corrections related to the principal international arbitral awards made before the request for execution was registered at the Central Jakarta District Court. While the obligations of the parties to international arbitral awards are to carry out international arbitral awards in good faith.
Keywords: International Arbitration Award; Rights and Obligations

Exploring the Voice of Populist Movements in the Employment of Foreign Nationals: A Comparative Study of Botswana and South Africa - Utete, Reward; Zhou, Sheunesu; Ajani, Oluwatoyin Ayodele (International Journal of Social Science Research and Review, 2023)
Labour immigration has been on the rise and has had policy implications for public leaders of relatively stable Southern African Development Corporation (SADC) countries. In this paper, the status of populism and labour immigration in Botswana and South Africa was explored. The primary sources of labour immigration are Zimbabwe and Mozambique. Economic disparities and the disintegration of the socio-economic conditions of the neighbouring countries have been major antecedents for the labour movements of the masses. The study utilised a qualitative method and comparative case study design. The study found that populist movements have much influence on the termination of employment of foreign nationals in Botswana and South Africa as shown by their anti-immigrant attitudes, market protectionism, and close-the-borders protests. As these measures have become inefficient over the years, policies and proposals are recommended in response.
Keywords: Economy; Employment; Foreign Nationals; Immigrants; Policies; Populist Movements

Corporate human rights obligations of investors in recent investment agreements: The progressive hardening process of CSR clauses - Francis Maïnkade, Belengar (Heliyon, 2023)
Since the earlier indirect Corporate Social Responsibility (CSR) provisions failed to hold investors responsible for human rights abuses, the recent hardening process of direct CSR clauses has resulted in incorporating CSR clauses under sections or chapters entitled “investors obligations” and tying CSR obligations to binding human rights and environmental prohibitions, as well as to human rights obligations established by the host state's legislation. This paper provides a non-exhaustive analysis of recent developments in treaty practice based on research primarily sourced from investment agreements concluded between 2012 and 2021, doctrinal input, and normative analysis. As shown in this paper the hardening process has not yet been completed, and reformations are necessary. Specifically, new investment agreements should enshrine investor human rights obligations as legally binding obligations, consider violations of these CSR obligations as part of investment disputes and provide direct remedies to victims. This study contributes to the literature on the international responsibility of TNCs with regard to human rights by examining the process of hardening up the CSR obligations within investment agreements as an approach that could lead to effective human rights protection.
Keywords: Corporate Social Responsibility; Corporate human rights responsibility; Hardening of corporate social responsibility clauses; International responsibility of transnational companies; Investors' human rights obligations

Introduction: International Adjudication and the Legacy of the Mixed Arbitral Tribunals - Ruiz Fabri, Hélène (The Mixed Arbitral Tribunals, 1919–1939: An Experiment in the International Adjudication of Private Rights, 2023)
This introduction provides the reader with a general characterization of the 39 Mixed Arbitral Tribunals (MATs) created by the 1919-1923 peace treaties to address disputes between private persons and between private persons and states as a result of the First World War. Noting that the rich literature published on the MATs was followed by near-silence after 1945, it mentions the numerous questions that they still raise today, before explaining how the various contributions to the book edited by the authors address them.

The protection of EU technological sovereignty in the area of foreign direct investments: legal challenges after the EU regulation 452/2019 - Vecchio, Giuseppe (LUISS Guido Carli, 2023)
EU’s competence over FDI: European technological sovereignty. Definition, origins, and scope of EU foreign investment law. EU competence over foreign direct investments. European technological sovereignty. Regulation 452/2019–screening mechanisms in national legislation with a focus of the Italian regime. Structure of regulation 452/2019. Implementation in national legislation. The screening regulation as a tool to enforce technological sovereignty. EU technological sovereignty in practice. First and second annual report on the screening of foreign direct investments into the Union. A first appraisal of the problematic interplay between FDIs and technological sovereignty.

Liability in the atmosphere of groups of companies - Motassim, Sofia (Universitat de Barcelona, 2023)
Groups of companies are a complex corporate structure, whose regulation can be problematic, especially when it comes to liability. Indeed, liability within corporate groups draws forth a series of issues principally due to the principles of separate corporate personality and limited liability. In the context of limited liability, which is based on the notion of separate legal personality, the main issue waxes the protection of the creditors, in particular the creditors of the subsidiaries. One can find three regulatory templates for handling corporate groups and their liability: policing via general company and/or civil law (such as the English model); policing via special group legislation (such as the German model); and policing via branches of law such as insolvency law, antitrust law, and contract law, among others (which is the case in numerous jurisdictions, either coupled with the first or the second model). Lifting the corporate veil has come as an answer to corporate separateness, by permitting to ignore the shareholders’ limited liability and hold them personally liable for the debts of their companies in specific circumstances. However, one can hardly find cases in which the corporate veil has been successfully lifted, due to many factors. Other important questions that are posed in the scope of corporate groups liability are the parent company’s liability for the payment of its daughter companies’ debts when insolvency strikes and other respects, besides the matter of group liability. Furthermore, liability is as well a key player in terms of tort law, and corporate social responsibility has therefore found a place in the sun in the present climate.
Alternate link : https://diposit.ub.edu/bitstreams/83cde66e-b943-45b6-830b-831df41cb73f/download
Keywords: Ciències Jurídiques; Commercial law; Conglomerate corporations; Corporations; Derecho mercantil; Dret mercantil; Econòmiques i Socials; Grupos de empresas; Grups d'empreses; Liability (Law); Responsabilidad (Derecho); Responsabilitat (Dret); Sociedades; Societats

Analysis of Intellectual Property Rights Disputes Between PS Glow and MS Glow in View of Law No. 20 of 2016 Concerning Marks and Geographical Indications (Analysis of Decision of Case Number: 2/Pdt.Sus.HKI/Merek/2022/PN.Niaga Sby) - Gracia, Indiera Fortuna; Kurniawan, Kurniawan; Sili, Eduardus Bayo (International Journal of Social Science Research and Review, 2023)
This study analyzes intellectual property rights disputes between PSGlow and MSGlow in terms of Law no. 20 of 2016 concerning Trademarks and Geographical Indications (analysis of case decision number: 2/pdt.sus.HKI/Merek/2022/pn.niaga Sby) which aims to explain and analyze the basic considerations of Surabaya Commercial Court judges in accepting lawsuits, explaining and analyzing how is the legal protection of trademarks that have been registered based on Law No. 20 of 2016 concerning Trademarks and Geographical Indications, explaining and analyzing whether there is an element of passing off between PS Glow and MS Glow based on Case Decision Number: 2/Pdt.Sus.HKI /Merek/2022/PN. Niaga Sby.The legal materials in this research are primary, secondary, and tertiary legal materials using normative research methods.The basis for consideration is that a lawsuit was filed from PS Glow for the use of the brand without rights against MS Glow. and legal protection for brands that have been registered under Law no. 20 of 2016 concerning Marks and Geographical Indications, namely that the penalties that will be imposed on these counterfeiters can be in the form of imprisonment, imprisonment and fines, as referred to in articles 100 to 102 of Law No. 20 of 2016 concerning Marks and Geographical Indications. and between PS Glow and MS Glow there is no element of passing off based on Case Decision Number: 2/Pdt.Sus.HKI/Merek/2022/PN.Niaga Sby, because the MS Glow brand registers its brand in HAKI in class 32 with the classification of powdered drinks and PS Glow registered their brand on Intellectual Property Rights in class 3 with a cosmetic classification.
Keywords: Brand; IPR; Passing off

Developing a regulatory framework for electronic commerce in the Southern African Development Community: the prospects and challenges - Chimeri, Vongai (University of Fort Hare; Faculty of Law, 2023)
Keywords: Community law; E-commerce; Electronic Commerce; Electronic Transactions; Intra-regional trade; Regional integration; SADC; SADC Model Law

The interface between competition and intellectual property law : finding common ground and resolving the tensions between these areas of law from a South African perspective - Dercksen, Juletha-Marie (Stellenbosch University, 2023)
Competition law and intellectual property law share the objective of incentivising innovation. However, this objective is achieved in different ways, which, at times, can create tension between the two areas of law. It is imperative that this tension at the interface of competition law and intellectual property law is resolved in a manner that encourages innovation. Issues regarding the licensing of intellectual property, Standard Essential Patents, pay-for-delay agreements and no-challenge clauses are instances where the tension between competition law and intellectual property law is especially prevalent. These instances will be discussed in detail, and what is learnt from how the European Union and Australia handles it, will be applied to South Africa. The European Union, Australia and South Africa have different ways of dealing with situations where the exercise of intellectual property rights has an effect on competition. The European Union has block exemptions, which contains “safe havens” for conduct in specific circumstances. The block exemptions are often accompanied by guidelines, providing firms and individuals with greater detail in order to self-assess their compliance with the exemption. Australia has authorisation, notification and class exemption procedures. Firms can apply to the Australian Competition and Consumer Commission to authorise conduct that might potentially breach the Competition and Consumer Act 2010. Exemptions may also be granted more broadly by the Australian Competition and Consumer Commission in terms of the class exemption procedures. In South Africa, the law concerning the interface between competition law and intellectual property is still in its infancy, and a lot can be learned from jurisdictions like the European Union and Australia regarding the most efficient way to handle this tension. Currently, the Competition Act 89 of 1998 in South Africa contains Section 10(4), the intellectual property exemption clause. A firm can apply to the Competition Commission for an intellectual property exemption from the application of Chapter 2 of the Competition Act “to an agreement or practice, or a category of agreements or practices” which pertains to the exercise of intellectual property rights. However, it is submitted that Section 10(4), by itself, is not the most efficient mechanism to resolve the tension that arises at the interface of competition law and intellectual property law in a way that incentivises innovation. It is proposed that the exemption provision can be made more effective if it is properly applied in conjunction with class exemptions and guidelines.
URI: http://hdl.handle.net/10019.1/127343
Keywords: Antitrust law; Australia; Competencia; Competition Act; 1998; Competition law; Conflict of laws; Intellectual property; South Africa; Trade regulation

The legal regulation of trade union recognition in South Africa in historical and comparative context - Germishuys-Burchell, Wilhelmina (Stellenbosch University, 2023)
This study investigates the impact and importance of the legal regulation of trade union recognition and associated challenges in South Africa. It evaluates the current regulation of trade union recognition, including legislation and judicial attitudes apparent from the interpretation, application, and enforcement of such legislation, to ascertain its continued appropriateness in the current South African industrial relations environment. The study considers the policy choices of both voluntarism and majoritarianism underlying the Labour Relations Act 66 of 1995 (“LRA”) and the “workplace” constituency to which it applies as factors that might be contributing to challenges experienced in the current regulation of collective bargaining in South Africa. It evaluates the current model of trade union recognition and representativeness as it applies to the acquisition by trade unions of organisational rights, collective bargaining rights and trade union recognition for purposes of retrenchment consultation. It recognises that the specific model chosen to regulate the representative status of trade unions has a significant effect on the ability of trade unions to organise and conclude collective agreements and, as such, on the distributive effects of such agreements in the labour market and broader society. The study commences with an historical overview of the regulation of trade union recognition under the 1956 LRA and thereafter considers the 1995 LRA as a product of criticism against the 1956 LRA. Specific issues considered, largely based on the analysis of the relevant decisions by the Constitutional Court, include the following: the impact of Constitutional Court jurisprudence relating to trade union recognition on the process of collective bargaining and on the legal regulation of the right to strike; the role of representativeness and its link with the workplace as the constituency for recognition and acquisition of organisational rights; the often winner-takes-all effect of the current model on collective bargaining as a major cause of labour unrest; the reactive role the legislature has played over the past, almost three decades to address challenges; the extent to which intervention should take place to safeguard the institution of collective bargaining from being undermined as well as the regulation of collective agreements as the product of collective bargaining and as the primary source of terms and conditions of employment. The comparative review of Canadian law focuses on a number of issues selected specifically for their potential to provide insights into how the weaknesses in South African regulation may be remedied. This includes insights into the accommodation of special or significant minority interests and how to address recognition in the context of multi-location employers. The thesis concludes with remarks on the insights gained from the Canadian model and the 1956 LRA. Where appropriate, suggestions are made on the way forward for South Africa as to the appropriate regulation of trade union recognition and representativeness.
URI: http://hdl.handle.net/10019.1/127125
Keywords: Collective bargaining; Collective labor agreements; Dismissal of employees; Employee rights; Industrial laws and legislation; Labor disputes; Labor unions; South Africa

Holding multinational corporations liable for their transnational environmental harms : a search for global liability - Roxburgh, Craig (Stellenbosch University, 2023)
For several decades, environmentalists have raised the alarm regarding the impending environmental catastrophe that results from the Anthropocene. Much attention has been given to the role that States play in contributing to ecological damage being wrought upon the Earth. However, we have only looked at the environmental destruction perpetrated by multinational companies (“MNCs”) in the past decade. Natural disasters like the Deepwater Horizon explosion have placed MNCs' dangerous impact on the environment in sharp relief. At the same time, revelations in the Carbon Majors Report and global litigation quantify the damage MNCs cause to the environment. Multinational companies (“MNCs), as a result of globalisation and trade liberalisation, are powerful entities within the global economy. Despite their size, MNCs remain primarily unregulated in international human rights law. Debates regarding who bears the duty for human rights intersect with a battle of political will between the Global North and Global South for developing binding human rights duties for MNCs. As a result, they can commit environmental harm, especially in the Global South, with relative impunity due to a lack of effective liability mechanisms. The doctrine of separate legal personality creates specific issues for holding MNCs liable for environmental harms in the Global South. Domestic courts in home States struggle to exercise jurisdiction over the environmental harms MNCs commit. In contrast, systemic barriers in host States create situations where victims are unable to seek redress within their State. To address these concerns, this thesis proposes a global liability regime founded on the principle of integrated regulation. This regime will utilise regulation at the institutional, national and international levels to enforce the environmental obligations of MNCs, rooted in the right to a healthy environment. This gives rise to multiple intersection human rights obligations which will regulate the behaviour of MNCs. This thesis recognises that such a framework requires a drastic reform in how the law and companies are conceptualised. However, such a reform would have wide-reaching implications for vindicating human rights violations.
Keywords: Corporations; Developing countries; Environmental law; Environmental protection; International business enterprises; International cooperation; Liability for environmental damages; Offenses against the environment

Mandatory Environmental, Social and Governance (ESG) Regulations: ESG Performance, Corporate Finance, and Investment - Michael, Emmanuel (Victoria University of Wellington, 2023)
This thesis investigates the relationship between cross-country mandatory environmental, social and governance (ESG) regulations and firm-level outcomes, such as ESG performance, corporate finance, and investment, for both developing and developed countries. ESG performance is initially examined to determine whether mandatory ESG regulations affect it and to what extent. Second, the study investigates the impact of mandatory ESG on corporate finance and investment. Lastly, the study explores whether mandatory ESG regulations affect firm-level outcomes based on countries' governance and economic systems, and industries. The study uses a large sample of 69,010 firm-years across 73 countries, over the period 2005 – 2020 to address the foregoing issues. In addressing the impact of mandatory ESG regulations on ESG performance, the study employs a difference-in-differences (DiD) design. The DiD technique can isolate the effect of regulatory shocks to firm-level outcomes. According to the DiD analysis conducted, cross-country mandatory ESG improves firm-level ESG performance in developed countries, but not in developing countries. The study also concludes that mandatory ESG regulations have a positive impact only on ESG components in developed countries and have a more dominant impact on environmental (E) component. The findings are robust to a range of checks and test cases, including a triple DiD design set-up and propensity score-matched sample. The study employs an investment Euler equation framework and generalised method of moments (GMM) estimators to explore how mandatory ESG impacts corporate finance and investment. Euler frameworks account for the dynamic nature of investment, whereas GMMs account for endogenous dynamics in dynamic models. The study demonstrates that mandatory ESG increases corporate investment by increasing firms' access to external funds. The findings are robust to a battery of tests, including a triple DiD design set-up, propensity score-matched sample and the parallel trends assumption. Using an investment Euler equation framework and the GMM estimators, the study explores whether the impact of mandatory ESG on corporate finance and investment is dependent on a country's governance and economic system. When mandatory ESG is affected by country factors such as governance systems and economic well-being, the effect of mandatory ESG on investment via internal finance channel persists, according to the study. However, while consistent results are found in developed countries, inconsistent results are found in developing countries. According to the study, oil, gas, and mining firms are likely to respond effectively to mandatory ESG regulations because of increased scrutiny and pressure. Overall, the findings from the study imply that cross-country mandatory ESG has had a positive impact on corporate ESG performance, finance, and investment. For firms located in developed countries, these findings hold consistently, while for those located in developing countries, the opposite holds true. Also, the study reveals that firms in the oil, gas, and mining industries effectively respond to regulatory requirements. As a result, this study provides policy makers and accountants with an understanding of how mandatory ESG impacts firm ESG activities and performance, which is crucial for regulatory reforms.
Keywords: Corporate Finance; Cross-Sectional Analysis; Developed countries; Developing countries; Economic Models and Forecasting; Finance; Financial Economics; Investment; Investment Euler equation; Mandatory ESG disclosure regulations; Panel Data Analysis; Sustainability Accounting and Reporting; Time-Series Analysis

Challenges of CSR in Sub-Saharan Africa: clarifying the gaps between the regulations and human rights issues - Ndong Ntoutoume, Achille Gildas (International Journal of Corporate Social Responsibility, 2023)
This paper discusses the practice of Corporate Social Responsibility (CSR) and its challenges in Sub-Saharan Africa. The main purpose is to highlight and clarify the gaps between CSR regulations and human rights abuses caused by business organizations.
Keywords: Business and human rights; CSR; Stakeholders; Sub-Saharan Africa

Banking System Fragility in Nigeria: Hanging on the Precipice? - Kayode, Peter; Oluwole, Foluso (AAU Journal of Business and Law, 2023)
The health of a country’s banking system is a key determinant to the development of the country. A fragile banking system portends danger not only to the financial system but the entire economy. This study investigates the state of the Nigerian banking system in terms of stability or fragility from 1981 to 2020. We used the banking system fragility index (BSFI) proposed by Kibritçioğlu (2003) to analyze Nigerian banking industry aggregate data from three risk areas: credit, market and liquidity. We estimated that out of the 40 years examined, the banking system was fragile for 23 years given their BSFI less than 0 while it was not fragile for 17 years with BSFI = 0 or greater. We found that most of the years when the Nigerian banking system was fragile were periods of relaxed monetary policies, deregulation and credit expansion. Secondly, the years of banking system stability were when the county’s banking system was subjected to stiff regulation and consolidation. Given the number of years that the system was fragile, we observed that sustained economic growth and development requires that the banking system remain strong as long as possible, and that the Nigerian situation could not promote this important objective. We recommend that the financial regulatory authorities put in place more stringent policies as banks are more fragile during the deregulation of the banking industry.
AAU Journal of Business and Law مجلة جامعة العين للأعمال والقانون
Keywords: Banking system fragility; Precipice

Who Are the Best Law Firms? Rankings from IPO Performance - Bates, Thomas W.; Lv, Jin Roc; Neyland, Jordan (The Journal of Corporation Law, 2023)
Recent scandals have brought rankings to the forefront of the legal profession. Several of the most prestigious academic institutions have withdrawn from being ranked, citing the problematic nature of the rankings. However, rankings persist for both legal academics and practice, and there is substantial sentiment to improve the methodologies, with little detail as to how to improve. In this paper, we rank law firms on their clients’ IPO performance. We focus on the most relevant outcomes: litigation, first-day returns, disclosure, and legal fees. The focus on these measures provides benefits relative to other methodologies, which typically focus on inputs or size-related characteristics. Namely, this ranking is less manipulable and more accurately captures performance metrics that matter most to clients’ shareholders. Our rankings control for observable and unobservable deal characteristics, which helps ensure we capture law firm quality, not client traits. With the rankings based on legal fees, potential clients can compare the benefits of a particular law firm (e.g., lower litigation or higher selling prices) against the additional cost of hiring a higher-quality law firm. Hence, our rankings allow for a value-for-the-money comparison of law firms for clients selling shares in an IPO.
Keywords: Disclosure; IPO; Lawyers; Litigation; Rankings; Securities Regulation

The Double Life of State-Owned Enterprises in International Economic Law: States, Corporations or Both? - Kikarea, Eirini (University of Cambridge, 2023)
State-owned enterprises (SOEs) have recently gained prominence in global markets and feature among the world’s most influential enterprises. The aim of this research project is to analyse the international norms in force regulating whether SOEs are considered state or non- state actors, and their conduct state or non-state conduct, the interpretation and application of these norms by adjudicators in different international regimes, and to provide alternative prisms through which these rules and decisions can be assessed and re-thought by political actors. I show that, in relation to SOEs, the concepts ‘state and ‘act of state’ have been ascribed diverse meanings by adjudicators and other international actors, who have employed legal standards with divergent wording and thresholds when dealing with similar questions. I argue that the fragmented meaning of these terms should be understood, in part, as a result of the inherent malleability of these terms and the different expert vocabularies employed across regimes. It is exhibited that adjudicators in the international trade and investment regimes are more inclined towards piercing the corporate veil of SOEs, potentially evidencing the existence of biases against SOEs, which are perceived as inherently economically inefficient and politically motivated actors in an indiscriminatory manner. In the last chapter, I introduce alternative lines of thought regarding the regulation of SOEs in international law. I suggest that, instead of engaging in theoretical discussions on the proper delineation between the public and the private sector, it is more useful to focus on the distributional impact of international rules on various actors, especially on developing and emerging economies where the presence of SOEs is very high. Such alternative prisms of analysis open paths for future research and practice, with the goal of designing an international economic order that incentivises institutional experimentation in the pursuit of economic development and distributional equity.
Keywords: International Economic Law; International Investment Law; International law; International trade law; Public enterprises; State capitalism; State-owned enterprises

Third Party Funding in International Arbitration: A Critical Appraisal and Pragmatic Proposal - Sweify, Mohamed (Edward Elgar Publishing, 2023)
The author of Third Party Funding in International Arbitration challenges the structural inconsistencies of the current practices of arbitration funding by arguing that third party funding should be a forum of justice, rather than a forum of profit. The author introduces a new methodology with an alternative way of structuring third party funding to solve a set of practical problems generated by the risk of claim control by the funder.
Keywords: ACCESS TO JUSTICE; Arbitrage; Arbitral justice; Arbitration; Claim control; Dispute outcome; Financement; Funders; Third Party Funding; Tiers

Legal Protection of Trade Secret from the View of Civil and Criminal Law - Atika, Atika (International Journal of Social Science Research and Review, 2023)
Indonesia has ratified the WTO/TRIPs Agreement convention and is in full compliance and non-reservation, the insistence of developed countries’ owners of Intellectual Property Rights against Indonesia, and the need for national Intellectual Property Rights. By looking at the above, legal protection is needed for every product and service, especially licenses for trade secrets in the Intellectual Property Rights component. The state imposes criminal sanctions on violators of Trade Secret rights as stipulated in chapter 17 (1) constitution number 30/2000. However, it is also hoped that the act of imposing sanctions by the state will return to the interests of the protected party by making the crime a complaint offense chapter 17 (2) constitution number 30/2000. There are repressive legal actions that can be carried out as chapter 11 constitution number 30/2000 states that the holder of trade secret rights or the licensee may sue anyone who deliberately or without rights commits the actions referred to in the article in the form of (a). Compensations claim and/or; (b). Cessation of all actions referred to in chapter 4 constitution number 30/2000.
Keywords: Intellectual Property Rights; Legal Protection; Trade Secrets

Investigation of Investor-State Arbitration Problems in Afghanistan - Nikzad, Nezamuddin; Anwari, Gulaqa (International Journal of Social Science Research and Review, 2023)
The main purpose of this research is to explain and identify the major Investor-State Arbitration (ISA) problems in Afghanistan. Afghanistan's government is committed to providing legal security for the resolution of foreign investment disputes. The dispute resolution system's assessment is very important for foreign investors because they pay special attention to the dispute resolution system and consider it a criterion for their investments. This research will be the first comprehensive study about the Investor-State Arbitration problems in Afghanistan. In the writing of this research, the library method has been used. To extract reasons, laws, books, articles, and reliable scientific sources have been used. Afghanistan is a good market for foreign investment because it has good investment opportunities in different sectors. Foreign investors can choose the easiest and best mechanisms, such as arbitration in their contracts to deal with disputes. But the resolution of foreign investment through arbitration has some problems, and sometimes foreign investors are facing challenges with the settlement of their disputes through arbitration internationally and domestically in Afghanistan.
Keywords: Arbitration; Dispute; Foreign Investment; Investigation in Afghanistan; Problems

Procedural powers of arbitrators in international arbitration- Real or perfunctory? - Mishra, Ajit Kumar (International Journal of Law, 2023)
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrator; International Arbitration; Lex arbitri; Procedural powers; Tribunal power

The Dilemma of International Arbitration Awards in Indonesia - Puspita, Lona; Budiono, Abdul Rachmad; Kusumadara, Afifah; Widagdo, Setyo (International Journal of Social Science Research and Review, 2023)
The final and binding nature of international arbitral awards results in the nullification of the rights of the parties to file legal remedies against the arbitral award, as is the case with decisions of national courts that can be appealed, appealed, or reviewed. However, Article 68 paragraph (2) of Law Number 30 of 1999 concerning arbitration and Alternative Dispute Resolution provides an opportunity for parties who refuse to recognize and implement an international arbitral award that can be appealed to, as well as Article 70 must also be explained that Article this applies only to national arbitrations. This of course creates legal uncertainty, disuse, and injustice for the parties. Therefore, what is highlighted in this research is what is the position of the final and binding international arbitration award in Indonesia. The research method used in this article is legal research using primary and secondary legal materials. The results of the research show that the position of international arbitral awards in Indonesia is not the same as the decisions of national courts because they cannot be appealed, cassated, and reviewed. Therefore, it is necessary to completely amend international arbitration arrangements by removing Article 68 paragraph (2) of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution in order to provide legal certainty, benefit, and justice for the parties.
Keywords: Award; Final and Binding; International Arbitration

The adoption of international financial reporting standards and foreign direct investment inflows: the moderating effect of the institutional environment in Africa - Simbi, Chipo (Rhodes University; Faculty of Commerce, Accounting, 2023)
Globalisation has created a need for an international accounting language to facilitate the smooth flow of trade across countries. In 2003, in an effort to establish a global financial reporting language, the International Accounting Standards Board (IASB) developed a single set of high-quality accounting principles known as the International Financial Reporting Standards (IFRS). Over the last decade, several African countries have adopted IFRS, and Africa has become the second-largest adopting continent after Europe. IFRS promotes improved quality of disclosure of accounting transactions, reduces information asymmetry between preparers and users of financial information, lowers the cost of investing, and breaks down information barriers to cross-border investment. Researchers suggest many benefits of IFRS adoption for macroeconomic indicators such as Foreign Direct Investment (FDI). The reduction in information acquisition and processing costs which translates into the reduction in investment costs, has been cited by most researchers. Researchers have argued, however, that the economic benefits of IFRS in Africa depend on the strength of the institutional environment. They also argue that the Western environment in which the IFRS was developed differs from the African environment. Thus, the universal approach of the IASB may not be appropriate due to the historical, social, economic and political context of African countries. The impact of the adoption of IFRS by African countries requires further examination, particularly as a weak institutional environment confronts many African countries. Three research questions are designed for this study; (1) Is there a significant change in FDI inflows for IFRS adopters in selected African countries after the adoption? (2) Is there a significant change in FDI inflows due to the institutional environment? (3) Does the institutional environment in IFRS-adopting countries moderate the effect of IFRS on FDI in selected African countries? The present study is underpinned by the new institutional theory, the information asymmetry theory, the eclectic theory and the signalling theory, each of which provide reasons why African countries have adopted IFRS. Nine hypotheses are developed, based on the research questions, and tested using the Systems General Method of Moments and the Difference-in-Difference method. The study uses data from 26 African countries, 15 adopting and 11 non-adopting countries, over the period 1996 - 2018. First, the study establishes that the adoption of IFRS positively and significantly affects FDI inflows into the selected sample of African countries. Second, the study concludes that legal enforcement, accounting and auditing standards enforcement, and language origin positively and significantly impact FDI inflows into these countries. Legal origin, however, has a positive but insignificant association with FDI inflows. Third, legal enforcement, historical ties, accounting and auditing enforcement and the quality of the institutional environment are found to moderate the effect of IFRS adoption on FDI inflows. These results indicate that IFRS is a crucial determinant of FDI inflows into African countries, but a supportive institutional environment is needed for African countries to attract FDI inflows after adoption. The results contribute to the accounting and finance literature on FDI into African countries, and may assist the investment community to assess the institutional risk associated with investing in IFRS adopting African countries.
http://hdl.handle.net/10962/419230
Keywords: Accounting; Auditing; Difference in differences; FDI; Foreign direct investment; Generalized method of moments; IFRS adoption; Institutional infrastructure; International Financial Reporting Standards; Investments

Legal harmonisation of non-tariff barriers of regional economic communities as a catalyst to the realisation of the African continental free trade area - Achancho Etagha Epse Abia, Elisabeth (University of KwaZulu-Natal, 2023)
Legal harmonisation is an integral aspect of regional integration and the desire to promote regional and sub-regional economic integration in Africa is exemplified by the establishment of the African Continental Free Trade Area (AfCFTA) in 2018. The 2012 decision of the AU to create the CFTA by 2017 was reiterated in Aspiration two of Agenda 2063. The legal harmonisation of non-tariff barriers has been a vital instrument in the achievement of EU economic integration and the Organisation for the Harmonisation of Business Laws in Africa (OHADA). The study seeks to critically examine the theoretical and conceptual underpinnings of regional integration and legal harmonisation of non-tariff barriers by the AU and RECs. It also analyses the current political, economic, and legal reinforcements to regionalism in Africa and practices needed to advance intra-regional trade within the framework of Agenda 2063. This was done by evaluating the key legal frameworks of the AU (the Abuja Treaty, the Constitutive Act of AU, 2007 Protocol on relations between AU and RECs and Agenda 2063) with the aim of identifying best practices, gaps and impediments pertinent to strengthening Agenda 2063 CFTA. At the end of the study, the abilities of three selected RECs (SADC, COMESA and EAC) were assessed to drive home the AfCFTA. This was done by identifying flaws in existing treaties of RECs, while advancing a model of legal harmonisation of NTBs between them. It was found out that the AU and RECs have not vigorously considered the significance of legal harmonisation in their integration agendas. This resulted in the lack of unambiguous and concrete provisions for the legal harmonisation of NTBs in their guiding policies. Where some attempts are evident, such as in the EAC, they have been implemented unsatisfactorily with lack of a compliance mechanism. This study contended that if legal barriers to free trade are not eliminated, even if all other barriers were to be removed, the effective realisation of the AfCFTA would still be hindered. Hence, this study recommends the principles of direct applicability and direct effects of regional laws to addressing the legal harmonisation challenge underscored. Iqoqa Ukuvumelanisa okusemthethweni kwezithiyo ezingakhokhiswa intela kuyisici esibalulekile sokudidiyelwa kwesifunda kanye nesifiso sokugqugquzela ukuhlanganiswa komnotho wesifunda kanye nesifunda esincane e-Afrikha sibonakala ngokusungulwa kweNdawo Yezwekazi Lase-Afrikha Yokuhweba Ngokukhululekile (i-AfCFTA) ngowezi-2018. Isinqumo sowezi-2012 se-AU sokwakha i-CFTA ngowezi-2017 saphindwa Esifisweni Sesibili soHlelo- 2063. I-CFTA iphinde ibe wuhlelo olubalulekile oHlelweni-2063 futhi impumelelo yayo ibalulekile. Ucwaningo luhlose ukuhlola ngokujulile izisekelo zethiyori nezomqondo zokuhlanganiswa kwesifunda kanye nokuvunyelaniswa kwezomthetho kwezithiyo ezingakhokhisi yi-AU kanye nama-REC. Iphinde ihlaziye ukuqiniswa kwamanje kwezepolitiki, ezomnotho, kanye nezomthetho kuzwelonke e-Afrikha kanye nezinqubo ezidingekayo ukuze kuthuthukiswe ukuhwebelana kwangaphakathi kwesifunda ngaphakathi kohlaka loHlelo-2063. Lokhu kwenziwa ngokuhlola izinhlaka zomthetho ezibalulekile ze-AU (iSivumelwano sase-Abuja, UMthetho-sisekelo we-AU, 2007 Protocol on relationship between AU and RECs and Agenda 2063) ngenhloso yokuhlonza izindlela ezingcono kakhulu, amagebe kanye nezithiyo ezihambisana nokuqinisa uHlelo-2063 CFTA. Ekupheleni kocwaningo, amakhono ama-REC amathathu akhethiwe (i-SADC, i-COMESA kanye ne-EAC) ahlolwa ukuze aqhubekisele phambili i-AfCFTA. Lokhu kwenziwa ngokuhlonza amaphutha ezivumelwaneni ezikhona zama-RECs, ngenkathi kuthuthukiswa imodeli yokuvumelana okusemthethweni kwama-NTB phakathi kwawo. Kwatholakala ukuthi osopolitiki base-Afrikha abazange bayicabange indlela eqinile yokuhlanganisa umnotho wesifunda, nakuba indlela enjalo yaphakanyiswa abasunguli besifunda sase-Afrikha. I-AU kanye nama-REC awazange acabangele ngamandla ukubaluleka kokuvumelana kwezomthetho ezinhlelweni zawo zokuhlanganisa. Lokhu kuholele ekuntulekeni kwezinhlinzeko ezicacile nezibambekayo zokuvumelana ngokusemthethweni kwama-NTB kuzinqubomgomo eziqondisayo. Lolu cwaningo lwagomela ngokuthi uma izithiyo ezingokomthetho zokuhwebelana ngokukhululeka zingaqedwa, ngisho noma zonke ezinye izithiyo zizosuswa, ukufezeka ngempumelelo kwe-AfCFTA kusazothikamezwa. Ngaphakathi kwalokhu kwangemuva, lolu cwaningo luncoma izimiso zokusebenziseka okuqondile kanye nemiphumela eqondile yemithetho yesifunda ukuze kubhekwane nenselele yokuvumelana kwezomthetho egcizelelwe.
Keywords: Common External Tariff; Direct Effect; Legal harmonisation

Environmental protection under national legislation and agreements between oil and gas multinational corporations and host communities - Adedipe, F. (Canterbury Christ Church University, 2023)
The exploration, production and shipment of crude oil and gas by multinational corporations (MNCs), involved in bilateral treaties in Nigeria has perpetrated environmental disasters upon host communities. This has been as a result of oil and gas leaks from MNCs facility into the air, land, water, marine habitat, and cultural life of host communities are heavily polluted. International law has attempted to regulate the activities of MNCs particularly in the protection of the environment in which they operate through four main treaties: Universal Declaration of Human Rights,1International Covenant on Economic, Social and Cultural Rights (ICESCR), 2 Declaration of the United Nations Conference on the Human Environment (Stockholm Declaration)3and Declaration of the United Nations on Environment and Development (Rio Declaration). In addition, the demand for environmental protection is foregrounded under the right to life recognized in article 6 of the International Covenant on Civil and Political Rights (ICCPR). However, a major criticism of international law is its inapplicability to non-State actors such as corporations. This creates a lacuna in the legal framework of protections which has been exploited by opportunistic MNC’s. International soft law such as the Global Compact, Organization of Economic Cooperation and Development (OECD) Guidelines for Multinational Enterprises and United Nations Guiding Principles (UNGPs) on Business and Human Rights encourages corporations to respect environmental rights and creates substantive standards for States to hold corporations accountable for environmental and human rights violations. The challenge remains that these international laws having soft law status are not binding on corporations. Also, a further problem is that several developing state governments may be complicit in the environmental abuses perpetrated by MNCs for the purpose of boosting economic development. Therefore, this research proposes the regulation of MNCs under national legislation and bilateral investment treaties. It recommends certain preventive and mitigation measures against the adverse environmental effect of their activities in the exploration of natural resources, waste disposal and other connected operations in developing communities in Nigeria. Some of these preventive measures include environmental impact assessment (EIA), mandatory reporting and disclosures, community stakeholder participation, environmental management and safety practices, with activity, temporal and spatial management as mitigation measures. Also, clean-up and compensation by MNCs are effective remedies for environmental abuses. Furthermore, fines, blacklisting, withdrawal of license and criminal charges are recommended for the enforcement of environmental protection of host communities.
Permalink: https://repository.canterbury.ac.uk/item/95yw5/environmental-protection-under-national-legislation-and-agreements-between-oil-and-gas-multinational-corporations-and-host-communities
Keywords: Agreement; Environment (protection); Host communities; Multinational corporations; Oil and Gas Industry

African Economic Integration Initiatives and the Challenge of Responsible Business Conducts: Analysis of Corporate Social Responsibility Provisions in African Regional Trade and Investment Agreements - Azapmo, Jean Bertrand (Revue Interventions économiques, 2023)
Left alone, economic integration initiatives, which aim to promote growth through investment and trade liberalization, do not automatically generate win-win outcomes for all stakeholders, or lead to the inclusive economic growth and sustainable development of participating countries. This situation which is due among others to possible market failures and externalities of corporations’ activities, has increasingly become a matter of concern with the numerous corruption scandals; human rights violations and environmental degradation involving corporations observed in a recent past. How therefore to continue promoting economic integration while ensuring socially responsible conducts from businesses in societies where they operate? One approach that has recently gained traction is the institutionalization of corporate social responsibility (CSR) clauses in trade and investment agreements. This paper analyses 10 African regional trade and investment agreements concluded between 2000 and 2020 to determine the extent to which they converge with this trend and the approach adopted in regulating CSR. The research complements the literature on the nexus between international law and CSR in the African context. Laissées à elles-mêmes, les initiatives d'intégration économique, qui visent à promouvoir la croissance par la libéralisation commerciale et économique, ne génèrent pas automatiquement des résultats gagnant-gagnant pour toutes les parties prenantes, ou ne conduisent pas à la croissance économique inclusive et au développement durable des pays participants. Cette situation, qui est due entre autres à d’éventuelles défaillances du marché et à des externalités des activités des entreprises, est devenue de plus en plus préoccupante avec les nombreux scandales de corruption, de violation des droits de l’homme et de dégradation de l’environnement impliquant des entreprises. Comment donc continuer à promouvoir l'intégration économique tout en garantissant des comportements socialement responsables des entreprises dans les sociétés où elles opèrent ? Une approche qui a récemment gagné du terrain est l'institutionnalisation des clauses de responsabilité sociale des entreprises (RSE) dans les accords de commerce et d'investissement. Cet article analyse 10 accords régionaux africains de commerce et d'investissement conclus entre 2000 et 2020 pour déterminer dans quelle mesure ils convergent avec cette tendance à l’institutionnalisation des clauses sur la RSE, et l'approche adoptée dans la réglementation de la RSE. La recherche complète la littérature sur le lien entre le droit international et la RSE dans le contexte africain.
Keywords: Accords régionaux d'investissement; Accords régionaux de commerce; AfCFTA; CEDEAO; Corporate Social Responsibility; ECOWAS and SADC; Economic integration; Intégration économique; SADC; ZLECAf; regional trade and investment agreements; responsabilité sociale des entreprises

The regulation of Corporate phoenix activity in South Africa - Basson, André Stephan (University of Johannesburg, 2023)
Phoenix activity involves conduct whereby a failing company (the old company) is replaced by a second company (the new company) in the operation of the same or a similar business and that involves the same or similar company controllers. Transactions of this nature can be legal and even be beneficial to society, since entrepreneurs who pursue a viable business may, if the new company succeeds, benefit the economy and many other stakeholders. These transactions are referred to as legal phoenix activity. Problems arise however when phoenix activity is engaged in with the goal of evading the debt of the old company, known as illegal phoenix activity. In other cases, even well-intentioned company controllers can cause significant harm by resurrecting a fundamentally flawed business. This conduct, although not illegal, is unduly prejudicial to stakeholders and is known as problematic phoenix activity. While this thesis focuses on illegal phoenix activity, several measures identified should also curb problematic phoenix activity. This study identifies the elements and common characteristics of illegal phoenix activity. It then analyses regulation pertaining to those elements and common characteristics with the aim of finding effective solutions to the problem. This includes evaluating measures that reverse prejudicial transactions that occur during illegal phoenix activity as well as holding complicit parties, such as company controllers and the new company, accountable for their actions. Regulation aimed at preventing and investigating illegal phoenix activity is also considered. This thesis uses the comparative legal approach to analyse regulatory responses to illegal phoenix activity. Australia, the United Kingdom, and the United States of America are examined. Several reported cases in South Africa involving what appear to be illegal phoenix activity are explored, along with the existing measures that are applicable to illegal phoenix activity in South Africa. A single anti-phoenix provision is undesirable as it has the potential to unjustifiably infringe on legal phoenix activity. This thesis proposes a multi-pronged approach, which involves a combination of better enforcement of existing laws and the introduction of smaller targeted amendments to legislation aimed at reducing the incidence illegal phoenix activity.
Keywords: ABUSE OF THE CORPORATE FORM; Bankruptcy fraud; Evasion of liability; Fraud on creditors; Phoenix activity; Phoenixism; Strategic bankruptcy; Successor liability; Transactions prejudicing creditors; Transfers at an undervalue

A legal analysis on how France, Germany, the European Union and South Africa responded to the United Nations guiding principles on business and human rights - Buis, Jeanette (University of Pretoria, 2023)
Globally, companies pursue profitability; they want lower prices for the goods they buy and for the services they use. To gain profit and keep their prices low, they contribute to human rights violations and/or the devastation of the environment. The UNGP is the UN unanimously endorsed instrument that encourages states to pass legislation to compel companies to exercise human rights due diligence and to report on their efforts. The United Nations Guiding Principles (UNGP) impose a duty on companies to conduct human rights due diligence that apprises them of possible human rights or environmental risk exposure in their international operations. States have a responsibility to assist those harmed by a company’s activities to seek judicial relief. The UNGP is a soft law instrument but has had a major effect in the field of business and human rights. Though a voluntary obligation, the UNGP has become the reference document and is used by Civil Society Organisations (CSO) to pressure states into passing regulations on business and human rights. In 2016 Germany passed a National Action Plan (NAP) and the Lieferkettensorgfaltspflichtgesetz (Supply Chain Due Diligence Act) in 2021. France passed a Vigilance Law (Loi de Vigilance) in 2017. Additionally, a UN resolution has initiated a treaty-making process, which might lead to an internationally legally binding instrument that will articulate companies’ responsibilities to avoid, mitigate and remedy human rights violations that their activities cause. The South African government’s response to the UNGP has focused on negotiating a legally binding instrument at an intergovernmental level. This research examines three countries’ varying responses to the UNGP, a soft law instrument. In February 2022 the EU Commission published a proposed directive on corporate sustainability due diligence. The proposed EU legislation aims to advance respect for human rights and environmental protection. The goal is to create a level playing field within the European Union which leads to the exploration of the role China plays in a globalised world. China aims to be more than the world's factory and to become a leader in innovation and high-end manufacturing.
URI: https://repository.up.ac.za/handle/2263/93522
Keywords: CSR; Corporate Social Responsibility; Corporate governance; Human rights due diligence; Mandatory corporate due diligence; RSE; United Nations Guiding Principles; responsabilité sociale des entreprises

Redesigning Protection for Consumer Autonomy: The case-study of dark patterns in European private law - Guerra, Giorgia (FrancoAngeli, 2023)
European legal protection of consumer autonomy has been significantly changed in the digital environment, where algorithm-driven systems perform everything. This book focuses on protecting consumer autonomy facing the pervasive and global phenomenon of dark patterns: the expression includes various tactics that manipulate consumers by altering online choice architecture to thwart user preferences for objectionable ends. Overloading, skipping, stirring, hindering, and flicking are examples. Moving from the perspective that the sole traditional information approach is ineffective in protecting autonomy, the adopted methodology considers the multiple concerns revolving around the tight combination of transparent information and fair digital architectural design. Consequently, the comparative study of the new suitable regulatory directions arises across different legal fields, including data protection, consumer, and competition law. The relationship between deceptive designs, the nature of human-digital architecture interaction, and the techno-legal paradigms emphasises which future changes in European private law could integrate legal rules into fair designs to protect digital consumer autonomy effectively. Specific importance will be attributed to the functionality of comparative methodology to include non-legal essential insights (e.g. behavioural, informatic elements) into pragmatic and global regulatory paths and models.
Accepted: 2024-02-06T15:32:18Z
Keywords: Autonomy; Consumer law; Dark Patterns; Data protection law; Design regulation; Digital law; European private law

The commercial sexual exploitation of children perpetrated by the private sector: can international law be improved? - Hecht, Mark (Université de Sherbrooke, 2023)
International law is a robust system designed to unite world governments in an effort to, inter alia, cease human rights violations and hold those who commit them accountable. As it currently stands, and by its own design, the international human rights legal regime focuses on and applies only to state actors, meaning that violations committed by non-state actors, such as multinational corporations (MNCs), are seemingly conducted with impunity inside this space. Multinational corporations are powerful international players that have undoubtably fostered a significant role in reducing global barriers. By their very nature, they are far more mobile than states, allowing them to evade domestic power and regulatory schemes by detaching from their home state and relocating to a host state with weaker oversight and/or enforcement powers. Simply stated: even though MNCs have better financing, heightened mobility, and a disproportionate amount of influence when compared to world states, they operate with less global accountability. Commercial sexual exploitation of children (CSEC) is a fundamental violation of children’s rights. It consists of sexual abuse by the adult and remuneration in cash or kind to the child or a third person or persons. The child is treated as a sexual object and as a commercial object. Multinational corporations have been implicated in CSEC through acts of omission and commission. And despite the fact that much international law has been drafted to protect children around the world from CSEC—most notably the United Nations Convention on the Rights of the Child and its Optional Protocols—the numbers of children who have been emotionally and physically harmed by and through MNC conduct has only increased in the past decade. There have been numerous efforts by international organizations to address the challenges when regulating and monitoring human rights violations by MNCs. States, civil society organizations, and the private sector itself have also attempted to address these human rights violations through domestic law, modifying international law principles, and with civil regulation. Obstacles exist in the effectiveness of each of these approaches, leaving children at risk with no single effective strategy to combat and address rights violations by MNCs. The dissertation conducts a review of the current landscape of child law, through the lens of corporate accountability for CSEC. Then, it suggests a new alternative, putting forward an international solution to an international problem.
Keywords: Commercial sexual exploitation of children; Convention on the rights of the child; Corporate Social Responsibility; International child law

Effective Conflict Management - International Chamber of Commerce (ICC DRS Publications, 2023)

The International Validity of Domestic Law in Investment-Treaty Arbitration - Jarrett, Martin (Arbitration international, 2023)
Keywords: Arbitrage; Arbitragem; Arbitration; Investment arbitration; Investments

Land Reform in Sub-Saharan Africa: Exploring Interested Parties Perspectives on Cameroon's Land Tenure and Land Law Reform. - Kenfack Kenjio, Jacques Wilfried (Antioch University, 2023)
This research study seeks to understand interested parties’ perspectives on Cameroon's existing land tenure systems, the 1974 land law, and ongoing efforts to reform this land law. It identifies both concerns and specific recommendations from these parties on the formulation and implementation of future reforms. In the decades following the achievement of independence from European colonizers, most governments in sub-Saharan Africa (SSA) have adopted new national land tenure policies to meet their countries’ needs and aspirations. In some parts of SSA, however, this process of land tenure formalization has negatively impacted the land rights of people observing customary land tenure. This has been a result of government interventions such as compulsory land acquisitions, which while technically legal, are ethically questionable. In the face of this challenge, efforts to reform post-colonial land laws have become a matter of urgency. A national land reform process for Cameroon, announced in 2011 has adopted a multistakeholder approach. My study seeks to understand interested parties’ perspectives on Cameroon’s existing land tenure systems, the 1974 land law, and ongoing efforts to reform the land law. This study applied a case study methodological approach and a convergent mixed-method design. Evidence from this study shows that interested parties in Cameroon are in agreement on 1) the reform of the 1974 land law, 2) the recognition of customary land tenure, 3) the continued use of multistakeholder participation in land law reform, and 4) the promulgation of the new land law through mass sensitization and information dissemination.
URI: http://rave.ohiolink.edu/etdc/view?acc_num=antioch1684431556060359
Keywords: Government-Driven Land Dispossessions; Land Expropriations; Land Law; Land Reform; Land Tenure; Mixed Methods; Multistakeholder Participation; Sub-Saharan Africa

Critical Review of the Adoption of the Uncitral Model Law on International Commercial Arbitration in Africa - Mboya, Rachael A. (University of Nairobi, 2023)
Accepted: 2024-09-28T07:32:41Z

The Law Applicable to Security Interests in Intermediated Securities Under OHADA Law - Monsenepwo Mwakwaye, Justin (Mohr Siebeck, 2023)
In recent decades, the technical handling of custody business in the OHADA region has undergone a lasting change. There has been a shift from a direct to an indirect holding system, in which the interests of an investor in respect of the underlying securities are recorded in the books of an intermediary (such as a bank or a securities firm). Under the law of all states within the OHADA region, the traditional conflict of laws rule for determining the enforceability of a securities pledge that occurs in the indirect holding system is the lex rei sitae (or the lex cartae sitae or the lex situs ) rule. However, the traditional lex rei sitae rule cannot be appropriately applied to a system where the dematerialised securities are held through multiple layers of intermediaries located in different jurisdictions. Yet, until the intermediated system and the collateralisation of intermediated securities in the OHADA region will continue to operate in somewhat legally murky waters, leading to more instability in the financial markets. Therefore, Justin Monsenepwo aims to find an appropriate and consistent approach that reflects the reality of the indirect holding system in the OHADA region. “This publication is essential reading for policy makers, academics, market participants, and legal practitioners in the OHADA region and beyond. I am convinced that its in-depth analysis of OHADA’s substantive and conflict of laws rules will go a long way in filling the gap in this area and encouraging further development in the future.” Christophe Bernasconi, Secretary General of the „Hague Conference on Private International Law“ – HCCH in the foreword
Keywords: Commercial; Commercial law; Comparative; Comparative law; Competencia; Competition law; Conflict of laws; Law; Private international law

The Autonomy Doctrine in the Law of Letters of Credit and Demand Guarantees in Libya, Egypt and England: A Comparative Study - Mukhtar Elhouderi, Tajeldin Eissa Saleh (University of Leicester, 2023)
Letters of credit and demand guarantees play a prominent role in financing international trade. They provide assurance of payment and security for the performance of contractual obligations and have been described as the ‘lifeblood’ of international commerce. Autonomy is the central principle for the instruments of letters of credit and demand guarantees. Under the autonomy principle, the bank’s undertaking to pay for the beneficiary ought to be independent of the diversity of other relationships arising from the underlying contract. In spite of the autonomous nature of these instruments, in certain cases, the national laws will recognise some exceptions or limitations that restrict the application of the doctrine of autonomy. Exceptions such as fraud, nullity, and illegality will allow the national courts to interfere and override the autonomy doctrine by considering other matters, even those concerning the underlying contract. Furthermore, the exceptions of unconscionability or abuse of rights have an effective role in providing deep solutions, especially with regard to the problem of abusive calls for demand guarantees. The autonomy principle is recognised under Libyan commercial law but has yet to form the subject of serious academic literature covering its legal aspects. This study, in part, aims to fill that gap and will examine the extent to which legal aspects govern the principle of autonomy and its exceptions under Libyan law with reference to the new Libyan Commercial Code. A comparison of the laws in England, Libya, and Egypt will be conducted to examine how legal matters concerning autonomy and its restrictions in their laws are addressed. Furthermore, consideration will be given to the experience of Singapore, particularly with regard to the unconscionability and nullity exceptions. The results of this study will consider many different exceptions to autonomy and suggest that fraud is not the only exception to autonomy and that it is not imperative that all exceptions in letters of credit be equally applied to demand guarantees.
Keywords: Commerce international; Comparative study; Contractual obligations; Egypt; England; International Trade; International commerce; Letter of credit; Letter of guarantee; Lettre de crédit; Lettre de garantie; Libya; Obligation contractuelle

The concept of separate legal personality in South African company law: A critical examination of its origins, developments and current application - Myeni, Siphosethu (University of KwaZulu-Natal, 2023)
Section 19(1) of the current Companies Act 71 of 2008 states that once a company is incorporated in accordance with this Act, it is considered as a juristic person and exists indefinitely until its name is removed from the companies register. It exists independently from its shareholders and controllers. This effect grants the company with characteristics of a natural person. This analogy implies complete independence of the company. However, this concept finds refuge from the English legal system and was later adopted by South African company law. This notion provides some legal protection to businesses and shields their owners from personal liability for the company's debts and commitments. Companies can use this to enter new markets, reduce their taxes, and take advantage of advantageous business environments. Furthermore, this doctrine promotes joint ventures and partnerships among enterprises from many countries, allowing them to share resources and risks. As a result, this allows international enterprises to benefit by conducting international transactions, expanding abroad, and entering contracts in foreign countries. However, like any other concept, it is susceptible to abuse. Individuals take advantage of it to benefit themselves. This is detrimental to the significance of this doctrine. This dissertation aims to look deeply into this concept, by examining its origins and influence throughout the years and during its current application in the South African legal framework and highlight instances where this doctrine will be set aside. This will be conducted by fully analysing Salomon’s case and the influence it has over current company law. More importantly, the author will further examine the significance of this doctrine in modern company law. This will be done by testing the application of this doctrine to modern corporations and challenges they face.

Intellectual Property Law in Africa: Harmonising Administration and Policy - Ncube, Caroline B. (Taylor & Francis, 2023)
Examining the harmonisation of Intellectual Property policy, law and administration in Africa, this book evaluates the effectiveness of efforts to establish continental Intellectual Property institutions and frameworks. It also considers sub-regional initiatives led by the regional economic communities and the regional Intellectual Property organisations, focusing on relevant protocols and agreements that address Intellectual Property as well as the implementing institutions. The book assesses the progress of such initiatives with particular reference to the current socio-economic status of African states. It argues that that harmonisation initiatives need to be crafted in a way that is supportive of the developmental goals of African states and advocates for due consideration of individual states’ unique conditions and aspirations. This book will be of great relevance to scholars and policy makers with an interest in Intellectual Property law and its harmonisation in Africa.
Accepted: 2023-06-22T09:36:20Z
Keywords: Africa; Droit (harmonisation); Intellectual property; Public interest; TRIPs; governance; thema EDItEUR::G Reference

African Principles on the Law Applicable to International Commercial Contracts - Neels, Jan (UJ Press, 2023)
This booklet contains the first draft of the envisaged African Principles on the Law Applicable to International Commercial Contracts. The proposal could be used by national legislators on the continent and African economic integration organisations, particularly the African Union, in, respectively, domestic legislation and regional or supranational laws of a soft or binding nature. The existence of a reliable transnational legal infrastructure in respect of international commercial law, including commercial private international law, is a prerequisite for investor confidence, inclusive economic growth, sustainable development, and the ultimate alleviation of poverty on the African continent. The instrument may contribute to sustainable growth on a long-term basis. The regulation of private international law of contract is essential to the further development of the African Continental Free Trade Area. Jan L Neels is professor of private international law and director of the Research Centre for Private International Law in Emerging Countries at the University of Johannesburg.
Accepted: 2023-11-15T11:31:08Z
Keywords: African principles; International commercial contracts

The goals of competition law for merger analysis in developing jurisdictions : a critical appraisal of merger analysis under Kenyan competition law - Njako, Priscilla Mumbua (University of Pretoria, 2023)
This thesis considers whether jurisdictional exigencies should influence competition law enforcement, with a specific focus on merger analysis. It examines various approaches and schools of thought regarding the goals of competition law and how these play out within jurisdictional parameters. The history of enforcement of American antitrust is scrutinised to establish the nature of the interplay between greater economic policy direction and the goals of competition law. The study also explores the issue of convergence and whether developing jurisdictions should align their competition law to that of developed jurisdictions with mature competition law.
URI: https://repository.up.ac.za/handle/2263/91683
Keywords: American antitrust; Competencia; Competition law; Concurrence (droit); Kenya; Merger analysis

Trade between China and 45 African countries: does the Gravity Model matter? - Ondja'A Abeng-Abe, Christian Johan; Ebissemitie Kisso, Eunice (Revue d’Études Sino-Africaines, 2023)
The population of Africa and that of China put together amounts to a little over one-third of the world's total. The theoretical justification of the gravity model is applied to analyze the factors influencing bilateral trade between China and African countries using the panel data regression technique, covering the period between 2002 and 2021 and with special consideration for the income level of the African countries. Empirical results and estimates reveal that the economic size as well as the population of trade partners positively affect China’s trade with 45 African countries. The positive impact that distance has on trade is inconsistent with previous research. We conclude from the analysis that the factors affecting trade between China and African countries are, namely, the size of the population, the economic size represented by the GDP, and the distance between the countries. The indication of effects on the trade sector is important, and the sensitivity of the potential product to distance and countries varies considerably, giving a revealed comparative advantage. African countries should diversify their exports and improve their trade diplomacy.
Keywords: Africa; China; Gravity Model; Panel data regression; Trade

The International Handbook of Social Enterprise Law: Benefit Corporations and Other Purpose-Driven Companies - Peter, Henry; Vargas Vasserot, Carlos; Alcalde Silva, Jaime (Springer Nature, 2023)
This open-access book brings together international experts who shed new light on the status of social enterprises, benefit corporations and other purpose-driven companies. The respective chapters take a multidisciplinary approach (combining law, philosophy, history, sociology and economics) and provide valuable insights on fostering social entrepreneurship and advancing the common good. In recent years, we have witnessed a significant shift of how business activities are conducted, mainly through the rise of social enterprises. In an effort to target social problems at their roots, social entrepreneurs create organizations that bring transformative social changes by considering, among others, ethical, social, and environmental factors. A variety of social enterprise models are emerging internationally and are proving their vitality and importance. But what does the term “social enterprise” mean? What are its roots? And how does it work in practice within the legal framework of any country? This handbook attempts to answer these questions from a theoretical, historical, and comparative perspective, bringing together 44 contributions written by 71 expert researchers and practitioners in this field. The first part provides an overview of the social enterprise movement, its evolution, and the different forms entities can take to meet global challenges, overcoming the limits of what governments and states can do. The second part focuses on the emergence of benefit corporations and the growing importance of sustainability and societal values, while also analyzing their different legal forms and adaptation to their regulatory environment. In turn, the last part presents the status quo of purpose-driven companies in 36 developed and emerging economies worldwide. This handbook offers food for thought and guidance for everyone interested in this field. It will benefit practitioners and decision-makers involved in social and community organizations, as well as in international development and, more generally speaking, social sciences and economics.
Accepted: 2023-01-20T16:54:44Z
Keywords: B-Corps; BCorp Certification; Benefit Corporations; Business and Management; Business ethics; CSR; Commercial Law; Competencia; Competition law; Corporate Social Responsibility; Finance; Social Business Inititive; Social Enterprises; Social Entrepreneurship

Anti-Money laundering developments : A comparative appraisal - Schlebusch, Maria Elizabeth (Marlize) (University of Pretoria, 2023)
The objective of this study is to understand and explore the rapid pace at which ML has evolved and the global and local impact thereof.

The law applicable to an international commercial contract : a comparative study of private international law of contract in South Africa and South Korea - Setlhabi, Godiraona (University of Johannesburg, 2023)
Please refer to full text to view abstract.

Harmonisation in the rules governing the recognition of foreign judicial ship sales - Shao, Yingfeng (World Maritime University, 2023)
Ships, the high-value asset used in both seagoing and inland navigation, and in which various legal and natural persons have interests, must be secured against legal risks arising from any cross-border legal divergence. Legal certainty of ownership of the ship is therefore desirable but it is under challenge with regard to the judicial sale of a ship: the effects of a judicial sale may be denied in a jurisdiction other than the place where it was sold under the principles of state jurisdiction. Multiple efforts have been made to address legal uncertainty. Particularly important is a new treaty governing the international effects of judicial sales: the United Nations Convention on the International Effects of Judicial Sales of Ships (Beijing Convention). This dissertation is intended to contribute to that process by setting out two tasks; first, it seeks to identify the obstacles to the recognition of foreign judicial sales, providing additional knowledge which may aid national legal orders when deciding recognition approaches; second, it looks for a universal solution that better guarantees recognition which would benefit shipping. A comparative legal research exercise exploring similarities and dissimilarities in the municipal and international laws governing the recognition and sale procedures is undertaken. Research results are presented in this kappa and research papers, exhibiting the profuse difficulties a party seeking recognition may encounter in the current legal framework, and explains the new recognition approach under the Beijing Convention. Based on the research findings, a universal solution is proposed that avoids révision au fond, defines the finality of a judicial sale, and sets forth a fixed number of grounds for denial of recognition which may bring greater certainty. This purported optimal solution should guarantee equal treatment for all foreign sales seeking recognition before the registry while minimising the registrar’s burden of finding and examining foreign laws. In the interest of universality, this solution better accommodates disagreeing principles underlying certain aspects of the sale, viz., the ship’s location at the time of sale, the notification of sale, and the variance in the standard sale, namely, court-approved private sales, in a manner that more states may accept. This solution is largely in line with the recognition approach under the Beijing Convention. Considering the greater legal certainty the new instrument may bring, ratification is supported.

Arbitrability of Intellectual Property Dispute: A Pragmatic Dispute Resolution Mechanism - Singh, Vaishali (International Journal of Science and Research, 2023)
Conventionally, conflicts over intellectual property rights have been addressed primarily in national courts. Nonetheless, there has been a considerable inclination towards arbitration in recent years. For example, the number of cases decided under the WIPO Arbitration and Mediation Rules is constantly increasing, and the number of specific IP-related arbitral institutions is rising as well. This is due, in part, to the territorially limited reach of state court procedures, which no longer match the needs of modern international commercial processes. The transition to arbitration is appropriate since arbitration is particularly well suited to settling intellectual property conflicts. Arbitration is a private process, which is especially beneficial in IP issues due to the sensitive nature of the material involved. Furthermore, specific knowledge is necessary to properly settle technological disputes, a challenge that might be overcome by choosing adequately competent arbitrators.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrators; Intellectual property; WIPO (World Intellectual Property Rights Organization)

Impact of the Commercial Law on E-Commerce Practices and Business Sustainability in Nigeria - Ufua, Daniel Ebakoleaneh; Olujobi, Olusola Joshua; Al-Faryan, Mamdouh Abdulaziz Saleh (International Journal of Management, Economics and Social Sciences, 2023)
With the advent of global market interdependence and interaction, coupled with the consistent spread of the internet facilities across geographical boundaries, businesses engage in e-commerce practices either to augment existing on-ground businesses or as independent outfits. This study focused on the law on e-commerce practice and business sustainability in Nigeria. The study applied a conceptual review focusing on the trends of development of ecommerce practice and the supportive effects of the legal system in facilitating business sustainability in Nigeria. The study relied on extant literature sourced from various outlets, relevant to the topic of this study. The key findings highlighted and discussed factors for improved e-commerce practices in Nigeria. These included access to legal services, effective government policy and institutional support, time and fair interpretation of the law governing e-commerce, continuous evaluation of the ecommerce processes in Nigeria, increased awareness and familiarity with e-commerce facilities, and the adoption of suitable technology. The study provides valuable insight into the support of the Nigerian commercial sector on e-commerce practices. The adoption of systems theory enhances the promotion of fairness across the entire ambience of e-commerce practice and the support of the law. This implied focusing on the continuous evaluation of legal support and a flexible process of developing the needed approaches to address emerging changes in e-commerce that can enhance business sustainability in Nigeria.
eprints.covenantuniversity.edu.ng
Keywords: Business sustainability; E-commerce; Flexible process; Government Policy; Legal system support; Nigerian economy

Effective strategies for resolving labour disputes in the corporate sector: Lessons from Nigeria and the United States - Uzougbo, Ngozi Samuel; Akagha, Onyinyechi Vivian; Coker, Julie Olajumoke; Bakare, Seun Solomon; Ijiga, Amina Catherine (World Journal of Advanced Research and Reviews, 2023)
The relationship between an employer and employee though governed by various laws and regulations can still at some point witness some disagreements and dispute. Labour disputes are not uncommon neither are they peculiar to a particular industry in a country. Usually, trade disputes are hinged on agitation of employees for compensation, good working conditions, job stability and agitation against unlawful termination or dismissal of from service. Over the years, employees have adopted different ways to exhibit their discomfort and grievances in order to convey their message such as strike actions, peaceful protest and so on. There’s no doubt that these disputes will drastically reduce the level of productivity and overall beneficial impact of the industries in the economic growth of the country. Hence, there’s a need to adopt strategies for resolving these labour disputes. Some industries have applied round table discussions, arbitration, mediation, collective bargaining as well as grievances remedial processes. This work will provide an overview of the causes of disputes in the corporate sector, examine the features of the Nigerian and United States disputes resolution system and also juxtapose the strategies for resolving labour disputes in the two countries. Furthermore, it will provide recommendations to effectively addressing labour issues within the business sector.
Keywords: ADR; Alternative dispute resolution; Industrial relations; Legislative Framework; Multi-door courthouse; Trade unions

The public domain and the legal protection of Indigenous Knowledge Systems - Verhoef, Gerardus (North-West University, 2023)
IKS stakeholders often debate the divide between indigenous and other knowledge systems. IP rightsholders seek advice on how they can strengthen and secure their proprietary rights or broaden the public domain, while other interest groups such as indigenous peoples and local communities want to know how the public domain can be enclosed. One reason for this divide seems to be that the IP regime operates in a sphere where the public domain is demarcated by individual rights, as opposed to the indigenous knowledge systems regime where the public domain is demarcated by social embeddedness and connected to the land on which indigenous peoples and local communities live. This problem manifested itself over centuries of colonialism and technological development worldwide, but also because indigenous worldviews do not share the pre-appropriation narrative of the public domain than technological advanced societies. Within the context of this narrative the research question was posed, namely "what are the appropriate legal instruments for protecting Indigenous Knowledge Systems without compromising the public domain?" To answer this question, the public domain was analysed from three perspectives, namely international law instruments, human rights and IP rights. It was found that none of these perspectives lead to a narrow interpretation of the public domain – in fact, they all aim to broaden the public domain. These early findings on the public domain assisted to apply the fundamentals of the public domain to international law instruments and their application to IKS. In this regard it has been shown that the existing international law instruments, as well as the natural evolvement of these instruments over time, adequately provides for the protection and commercial exploitation of IKS worldwide. There is a proviso, though: IKS need to be viewed through the WIPO lens, which provides for the distinct delineation of categories of IKS, namely traditional knowledge, traditional cultural expressions and genetic resources. For example, the Bern Convention is founded on the three principles of droits des auteurs, droit moral, and domaine public. The boundaries of the public domain within the context of IKS can be reconciled with all three of these principles, and national legislators merely need to apply these principles to national legislation. With these insights gained on international law instruments, a few countries were analysed to ascertain how they address their local challenges pertaining to IKS. The countries that were analysed all aimed to appreciate international law instruments to which they are signatories, while they develop country specific IKS-related jurisprudence, although it cannot be said to be the same in each country. None of the findings pertaining to these countries could provide convincing arguments as to why a sui generis system for IKS can work. The research then moved to a legal analysis of South African legislation in relation to IKS. It has been shown that in general, South African legislation on IP is well aligned with international law instruments. These findings assisted with the research question at hand and was instrumental with coming to the early conclusion that IKS neatly fits into South Africa's current IP regimes and their associated public domains. Throughout the thesis, the rights and obligations of IKS rightsholders were demarcated since no right is absolute, as has been shown when the South African Constitution was discussed. In this regard, the droit moral of individuals from indigenous peoples and local communities, as well as the indigenous peoples and local communities, are to be respected. This approach led to more practical measures to ensure that matters such as prior informed consent, secrecy and sacredness, equity and access to TK, TCE and GR and benefit sharing were all understood within the boundaries of the public domain.
Keywords: Indigenous knowledge (protection); Intellectual property; Propriedade intelectual; Propriété intellectuelle; Savoirs traditionnels

The Law Applicable to Security Interests in Intermediated Securities under OHADA Law - Monsenepwo Mwakwaye, Justin (Universität Würzburg, 2022)
In recent decades, the technical handling of custody business in the OHADA region has undergone a lasting change. There has been a shift from a direct to an indirect holding system, in which the interests of an investor in respect of the underlying securities are recorded in the books of an intermediary (such as a bank or a securities firm). Under the law of all states within the OHADA region, the traditional conflict of laws rule for determining the enforceability of a securities pledge that occurs in the indirect holding system is the lex rei sitae (or the lex cartae sitae or the lex situs ) rule. However, the traditional lex rei sitae rule cannot be appropriately applied to a system where the dematerialised securities are held through multiple layers of intermediaries located in different jurisdictions. Yet, until the intermediated system and the collateralisation of intermediated securities in the OHADA region will continue to operate in somewhat legally murky waters, leading to more instability in the financial markets. Therefore, Justin Monsenepwoaims to find an appropriate and consistent approach that reflects the reality of the indirect holding system in the OHADA region. “This publication is essential reading for policy makers, academics, market participants, and legal practitioners in the OHADA region and beyond. I am convinced that its in-depth analysis of OHADA’s substantive and conflict of laws rules will go a long way in filling the gap in this area and encouraging further development in the future.” Christophe Bernasconi, Secretary General of the „Hague Conference on Private International Law“ – HCCH in the foreword
Keywords: Competencia; Competition law

Overcoming Divergence in English and French Contract Law: A Common Taxonomy of Commercial Contracts - Pedamon, Catherine (University of Westminster, 2022)
The works presented for the PhD by publication are all connected in the way they engage in a functionally comparative study of the English and French law responses to common problems pertaining to contractual performance and contractual interpretation. My comparative inquiry demonstrates that both France and England have stayed true to their historic responses in times of peace and crisis confirming different mentalités juridiques. As neither England nor France offers ideal solution, parties may be better off finding a resolution to their disputes beyond the legal realm and respond to calls for collaboration. This nevertheless shows persisting differences in Anglo-French approaches. This thesis however argues that these divergences may nevertheless lead to common results through the lens of a taxonomy of commercial contracts – professionally drafted contracts may lead to converging results given the common application and interpretation of frequently used clauses beyond a domestic legal culture; by contrast, rudimentary contracts produce diverging results as the interpretation of these agreements is marked by a distinctive domestic socio-legal culture. This taxonomy has the potential to improve the predictability of outcomes in commercial disputes in England and France.
Keywords: Commercial contracts; Contract law; England; France

Reforming investor-state dispute resolution: Focusing on the roles of domestic courts - Ma, Wanli (Erasmus University Rotterdam, 2022)
While a universally applicable multilateral agreement on investment is not yet available, a broad network of BITs and investment chapters in FTAs has been put in place to protect foreign investors and their investments. Meanwhile, investment arbitration has become a defining feature of modern international investment law over the recent decades, enabling foreign investors to launch an investment arbitration against host states, often without the need to go through local remedies before that. With the caseload of investment arbitration increasing at a rather rapid speed, such a dispute resolution method has also attracted fierce criticism. Many commentators have alleged, among other, that the decision-making of investment arbitrators has been inconsistent and unpredictable, that investment arbitration has become a threat to public interest, that investment arbitration proceedings are not transparent enough, that the arbitrators involved are not independent nor diverse enough, that the lack of an applellate mechanism compromises the quality of decision-making, and that investment arbitration has become far too costly and time-consuming. Against such a backdrop, the global community has made joint efforts to reform the investment arbitration system, not least through various initiatives developed at ICSID and UNCITRAL. Almost at the same time, national states also seem to have started to reconsider the costs and benefits of including investment arbitration in their investment agreements as a method for the resolution of disputes with foreign investors. Although the caseload of investment arbitration continues to grow and national states keep concluding IIAs containing investment arbitration clauses, at least some countries in their more recent investment treaty making practice have demonstrated a policy trend to rein in investment arbitration and ramp up the role of domestic courts in resolving investment disputes. They often do so by exiting the ICSID system, terminating their investment agreements with economic partners, excluding investment arbitration from their investment agreements, and conditioning investment arbitration upon the prior use of litigation via domestic courts. While the state practice mentioned above surely does not suggest the global society has any intention to abandon investment arbitration any time soon, it prompts us to take a step back and reconsider the role that domestic courts may play in resolving investment disputes, instead of solely focusing on the piecemeal reform of investment arbitration. When it comes to investor-state dispute resolution, domestic courts can indeed play different roles along the process. Like investment tribunals, domestic courts can also adjudicate investment disputes between foreign investors and local authorities. Such a judicial role sometimes is also confirmed in investment agreements through, for example, the exhaustion of local remedies rule, the clause demanding pursuit of local remedies prior to investment arbitration and the fork-in-the-road provision. In the context of non-ICSID arbitration, disputing parties are often entitled to applying for the review by domestic courts loci arbitri of the rulings and awards rendered by investment tribunals. Domestic courts loci arbitri would thus assume a supervisory role with regard to arbitration proceedings and arbitral outcomes, as they may set aside arbitration awards in question according to the review grounds enumerated in local arbitration laws. Moreover, domestic courts in a broader sense may be called upon to support the conduct and / or authority of investment arbitration, by recognizing and enforcing the investment awards rendered by arbitral tribunals and issuing interim measures of a judicial nature to facilitate the arbitration process. Since litigation through domestic courts and investment arbitration are two primary remedies that foreign investors often rely on for the resolution of investment disputes, this study constructs three models of institutional design with regard to the allocation of jurisdiction over investment disputes between domestic courts and investment tribunals. While the reality may turn out to be more complicated, such three models roughly represent the institutional choices facing national states. These three models are: (i) utter reliance on domestic courts as the exclusive forum for investor-state dispute resolution, (ii) investment arbitration operating as a substitute for litigation via domestic courts, and (iii) investment arbitration working as a complement to litigation via domestic courts. In order to conduct a comparative institutional analysis of the three models to reveal their respective tradeoffs, this study employs a goal based approach which is increasingly used to analyze the effectiveness of international adjudicatory mechanisms. As a result of the employment of the goal-based approach, the goals of investor-state dispute resolution are recognized as achieving fair and efficient dispute resolution, promoting state compliance with investment treaty norms, facilitating the objectives of the investment law regime, and legitimizing the underlying investment treaty regime. While the quality of the national judiciaries of many developing countries is not the same as it was decades ago largely due to the judicial reforms launched around the world, fairness and efficiency in dispute resolution still cannot be fully guaranteed in the domestic courts of those countries without a robust legal system and a good record of the rule of law. However, there are certain institutional characteristics of court litigation that may facilitate the efficiency in the resolution of investment disputes, such as the unique advantage of domestic courts that they can work as a single forum for dispute resolution and the better knowledge of court judges of the domestic legal framework at issue. Domestic courts also hold great potential in promoting the compliance by national states with investment treaty norms not least because they have more flexibility in awarding both primary and secondary remedies, but that of course depends on whether domestic courts can adjudicate investment disputes in a fair and impartial manner. Moreover, while utter reliance on litigation via domestic courts may strengthen the domestic rule of law and improve the investment climate in the long term by pressing host states to improve their legal systems and judicial institutions, it may also invite the politicization of investment disputes and the diplomatic intervention from home states in investor-state dispute resolution. Furthermore, despite the risks created for foreign investors, reliance on domestic courts as the exclusive forum may enhance the legitimacy of the investment treaty regime by reducing the sovereignty costs incurred by national states and putting domestic investors and foreign investors on the same footing. Investment arbitration operating as a substitute for domestic courts, on the other hand, demonstrates certain advantages, which are typically affiliated with international arbitration, in achieving the fair and efficient resolution of investment disputes. Unlike domestic courts, which are an integral part of the state apparatus, investment arbitrators are often immune from the influence of domestic politics and are thus believed to be independent and impartial. Meanwhile, the specialization of arbitrators in a particular area of knowledge and the procedural flexibility of arbitration proceedings, among others, are expected to improve efficiency in the resolution of investment disputes. However, empirical evidence presented in the literature sometimes suggests that, in reality, investment arbitrators may not be that unbiased and investment arbitration proceedings often drag on with a bill of a massive amount. Besides, although investment tribunals have a broad scope of jurisdiction over the behavior of different government branches, the practical difficulties they face in awarding primary remedies may damage their ability in promoting state compliance with investment treaty norms. In addition, the introduction of investment arbitration grants to foreign investors a standing in international arbitration proceedings, to a large extent reducing the need for diplomatic protection and home state intervention. However, the positive impact of investment arbitration in facilitating the development of the domestic rule of law and the maintenance and increase of foreign capital is less certain. As for the preservation of the legitimacy of the underlying investment treaty regime, investment arbitration as an alternative to domestic courts cannot be relied on to produce much positive impact. For instance, the increasing sovereignty costs and financial burden imposed on national states would probably prompt more of them to turn against the investment treaty regime. The complement model, in which domestic courts assumes primary jurisdiction and investment tribunals secondary jurisdiction over investment disputes, stands a good chance in keeping the advantages of both court litigation and investment arbitration while avoiding their disadvantages. In the complement model, domestic courts will act as the first line of defense in adjudicating investment disputes, and the institutional advantages of court litigation will be enabled to release their potential. At the same time, even if foreign investors are not satisfied with the judicial outcome or regard the court proceedings as corrupt or unfair, they may escalate the specific disputes to investment tribunals for further consideration. Since court judges are more knowledgeable and experienced in the interpretation and application of domestic law, the legal analysis of court judges will also benefit the decision-making of investment arbitrators in the subsequent arbitration proceeding. Allowing domestic courts to have a first try at investment disputes will also increase the likelihood that primary remedies could be accorded, thus the unique advantages of primary remedies in promoting state compliance with investment treaty norms are not discarded in the complement model. Moreover, the complement model is also more promising in facilitating the achievement of the objectives of the investment treaty regime, and that is because domestic courts are not marginalized in the complement model, the antagonism between foreign investors and host states may be expected to decrease, and the depolicization of investment disputes will not be lost since investment arbitration is kept as an option. Furthermore, the complement model strikes a better balance among the interests of foreign investors, host states and other stakeholders, thus it is more likely to preserve and even enhance the legitimacy of the underlying investment treaty regime than the other two institutional choices. Although the complement model serves the goals of investor-state dispute resolution the best in theory, not any casual combination of court litigation and investment arbitration will do the job; instead, only a smart mix of the two dispute resolution methods can give full play to the advantages of the complement model. Now, we switch to the supervisory role of domestic courts in investor-state dispute resolution. While a systemic appellate mechanism has not been created for investment arbitration, disputing parties may rely on setting-aside proceedings in non-ICSID arbitration to challenge arbitration awards. In other words, domestic courts loci arbitri may conduct a judicial review of the rulings and awards made by investment tribunals. However, a theoretical analysis of the judicial review mechanism supported by empirical evidence has shown that the mechanism has several flaws, which include but are not limited to the points that follow immediately. Since there is only a casual link between the seat of arbitration and the investment dispute, it is inappropriate to subject the decision-making of arbitrators to the judges from the place where the arbitration proceedings took place. The very fact that review courts have been overwhelmingly located within the developed North could raise concern that the judicial review mechanism is inherently biased against developing countries which have already shown a somewhat negative sentiment towards investment arbitration. Given that judicial review proceedings could easily go through more than one instance of court proceedings in many jurisdictions, the dispute resolution process may consume more time and generate higher costs. From this point of view, the judicial review mechanism favors the richer party in investment arbitration and could become a weapon of dilatory tactics available for such a party. Considering the higher error costs relating to investment arbitration than that relating to commercial arbitration, limited review grounds and a copious amount of deference to arbitral tribunals may not prove to be as effective in the scrutiny of investment awards. Moreover, the idiosyncrasies as to review grounds and standards across jurisdictions indicate that inconsistency would also probably permeate the judicial review practices, which would then encourage forum shopping that leads to increased costs and decreased efficiency. In addition, as both review courts and enforcement courts may exercise control over investment awards, the setting-aside decision may be merely disregarded at the enforcement stage and the overall efficiency of investor-state dispute resolution may be reduced. In order to overcome many of the flaws mentioned above, a delocalized form of review should be introduced to take place of the current judicial review mechanism.

Corporate Governance and Women on the Board of Directors : the Legal Framework towards a Minimum Harmonisation in the European Union - Lamy Martin, Joy (Université Paris-Saclay, 2022)
This thesis concerns the recent and considerable change in corporate governance legislation, specifically how boards of directors address the issue of parity and the appointment of its members in public limited companies. This research will challenge European Union law which, to date, does not propose EU harmonization.The UK, France, Germany and Norway (a non-member country but one that will be included in this research) have introduced changes to their national legislation in relation to company boards in public listed companies. This research will focus on a comparative study of parity on company boards under European Union law and its application in the UK (pre-Brexit), Germany, France and Norway. The application of corporate governance codes or soft law and the proposal for a hard law directive demonstrate a fragmentation in the EU, as the application of law by hard quotas divides member states and parliamentarians in European Union law. Corporate governance law in the member states varies considerably, but it must respect the EU's primacy law. Comparisons of legislation between member states reveal the marked differences in law.Women are significantly under-represented on the corporate boards of public limited companies in Europe. Legitimate questions need to be asked. Does the European Commission have the right to make a proposal for a directive allowing for parity on the boards of public limited companies in the EU? The reality is that the Commission does not have a solid approach in dealing with the issue of parity. As long as there is too much inconsistency between Member States, this leaves considerable room for further research. Legislation and governance law between member EU member states diverge considerably and demonstrate inconsistency with the legislation between them, resulting in little or no consensus in the interpretation of EU law. Or member states diverge with opposing interpretations of EU law, especially concerning sovereignty.National legal systems differ considerably in the way legislation allows for the appointment of board members and the notion of parity. A review of corporate governance matters concerning shareholders, the composition and appointment of board members corporate governance codes reveal the gap between member states. The research focus on parity by way of a comparison of the soft and hard laws of the member states.. The research upholds European law Article 157(3) Treaty of the Functioning on the European Union (TFEU), which is the fundamental principle of EU law and basis of gender equality and parity.The research will contribute to raising awareness of this issue through quota legislation and the question of parity on boards in public limited companies in the EU.
Issue: 2022UPASH012
Keywords: Board of directors; Comparative Law; Conseil d'administration; Corporate Governance; Droit comparé; Gender and parity; Genre et parité; Gouvernance des entreprises; Quotas; The European Union; Union européenne

The protection of the national labour force against foreign competition under labour migration laws and policies : a comparative analysis between the Democratic Republic of Congo and South Africa - Kamwimbi, Kasongo Theodore (University of South Africa, 2022)
Labour migration, which involves both labour immigration and labour emigration, refers to ‘the cross-border movement of people from a homeland to a location outside that homeland, with the purpose of taking up employment’.1 Labour migration has become an ever more important feature of the globalising world as it plays an important role and has a direct impact on African countries’ economies and societies. Recognising the significant benefits of labour migration to countries of origin and destination, the African Union urges African States to enact labour migration laws, regulations, and policies in a regular, transparent, and comprehensive manner at both continental and country levels. In this regard, many African countries have exercised their prerogative to regulate labour migration, which falls within each state’s sovereign discretion. By way of illustration, this thesis focuses on two specific countries, namely the Democratic Republic of Congo (DRC) and South Africa, which have regulated the employment of foreign-born workers. The two countries have established a legal and regulatory framework aimed at protecting the national labour force against foreign competition. The two countries have been selected for this study because they are comparable in many ways while differing as much as possible in terms of the institutional set-up of their migration systems and labour markets. In fact, this study seeks to compare the DRC’s and South Africa’s labour migration laws, regulations and policies, particularly how these legal and regulatory instruments effectively protect the national labour force against foreign competition. In this sense, the study explores the overall successes and challenges of these legislative and regulatory endeavours, while identifying the shortcomings and merits of the implementation of the laws and policies in the two countries.
Keywords: Congo (Democratic Republic); Contract of employment; Emigration and immigration law; Foreign workers; Labor laws and legislation; Labour market; Manpower policy; Migrant workers; South Africa

A comprehensive analysis of the law regulating equal pay in South Africa - Ebrahim, Shamier (University of South Africa, 2022)
The purpose of this thesis is as follows. Firstly, to identify the problems associated with the causes of action in section 6(4) of the EEA; the onus in section 11 of the EEA; the right to access pay related information; the grounds of justification in section 6(2) of the EEA and the Employment Equity Regulations; the equal pay provisions in sections 198A-198C of the LRA; and section 27 of the EEA. Secondly, to discuss and analyse the South African equal pay legal framework in order to provide answers and solutions to the research problems. Thirdly, to discuss and analyse the international legal framework regulating equal pay and the United Kingdom equal pay law in order to provide answers to the research questions to the extent and breadth called for. Fourthly, to summarise the answers to the research questions as sourced from South African law, international labour law and the United Kingdom equal pay law.
Keywords: Comparator; Equal pay claims; Equal pay for substantially the same work; Equal pay for the same work; Equal pay relating to non-standard (atypical) employees; Grounds of justification; Hypothetical comparator; Onus in section 11 of the EEA; Right to access pay-related information; Same employer; Section 27 of the EEA; Section 6(4) of the EEA; Sections 198A-198C of the LRA; Subordinate comparator; Terms and conditions of employment

Situation of Earning Management After Revision of the Ohada Accounting Standards Adopted on January 26, 2017 - Georges, Wandji; Nebasi, Akoso Wilfred (Law and Economy, 2022)
Following the mandatory adoption of the revised OHADA Accounting Standards that have moved closer to the International Financial Reporting Standards (IFRS), this study examines whether the level of Earnings Management of Companies making public offers or listed firms, in the West African Stock Exchange Market Abidjan-Ivory Coast (BRVM) has reduced. The study avails of Financial Statement figures during pre-adoption (2014–2017) and post-adoption (2018–2021) periods, for 26 selected listed firms in the BRVM. Findings suggest that firms in the post-adoption period of the revised OHADA Accounting Standards (2018–2021) are less likely to smooth earnings compared to the pre-adoption period (2014–2017). This indicates that adopting accounting standards of higher quality can bring an improvement in Financial Reporting Quality, everything being equal.
Number: 4
Keywords: Earnings management; IFRS; International Financial Reporting Accounting Standards (IFRS); Revised OHADA Accounting Standards; SYSCOHADA

Legal texts on trade facilitation: comparative analysis of the World Trade Organisation and the African Continental Free Trade Area - Shumba, Willie (University of South Africa, 2022)
Trade agreements are a common feature in international economic law as they govern trade relations between states. These agreements are anchored by a firm foundation of the requisite legal provisions to support trade. In this regard, the World Trade Organisation (WTO) and the African Continental Free Trade Area (AfCFTA) have each developed their own legal texts that acknowledge the significance of trade facilitation and would, when implemented, facilitate the movement of goods and services across international borders. The thesis was a comparative analysis of the legal texts on trade facilitation of the WTO and the AfCFTA whose aim was to identify the resemblances and divergences between the two. The WTO has a broader mandate of global trade and ensures that trade amongst its members is conducted in conformity with global rules. On the other hand, the AfCFTA is a trade agreement that has been negotiated by African member states pursuant to the political vision of the African Union (AU), and within the confines of WTO, specifically Article XXIV of GATT 1994. This research was therefore undertaken against the backdrop of these seemingly contradicting circumstances. The central research question for the study concerns the differences and similarities between the legal texts on trade facilitation of the WTO and the AfCFTA. The study was qualitative involving a desktop review of primary and secondary sources of data. Among others, the thesis finds that the AfCFTA complies with the strategic goals of the AU, and at the same time, complements the multilateral trading system of the WTO. The thesis concludes that while there are certain similarities, the legal texts on trade facilitation of the WTO and the AfCFTA are different. The inherent dissimilarities in the texts are not contrary to the principles of the WTO. The thesis contributes to scholarly literature in trade facilitation with respect to both the AfCFTA and the WTO. It also identifies new areas for further studies and provides the necessary groundwork. The study recommends some improvements that can be made to the respective legal texts on trade facilitation.
Keywords: AfCFTA; AfCFTA Agreement; African Continental Free Trade Area; Comparative analysis; Customs union; Free trade area; GATT; General Agreement on Tariffs and Trade; Global trade; International Trade; Legal texts; Multilateralism; Regional Economic Community; Regional Trade Agreements (RTAs); Regionalism; Trade Facilitation Agreement (TFA); Trade agreement; Trade facilitation; World Trade Organization

International Commercial Law Emerging in Africa - Neels, Jan L. (Potchefstroom Electronic Law Journal, 2022)
This article provides an overview of the history of international commercial law in Africa with reference to instruments of the three sister organisations of private international law (in a wide sense): UNCITRAL (the United Nations Commission on International Trade Law), UNIDROIT (the International Institute for the Unification of Private Law) and the HCCH (the Hague Conference on Private International Law). The adoption of UNIDROIT's Cape Town Convention on International Interests in Mobile Equipment of 2001 is identified as a possible watershed moment in respect of the future development of international commercial law in Africa. Following the creation of an African Continental Free Trade Area by member countries of the African Union, it is suggested that participating states reconsider joining the United Nations Convention on the International Sale of Goods (1980) (CISG) and incorporating the UNCITRAL Model Law on International Commercial Arbitration (1985/2006), which are in a certain sense the two founding documents of the modern lex mercatoria. Another priority, the author suggests, is that Africa needs a supporting instrument on the private international law of contract. The first draft of the African Principles on the Law Applicable to International Commercial Contracts is then discussed with an emphasis on the role of substantive law instruments, in particular the CISG
Keywords: African Principles of Commercial Private International Law; African Principles on the Law Applicable to International Commercial Contracts; International Commercial Law; International commercial contracts; Private international law

An evaluation of the strengths and weaknesses of South Africa’s corporate rescue regime as a potential benchmark for Uganda - Waiswa, Abudu Sallam (University of South Africa, 2022)
This thesis evaluates the strengths and weaknesses of the legal framework on corporate rescue in South Africa and Uganda. Although corporate rescue was initially not one of the objectives of insolvency law, it has now become the focus of modern insolvency law. South Africa became the first country to recognise the need to create a legal framework for rehabilitating financially distressed companies when it incorporated judicial management in the Companies Act of 1926. Judicial management was, however, not successful as a corporate rescue procedure. The South African policy makers however continued to explore ways through which financially distressed but viable companies could be saved from collapsing. This culminated into the introduction of business rescue in Chapter 6 of the Companies Act 71 of 2008. The study presents a detailed analysis of the strengths and weaknesses of the South African business rescue framework. It posits that unlike the Ugandan system, the South Africa legal regime reflects the principles of a modern and effective corporate rescue system. Whereas the government of Uganda attempted to embrace corporate rescue through the introduction of administration in the Insolvency Act 2011, the law is devoid of the internationally recognised features of a modern and effective business rescue framework. Administration has remained a white elephant in Uganda’s insolvency system, with liquidation continuing to be the predominant procedure used by both creditors and financially distressed companies. It is recommended that Uganda’s policy makers should benchmark the South African system to reform Uganda’s corporate rescue framework. This thesis is based on the law as at 31st of May 2022, found in the sources available in South Africa and Uganda.
Keywords: Bankruptcy; Business rescue; Corporate insolvency; Corporate insolvency law; Corporate reorganizations; Corporate rescue; Insolvency; Judicial management; Provisional administration; Rescue finance; South Africa; Uganda

Impact of Lack of Self-efficiency and Assets Evaluation on Resistance of IPSAS Implementation - Alhuda Tawffek Al-otoom, Nour; Alrabba, Hussein Mohammed (Information Sciences Letters, 2022)
This study examines factors influencing the international public sector accounting standards (IPSAS) implementation and presenting of accounting information related to the Jordanian public sector, also the information of reports is based on “Accounting principles and practices (No.39/1962) among government accountants. This study identified several important factors influencing the IPSAS implementation which are; lack of self-efficiency and assets evaluation. In addition, a quantitative approach was employed by distributed the questionnaires to 100 respondents enrolled at Jordanian General Budget Department using simple random sampling. The data were analyzed using SPSS to verify the relationships between the variables. The results found significant positive relationships between lack of self-efficiency and assets evaluation and IPSAS implementation resistance among government accountant in the public sector of Jordan. To sum up, this study contributes in expanding the literature concerning IPSAS implementation in Jordanian context, it’s also provides meaningful guideline to the government of Jordan for IPSAS implementation resistance. Finally, providing insights on the critical success factors to ensure successful implementation process.
Keywords: Accrual Accounting; Assets Evaluation; IPSASs; Public Sector Accounting; Self-efficiency

Article 255 of the OHADA Uniform Act on General Commercial Law and Consumer Protection: The Need to Experiment - Djieufack, Roland (International Journal on Consumer Law and Practice, 2022)

Business Dispute Settlement Through Mediation in State Courts and Arbitration Institutions - Yuspin, Wardah; Aziz, Abdul (International Journal of Social Science Research and Review, 2022)
In social life, there are often differences in perceptions between humans, causing problems or disputes, whether minor or serious. Likewise in the relationship of economic activities or more commonly known as business relations. Not infrequently humans experience a clash and differences of opinion that lead to disputes. Various problems will always arise in business as long as humans run their business solely for profit, so there are often differences of opinion because the parties will not be harmed which will eventually lead to disputes. In the end, dispute resolution, especially business disputes, is often resolved through a trial in court through a lawsuit by one of the parties who feel aggrieved. However, what was expected from the settlement turned out to be unsatisfactory for the parties because the settlement through litigation sometimes took a long time to obtain legal certainty so that it actually harmed business people because of the loss of time, energy and materials. As an alternative to resolving business disputes, business actors have a tendency to avoid disputes in court and choose to use mediation or through arbitration institutions. This study will briefly describe the comparison of business dispute resolution through court mediation with settlement through arbitration institutions. The research was conducted through descriptive empirical legal research.
Keywords: Arbitration; Business; Dispute

The application of knowledge stylised facts in West Africa Economic and Monetary Union (WAEMU) - Amanzou, Nogbou Andetchi Aubin; Ballo, Zie; Troupa, Sery Guy Flavien (Journal of Innovation and Entrepreneurship, 2022)
Sub-Saharan Africa has one of the dynamic economies in the world. Unfortunately, the performance achieve has not led to a reduction of social issues. So, the government are making massive investment to overcome social issues. This massive public investment highlights the exogenous nature of the current economic growth. So, a change of the strategy in the economic management of sub-Saharan Africa is required. One solution remains the change of economic paradigm: the transition from exogenous economic with decreased return to endogenous economic with increased return. The theoretical explanation of such arguments are supported by New Growth Theory. However, the implementation of the new theory required compliance to a set of indicators known as stylized facts. In 2009, Romer and Jones have developed a list of stylized corresponding to the need of New Growth Theory. The stylized facts of the West African Economic and Monetary Union (WAEMU) have been compared to the standard facts of Romer and Jones in order to apply the recommendations of New Growth Theory in this area. To reach that aim, the stylized facts have been described and analysed with econometric panel model. As result, we find that the description of the stylized facts in WAEMU fitted perfectly with that of Romer and Jones for the same period. Unfortunately, when using data, institution don’t work as expected by Romer and Jones. This study strengthens the argument for the implementation of economic policy based on the valorisation of knowledge economic in WAEMU.
Keywords: Africa; D83; Economic development; Economic growth; Knowledge economic; Macroeconomic Analyses; N17; O11; O17; O40

Analysis of the Determinants of the Effectiveness of the Board of Directors in Family Businesses in Cameroon - Roukatou, Aboubakar; Dretti, Denise (Open Journal of Business and Management, 2022)
The composition of the Board of Directors is commonly presented as an understandable variable for its effectiveness. However, the work that examined the relationship between the composition and effectiveness of the Board is not characterized, as they require about whether or not certain categories of directors (internal, external, independent) are relevant and the related empirical results are mixed. This work examines the relationship between the characteristics of the board of directors and its effectiveness in a type of business that is very common in the world, respecting the family business. Thus, the problem that this study tries to solve is to identify the characteristics of the board of directors that can contribute to its effectiveness in Cameroonian family businesses. We found that the size of the Board, the presence of external directors, and the cumulative management and control functions appear to have an impact on the effectiveness of the Board.
Number: 5
Keywords: Board of directors; Family Business; Governance; Public Limited Company

Comparison of IAS/IFRS and OHADA standards in terms of taking inflation into account in financial accounting - Matofali, Victoire (Revue du Contrôle de la Comptabilité et de l’Audit, 2022)
Financial accounting is one of the indispensable management tools in an organization, its objective is to present financial statements that reflect a true and fair view of the assets, financial position and results of the entity. In times of high inflation, however, money loses its purchasing power at such a rate that comparing amounts resulting from transactions and other events that occurred at different times, even during the same accounting period, can be misleading. This can cause the figures in the financial statements to be misleading. It is therefore essential to adjust these figures to the actual economic conditions in order to preserve a true and fair view of the company's assets, financial position and results. International financial standards such as those of OHADA analyze this problem of inflation in accounting through different methods of restatement of the figures of the financial statements to make them faithful and consistent with the economic reality. In this work, we will identify the points of divergence as well as the points of convergence between OHADA and IAS/IFRS accounting standards in terms of inflation accounting.
CERN European Organization for Nuclear Research
Keywords: Accounting; IAS/IFRS; Inflation; Standardization

The Effects of Covid-19 Crisis on Good Governance at the Local Level, The Case of Tunisia - Braham, Fatma; Seguir, Sonia (Journal of the Association of Arab Universities for Research in Higher Education, 2022)
The COVID-19 crisis, in addition to its serious health impact, has negatively affected key socio-economic aggregates and has shocked the strategic planning of all economic and social actors, including local communities. In search of resilient, skillful and intelligent good territorial governance, the municipalities are working to adapt their governance systems to the new social and environmental priorities. This work proposes a new reading of the acquired approaches to good governance, a new paradigm related to the new conjuncture and an assessment of the performance system at the central and local levels

Three Essays on Digital Platforms and Competition Policy - Yan, Jun (Université Toulouse 1 Capitole, 2022)
Cette thèse se compose de trois chapitres indépendants et examine différentes questions antitrust liées aux plateformes de gatekeeper. Le chapitre I explore le problème du verrouillage vertical dans les marchés bifaces. Dans le cadre des Accelerated Mobile Pages (AMP) de Google, le chapitre 2 examine la question de l'accès des plates-formes de contrôle d'accès aux données des utilisateurs professionnels. Le chapitre 3 se concentre sur le droit d'auteur numérique et étudie le comportement de Google consistant à utiliser le contenu des éditeurs pour afficher des réponses courtes sur les pages de résultats de recherche.Le premier chapitre examine comment l'intégration verticale d'une plate-forme monopolistique, qui se caractérise par des externalités de réseau bilatérales entre groupes, influe sur son incitation à s'engager dans le verrouillage en aval. Je me concentre sur un environnement où la plate-forme et les vendeurs en aval sont confrontés à l'incertitude quant aux gains du commerce au stade de la passation des marchés. Le choc aléatoire étant non contractile, la contractualisation crée des frictions qui faussent la structure tarifaire de la plateforme. En revanche, l'intégration verticale atténue ce problème en permettant à la plate-forme d'intégrer le choc aléatoire des prix à la consommation. En raison de l'interaction entre la friction des transactions et les externalités de réseau intergroupes, je trouve que l'intégration verticale pourrait réduire l'incitation de la plate-forme à la forclusion.Le deuxième chapitre est un travail conjoint avec Doh-Shin Jeon. Nous étudions comment l'adoption par les journaux d'AMP, un format de publication qui permet le chargement instantané de pages Web dans les navigateurs mobiles, modifie l'allocation des données et, par conséquent, les incitations des journaux à investir dans un journalisme de qualité. L'adoption d'AMP permet à Google d'obtenir des données sur les consommateurs à partir d'articles AMP et de les combiner avec d'autres sources de données sur les consommateurs pour améliorer le ciblage des publicités diffusées par Google sur d'autres sites Web. Même si une telle combinaison de données augmente l'efficacité statique, elle peut réduire l'efficacité dynamique lorsqu'elle diminue les revenus publicitaires par trafic de journal, réduisant ainsi la qualité du journalisme. Les journaux sont confrontés à un problème d'action collective car l'adoption de l'AMP par un journal génère des externalités négatives pour les autres journaux via le classement des recherches et la fuite de données. Google peut tirer parti de son pouvoir de marché dans la recherche et l'intermédiation publicitaire pour inciter les journaux à adopter AMP. Nous fournissons des recours politiques.Le troisième chapitre construit un modèle théorique de biens d'information divisibles pour examiner comment l'utilisation d'extraits par un moteur de recherche monopolistique impacte la consommation et la création de contenu. En affichant des extraits dans la zone de réponse sur les pages de résultats de recherche, le moteur de recherche dissocie les informations essentielles et les informations supplémentaires des articles. Elle crée donc deux effets opposés sur l'incitation des éditeurs à investir dans la qualité : l'effet de taille du marché et l'effet d'élasticité. Son impact sur le bien-être social est ambigu. D'une part, la boîte de réponse améliore l'efficacité de la recherche en offrant un accès plus large aux informations essentielles et en permettant aux consommateurs inframarginaux de substituer les informations essentielles à l'article complet. D'un autre côté, cela pourrait réduire le trafic sur le site Web, réduire les revenus publicitaires des éditeurs et les inciter à investir dans la qualité. J'examine les impacts des différentes politiques qui obligent le moteur de recherche à payer pour l'utilisation d'extraits.
Keywords: Antitrust law; Competencia; Competition Policy; Competition law; Concurrence; Concurrence (droit); Digital Platforms; Economie des médias; Google; Intellectual property; Marché biface; Media Economics; Online Advertising; Plateformes digitales; Propriedade intelectual; Propriété intellectuelle; Publicité en ligne; Technologies de l'information et de la communication – Aspect économique; Two-Sided Market

Free movement of goods and new agreements in the aftermath of Brexit - Police, Cecilia (LUISS Guido Carli, 2022)
The main principles of EU internal market vs the new UK internal market: a background. The internal market of the European Union. UK membership: accession to the European economic community in 1973. The nature of the EU internal market and the free movement of goods. The UK internal market after the internal market act 2020. The EU common commercial policy and the post-Brexit scenario. Brexit: new agreements and legal framework. EU-UK post-Brexit relationship: a new framework for a new partnership. Brexit history and the question of sovereignty. Brexit history: the timeline. Brexit and the withdrawal agreement. Brexit and Northern Ireland protocol. Brexit and trade: perspectives on a new partnership. Brexit and trade: trade and cooperation agreement. Trade and cooperation agreement: EU-UK trade relations, institutional and governance structures. Preliminary remarks. Analysis of the TCA: trade in goods provisions. 0,0 agreement: zero tariffs, zero quotas and rules of origin. The TCA: technical barriers to trade (TBT). The TCA: sanitary and phytosanitary standards (SPS). The TCA: the principle of mutual recognition. Level playing field (LPF). The Northern Ireland protocol and the trade in goods regime. TCA’s main concerns and application issues. TCA dispute settlement mechanisms. Some conclusive remarks on TCA provisions.

Influence of current and capital account liberalization on economic growth: Evidence from heavily indebted SSA economies - Leykun, Fentaw (African Journal of Economic and Business Research, 2022)
Capital and current account restrictions were widely used in the past but were largely released during the liberalization movement of the 1990s, as interventionist policies got widespread support that paves the way to the renewed conception of government as an impartial referee. Such a restriction has come back on the agenda with the surge in public debt in the rouse of the Global Financial Crisis. By distorting market signals and incentives, financial repression persuades losses from inefficiency and rent-seeking that cannot be easily quantified. This paper seeks to investigate the impact of current and capital account liberalization on growth, using recent de jure and de facto measures, covering 26 heavily indebted Sub-Saharan African countries over 2000-2020. The results suggest that capital account liberalization escalates growth, brought distributional efficiency in conformity with the neoclassical growth model.
Keywords: Capital account; Current account; Economic growth; Financial liberalization; Financial repression

EU copyright reform : an institutional approach - Mangal, Natasha (Université de Strasbourg, 2022)
Cette thèse a pour objet d’étudier comment le dispositif institutionnel actuel pour l’adaptation du droit d’auteur dans l’Union européenne peut être reconsidéré afin de promouvoir le niveau de cohérence plus élevé dans les pratiques réglementaires des États membres, ainsi que dans l’intérêt de la promotion d’un corps de règles européennes plus dynamiques en la matière.À l’aide de l’outil normatif de l’analyse institutionnelle comparative, les dispositions institutionnelles actuelles sont examinées, en se concentrant sur la qualité de la participation des parties prenantes du droit d’auteur dans le système politique, le marché et les tribunaux. Des exemples d’institutions administratives du droit d’auteur dans certaines juridictions (États-Unis et Canada) sont analysés plus en détail, en tirant des conclusions sur leurs fonctions et leurs rôles dans leurs systèmes juridiques respectifs. Enfin, cette thèse propose plusieurs solutions politiques, y compris la possibilité d’envisager une nouvelle autorité au niveau de l’Union européenne pour le droit d’auteur. En fin de compte, la remise en question du statu quo institutionnel dans l’Union européenne peut révéler de nouvelles voies prometteuses pour développer les fonctions administratives, quasi judiciaires, d’observation et de conseil nécessaires à la gestion du droit d’auteur à l’ère du numérique.
Keywords: Analyse institutionnelle comparative; Comparative Institutional Analysis; Copyright; Digital Single Market; Droit de la propriété intellectuelle; Droit d’auteur; Droits d'auteur; Institutions; Intellectual property; Intellectual property law; Marché unique numérique; Union européenne

Investment Law and its Others - Schneiderman, David (Temple International Law Journal, 2022)
Accepted: 2024-06-06T13:17:31Z

Assessment Report of Arbitration Centre in Egypt (CRCICA) - SNFI (African Development Bank, 2022)

The Idea of Economic Constitution in Europe: Genealogy and Overview - Grégoire, Guillaume; Miny, Xavier (Brill, 2022)
Derrière les controverses qui jalonnent l’histoire de l’idée de Constitution économique émerge la question éminemment politique de la marge de manœuvre laissée aux autorités publiques dans la sphère économique. La notion cristallise ainsi une tension fondamentale : entre démocratie et État de droit, quel doit être modèle d’organisation et d’ordonnancement juridique de l’économie? Des physiocrates aux néolibéraux, de la République de Weimar à l’intégration européenne, des constitutions nationales à la Global Governance, cet ouvrage collectif nous invite dès lors à explorer la généalogie du concept polémique de Constitution économique. Les auteurs ouvrent alors, à travers un dialogue interdisciplinaire constant, une réflexion globale autour des enjeux juridiques et politiques du processus actuel de constitutionnalisation de l’ordre de marché en Europe.
Keywords: Constitutional Law; Economic History; History; International Law; Legal History

Determining the Liability for Carriage of Goods by Road in West Africa - Can OHADA Uniform Rules on Transport be a Foundation? - Osinuga, Damilola (Southern African Journal of Policy and Development, 2022)

La mise en concurrence des systèmes juridiques nationaux et l’idée de Constitution économique - Salah, M. Mahmoud Mohamed (The Idea of Economic Constitution in Europe, 2022)
Conséquence de la compétition que les États se livrent pour attirer le maximum d’investisseurs, la mise en concurrence des systèmes juridiques nationaux s’est traduite par une libéralisation continue du droit qui a eu un effet direct sur l’idée de Constitution économique. Celle-ci a non seulement vu son épaisseur normative se renforcer du fait de la neutralisation des dispositifs juridiques dirigistes mais elle s’est également universalisée en raison de la conversion de la quasi-totalité des pays au dogme de « l’attractivité ». Toutefois, ce mouvement généralisé vers le tout libéral commence à être remis en cause sous l’effet de facteurs divers qui se traduisent par une demande sociale et politique pour plus de régulation étatique. Il en résulte à la fois un regain de l’unilatéralisme qui affecte la force des principes qui sous-tendent l’idée de constitution économique et une prise en compte plus affirmée des valeurs et intérêts collectifs qui altère la substance de ces principes.
Section: The Idea of Economic Constitution in Europe
Keywords: Constitutional Law; Economic History; History; International Law; Legal History

Performance and rarity of worker-owned firms : empirical evidence from France - Mirabel, Thibault (Université Paris 10, 2022)
This thesis compares the performance of worker-owned firms (WOFs) and conventional firms (CFs). These firms differ by their distribution of ownership rights and their mode of governance. In WOFs, the ultimate control is held by the suppliers of labor, whereas in CFs the ultimate control is held by the suppliers of capital. WOFs represent an implementation of democracy in firms and, as such, are likely to be immune to institutional harassment and socialwashing. WOFs have also been supported by citizens, politicians, and economists from across a wide ideological spectrum. Despite their attractiveness, WOFs represent a minute proportion of firms in our contemporary economies. This thesis seeks to bring new insights and stylized facts to better understand the rarity of WOFs. Chapter 1 studies how the interaction of the sunk costs of human capital and physical capital impacts the probability of WOF entry. I show that the likelihood of WOF entry is the highest when the sunk cost of human capital is dominant while the sunk cost of physical capital is negligible. Chapter 2 compares the survival patterns of WOFs and CFs. I show that WOFs survive longer than CFs regardless of whether they have different or similar entry resources, and that some entrepreneur and firm characteristics impact WOF and CF survival differently. Chapter 3 compares the survival patterns of WOFs distinguished by their entry mode (i.e., newly created, worker buyouts of sound CFs, worker buyouts of CFs in difficulty, and worker buyouts of nonprofit organizations). I show that any type of worker buyout survives longer than newly created WOFs. Overall, this thesis suggests that the rarity of WOFs is more likely to result from entry barriers specific to WOFs rather than from poor performance compared to CFs. Cette thèse compare la performance des coopératives de travailleurs (SCOPs) et des entreprises conventionnelles (ECs). Ces entreprises diffèrent par leur distribution des droits de propriété et leur mode de gouvernance. Au sein des SCOPs, les travailleurs ont le contrôle ultime de leur entreprise. Les SCOPs instituent la démocratie dans le monde économique et, à cet égard, furent et sont encore défendues par des économistes appartenant à une large palette idéologique. Malgré leur attractivité, les SCOPs représentent une fraction minuscule des entreprises dans le monde. Cette thèse entend apporter des éléments nouveaux pour comprendre la rareté des SCOPs. Le Chapitre 1 étudie comment l’interaction des coûts échoués en capital et en travail impacte la probabilité de créer une SCOP. Je montre que la probabilité de créer une SCOP est maximale lorsque le coût échoué en travail est dominant et que le coût échoué en capital négligeable. Le Chapitre 2 compare les profils de survie des SCOPs et des ECs. Je montre que les SCOPs survivent plus longtemps que les ECs indépendamment du fait que leurs ressources à l’entrée diffèrent ou non. Je montre aussi que certaines caractéristiques de l’entrepreneur différemment la survie des SCOPs et des ECs. Le Chapitre 3 compare les profils de survie des SCOPs en distinguant quatre modes d’entrée (les SCOPs nouvellement créées, les reprises d’entreprises saines, les reprises d’entreprises en difficulté et les reprises d’organisations à but non-lucratif). Je montre que les reprises en SCOPs survivent plus longtemps que les SCOPs nouvellement créées. Dans l’ensemble, cette thèse suggère que la rareté des SCOPs est due à des barrières à l’entrée spécifiques aux SCOPs plutôt qu’à leur prétendue moindre performance vis-à-vis des ECs.
Keywords: Coopératives; Coopératives ouvrières de production; Coûts échoués; Democracy; Efficacité de l'organisation; Entry mode; France; Mode de création; Participation à la gestion; Performance; Personnel; Scop; Sunk costs; Survie; Survival; Worker-owned firms; Études comparatives

An examination of the challenges posed by the internet economy for the South African income tax regime - Odhiambo, Oluoch Rodney (University of South Africa, 2022)
The way of doing business has changed significantly since the turn of this century due to the growth of internet technology and the global digital economy. This growth has reduced the importance traditionally attached to tangible assets and physical location in both commerce and taxation. This implies that any country that relies on physical presence to trigger tax liability in today’s digital economy may be forced to reconsider the relevance, effectiveness, and efficiency of its income tax legislation. This thesis postulates that South Africa’s income tax law and the international taxation principles it relies on in taxing cross-border and digital transactions have not grown in tandem with the changing landscape of today’s digital economy. The thesis contends that South Africa will not receive its fair share of tax from giant multinational enterprises such as Google, Facebook, and Amazon which operate and trade in the country, if it does not amend its income tax laws to address the challenges posed by the internet economy. In examining the challenges posed by the internet economy to South Africa’s income tax regime, the thesis commences in Chapter 2 by discussing the growth of the digital economy and its implications for South Africa’s income tax system. Chapter 3 offers a critical analysis of South Africa’s income tax laws and the international principles on which they rely in taxing the digital economy. Chapter 4 discusses the measures that South Africa’s government has taken to tax its digital economy, while Chapter 5 compares how the Organization for Economic Cooperation and Development (OECD), the European Union (EU), Kenya, India, and New Zealand have dealt with the issue of taxing the digital economy and the lessons to be learned from these jurisdictions. The thesis concludes in Chapter 6 by proposing recommendations that South Africa could consider to make its income tax regime more efficient and effective in taxing transactions that take place in today’s digitised economy.
Keywords: Cryptocurrency; Digital economy; Digital tax; E-commerce; E-signature; Electronic commerce; Formulary apportionment; Income tax; Internet industry; Signature électronique; Taxation; Virtual currency

Innovative Approaches for Tackling Tax Evasion in the South African Minibus Taxi Industry: Lessons from Ghana, Zambia, and Zimbabwe - Ndlovu, Jane; Mohale, Enhle (Journal of Law, Society and Development, 2022)
In South Africa, minibus taxis are a crucial mode of public transport for many commuters and a vital informal business sector with an estimated value of R90 billion. Concerns have been raised that the South African Revenue Service (SARS) is not collecting the optimal amount of tax revenue from this industry, with estimated tax collection at only R5 million in 2021. As a result of concerns that this industry might be involved in tax evasion or massive tax avoidance, this study investigates the taxation of minibus taxis in South Africa and explores alternative tax regimes that could be implemented to improve revenue collection. The study compares the current South African turnover tax system for minibus taxi operators to other African tax systems and evaluates a viable alternative tax regime or tax collection system. To improve tax collection from the industry, South Africa could consider a tax system tailored to the industry’s informal nature, utilising metrics such as vehicle seating capacity or distance travelled. A standardised tax system for small, medium, and micro enterprises may not be suitable. Consultation with industry stakeholders is essential for the proposed tax system to be acceptable. The study’s findings could inform South Africa’s National Treasury in creating a tax structure or collection scheme targeting the minibus taxi industry. This could increase tax revenue collection from the industry and support government expenditure, including income and wealth redistribution. This study distinguishes itself from prior publications on the South African minibus taxi industry by addressing tax compliance and collection challenges. It offers recommendations for alternative tax regimes to mitigate these challenges.
Keywords: Informal sector; Micro-enterprises; Minibus taxi; Presumptive tax; Tax relief; Turnover tax

The use of MASS in the context of International Law of the Sea - Mandrioli, Daniele (Università degli studi di Milano, 2022)
L'automatisation et la numérisation redéfinissent l'ergonomie des comportements humains. En se limitant au domaine maritime, les nouvelles technologies permettent d'automatiser entièrement l'activité traditionnelle de la navigation ; aujourd'hui, les navires peuvent être contrôlés depuis le rivage et l'intervention humaine dans la boucle de décision n'est plus nécessaire.Cette innovation disruptive offre de grandes opportunités pour l'industrie maritime. Intuitivement, les profits tirés du transport de marchandises et de personnes en mer peuvent être maximisés ; la réduction ou l'absence d'équipage à bord entraîne une réduction considérable des coûts pour les opérateurs (et pour les consommateurs), surtout en cette période historique marquée par la propagation mondiale du virus SARSCOV-2. En ce qui concerne la sécurité maritime, l'innovation que constitue le contrôle autonome réduit fortement le risque d'accidents dus à des erreurs humaines, qui sont à l'origine de la plupart des accidents maritimes. En ce qui concerne la protection de l'environnement marin, la navigation autonome peut en outre rendre le transport maritime plus durable.Pour ces raisons, les États et les entités privées financent plusieurs projets de développement de navires autonomes : au cours des dernières années, les premiers navires de surface autonomes (ci-après dénommés MASS) ont été testés et produits. En l'état actuel des connaissances, l'adoption de cette nouvelle technologie n'est plus un événement futuriste : plus d'un millier de MASS naviguent actuellement sur les océans du monde.Étant donné que l'activité humaine de la navigation est sujette à des changements, on peut se demander si les règles internationales qui la régissent sont d'une certaine manière remises en question par l'essor de l'automatisation.Habituellement, une nouvelle invention technologique s'accompagne de nombreuses questions réglementaires. D'une part, la loi est tenue de contrôler et de prévenir les conséquences involontaires découlant du recours à la nouvelle technologie. D'autre part, la loi est appelée à admettre et à autoriser son utilisation.Par conséquent, l'objectif de cette thèse est d'étudier les implications juridiques internationales découlant de l'utilisation croissante des moyens autonomes de transport maritime. En quelques mots, il s'agit ici d'aborder la question de savoir si et comment le recours à la technologie MASS a un impact sur le cadre juridique international préexistant qui régit l'exécution de la navigation et le contrôle de l'Etat sur celle-ci.Au cours des dernières années, ce sujet a suscité une attention croissante. En particulier, en 2019, le Comité de la sécurité maritime (CSM) de l'OMI a approuvé les "Directives provisoires pour les essais de navires autonomes de surface (MASS)". En outre, l'Organisation a très récemment achevé le "Regulatory Scoping Exercise on Maritime Autonomous Surface Ships" (ci-après RSE), qui avait débuté trois ans auparavant.La recherche proposée veut s'inscrire dans ce débat ouvert (et le dépasser) afin de fournir un panorama étendu des implications juridiques internationales émergeant de l'utilisation de l'automatisation et du contrôle dans le domaine maritime. Ce faisant, l'attention se concentrera sur trois blocs normatifs : les règles internationales sur la sécurité de la navigation (chapitre I), les règles internationales régissant l'attribution de la juridiction des États sur les navires (chapitre II) et les règles internationales traitant de l'assistance aux personnes trouvées en détresse en mer (chapitre III).
Keywords: Commande automatique; Droit de la mer; Droit maritime; Law of the Sea; Mass; Navires; Pilotes automatiques (navigation); Ships; Systèmes de guidage

Effectiveness of the Recognition and Enforcement of the OHADA's Arbitral Award - Rezara, Juvelin (International Journal of Social Science and Human Research, 2022)
OHADA is amongst an international organization which consists of arbitral tribunal within some regions in Africa in handling international investment and commercial disputes. Henceforth, the purpose of this study is to examine the effectivity of the enforcement of arbitral awards under the perspectives of OHADA arbitration rules. The study axed through qualitative approach by interpreting legal rules, analyzing cases and commenting the weakness of the charter in terms of enforcement and recognition of arbitral awards. The decision of OHADA arbitral tribunal shall contain intrinsically legal binding to member countries, however it leads problematics as the enforcement and recognition rules may be different in every country involved. Hence, the study interpreted the legal rules concerning enforcement and recognition of arbitral awards and the effectiveness of the rules. In addition it exerted also the challenges and significant recommendation for improving arbitration rules relating to enforcement of the awards. It is found that the weakness of the arbitral awards locates on refusal of concerned State to enforce the awards under the domestic law due to conflict of interest.
Keywords: Arbitral Awards; Enforcement; Exequatur; res judicata

Effectiveness of the Recognition and Enforcement of the OHADA`S Arbitral Award - Juvelin, Rezara (International Journal of Social Science and Human Research, 2022)
OHADA is amongst an international organization consists of arbitral tribunal within regions in Africa to deal with international disputes on investment and commercial related. Henceforth, the purpose of the study examines the effectivity of arbitral awards enforcement under the perspectives of OHADA arbitration rules. The study axed through qualitative approach by interpreting legal rules, analyzing cases and commenting the weakness of the charter in terms of enforcement and recognition of arbitral awards. The decision of OHADA arbitral tribunal shall contain intrinsically legal effect to country members, however it leads problematics as the enforcement and recognition rules may be different in every country involved. Hence, the study interpreted the legal rules concerning enforcement and recognition of arbitral awards, effectiveness of the rules. In addition it exerted also the challenges and significant recommendation for improving the arbitration rules on enforcement of arbitral awards. It is found the weakness of the arbitral awards locates on refusal of concerned State to enforce the awards under the domestic law for undefinable conflict of interest
Keywords: Arbitrage; Arbitragem; Arbitral Awards; Arbitration; Enforcement; OHADA; res judicata and exequatur

Trade facilitation through border enforcement of Intellectual Property Rights: issues, concerns and possible remedies - Hossain, Syed Saifuddin (Macquarie University, 2022)
In the present era of rapid globalisation, countries are intrinsically integrated with each other by way of international trade to ensure optimal utilisation of their resources. Trade facilitation is now recognised as a key driving factor in determining export competitiveness of a country. Customs administrations, the frontier border agency responsible for regulating import and export of legitimate goods, are increasingly faced with the challenge of intellectual property rights (IPR) infringement. In addition to national governments, various international organisations have devised guidelines and tools to facilitate and empower Customs agencies in their fight against IPR infringement. In particular, the multilateral Agreement on Trade Related Aspects of Intellectual Property Rights (TRIPS) of the World Trade Organization (WTO) articulates a prescription for border enforcement of IPRs in Articles 51-60. In this backdrop, this thesis attempts to answer a very fundamental question: What are the implications of ‘Border Measures’, specified under the WTO TRIPS Agreement, for facilitating international trade? To this end, it critically examines the concepts of trade facilitation, TRIPS and IPR protection to highlight the links that connect them and the missing links that need to be established. Obligations to protect IPR under national and international laws are also scrutinised. Research shows that efforts by WTO, World Customs Organization (WCO) and World Intellectual Property Organization (WIPO) have been instrumental in this context. While policy planning at the national level should be the first priority, commitment by the advanced economies to support their less developed counterparts through technology transfer (TT) is of paramount importance. The thesis suggests that TRIPS-plus provisions, if implemented arbitrarily by developed countries, have the potential to undermine the interests of countries with resource constraints. In this context, the thesis analyses the effects and implications of the Trans-Pacific Partnership (TPP) and the Trans-Atlantic Trade and Investment Partnership (TTIP) agreements, and the Revised Kyoto Convention (RKC) for the border protection of IPRs. The thesis investigates the socio-economic impacts of IPR infringement and articulates strategies to be adopted and applied at individual, collective, business and government levels to stop trade and use of IPR infringed goods. Drawing on the analysis of the relevant WTO Articles, scrutiny of various border measures put in place by national governments and international bodies, and current state of play under the Doha Development Round (DDR), the thesis puts forward a set of short and long term policy recommendations for all relevant stakeholders. These inclusively include: (i) strengthening risk management procedures; (ii) cooperation and coordination at national and international levels; (iii) awareness raising initiatives; (iv) establishing advanced technologically driven border enforcement system; (v) empowering Customs with effective administrative authority; (vi) IP related technical capacity building within the Customs and business community; (vii) technology transfer to LDCs from developed countries; and (viii) LDC friendly dispute settlement process under the WTO.
Keywords: Border protection; Customs; IPR; Intellectual property; Intellectual property infringement; Intellectual property rights; Trade facilitation

Hyperlinking and copyright - Karjiker, Sadulla (The South African Law Journal, 2022)
This article critically considers the legality of hyperlinking to copyright-protected material on the Internet. It considers the position with respect to standard hyperlinks, and attempts to provide a possible approach in light of the proposed introduction of two new exclusive rights, namely (i) the right of communication to the public; and (ii) the making-available right. These new exclusive rights appear to be an attempt to amend the South African Copyright Act in order to give effect to the 1996 WIPO Copyright Treaty, which sought to ‘digitise’ copyright law in light of the digital technology that had developed. The WIPO Copyright Treaty supplements, in particular, the rights granted to copyright owners under the Berne Convention, extending the right of communication to the public to include the making-available right. Use will be made of the case law of the Court of Justice of the European Union, which has given effect to the right of communication to the public (including the making-available right), following its inclusion in the WIPO Copyright Treaty of 1996. Through a more focused analysis of these exclusive rights, it is intended that this article can provide some guidance to South African lawyers and our courts when considering the application and scope of these exclusive rights.
Keywords: Copyright; Hyperlinking; Intellectual property; Legality

Exporting the Luxembourg Rail Protocol to the Convention on International Interests in Mobile Equipment to Africa - Otabor-Olubor, Iyare (Uniform Law Review, 2022)
This article recommends the Cape Town Convention on International Interests in Mobile Equipment and appeals to African countries to accede to the Luxembourg Protocol on Railway Rolling Stock (Rail Protocol). The discussion in this article focuses on the extent to which Article XXII of the Rail Protocol can be applied with respect to Africa. The article critically analyses the competence of the African Economic Community (AEC) and its sub-regional organizations to accede to the Cape Town Convention and Rail Protocol. The author provides a detailed argumentative analysis of the legal mandate of the AEC and the influence of African Union (AU) laws on the competence of the AEC’s sub-regional organizations to make declarations under the Cape Town Convention and Rail Protocol. The analysis confirms that competence to accede to the Convention and Rail Protocol resides with sovereign States in Africa and not with the AU, the AEC, the Organisation pour l’harmonisation en Afrique du Droit des Affaires, or any existing sub-regional organization in Africa.

Soil protection and legal aspects of international trade in agriculture in times of climate change: The WTO dimension - Ruppel, Oliver C. (Soil Security, 2022)
Soils are essential for food security and the right to food. But where is the connect between soil, trade in agriculture and the rules of the World Trade Organization (WTO)? While the WTO is not an environmental protection agency (as per its initial design at least), existing WTO rules fail to make agricultural trade patterns sustainable when it comes to the medium of soil. Notwithstanding, trade policy is of growing importance to soil protection, biodiversity preservation, deforestation, land degradation and desertification. Soil is key in this regard not only because it is the world's second-largest carbon sink after the oceans. Unsustainable trade in agricultural commodities should increasingly be seen in light of an industrial transition to increased climate neutrality and decarbonisation. This in turn should be guided by the leitmotiv – in times of climate change - to place soil protection for sustainable food security at the centre of any economic policy, also in terms of the rules on international trade in agriculture under the WTO.
Keywords: Climate change; Decarbonisation; Food security; Soil protection; Trade in agriculture; World trade law

The Economics of Trade, Innovation and the Technology Revolution - Tharwat, Ismaeel (Université Paris-Saclay, 2022)
Cette thèse étudie principalement l'impact du commerce international sur l'innovation, avec un accent particulier sur les pays en développement. Elle couvre également l'impact des retombées commerciales sur les inégalités de genre. Le chapitre 1 présente un aperçu de la littérature économique théorique et empirique récente traitant de l'effet de la concurrence des importations sur les résultats liés à l'innovation. Ce chapitre est divisé en quatre sections. Tout d'abord, un historique des brevets et des marques déposées en tant qu'indicateurs d'innovation est présenté. Deuxièmement, les mécanismes théoriques qui sous-tendent l'impact de la concurrence des importations sur l'innovation sont discutés. Troisièmement, une revue de la littérature des études empiriques récentes sur le commerce et l'innovation est résumée. Enfin, une analyse empirique est menée pour examiner l'impact de la concurrence des importations chinoises sur l'innovation, mesurée par l'activité de dépôt de brevet, dans les pays en développement.Le chapitre 2 est un exercice empirique qui examine l'impact de la concurrence des importations chinoises sur l'innovation, en utilisant une nouvelle mesure qui est le dépôt de brevet. L'étude utilise un ensemble de données de panel de 1995 à 2018 sur plus de 100 pays en développement. Le modèle empirique corrige l'endogénéité en utilisant une approche de variable instrumentale qui permet d'identifier la part du développement dû aux importations chinoises dans d'autres pays en développement. Les principales estimations trouvent un effet global décroissant de la concurrence des importations sur l'activité de dépôt de brevet. Les résultats de la variable instrumentale sont particulièrement robustes pour les demandes de brevet, mais pas pour les enregistrements. Cela suggère que la concurrence des importations affecte négativement les nouvelles innovations locales de produits ou de services dans les pays en développement.Enfin, le chapitre 3 aborde la question de l'impact des retombées du commerce international sur les normes d'égalité de genre. La majorité des études existantes documentent l'effet des épisodes de libéralisation sur les inégalités de genre. Celui des acteurs commerciaux, en revanche, a été largement ignoré. L'inégalité de genre au sein d'un pays est-elle affectée par ses partenaires commerciaux? Nous avons examiné cette question dans cet article en adoptant un modèle spatial du commerce entre 123 pays sur la période 1997-2013. Nous utilisons l'indice d'inégalité de genre pour capturer les tendances globales sur le genre au sein d'un pays. Nous avons ensuite désagrégé les échanges commerciaux au niveau produits afin d'identifier un canal technologique. Les résultats montrent que des normes d’égalité de genre plus élevées à l'étranger se répercutent, via les importations de produits de moyenne, haute technologie et minéraux, sur des normes d'égalité de genre plus élevées au niveau national. Ces résultats suggèrent qu'une révolution technologique affecte les entreprises, les ménages et les gouvernements en ayant un impact sur l'autonomisation des femmes.
Keywords: Brevets; Brevets d'invention; Economie du genre; Economie internationale; Gender Economics; Innovation; International Trade; Marques commerciales; Marques de commerce; Patents; Technologie; Technology; Trademarks; Économie de marché; Études sur le genre

Does the implementation of IFRS improve transparency regarding the company's financial conditions?: evidence from an emerging market - Ebaid, Ibrahim El-Sayed (PSU Research Review, 2022)
Purpose This study aims to examine whether there are differences between financial statements prepared in accordance with International Financial Reporting Standards (IFRS) and financial statements prepared in accordance with local accounting standards in terms of its ability to present the financial conditions of companies listed on the Saudi Stock Exchange as one of the emerging markets. Design/methodology/approach Data on study variables were obtained from the published financial statements of 67 of listed companies in the Saudi Stock Exchange during the period 2014–2019. The study addressed the research hypotheses by using Altman Z-score model. Both the T-test and Wilcoxon rank test were used to investigate the significance of differences between the values of Z-score and the individual variables included in the model in the pre- and post-IFRS mandatory adoption periods. Findings The results revealed a decrease in the values of Z-score as well as the values of the individual variables included in the model in the period following the adoption of IFRS than it was before the adoption of IFRS, which indicates the ability of IFRS to show the financial conditions of companies more transparently than local accounting standards. However, the results of the T-test and Wilcoxon test showed that these decreases were not statistically significant. Research limitations/implications This study has some limitations, including the small sample size as a result of the small size of the Saudi Stock Exchange, As well as the reliance of this study only on the Altman model with its five variables in assessing financial conditions without examining the impact of other factors that may affect the financial conditions of companies. Practical implications Financial conditions of the companies have important implications for multiple parties such as management, government, investors and others as an early warning sign that enables them to take the necessary measures early before the actual bankruptcy occurs and what results in costs. Originality/value Although assessing financial conditions of the companies is one of the basic uses of accounting information, this topic has not received sufficient attention as a means to test the benefits of adopting IFRS, especially in emerging markets such as Saudi Stock Exchange. This is the first study to examine the impact of adopting IFRS on the transparency of financial reporting in assessing financial conditions in Saudi Arabia.
Keywords: Financial conditions; IFRS; Saudi Arabia; Z-score

Factors affecting the probability of formalizing informal sector activities in Sub Saharan Africa: evidence from World Bank enterprise surveys - Moyo, Busani (African Journal of Economic and Management Studies, 2022)
Purpose This study aims to investigate the factors that affect the likelihood of formalizing informal sector activities in 13 Sub-Saharan African countries, using World Bank enterprise survey data collected between the periods 2009 and 2018. Notwithstanding the great contribution of the informal economy in Africa, developing countries may stand to gain more if they make inroads in formalizing the informal sector. Design/methodology/approach Since the dependent variable is binary taking the value of one if the firm is willing to formalize and zero otherwise, the study will employ a discrete choice probit model. Findings Results inter alia show that firms that are more likely to formalize are young, owned by individuals with high levels of education and, have registered before. Governments should therefore target firms that are young and provide them with information about the benefits of registration, and if these firms are owned by experienced and educated individuals, the likelihood for them to register would be high. Research limitations/implications The study uses cross sectional data and therefore cannot capture time variant factors affecting the probability to register and also cannot correct effectively for endogeneity. Practical implications Governments should therefore target firms that are young and provide them with as much information as possible about the benefits of registration, and if these firms are owned by experienced and educated individuals, the likelihood to convince them to register would be high. They should also reduce the cost of registration so as to improve net benefits in line with the rational exit view. Social implications Formalizing informal activities will help improve the performance of these firms, reduce vulnerable employment as well as crime, poverty and inequality. Providing decent operating and working conditions to informal players will reduce social and political unrest. Originality/value The African continent is home to many informal firms accounting for roughly 55% of economic activity with 90% of workers eking out a living in a sector that does not respect worker rights, provide decent working conditions and where changes in growth have done little to reduce its size. Regulatory reforms have also been implemented resulting in the number of start-up registration procedures falling from 11 in 2003 to seven in 2019. The uniqueness of Sub Saharan Africa in terms of entrepreneurial culture, political, institutional and economic conditions as well as lack of consensus in the extant empirical literature make this study pertinent.
Keywords: Formalization; Informal; World Bank and Africa

The legal framework for multimodal transport in West Africa: the African Continental Free Trade Area in perspective - Osinuga, Damilola (World Maritime University, 2022)
This thesis examines how multimodal transport can play a role in achieving the objectives of the African Continental Free Trade Area (AfCFTA). The thesis argues that multimodal transport is cheaper compared with unimodal transportation. While there are a number of issues affecting the operationalisation of multimodal transport in Africa, this study considers, at its core, the legal regimes and other fragmented institutional and governance frameworks of multimodal transport in West Africa. The fragmentation of the legal framework governing multimodal transport leads to uncertainty and unforeseeability of the liability of parties involved in multimodal transport, consequently leading to increased legal costs. There is an undisputed view that for effective regional integration, which Africa is seeking to achieve through the establishment of the African Continental Free Trade Area, there is a need to eliminate all trade barriers. Trade barriers (tariff or non-tariff barriers) should be removed to improve competitiveness and reduce trade friction costs. In other words, to achieve the objectives of the African Continental Free Trade Area, it is essential that all unnecessary costs associated with trade are eliminated or reduced to the barest minimum. The process of doing this is called trade facilitation. This thesis looks at the impact of trade facilitation on regional integration and trade. This thesis’ original contribution to knowledge is that Africa’s regional integration process needs cost-effective transportation in order to achieve smooth market access, and multimodal transportation can provide the most cost-effective solution. However, the legal uncertainty and complexities that could potentially ensue from the use of multimodal transport make it unattractive to prospective users. Accordingly, actions must be taken to reduce legal ambiguity and create a system in which liability is foreseeable and predictable. This study reveals that the current legal framework is incomplete, unsatisfactory and, ultimately, leads to uncertainty. The thesis further contends that neither the option of freedom of contract nor improving the current system of various Economic Community of West African States (ECOWAS )member-states’ view of multimodal transport, can significantly improve the current fragmented system or deliver the needed certainty. Accordingly, the thesis proposes that a modified uniform system would help achieve the legal certainty needed for multimodal transport. The thesis finally submits that the ECOWAS should establish a legally binding, regional governance regime on multimodal transport and a majority of its member-states should ratify the instrument.

The impact of the pandemic on the legal regulation of entrepreneurial activity of transport companies - Rubtsova, Natalya (Transportation Research Procedia, 2022)
The purpose of this paper is to analyze the trends of legal regulation in the business activity under the conditions of new coronavirus infection. The dialectical method of research in conjunction with a retrospective and comparative analysis made it possible to identify three main trends in the legal regulation of entrepreneurial activity in the framework of new socio-economic realities. The increasing role of state regulation of entrepreneurial activity, based on the use of public and legal means, due to the need to increase state intervention in the activities of entrepreneurs is shown. The state support of business for the subsequent development of the economy and compliance with the social balance is also increasing. Accordingly, the social importance of entrepreneurial activity is growing. The pandemic has also intensified the digitalization of entrepreneurial activity, of transport companies, since many traditional forms of doing business are limited by the forced isolation of society. Individual means of digitalization, including the industrial Internet of Things, e-commerce, and smart contracts, have become most prevalent. Consequently, the pandemic cannot be viewed only as a negative factor, its impact on entrepreneurial activity also has a positive effect.
Keywords: Business; axiology; digitalization; means of legal regulation; pandemic; transport companies

Does the impact of IFRS on audit fees differ between early and late adopters? - Tawiah, Vincent Konadu (International Journal of Accounting & Information Management, 2022)
Purpose This study aims to examine whether the impact of international financial reporting standards (IFRS) on audit fees differs between early and late adopters. Design/methodology/approach The authors use robust econometric estimation on a sample of 314 firms from both early and late IFRS adopting countries. Findings The authors find that IFRS is positively and significantly associated with an increase in audit fees for early adopters, but the impact is very weak for late adopters and insignificant in some cases. The results on auditing time suggest that increase in audit fees around IFRS adoption is due to an increase in audit reporting lags. After accounting for pre- and post-years, the authors find that the relationship between IFRS and audit fees, as well as audit time for late adopters, is significant only in the adoption year. However, early adopters experience a significant increase in audit fees and audit time in the transition year to one-year post-adoption. Practical implications The findings imply that countries that are yet to adopt IFRS are less likely to experience a significant increase in audit fees audit time. Hence, is probable that the benefit of IFRS will outweigh the cost. Originality/value The results, therefore, suggest that early adopters paid a premium for been the first users of IFRS, which is consistent with any innovation. The study provides new insights by demonstrating that the consequences of IFRS differ between early and late adopters.
Keywords: Africa; Audit fees; Audit reporting lags; Early adopters; IFRS; Late adopters

Accountability during the Incorporation of Public and Private Limited Companies under Ohada Law - Sama, Merinda Afanui (International Journal of Research and Innovation in Social Science, 2022)
This work sets out to evaluate the OHADA Uniform Act’s laws on accountability in Private and Public Limited Companies. Normally, laws which provide for effective accountability, guarantee the smooth functioning and stability of companies since its rules work at averting all forms of mismanagements. The inspiration of this work stems from the realization that, levels of accountability in these companies are still wanting. Hitherto, companies are plagued with vices of obscured activities, fake transactions, non-transparent reporting and acute dishonesty by its organs. It is therefore baffling that, these are still prevalent despite the existence of the Uniform Act’s laws which contains accountability mechanism aimed at dispelling all these forms of corporate transgressions. From this arose lingering doubts as to how these laws are.

Foreign Bank Penetration, Institutional Structures and Banking Sector Stability in Sub-saharan Africa - Abeka, Mac Junior (University of Cape Coast, 2022)
Link broken
Keywords: Bank penetration; Banking sector; Sub-Saharan Africa

The Singapore Convention on Mediation: a commentary - Alexander, Nadja; Chong, Shouyu; Giorgadze, Vakhtang (Kluwer Law International, 2022)
Article-by-article commentary
Selected contents: Foreword by Anna Joubin-Bret, p. xiii
Keywords: Dispute Settlement; MARD; Mediación; Mediation; Mediação; Médiation; UN Convention on International Settlement Agreements resulting from Mediation (2018)

Do corporate governance codes matter in Africa? - Areneke, Geofry; Khlif, Wafa; Kimani, Danson; Soobaroyen, Teerooven (Research Handbook on Corporate Board Decision-Making, 2022)
Africa is often depicted in the literature as the ‘patron late to the party’ on account of her low uptake of corporate governance codes. Notwithstanding, countries that have an existing corporate governance code continue to exhibit weak corporate accountability and governance practices. This prompted a critical analysis based on a detailed review of published articles and existing codes in the African multiple-contexts. Our findings reveal that the efficacy of many codes remains very limited in terms of pragmatic outcomes whilst firms in countries that have adopted codes continue to face uneven performance and poor accountability. We conclude by urging for an understanding of the reasons underlying such results. We recommend an African led re-think (independence, ownership, board processes) of existing codes to make them more aligned with the governance needs of African firms and their complex sociocultural background. We call for further research to illuminate Africa’s actual governance experiences and necessities.
Keywords: Africa; African principles; Board of directors; Boardroom processes; Codes; Corporate governance; Developing countries; Neo-colonialism

La jurisprudence de la Cour commune de justice et d'arbitrage (CCJA) sur l'immunité d'exécution au profit des entreprises publiques - Quo vadis? - Ayikaba, Jules Masuku (Recht in Afrika, 2022)
This study traces the evolution of the CCJA case law on the principle of exemption from enforcement for public companies. It aims in particular to highlight the direction in which this case law is moving. It appears that the CCJA has so far not succeeded in elaborating its own definition of the concept of 'public companies'; yet it is there that, in our view, the mystery of the immunity from execution that it has long recognized to these companies hides; even when they were incorporated in the form of a corporation. However, over time, the Court has rightly reversed its previous decisions by moving from an extensive to a restrictive interpretation of exemption from enforcement. In any case, the involvement of the lawmaker is more than welcome in order to put an end to the situation of inequality, which has existed for a long time in terms of enforcement under OHADA law, between corporations having the State or its branches (public companies) as shareholders and those whose shareholders have no State participation.

Dissenting opinions in international arbitration : More than an opinion? - Baltag, Crina (Principia, 2022)
Dissenting opinions have increasingly gained acceptance in international arbitration, with arbitration rules and laws allowing them, by either providing directly for such a possibility, or indirectly, by referring to ‘arbitral awards taken with majority of votes.’ Alan Redfern’s seminal 2003 Freshfields Lecture on dissenting opinions has highlighted the benefits, as well as the concerns with dissenting opinions, in particular, with those directed to alleged irregularities in the arbitral procedure. More recently, in the motion to set aside the arbitral award in Vantage Deep Water Co. v. Petrobras Am., Inc., the US District Court for the Southern District of Texas has rejected Petrobras’ argument that ‘the arbitral process was [so] “fundamentally flawed” … that “produced the extraordinary Dissent filed” by Mr Gaitis.’ While it is accepted that dissenting opinions have no legal effects, and in particular no legal effects similar to arbitral awards, they can have significant impact on the set aside and recognition and enforcement of arbitral awards. Las opiniones disidentes han ganado aceptación en el arbitraje internacional mediante reglas de arbitraje y leyes permitiéndolos, ya sea aceptando directamente la posibilidad de emitirlos, o indirectamente refiriéndose a ‘laudos arbitrales decididos por mayoría de votos’. El seminario del 2003 de Freshfields dictado por Alan Redfern sobre opiniones disidentes llamó la atención sobre los beneficios y las preocupaciones, en particular, aquellas opiniones disidentes dirigidas a señalar irregularidades en el procedimiento arbitral. Más recientemente, durante el procedimiento para anular el laudo arbitral de Vantage Deep Water Co. v. Petrobas Am., Inc., la Corte del Distrito Sur de Texas rechazó el argumento de Petrobras de que ‘el procedimiento arbitral había sido [tan] “fudamentalmente viciado…” que “produjo la extraordinaria opinión disidente consignada” por el Sr., Gaitis’. Mientras que es aceptado que las opiniones disidentes no tienen efectos legales, y en particular ningún efecto legal parecido a los laudos arbitrales, pueden lograr impactar significativamente a lograr la nulidad y el reconocimiento y ejecución de los laudos arbitrales.
Keywords: Anulación; Arbitral Awards; Dissenting opinions; Laudo arbitral; Recognition and enforcement; Reconocimiento y ejecución; Set aside; Voto salvado

Digitalization, institutions and new venture internationalization - Brieger, Steven A.; Chowdhury, Farzana; Hechavarría, Diana M.; Muralidharan, Etayankara; Pathak, Saurav; Lam, Yan Tong (Journal of International Management, 2022)
This study examines the effect of digitalization on the internationalization of new ventures and further investigates the influence of a home country’s presence of institutional voids and digital infrastructure on the extent of internationalization by new ventures, with the prediction that a home country’s institutional voids and a weak digital infrastructure strengthen the positive relationship between new ventures’ digitalization and internationalization. Applying multilevel modeling on a sample of more than 6000 entrepreneurs from 62 countries the study offers empirical support for these predictions. The findings are robust to alternative specifications. Entrepreneurs using the internet to sell their products and services are more likely to focus on customers in foreign markets when they face institutional voids and a lack of digital infrastructure in their home countries. The study contributes as follows: From a theoretical view, it provides a better understanding of the boundary conditions of the digitalization-new venture internationalization linkage. From a practical perspective, the findings of the study suggest the complementary roles of institutional voids and digital infrastructure at home to help entrepreneurs grow domestically and facilitate their internationalization.

The Limits of Public Contract Law - Casey, Anthony J.; Niblett, Anthony (Law and Contemporary Problems, 2022)
This work received SSHRC funding
Accepted: 2023-06-19T20:16:27Z

The rising role of China and Chinese enterprises in transnational labour law: Theoretical inquiries and case studies in the context of Chinese outward mining investment in Africa - Chen, Si (McGill University, 2022)
Transnational labour law scholarship has emerged over the past three decades. However, relatively limited scholarship has explored the role of actors from emerging market economies and the challenges and opportunities they have brought for achieving decent work in a globalized economy. This thesis addresses the research gap through an in-depth investigation into the role of actors from China in the dynamics of multi-level governance of labour rights in a globalized economy. Building on a multi-level, actor-centred and processual approach, this thesis argues that China and Chinese enterprises are playing a rising role in developing and shaping the dynamics of multi-level governance of labour rights in the global cobalt supply chain. Furthermore, the thesis suggests that actors from China have started challenging some unequal patterns of existing labour governance in the global cobalt supply chain and have demonstrated the potential to form a counterbalancing force to challenge the dominant role of actors from the global North. A multi-level governance framework has recently emerged and rapidly evolved in the global cobalt supply chain to eliminate child labour in the artisanal copper-cobalt mining sector in the Democratic Republic of the Congo. This framework is complex, pluralistic, and decentred. A wide range of state and non-state actors are developing various governance initiatives and shaping the dynamics of multi-level governance. Actors from China are playing a rising role in the global cobalt supply chain alongside a few other actors that have also provided proposals from the global South. Over the past decade, Chinese state agencies, nationwide industry associations and mining enterprises have proactively engaged in developing and shaping the multi-level governance framework to address governance deficits on decent work in the global cobalt supply chain. State agencies have developed various regulatory documents to enhance the social dimension of the Chinese regulatory framework for outward foreign direct investment. Nationwide industry associations have further conceptualized the term “corporate social responsibility” and have taken labour rights as key to the social responsibilities of Chinese enterprises operating overseas. Specifically, a Chinese nationwide industry association for the mining industry has developed comprehensive guidelines and initiatives to clarify and operationalize the labour component of social responsibilities in Chinese outward mining investment. The changing dynamics of multi-level governance have played a crucial role in shaping the private labour governance initiatives that Chinese mining enterprises are developing in the global cobalt supply chain. The contributions of this thesis are original, significant, and timely, given the notable research gaps on China and Chinese enterprises’ engagement with the dynamics of multi-level governance of labour rights in a globalized economy and the ongoing development of a multi-level governance framework in the global cobalt supply chain
Identifier: https://escholarship.mcgill.ca/concern/theses/7d2790853
Keywords: Chinese enterprise; Droit du travail; Investment in Africa; Labour law; Transnational labour law

Contract Interpretation in Investment Treaty Arbitration: A Theory of the Incidental Issue - Chernykh, Yuliya (Brill, 2022)
For the first time, a monograph provides a systematic, in-depth account of contract interpretation in investment treaty arbitration and offers a conceptual paradigm that would enhance the quality of the tribunals’ reasoning.; Readership: The monograph is of relevance for legal scholars, practitioners and policymakers in the field of investment treaty arbitration. The book will also be of additional value to postgraduate and doctoral students.
Accepted: 2022-04-07T09:15:30Z
Keywords: Arbitrage; Arbitragem; Arbitration; Contract interpretation; International law; Investment arbitration; Investments

Local Content Requirements in WTO Law: Between Free Trade and the Right to Development - De Lima Figueiredo, Natalia (Maastricht University; Universidade de São Paulo, 2022)
In the international arena, there is a strong rhetoric against a type of industrial policy measure called local content requirements (LCRs). They are often characterised, especially by developed countries, as protectionist measures. However, under certain circumstances, LCRs can have a central role in a country’s development process. Indeed, both developed and developing countries use them to boost their economies. Despite this developmental aspect of LCRs, WTO (World Trade Organization) rules restrict their use. The WTO Agreement, however, has a development dimension and WTO law is supposed to be read in light of the wider corpus of international law. The right to development, in turn, is a principle rooted in core human rights treaties, is consolidated in several instruments of soft law nature and could potentially play a role in the interpretation of WTO provisions. In this scenario, the thesis investigates if it is possible to further a development-oriented interpretation of WTO rules affecting LCRs so that those measures that incorporate genuine development goals are not considered a violation of WTO rules.
Keywords: Development; Free Trade; Human rights; Local content requirements (LCRs); WTO; World Trade Organization

The conclusion of contracts by electronic agents in the age of the Fourth Industrial Revolution : a South African perspective - Doughan, Albert Nana (University of Johannesburg, 2022)
Please refer to full text to view abstract.
Keywords: Commercial law; Contracts; Electronic data interchange; Industry 4.0

COFOLA International 2022: Current Challenges of Resolution of International (Cross-Border) Disputes - Drličková, Klára; Malachta, Radovan; Provazník, Patrik (Masaryk University Press, 2022)
- Bridging the Public-Private Law Divide in the Conflict of Laws; - New Practices in Alternative Dispute Resolution: New Pathways to Peace; - The Singapore Convention: A Giant Leap for Mediation or Just Too Good to Be True; - Potential Nexus Between the Enforceability of Foreign Judgments and the Quality of Civil Justice in ASEAN Did the Preliminary Objections Judgment Resolve the Chagos Archipelago Sovereignty Dispute? - The Order of Periodic Penalty Payments by the CJEU in Cases Filed by a State Against Another State; - The Dichotomy of Obligations of Conduct and Result in International Investment Law; - Investment Arbitration Reform: Third-Party Funding in Investment Arbitration; - Between Protection and Access to Justice: On the Regulation of Returns in Third-Party Litigation Funding; - Contract Adjustment in Arbitration : Should the Approach Be Adjusted? - Current Challenges of Enforcing Annulled Arbitral Awards; - Condifentiality of Arbitral Awards on National, International and Institutional Level; - Digitalisation of Judicial Cooperation in the EU: A Long Road Ahead; - Resolving Cross-Border Consumer Disputes: The Digital Experience in China; - Law Applicable to Non-Consumer Contracts Concluded at an Electronic Auction; - Can Robot Judges Solve the So-Called “Hard Cases”? - Current Challenges of Cross-Border Disputes in Slovakia : Is Slovak Law Anchored in the 21st century

Bank Bail-ins in International Investment Law - Duque-Cordero, Luciano (Universität Wien, 2022)
The global financial crisis led to the introduction of special resolution regimes for financial institutions. The most prominent innovation of these resolution regimes is the so-called bail-in tool, which allows regulators to recapitalise financial institutions by expropriating shareholders and creditors. This thesis analyses the conditions under which a hypothetical bail-in of a financial institution would constitute a compensable breach of international investment law. It identifies the issues that are most likely to be relevant if a bail-in were to be litigated before an investment arbitration tribunal. The thesis first addresses jurisdictional issues, in particular the question of whether bail-inable instruments can even be considered an investment in procedural terms. The analysis then continues to substantive standards of protection. It deals comprehensively with the question of expropriation and related issues such as compensation, the right to regulate, and causation. It concludes with possible violations of the fair and equitable treatment standard.
https://phaidra.univie.ac.at/detail/o:1417287
Keywords: Bail-in; Bank resolution; Expropriation; International Investment Law; Investments

The role of good faith in South African contract law - Govender, Tashri (University of KwaZulu-Natal, 2022)
This research paper seeks to address the role that good faith plays in South African contract law by first discussing its origin and then chronologically tracing its position from pre-1994 to today. The judgements of both the Supreme Court of Appeal and the Constitutional Court will be unpacked, as a means to understand the development of good faith over the years. The position that good faith plays in foreign jurisdictions will also be discussed, for the sake of achieving a universal understanding of how good faith is perceived around the world. The research concludes by placing good faith in its current role and context in South Africa, and also proposing a way forward.
Keywords: Bona fides; Contract Law

Guide to the writing of law for the Social and Solidarity Economy - Hiez, David (SSE International Forum, 2022)
Keywords: Cooperatives; Social Enterprises; Social and Solidarity Economy

Arbitration Rules In force as from 1 January 2021 and Mediation Rules In force as from 1 January 2014 - International Chamber of Commerce (ICC DRS Publications, 2022)
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration rules; MARD; Mediación; Mediation; Mediation rules; Mediação; Médiation

Sanitary and phytosanitary measures as barriers to trade : a South African perspective - Joubert, Biandri (North-West University, 2022)
Sanitary and phytosanitary (SPS) measures are measures aimed at the protection of human, animal and plant life and health, within World Trade Organization (WTO) Member territories, from the risks associated with the introduction and spread of pests and diseases into such territories through trade. The WTO, through its Agreement on the Application of Sanitary and Phytosanitary Measures (WTO-SPS), guides the application of sanitary and phytosanitary measures and provides a set of guiding principles, rights and obligations applicable to Member States. Dispute resolution through the processes of the WTO is available to Members on a Member to Member level within a defined scope and on specific terms. Private parties who operate within the SPS chain at a national level, whether involved in import or export or neither, are dependent on solutions to barriers or disputes available to them through national legislation. In the absence of an enabling legal framework to facilitate aspects of trade such as certainty and continuity in standard setting, the basis of measures taken in science, transparency and legal recourse to resolving barriers or disputes arising, private parties are vulnerable to fluctuations in, for example, their country’s disease-free status. Private parties are also vulnerable to losing relevance as trading partners in periods of ongoing SPS events and to the loss of trust that trading partners have in the country’s ability to trade safely. These are matters that affect private parties who do not have legal recourse to the WTO dispute resolution procedures which are well within WTO concern as they are directly related to the purpose of SPS measures, the principles, rights and obligations on which they are based. Given the importance of agriculture and the increasing inseparability of international rights, obligations and principles in a field of WTO law such as SPS, the importance of a national legislative framework in as far as being the translator of such rights, obligations and principles into legally enforceable rights, obligations, principles, processes and procedures is significant. The rights, obligations, and principles of SPS measures apply to all products, processes and procedures that are within the scope of the agreement and may include at least 36 chapters of the harmonised tariff book. It is necessary to consider also that international trade, national trade and the associated rights, obligations, and principles of the WTO-SPS agreement interact with the social, political, and economic realities of the country within the countries to which the agreement applies. Therefore, researching some of the persistent challenges experienced by the red meat industry in South Africa prone to negative trade-related consequences during and after the outbreak of a notifiable disease, provides insight into the perception of the ability of the legislative framework to provide solutions to these consequences. This research applies a mixed methodology approach whereby qualitative research by means of semi-structured interviews was combined with doctrinal legal research and a quantitative content analysis using Rprogramming. The qualitative research focused on the role of legislation and the perspectives of selected actors in the red-meat industry, specifically in reference to the foot-and-mouth-disease (FMD) outbreaks and subsequent loss of disease-free status since 2019. The doctrinal legal analysis and content analysis focused on the SPS-related legislative framework. The combination of these methods provides a multi-perspective analysis of SPS measures as barriers to trade from a South African perspective and contributes to the mixed-methods turn in legal studies. The objective of this research is to identify and explore persistent challenges to the prevention and resolution of barriers or disputes connected to sanitary and phytosanitary (SPS) measures in the South African context. Ultimately, this research recommends potential practical solutions to the identified challenges with specific focus on SPS-related barriers or disputes that are beyond the strict terms of dispute resolution available through the World Trade Organization (WTO).
Keywords: AfCFTA; Barriers to trade; CADA; CAQDSA; Content analysis; Dispute resolution; FMD; NTB; OIE; Qualitative research; Rstudio; SADC; SPS; Sanitary and phytosanitary measures; WTO

Privacy Between Regulation and Technology: GDPR and the Blockchain - Jusić, Asim (IUS LAW Journal, 2022)
Compliance with the GDPR while using blockchain technology for data processing results in compliance issues, due to the fact that the blockchain and the GDPR employ different methods to ensure privacy-by-design and privacy-by-default. The blockchain is built on disintermediation and relative decentralization, whereas the GDPR aims for re-intermediation and relative centralization of the data protection process. This paper provides an overview of and suggestions on how to secure compliance with the GDPR while processing data using the blockchain. A focus is placed on the data protection impact assessment on the blockchain network, issues in identifying and determining the role(s) of sole and joint data controllers and data processors, obstacles to exercising the right to rectification and right to be forgotten when the data is recorded on the blockchain, GDPR data transfer requirements as applied to the blockchain, and the protection of privacy in the process of creating blockchain-based smart contracts.
Keywords: Blockchain; Compliance; GDPR; Privacy

Paradigm Shift in Investment Treaty Arbitration: Toward Stricter Control over the Qualifications and Conduct of Arbitrators - Kamalinejad, Hassan (University of Victoria, 2022)
There is a growing concern over the qualifications and social interactions of investment treaty arbitrators. The characteristics of this class of international adjudicators have significantly evolved over the past few decades. The contemporary arbitration panelist interacts within a broad and complex network of arbitration participants. Their patterns of social behavior both within the community of panelists and within the broader network of actors in arbitration proceedings have fundamentally reshaped the composition, dynamics and culture of the arbitration community. These new forms of relationships and patterns of conduct are new in the context of public international law. These have created unprecedented challenges to the investment treaty arbitration system. New manifestations of attributes and social behavior of panelists demonstrate inadequacies of the existing standards, rules and procedures that govern panelists. This study surveys problematic patterns of social behavior of investment treaty adjudicators and shows how certain instances of social behavior inevitably or potentially jeopardize the very foundations of the system. This research empirically examines the voting behavior of two distinct groups of party-appointed panelists, and the results reveal a relationship between appointments and the decision-making attitude of adjudicators. It further methodically maps the pool of ICSID panelists and answers the question ‘who are ICSID panelists?’ It reviews the evolution of the attributes of ICSID adjudicators, assesses the composition of the ICSID pool, and evaluates the social interactions of this group of investment treaty adjudicators. To address the challenges that investment treaty arbitration faces, a radical and multidimensional shift is occurring in the system. This transformation is directed towards greater control over the qualifications and conduct of adjudicators. These developments reconstruct the composition of the pool of adjudicators and influence how they interact with other actors in investment treaty arbitration proceedings. The ongoing reform progress indicates that the attributes and behavior of future investment treaty adjudicators would likely be different from the characteristics and conduct of the contemporary generation of panelists.
URI: http://hdl.handle.net/1828/14772
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrators; Code of conduct; ICSID; Impartiality; Investment treaties; Investment treaty arbitration; Investments; Permanent court system; Qualifications; State practice

A critical analysis of the institution of business rescue proceedings during liquidation proceedings - Krishundutt, Sanam (University of KwaZulu-Natal, 2022)
South Africa is currently undergoing harsh economic times, and as such, many companies are feeling the brunt of the situation. As a result, these companies begin to trade at a loss and are left without any other option but to liquidate their affairs in order to pay off creditors. However, with the development brought by the Companies Act 71 of 2008 (“the Act”), business rescue was introduced. Business rescue is an alternative to liquidation and it allows the company to undergo rehabilitation and continue trading if certain requirements are met. Chapter 6 of the Act aims to assist businesses in providing some sort of relief in the form of business rescue to provide them with the breathing space that they require to try and become a viable business again. Just like any new formulated concept, it is susceptible to abuse. Many companies that are already under liquidation are suspending their liquidation in favour of business rescue, despite, in some instances, the liquidation order having already been granted against the company. The Covid-19 pandemic has made the question of whether a business can suspend liquidation proceedings in favour of business rescue more prevalent as the pandemic has caused a detrimental financial impact on a number of businesses. Now more than ever businesses find themselves struggling to keep afloat, and as a result many of them have to consider the avenues of liquidation or business rescue. This dissertation aims to look at both liquidation and business rescue proceedings and decipher whether the courts were correct in their decision regarding when business rescue proceedings can be instituted during liquidation proceedings. The importance of taking into account the above is due to the fact that many companies in present day are experiencing financial difficulties, and liquidation or business rescue proceedings are the options that they are left with. However, one has to carefully consider both options, taking into account the company’s financial circumstances. This is of importance, as one needs to establish if there is a reasonable prospect of rescuing the company or not. If there were, then business rescue would indeed be the route to be taken, but if not, then liquidation proceedings would be. However, many companies that have no prospect of being rescued, and that have already opted for liquidation may want to institute business rescue proceedings to delay the inevitable and frustrate creditors, thus leading to the abuse of the newly formulated concept, which has to be curbed.
Keywords: Business failure; Companies Act 71 of 2008; South Africa

Climate change and development : the global administrative law of the UNFCCC financial mechanism - Larrea, Gonzalo (European University Institute, 2022)
This research deals with the legal responsibility of states to provide climate finance to developing countries in order to facilitate climate mitigation and adaptation. The research demonstrates that the area of climate finance has not escaped globalization, where global actors operating at a level beyond the state (the UNFCCC and several Climate Funds) have increasingly taken over some of the climate finance functions previously performed by states. Against this backdrop, the thesis also examines the role of international bodies in providing climate finance, assesses to what extent these bodies are accountable to affected local stakeholders, and puts forward recommendations to foster increased accountability. The research project employs Global Administrative Law (GAL) as a normative framework for assessing and fostering accountability. This thesis is relevant, first and foremost, as an examination of the extent to which global climate finance is adequate for addressing climate change impacts in developing countries. To this end, it engages in a detailed analysis of the international legal framework for climate change and of the relevant financial instruments. It also engages in a normative evaluation of these instruments using the standards proposed by GAL. In keeping with this, the research gives substance and a better definition to these standards. As such, the thesis has the potential to contribute not only to the literature on climate finance, but also to the literature on GAL. It also sheds light on the relationship between climate finance and GAL, a topic that has been largely neglected in the academic literature so far.
Accepted: 2022-03-02T09:10:59Z
Keywords: Climate Change; Climatic changes; Environmental Law

Letters of credit and demand guarantees : a legal study on the impact of targeted financial sanctions from a South African perspective - Lupton, Cayle Selwyn (University of Johannesburg, 2022)
The purpose of this study is to provide a legal analysis of the impact of targeted financial sanctions on letters of credit and demand guarantees. The letter of credit is an important method of payment used in international trade. The demand guarantee plays a significant role as an instrument of security in commercial transactions. In their simplest form both instruments constitute an undertaking by a bank to pay a beneficiary against delivery of certain stipulated documents. Letters of credit and demand guarantees are known to be reliable and provide a considerable measure of certainty and predictability to the underlying transaction. Consequently, they have been described as the “lifeblood of international commerce”. Targeted financial sanctions entail assets freezing and prohibitions to prevent funds or other assets from being made available, directly or indirectly, for the benefit of designated individuals and entities. Endorsed by the United Nations and implemented by the vast majority of jurisdictions around the world, targeted financial sanctions are increasingly being used to combat financial crime, including money laundering, terrorism financing and weapon proliferation financing. Banks play a critical role in financial crime prevention and detection. Hence they have been identified as institutions that must comply with targeted financial sanctions. The relationship between targeted financial sanctions and letters of credit and demand guarantees has generally not been well documented. It is hoped, therefore, that this study will make a meaningful contribution to the jurisprudence on letters of credit and demand guarantees. In investigating the impact of targeted financial sanctions, the study can be categorised into three parts. Part one investigates a bank’s compliance with domestic targeted financial sanctions. The chief findings of the study in this regard are that banks are under a legal obligation to comply with sanctions and, as a result, a bank that refuses to perform its contractual obligations under a letter of credit or demand guarantee may have a defence in law. In South African law the bank can raise the so-called defence of legal impossibility of performance to resist a claim for, or potential litigation in respect of, payment. Part two investigates a bank’s compliance with foreign targeted financial sanctions. Because compliance in this regard has no (legal) basis, the bank may conceivably be sued by the beneficiary for payment on the basis of breach of contract. Part three investigates problematic documentary practices that banks have adopted or conceivably may adopt to manage their sanctions risk exposure. In this regard, attention is given to so-called sanctions clauses and other non-documentary conditions. The issue of unjustified amendments by the beneficiary for the purposes of sanctions evasion is also considered in part three. The general conclusion arrived at is that by interfering with payment, targeted financial sanctions render letters of credit and demand guarantees unreliable, thereby having the effect of reducing their value to international trade and commerce. The author proposes certain recommendations and initiatives aimed at mitigating the impact of targeted financial sanctions on credits and guarantees. Key terms: letters of credit; demand guarantees; financial crime; sanctions evasion; targeted financial sanctions; compliance; banks; due diligence; payment; reimbursement; credits; guarantees.
Keywords: Banks; Compliance; Credits; Demand guarantees; Due diligence; Financial crime; Guarantees; Letters of credit; Payment; Reimbursement; Sanctions evasion; Targeted financial sanctions

A critical analysis of the role, appointment, and powers of a business rescue practitioner - Luthuli, Bayanda Nompumelelo (University of KwaZulu-Natal, 2022)
No abstract provided.
URI: https://researchspace.ukzn.ac.za/handle/10413/20930
Keywords: Corporate rescue regime; Financially distressed companies; Judicial management

Relationship between International and Domestic Law in the Constitutions of the States of the Economic and Monetary Community of Central Africa - Mairema, Jacqueline (Journal of Law and Criminal Justice, 2022)
The purpose of this paper is to analyze the constitutional provisions relating to the relationship between international law and domestic law of the States of the Economic and Monetary Community of Central Africa reveals an ambivalent conception of the system relationships. This is all the more true since the choice of monism with primacy of international law is affirmed both formally and materially. Even if this variant of monism seems to be tempered by certain constitutional provisions, the treaties have considerable effects in the domestic legal order. Once integrated into the legal order through the modalities of insertion, treaties have a supra-legislative and infra-constitutional rank. However, some constitutions of the States of the Economic and Monetary Community of Central Africa, such as Gabon and Equatorial Guinea, have not enshrined constitutional provisions on the place of treaties in the legal order. The concern to safeguard the supremacy of the constitution and consequently of national sovereignty may justify such a constitutional practice.
Keywords: Droit d’origine externe; Dualism; Insertion; International law; Monism; Monisme; National law; System relationship; Sécurité juridique

Airport Charges Regulation: A Private Law Approach - Mei, Di (McGill University, 2022)
This thesis explores the regulation of airport charges, which is an important but marginalised topic. It particularly examines how private law instruments can play a role in the regulatory process. Airports used to be subject to traditional regulation, which operates in a command-and-control mode. As the airport industry becomes increasingly complicated, traditional regulation seems problematic. First, the method that is associated with traditional regulation to draw a line between regulated and unregulated airports has downsides. Second, the international regulatory framework on airport charges lacks binding rules. This suggests that traditional regulation is not the best niche for airport charges regulation. Third, good regulation needs independent regulatory bodies, which are hard to achieve in practice.In this context, this thesis argues that a private law approach can serve as a more flexible and effective way to regulate airport charges. There are two instruments under this overarching approach. First, contracts can be adopted to incorporate airport charges regulations. Second, robust corporate governance generates the effect of good regulation. This is an interdisciplinary work that has engaged air law, contract law, corporate law, competition law, and aviation business and management. It also employs the method of case studies. Chapter 4 examines the regulation of airport charges in the UK, Canada, and India. The three case studies demonstrate that private law instruments have been implicitly implemented to different degrees in these countries. These demonstrate the feasibility of applying private ordering in the regulatory process. I also look into the regulation of countries and regions including Australia, Ireland, the EU, and Germany throughout this thesis. This study also examines a specific sector of airport charges, namely, charges for ground-handling services. This sector possesses a unique feature in that it is between aeronautical and non-aeronautical services. A private law approach can also be adopted in the regulation of charges relating to ground-handling services. Additionally, ICAO as an important international organisation governing international air transport can also contribute to a private law approach of airport charges through its soft-law making function. This thesis aims to shed light on a private law approach, as an innovative regulatory mechanism, to airport charges. That said, regulation by this approach and traditional regulation are not contradictory but can cooperate to an extent, depending on how much power one wants to give to private ordering
Identifier: https://escholarship.mcgill.ca/concern/theses/8910k0504
Keywords: Airport; Regulation

The abuse of dominant position in digital markets: Google Shopping case - Moroni, Filippo (LUISS Guido Carli, 2022)
Abuse of dominance in the digital markets. Digital markets. Art.102 TFEU: how can it be applied to digital markets? A global perspective: the evolution of the abuse of dominance in digital markets around the world. Europe: the proposal for a regulation on contestable and fair markets in the digital sector (digital market act). United States of America: a time for reforms. China: a new approach towards digital markets. The Google Shopping case: the first step for competition enforcement in digital markets. The European Commission decision (AT.39740). The general Court decision (T-612/17). The Google case in the US: completely different results. A glimpse into the future: the Google Shopping case under the DMA.
Keywords: Abus de position dominante; Competencia; Competition law; Concurrence; Dominant position; Monopole

The use of blockchain technology in international commercial transactions, with specific reference to secured payments in international contracts of sale - Muza, Chido Teclar Mitchel (University of Johannesburg, 2022)
Please refer to full text to view abstract.
Keywords: Blockchains (Databases); Commercial law; Electronic funds transfers; Export sales contracts.; Foreign trade regulation

Conflict Management over Maritime Territories : Use of ADR in Maritime Disputes: Kenya vs Somalia - Mwala, Natasha Lulia (Universität Wien, 2022)
The recent discoveries of natural resources on both territorial and maritime borders have heightened the probability of conflicts between states specifically in the Horn of Africa and the Greater Lakes Region. As a highly volatile region, conflicts are not a foreign phenomenon which have been plaguing the region since transition to the post-colonial era. It is simple to argue that the cause of disputes is due to the arbitrary borders drawn by the European powers, however, the region is experiencing a contemporary ‘scramble and petition’ with countries racing to exploit and gain over the newfound resources. In addition to this, the rise of nationalist sentiments combined with the burgeoning population and struggle of governments to finance their domestic budgets while trying to reduce borrowing from foreign markets due to the inflation costs which makes it expensive, also plays a key role in the quest to benefit from mineral exploration and excavation. While traditional conflicts rose from land border disputes that escalated to violence especially between border communities, maritime conflicts tend to be handled in legal ways with parties seeking intervention from bodies such as the International Tribunal of the Law of the Sea (ITLOS) and the International Court of Justice (ICJ). Most cases are solved by outright delimitation of the maritime borders rather that joint management of marine land masses or natural resources based on mutual understanding or mutually assured benefits. The recent Kenya-Somalia Maritime dispute is an excellent case study. The aim of this research is to not only show alternative dispute resolution methods that can be used in maritime border disputes but also analyse the switch from pacific means of settlement of disputes to judicial intervention of the court. It begins by looking at the evolution of land border disputes between the two states, touches on the maritime dispute and their diplomatic, economic and security relationship. It further critically analyses the points of view of the two countries and the court’s ruling. Finally, it examines alternative dispute settlement mechanism that could have been used.
Keywords: ICJ; Joint maritime agreement; LOS; Maritime boundary dispute; Maritime délimitation; Memorandum of understanding

Articulating clearer fair and equitable treatment clauses within Tanzania’s international investment agreements: correcting the disparity between host state and international investor interests - Ntangeki, Joanitha (Canterbury Christ Church University, 2022)
International Investment Agreements seek to promote foreign investment whilst protecting foreign investors. Despite the goal of International Investment Agreements being to secure parity between the interests of the host State and the foreign investor, there has been consequential disparity in the protection of the interests of both parties. Notably, the host State is susceptible to disadvantage. This research examines the extent to which International Investment Agreements in Tanzania have facilitated this disparity. In particular, the research evaluates the inclusion of fair and equitable treatment provisions in Tanzania’s International Investment Agreements and the extent to which fair and equitable treatment provisions have in some way facilitated this disparity. The research examines systematically the fair and equitable treatment provisions contained in twenty IIAs signed by Tanzania between 1965 and 2013 (eleven of which are still in force). The research takes a comparative approach in evaluating and contrasting the Tanzanian provisions with other fair and equitable treatment clauses in IIAs signed by India, Morocco and the Netherland. The Tanzanian provisions are vague and non-uniform in comparison. The research is situated in the broader context of national sovereignty and the relationship between Tanzania and its foreign investors under international law. The substance of the analysis centres on foreign investors in the mining sector in Tanzania and the extent to which these investors have sought to take advantage of the fair and equitable treatment clauses in the IIAs in order to pursue their activities to the detriment of local populations. The research evidences the negative impact of their claims that changes in government policy (often aimed at benefiting citizens) amount to unfair treatment of the foreign investor. This has a significant impact on the ability of the government to develop its policies around sustainable development, environmental protection and the guarantee of human rights of the citizens of the host State. The research demonstrates that a clearer and fuller articulation of fair and equitable treatment clauses within Tanzania’s IIAs can act as a corrective to the disparity between the host State and the international investor. This requires that IIAs are drafted to include an exhaustive and full list of the State’s obligations towards the foreign investor so as to limit foreign investor claims against the host State. The impact of not doing so has grave implications for the rights of the citizens of Tanzania and unnecessarily tips the balance of power in favour of the foreign investor and away from the host State. This undermines the ability of the host State to assert its sovereignty within its own borders.
Permalink: https://repository.canterbury.ac.uk/item/9714v/articulating-clearer-fair-and-equitable-treatment-clauses-within-tanzania-s-international-investment-agreements-correcting-the-disparity-between-host-state-and-international-investor-interests
Keywords: Foreign investment; International investment; Investor interest; Tanzania

The Processes of Democratization and Economic Development in Africa: A Case Study of the Democratic Republic of Congo (DRC) Since 2006 - Otshudi Talo, Esperance (Near East University, 2022)

Rising from its ruins? The Southern African Development Community (SADC) Tribunal - Shumba, Tapiwa (Law, Democracy and Development, 2022)
The Tribunal of the Southern African Development Community (SADC) was established to ensure adherence to and the proper interpretation of the provisions of the SADC Treaty and its subsidiary instruments, and to adjudicate upon such disputes as might be referred to it. However, since its establishment, it has had a troubled history. After the rulings it made against the Government of Zimbabwe in the landmark Campbell land seizures case, the Tribunal's operations were unceremoniously suspended. This was followed by a process to revise its mandate, one that ultimately condemned it to paralysis and ruin. The new 2014 Protocol on the Tribunal, meant to revise the mandate of the Tribunal to confine it to hearing disputes involving states only, has been criticised as an attempt to undermine the rule of law and human rights in the region. Since the adoption of this 2014 Protocol by the SADC Summit, stakeholders have mobilised regionally to resist its ratification by member states. In particular, lawyers in SADC countries are embarking on legal petitions to reverse the Protocol and promote the revival of the Tribunal in terms of its old mandate. So far, there have been victories in these cases in two influential SADC member states, South Africa and Tanzania. However, it remains important to assess the significance of these developments. As such, the article raises the question: Is the Tribunal rising from its ruins?
Keywords: Regional integration; Rule of law; SADC Tribunal

Reassessing State Consent to Jurisdiction: The Indispensable Third Party Principle before the ICJ - Sparks, Tom (Nordic Journal of International Law, 2022)
Keywords: Adjudication; Advisory opinion; Certain Phosphate Lands; Chagos Archipelago; Consent; East Timor; Indispensable third party principle; International Court of Justice (icj); Jurisdiction; Monetary Gold

A Closer Look at the Doctrine of Separability in Arbitration - Todorović, Ilijana (IUS LAW Journal, 2022)
In the ever-growing business world impacted by globalization, many commercial contracts nowadays contain an arbitration clause. This article focuses on the history behind arbitration as an alternative method of dispute resolution and its penetration to the forefront of mechanisms for resolving commercial disputes -with focus on England, France, and the United States. The article also delves into some of the key questions related to the relationship between an arbitration clause and the underlying contract in which it is contained. And those are the infamous separability and competence-competence doctrines. The author’s conclusion is that the efficiency of an arbitration clause is feasible only if its autonomy is entrenched and safeguarded from preventative and baseless court intervention. In that regard, the author addresses the consequences, current challenges, judicial and academic discourse, and the need for improvement when it comes to these two arbitral principles -all with the goal to provide contracting parties with forethought as to what to consider when drafting their contracts as to avoid unwelcome consequences.
Keywords: Arbitrage; Arbitragem; Arbitration; Competence-Competence; Doctrine; International Arbitration; Issues of Jurisdiction

A legal comparison on the effectiveness of judicial management in Botswana against business rescue in South Africa - Topi, Sharon (University of Johannesburg, 2022)
Please refer to full text to view abstract.

Emergence in the WAEMU and EMCCA areas - Ntwali, Valéry IRAGI; Centwali, Guillain CIRHUZA (Studia Universitatis Babeș-Bolyai Studia Europaea, 2021)
The Economic and Monetary Community of Central Africa (EMCCA) and the West African Economic and Monetary Union (WAEMU) have succeeded in stabilizing their monetary systems, but this monetary stability has not been accompanied by real emergence. The economies of most of the member states of these two organizations are based on commodities and cocoa, which means that they are completely volatile and therefore lack the stability necessary for real emergence. This study based mainly on documentary research through the exploitation of reports produced by various international and regional institutions such as the IMF, the World Bank, the African Development Bank, ECOWAS, etc., and the writings of various emergence theorists, shows the role that industrialization and diversification of the economies of the WAEMU and EMCCA zones should play in the development of the economies of the member states and the improvement of the living conditions of the populations.
Keywords: CEMAC; Emergence; Spaces; UEMOA; WAEMU

The Impact of Covid-19 Pandemic on Women In Nigeria - Iheanacho-Shahid, Jennifer (African Journal of Politics and Administrative Studies, 2021)
The paper examines the impact of corona-virus pandemic on women in Nigeria. Emergencies and times of unrest have been linked with increasing reports of Gender Based Violence. Pandemics and Epidemics on the other hand are no exception. The COVID-19 pandemic has been associated with an increase in Gender Based Violence termed the Shadow Pandemic due to the control measures adopted in containing the spread of the virus. The paper adopted the Social Ecological Model to explain and understand the factors that contribute to the increase of Gender Based Violence against women during emergencies or natural disasters and how interaction of individual and environmental factors influence behavior and attitudes that create an atmosphere that encourages violence. The paper was based on secondary sources of data.  The findings of the paper revealed that the lockdown isolated women and attenuated opportunities for them to divulge the abuse or receive necessary support services or resources.  The paper also discovered that there has been an increased rate of reported cases of Gender Based Violence during the months of lockdown in Nigeria. The paper concluded that the corona-virus outbreak has exposed the shadow pandemic of violence and inequality and the exclusion of the Minister of Women Affairs and Social Development is a step in the wrong direction . The paper recommended that it is pertinent to integrate gender lens into disease response and protection mechanism and Gender Based Violence services should be termed as essential duties during crisis and emergencies.

Story of a legal codex(t) : writing law in code - Ma, Megan (Institut d'études politiques, 2021)
How is the law measured? For long, it appeared that the law cannot be measured. While there are standards and processes, the law was not regarded as quantifiable. Only in the advent of recent technological advancements in law have there been considerations for metrics. These technologies sought to tackle the legal field’s inherent protectionism fueled by deep asymmetries in information. Consequently, the rise in legal ‘metrics’ stems from an access to justice perspective. The assumption is that in making the law more quantifiable, knowledge that has been historically opaque and inaccessible outside of the legal community may be revealed.Alternatively, it may be argued that the law has always been measurable. Words, through linguistic devices, have shaped legal meaning. In effect, the law conceivably has been measured by its words. In fact, “law exists as text” (Hildebrandt, 2015). I further this line of thinking by investigating natural language as the key vessel through which the law has manifested itself. Does the law depend on natural language to do its work? Importantly, is the language sufficient at housing legal norms?This dissertation seeks to tell a narrative. Broadly, it chronicles the story of law’s intimate relationship with language. But more specifically, the thesis details the law’s recent encounter with the digital. When law met technology, its relationship with language changed, invoking skepticism around its fitness for the conveyance of legal concepts. With the introduction of an innovative player – code – the law had perceivably found its new linguistic match. As a result, code was tested for its ability to perform and accommodate for the law’s demands. Ultimately, confronted by natural language and code, the law is asked whether code can be its language. Comment mesure-t-on le droit ? Longtemps, le droit semblait résister à la mesure. Bien qu'il existe des normes et des processus, le droit n'était pas considéré comme quantifiable. Ce n'est qu'avec l'avènement des récentes avancées technologiques dans le domaine du droit que l'on a commencé à envisager une telle quantification. Ces technologies ont cherché à s'attaquer au protectionnisme inhérent au domaine juridique, alimenté par de profondes asymétries d'information. Par conséquent, l'essor de la "métrique" juridique découle d'une perspective d'accès à la justice. L'hypothèse est qu'en rendant le droit plus quantifiable, des connaissances historiquement opaques et inaccessibles en dehors de la communauté juridique peuvent être révélées.On peut également faire valoir que le droit a toujours été mesurable. Les mots, par le biais de dispositifs linguistiques, ont façonné la signification juridique. En effet, il est concevable que le droit ait été mesuré par ses mots. En effet, "le droit existe en tant que texte" (Hildebrandt, 2015). J'approfondis cette ligne de pensée en examinant le langage naturel en tant que vecteur clé à travers lequel le droit s'est manifesté. La loi dépend-elle du langage naturel pour faire son travail ? Plus important encore, le langage est-il suffisant pour abriter les normes juridiques ?Cette thèse cherche à raconter une histoire. De manière générale, elle relate l'histoire de la relation intime du droit avec le langage. Mais plus spécifiquement, la thèse détaille la rencontre récente du droit avec le numérique. Lorsque le droit a rencontré la technologie, sa relation avec le langage a changé, suscitant le scepticisme quant à son aptitude à transmettre des concepts juridiques. Avec l'introduction d'un acteur innovant - le code - le droit a visiblement trouvé sa nouvelle adéquation linguistique. En conséquence, le code a été mis à l'épreuve quant à sa capacité à fonctionner et à répondre aux exigences du droit. Finalement, confronté au langage naturel et au code, le droit se demande si le code peut être son langage.
Keywords: Connaissance du contexte; Contextual knowledge; Droit et informatique; Informatique; Langage juridique (informatique); Langages de programmation; Law and computation; Linguistics; Linguistique; Programming languages

Four Essays on Tax Transition Reform in Developing Countries - Adandohoin, Kodjo (Université Clermont Auvergne, 2021)
Ces dernières années, la plupart des pays en développement sont confrontés à la nécessité de concilier deux impératifs : d’une part, une demande sociale forte qui nécessite un besoin de ressources publiques supplémentaires, et d’autre part le désarmement tarifaire consécutif aux politiques d’ouverture commerciale, qui les prive de la majeure partie de leurs recettes budgétaires. D’où l’impérieuse nécessité pour ces pays d’assurer une transition dans la structure de leur prélèvement public c’est à dire de transférer la pression fiscale du commerce extérieur vers la fiscalité domestique. Cette thèse s’intéresse à cette problématique et vise à étudier les conditions de réussite d’un tel phénomène dans les pays en développement au travers de quatre essais empiriques. Le premier essai concerne le rôle de la TVA et des droits d’accises dans une première vague de transition. La TVA étant un impôt neutre et à très large assiette fiscale, cette dernière a été suggérée comme outil majeur pour réussir le transfert des ressources publiques du cordon douanier vers la fiscalité domestique et en complémentarité avec les droits d’accises. Nos investigations empiriques soutiennent cette assertion théorique et montrent que le couple TVA-accise joue bien ce rôle de substitut aux recettes de porte en quasi baisse suite au démantèlement tarifaire dans les pays. Néanmoins le rôle d’appui de la TVA et des droits d’accises est limité à partir d’un certain seuil de baisse des recettes de porte, qui traduit aussi le fait que le potentiel de mobilisation fiscale par la TVA dans ces pays est limité et qu’il faudra s’en préoccuper. Dans le second essai nous analysons la transition de seconde génération basée sur les impôts directs (impôts sur les revenus et impôts fonciers). Nous trouvons que les impôts directs sont des outils pauvres de transition fiscale dans les pays en développement. Pourtant, nous trouvons que le développement financier est un médiateur certain et incontestable à une politique de transition fiscale de seconde génération basée sur les impôts directs, car permettant de recouper l’information sur les revenus des contribuables et de générer des traces documentaires à l’administration fiscale, qui permettent d’envisager une mise à fiscalisation des contribuables, gage de recettes fiscales directes supplémentaires dans les pays. Dans le troisième essai, nous nous intéressons à l’effet de la mise en place d’une réforme de transition fiscale sur l’efficience dans la collecte des recettes en menant une étude de cas pour l’union économique et monétaire ouest africaine (UEMOA). Nos résultats supportent l’affirmative, en ce sens que la réforme accroit globalement une mobilisation efficiente des recettes dans la zone UEMOA. Cette efficience entrainerait par ailleurs avec elle une amélioration du climat des affaires dans la zone, suite à la mise en place de cette réforme. Enfin nous terminons cette thèse par un quatrième essai qui interroge quand à lui les impacts distributifs et de pauvreté d’une réforme de transition fiscale basée sur la TVA. Quoique les résultats montrent une incidence régressive de la réforme sur le revenu des ménages, une redistribution par la dépense aurait le mérite d’atténuer l’incidence sociale de cette stratégie de réforme sur le revenu des contribuables.
Keywords: 2SLS-IV model; Accises; Administration fiscale; Analyse des frontières stochastiques; Business climate; Climat des affaires; Computable general equilibrium; Contrôle Synthétique; Coordination fiscale; Corporate tax; Developing countries; Développement financier; Efficience; Efficiency; Effort fiscal; Excise; Exemptions; Exonérations; Financial development; Fiscalité; GMM; Harmonisation; Harmonization; Impôt foncier; Impôt sur le revenu; Impôt sur les sociétés; Income tax; Inequality; Internet; Inégalités; Micro-simulation; Modèle 2SLS-IV; Pauvreté; Pays en développement; Politique fiscale – Pays en voie de développement; Potentiel fiscal; Poverty; Probit and Logit; Probit et Logit; Propensity scores; Property tax; Réforme fiscale; Scores de Propension; Stochastic frontier analysis; Synthetic control; TVA; Tax administration; Tax coordination; Tax effort; Tax potential; Tax reform; Tax transition; Taxation; Taxes sur le commerce extérieur; Trade taxes; Transition fiscale; VAT; Équilibre général calculable

Abuse of dominance and the Internet : an assessment of the South African Regulatory Framework - Koornhof, Pieter Gerhardus Jacobus (Stellenbosch University, 2021)
While electronic commerce in South Africa is still comparatively small, it is growing rapidly. The advent of the internet has potentially fundamental impacts on business and the law both locally and internationally. It is submitted the free competition on the internet is important and will continue to be so in the future. The research in this thesis relates to the rise of so-called internet monopolies (such as Google, Facebook and Amazon) and its implications for competition law enforcement. A particularly problematic aspect of the products provided by some of these companies is that their products and services are ostensibly free to consumers. This thesis examines whether the traditional model for the regulating abuse of dominance would be effective in the instance where such an internet monopoly is charged with a contravention under South African competition law. The research and analysis in the thesis are effectively divided into three parts. The first considers whether abuse of dominance related to the internet deserves closer analysis and also assesses the purposes of competition law and how these are changing (or should change) in the light of new technology and markets. The second part deals with abuse of dominance both generally and specifically in relation to the internet. In this context, the thesis considers how harms may manifest and how dominance may be determined in the context of the internet. The final part considers specific issues that may be problematic in light of the internet. The interrelationship between intellectual property and competition law is analysed, along with aspects pertaining to the assertion of jurisdiction, the nature of competition law enforcement and the extent to which different jurisdictions may (and/or should) cooperate in dealing with abuse of dominance on the internet. The thesis submits that the South African legislative framework for regulating abuse of dominance on the internet is broadly fit for purpose, but that there is a need for developing new approaches and policy within that framework. It contributes to the existing body of knowledge and discourse by providing a comprehensive overview of the regulatory framework in South Africa, informed by comparative analysis; by applying this in a new context (hitherto under-researched in the South African context), and by offering concrete suggestions to frame policy and approach.
URI: http://hdl.handle.net/10019.1/123687
Keywords: Competencia; Competition law; E-commerce; Electronic commerce; Internet monopolies; South African competition law; South African legislative Framework

Adoption des normes IFRS dans l’espace OHADA : Fondement théorique, intérêt et enjeux - Nyasseu, Emma Joachim; Yepdo, Florentin Gaël; Tatang Atabonfack, Pulchérie Léonie; Myskinole, Cheguem Shupo Davine (International Journal of Financial Accountability, Economics, Management, and Auditing, 2021)
Du fait des changements profonds qu’apportent les nouveaux concepts sur lesquels se base le référentiel de l’IASB, le passage aux normes IFRS a été qualifié d’une révolution comptable. Le but d’harmonisation de cette institution se réalise à travers la diffusion mondiale progressive des normes IFRS. Toutefois, les entreprises de la zone OHADA sont concernées par ce changement. Compte tenu de la rareté des travaux de recherche dans le domaine, nous essayons d’analyser à travers ce papier, l’adoption de telles normes en contexte OHADA. Pour y parvenir, cet article rappelle le mécanisme de passage aux normes IFRS dans l’espace OHADA, étudie ensuite l’intérêt pour les entreprises de cette zone et enfin met en évidence les enjeux liés à un tel projet. Les principaux résultats montrent que loin d’être un simple outil de présentation et de communication de l’information financière, les IFRS constituent pour les entreprises de la zone OHADA, un levier d’attraction des investisseurs et d’intégration économique.
Keywords: Normalisation comptable; Normes IFRS; OHADA; Référentiel; Révolution comptable

Botswana’s Anti-Money Laundering and Combating the Financing of Terrorism Regime - Tshiamo-Kgati, Kuda (University of Pretoria, 2021)
Money laundering, the financing of terrorism and proliferation financing continue to be serious threats to the stability of the international financial system. The international community therefore has prioritised the fight against these activities. For example, international bodies such as the Financial Action Task Force (FATF) and others have developed standards and recommendations against which countries and organisations are measured in this regard. Against this background, this thesis investigates to what extent Botswana’s legislative framework regarding money laundering, terrorism financing and other illicit financial flows complies with international standards, especially the FATF Recommendations. The study sets the scene by defining and describing money laundering, financing of terrorism and proliferation financing, after which the current statutory framework in Botswana is discussed in detail. After subsequently setting out the various global and regional (specifically African) initiatives in the fight against money laundering and other financial crimes, the current state of affairs in Botswana is benchmarked against both the South African framework as well as the FATF Recommendations. The investigation is limited to a technical assessment (doctrinal analysis) of Botswana law to determine the current compliance (or lack thereof) of the country’s statutory provisions and to make recommendations regarding how the framework can be improved. It is difficult for some countries, especially African countries like Botswana, to comply fully with the FATF Recommendations, since compliance can be expensive and dependent on high levels of expertise on the part of the relevant authorities. Therefore, such more vulnerable countries tend to face a higher risk of being used as conduits for money laundering and related activities. Despite these and other challenges, Botswana has gone to great lengths to re-assess and improve its anti-money laundering and combating the financing of terrorism (AML/CFT) legislation with a view to move towards full compliance with the FATF Recommendations. Nevertheless, the evaluation indicates that there are some remaining shortcomings in Botswana’s legislation. Consequently, the thesis concludes by proffering certain recommendations towards ensuring that Botswana’s AML/CFT legislation is rendered fully compliant with the FATF Recommendations.
URI: https://repository.up.ac.za/handle/2263/82675
Keywords: AML/CFT; Anti-money laundering; Botswana; Financement du terrorisme; Financial law; LBC/FT; Lutte contre blanchiment de capitaux; Money laundering

Challenges and solutions for the harmonisation of contract law within the BRICS countries. Invalidity of contracts and hardship - Veronese, Lígia Espolaor (Universidade de São Paulo, 2021)
The present thesis is concerned with a comparative study of contract law applicable in the BRICS countries Brazil, Russia, India, China and South Africa with a strong focus on the issues of invalidity of contracts and hardship. The purpose is to identify commonalities and divergences in these systems with different legal backgrounds, particularly the influence of civil law tradition in Brazil, Russia and China as opposed to common law in India, and the mixed system in South Africa. Among the identified divergences and challenges, the thesis purports to demonstrate that the obstacles are not insuperable and that there are rooms for the harmonisation and compatibility within the BRICS context with respect to the two selected topics of contract law. Even when full harmony is not reached, the research also purports to demonstrate that some countries may benefit from others divergent experiences. Detecting mutual contribution is of particular relevance to this group of countries, since they share the characteristic of being evolving systems which have undergone recent reforms in their legislation on contract law and may be more open to assess and incorporate more efficient contract practices.
Keywords: BRICS; Brazil; Common law vs. Civil law; Comparative law; Contract law; Contribuição; Contribution; Direito comparado; Direito contratual; Hardship; Harmonisation; Harmonização; Invalidade dos contratos; Invalidity of contracts; Russia; South Africa; Validade dos contratos; Validity of contracts

The (Domestic) Enforcement of AU International Economic Law Instruments: Exploring the Desirability of Direct Effect - Simo, Regis Yann (The Emergent African Union Law: Conceptualization, Delimitation, and Application, 2021)
This chapter deals with the principle of direct effect as applied in European Union law and explores its suitability in the enforcement of African Union (AU) legal instruments, notably those setting up the African Continental Free Trade Area (AfCFTA). What motivates the issue of direct effect is the noted reticence of African countries to litigate trade matters between themselves despite the existence of provisions of regional trade treaties creating courts of justice which give standing to Member States. Therefore, it surveys the avenues through which natural and legal persons can uphold their rights stemming from AfCFTA treaties thus contributing to treaty interpretation and increasing security and predictability. Currently, the AfCFTA Dispute Settlement Protocol, modelled after the WTO, does not allow such a possibility, contrary to rights acquired by natural and legal persons before some African Regional Economic Communities (RECs) courts. Nevertheless, this chapter finds that carving out access of natural and legal persons to AfCFTA proceedings may not always work as intended since there are other ways to bypass these obstacles. These loopholes could be the gateway through which direct effect will develop and become a principle of AU law broadly speaking. These gaps further complement this chapter’s suggestions to explore amending the AfCFTA legal instruments, even though its dispute settlement system is yet to be tested, in order to match the standing that natural and legal persons have acquired under the RECs, which, in fine, are building blocs towards achieving the AfCFTA and, eventually, the African Economic Community.
Keywords: AfCFTA; Africa; Direct effect; International Economic Law; International Law; International Trade Law; Regional courts; Regional integration

Soft Law in International Investment Law and Arbitration - Adinolfi, Giovanna (The Italian Review of International and Comparative Law, 2021)
In the more recent decades, international investment law (“iil”) and arbitration have been going through a process of recalibration prompted by both the intensification of cross-border capital flows and the States’ growing concerns over the potential restraints iil may impose upon the pursuit of public interests. The present contribution will pay attention to a specific feature that can be observed within these developments, i.e. the role played by soft law in investment arbitration and, more generally, under iil, also with a view to assessing the impact on the formation of binding international law of instruments formally devoid of normative force within the international legal order. After an introduction (Section 1), the contribution is articulated into four sections. Section 2 will first define the field of investigation. The case law of investment tribunals and the treaty practice under the more recent iia s will be then explored as to the reliance on soft law instruments for the purposes of settling procedural (Section 3) and substantive issues (Section 4). Some final remarks will close (Section 5).

Arbitration as a Legal Mechanism in the Settlement of Disputes under Cameroonian Law - Tambe, Hans; Forbi, Nduah Esther; Epie, Mousinga Adele (Social Science Research Network, 2021)
Recently, commercial activities in the state of Cameroon are evolving and there is an inflow of investors from within the OHADA Zone and other regions of the world to Cameroon. This has led to the proliferation of commercial contracts such as concession contracts, production sharing agreements, risk contracts between the Republic of Cameroon and foreign investors, or contracts between individuals of foreign countries as well as with Cameroonian nationals. Commonly, contracts may be breached and disagreements surface among the contracting parties. The difficulties pose is in the manner to settle such disagreements in a friendly manner to maintain the relationship between the parties and to enables the contracting parties to resolve the disputes more cost-effectively and increase business efficiency in Cameroon. However, the state of Cameroon has a favorable attitude towards bilateral and multilateral investment treaties to guarantee protection to investors in the territory. This elucidates the reason why the government of Cameroon has enacted laws and ratified regional and international treaties, aimed at safeguarding a smooth atmosphere for investors and other commercial traders particularly in the domain of arbitration to help in resolving disputes in case of any disagreement among contracting parties. This article will present the authorities involved in arbitration with the experience regarding the application of the various law and institutions concerned with the arbitration. This will also help contracting parties or investors to understand the legal mechanisms in the settlement of disputes through arbitration in Cameroon.
Keywords: Arbitrage; Arbitragem; Arbitration; dispute; legal; mechanism; settlement

Legal Guide on Agricultural Land Investment Contracts - UNIDROIT; IFAD (UNIDROIT/IFAD, 2021)

Firm Performance, Financial Constraints, and Dual-Class Share Structure - Ahamed, Fatematuz Tamanna (Victoria University of Wellington, 2021)
This thesis addresses two aspects of financial constraints focusing, firstly, on the impact of financial constraints on firm performance and, secondly, on the impact of dual-class share structure on financial constraints. The first issue has been addressed in a large number of research studies, but the results are mixed. This study, therefore, conducts a meta-analysis of those earlier studies to provide a summary view of the results which, in contrast to narrative reviews of the empirical literature, provides an objective overview. The second issue examines the impact of dual-class share structures on financial constraints. The period of the global financial crisis is used to test the impact of the state of the economy on that relationship. To examine the impact of financial constraints on firm performance, 26 empirical studies with 189 effect sizes representing listed firms have been analysed. The study finds that overall there is a positive relationship between financial constraints and firm performance. The study also shows that the set of market-based measures of firm performance has a significant negative impact on the relationship, compared with the set of accounting-based measures. In terms of the financial constraints measure, the set of external financial constraints measures have a positive and highly significant impact on the relationship. The meta-regression analysis suggests that the choice of measure, regional difference, journal quality and publication status all have a significant impact on the relationship, and explain the variation in the association. To examine the impact of dual-class share structures on financial constraints the study analyses a sample of non-financial US firms over the period 2002-2018. Share structure is measured by the existence of a dual-class structure and also by excess voting rights and the proximity of the superior class shareholders in such structures. The study also shows that if financial constraints are measured by the WW index, irrespective of how dual-class share structure is measured, it increases the level of financial constraints. Similar results are obtained where financial constraints are measured by the KZ and SA indexes, except where dual-class share structure is measured by the proximity of superior class shareholders. The study also finds that if financial constraints are measured by the WW index, dual-class had a reduced impact during the period of the global financial crisis, thus, providing support for the propping theory. However, if financial constraint is measured by the SA index, dual-class share structure appears to have an increased impact during the GFC years. Among the additional tests, the HM index has been used as a measure of financial constraints, and the findings show that the impact of dual-class structures on financial constraints appears to be driven by their effect on debt constraints. The study also shows that firm age moderates the impact of dual-class share structures if financial constraints are measured by the WW index. The KZ, WW, and SA indexes are based on firm characteristics and, therefore, the study also tests for an impact of dual-class structures when financial constraint is measured by a text-based index, the BLM index. However, the results do not provide evidence of an impact in that case.
Keywords: Dual-class share structure; Financial Accounting; Financial Constraints; Firm Performannce; Meta analysis

Comparison of Egyptian and English Mediation Procedures in Construction - Swelam, Ahmed; Eldosouky, Adel Ibrahim; El Korany, Tamer Mostafa (Journal of Engineering Research, 2021)
The mediation process is the parties' will to the dispute to reach an amicable, non-binding settlement to end their dispute. The Egyptian legislature adopted the idea of issuing a draft law on mediation in civil and commercial matters to settle disputes between the parties, whether before the litigation stage or after appearing before the courts. The Egyptian Ministry of Justice held many community dialogue sessions to find the final version of the draft law. However, the concerned authorities have not issued the law until writing this paper. This research aims to compare and analyze the Egyptian mediation procedures and the British mediation procedures to improve, develop, and enhance the Egyptian ones especially the draft law as well as overcoming the obstacles that hinder the spread of mediation. On the one hand, presenting the Egyptian procedures in the draft mediation law and the rules of the Cairo Regional Center for International Commercial Arbitration, CRCICA. On the other hand, the British procedures represented in the Institute of Civil Engineers' mediation rules, ICE.
Keywords: Egypt; England; Mediation

Big Data and Global Trade Law - Burri, Mira (Cambridge University Press, 2021)
This collection explores the relevance of global trade law for data, big data and cross-border data flows. Contributing authors from different disciplines including law, economics and political science analyze developments at the World Trade Organization and in preferential trade venues by asking what future-oriented models for data governance are available and viable in the area of trade law and policy. The collection paints the broad picture of the interaction between digital technologies and trade regulation as well as provides in-depth analyses of critical to the data-driven economy issues, such as privacy and AI, and different countries' perspectives. This title is also available as Open Access on Cambridge Core.
Keywords: AI; Artificial Intelligence; Big data; Blockchains (Databases); Data protection––Law and legislation; Foreign trade regulation; Inteligência artificial; Intelligence Artificielle; Law and legislation; Transborder data flow––Law and legislation.; World Trade Organization

The inclusion and assessment of climate related and environmental related risks in the banking industry: the UniCredit case. - Gioia, Giovanni Luigi (LUISS Guido Carli, 2021)
The nexus between climate-related risks and financial risk. From nuclear to climate apocalypse. The turning point: Paris agreement and UN 2030 agenda for sustainable development. The VUCA world. The European Union as pioneer of ESG revolution. Climate-related risks in the banking sector. The EBA framework of ESG risk for financial institutions. The principles for responsible banking. Environmental-related risk assessment. The mispricing of the environmental-related risks. The environmental-related disclosure as a risk mitigation tool. How do UniCredit assess, monitor and mitigate climaterelated risks. UniCredit’s financial risk management framework. Comparison with KPMG benchmark.

Post award arbitral tribunal's mandate under the UNCITRAL Model Law and national laws based thereon - Al Hyari, Omar Hisham; Al Ani, Abdullah Rabee (Heliyon, 2021)
The UNCITRAL Model Law on International Commercial Arbitration provides for the extension of the mandate of the arbitral tribunal post issuance of the final award for the issuance of correction, interpretation, additional award, and remittance of the award back to the arbitral tribunal to remove grounds for challenging the award. Using a doctrinal approach, this paper examines the deviations of the national laws of adopting jurisdictions from the Model Law in regards to this extended mandate, and evaluates the improvements and drawbacks in these deviations. Mainly, the findings of this paper are that, of the many deviations, the positive changes are those that provide comfortable and lenient default provisions for the benefit of inexperienced parties, and since correction, interpretation, additional award, and remittance are useful provisions that are designed to help self-rectify the arbitral process, without adversely delaying it, then the changes that increase the efficacy of these provisions are welcomed. On the other hand, unnecessary deviations are seen as drawbacks that hinder the harmonization of national arbitration laws aimed at by the Model Law. The adopting jurisdictions shall be limited to those acknowledged as such by the UNCITRAL.
Keywords: Additional award; Arbitrage; Arbitragem; Arbitration; Arbitrators' mandate; Award; Correction; Interpretation; Model Law jurisdictions; UNCITRAL Model Law

Reasonable awareness in compensation for infringement of IP rights - Vanbrabant, Bernard; Glorieux, Dietger (Revue de Droit Intellectuel. L'Ingenieur-Conseil, 2021)

Value Relevance of Integrated Reporting using a Novel Approach: Comparative Cross Country Evidence of Mandatory and Voluntary Implementers - Mohaimen, F. J. (Victoria University of Wellington, 2021)
This thesis examines the value relevance of accounting information under integrated reporting (IR) in a comparative mandatory and voluntary setting. A meta review is conducted of all published work focusing on integrated reporting since 2011, which provides detailed insight into the gaps in the IR literature. Multiplicative log-linear model is used in measurement, which is a novel technique that mitigates the shortcomings of traditional value relevance models. The findings show that value relevance of summary accounting information increases after the implementation of IR in the mandatory setting. In the voluntary setting, market effect and the existing reporting paradigm effect the value relevance of accounting information under IR. If the market is large and existing reporting requirements are robust voluntary adoption of IR has minimal to no effect. However, in smaller markets with less rigorous reporting environment, adoption of IR does result in increased value relevance of accounting information. Compared to traditional models, the multiplicative model provides estimates that are more stable over time and shows better explanatory power. Overall, the findings of this thesis show that capital providers value the information content of IR under specific circumstances. This thesis contributes to the IR and value relevance literature by providing the first comparative cross-country evidence of the effect of IR in the change in value relevance of reported accounting information. It provides policy relevant input to the standard setters of IR by demonstrating the effect of IR in the decision usefulness of summary accounting information. The thesis further provides robust evidence of the efficacy of using the multiplicative log-linear model in measuring value relevance instead of the traditional linear additive models.

Compensation for Regulatory Expropriation in International Investment Law - Khachvani, David (Université de Genève, 2021)
The States, international organizations and interest groups are increasingly concerned with treaty claims of foreign investors, who sometimes seek compensation for the States' legitimate regulatory measures, such as tobacco plain packaging, nuclear energy phase out and environmental regulations. International investment law has yet to develop a comprehensive and predictable framework addressing some of the basis questions related to compensability of legitimate regulatory measures. The thesis carries out a comparative legal analysis to identify the key features of the prohibition of uncompensated expropriation as a general principle of law, and explores the rationale of that principle in political philosophy. Equipped with the results of this analysis, it proceeds to propose an analytical approach addressing practical questions related to the compensatory protection of foreign investments.
Keywords: Climate Change; Compensation; Expropriation; Investments; Police Powers; Regulatory Powers

Legal Protection of Foreign Direct Investment in the OHADA Area - Ngoya, Dominique (Social Science Research Network, 2021)
This paper analyzes the protection of Foreign Direct Investments in the OHADA area, specifically, its regulation by the Treaty of Organization and Harmonization in Africa of Business Law (OHADA Treaty). It is to restore legal and judicial security within their scope that OHADA member countries have undertaken to harmonize and unify their economic sector legislation to attract foreign investment as a factor in economic development. Several national and international legal instruments are responsible for the protection of foreign direct investment in OHADA countries. Indeed, the volume of foreign direct investment (FDI) to developing countries increased considerably during the 1990s; As Africa is now one of the favorite destinations for Western and even African investors, it is becoming a very profitable continent for investors. However, the issue of regulating or securing foreign investment in African countries is still flawed. The establishment of OHADA, in a way, is in the same direction; if we stick to the purpose of the organization prescribed in paragraph 5 of the preamble to the OHADA Treaty, which states that the purpose of the OHADA law is to "promote the growth of economic activity and encourage investment." Unfortunately, this objective remains only an announcement of the preamble to the Treaty, because of the definition of business law given by Article 2 of that treaty. However, the list of subjects is not exhaustive, investment remains absent. Thus, foreign investment is not regulated by the OHADA Treaty, so even investment-related activities are held by other subjects (corporate law, commercial law, and security law). The omission of FDI in the scope of the OHADA Treaty leads us to raise the question of its regulation.This work proposes a reflection that the OHADA Treaty should be modernized through reform including investment and many other issues to deal effectively with the issue of foreign investment given the ineffectiveness of national and sub-regional instruments in this area.
Keywords: Foreign direct investment; Investment Law; Investment Protection; OHADA

A developing country's perspective on forum shopping and long arm jurisdiction in light of US and UK insolvency laws - Gatoto, Phoebe Njoki (Nottingham Trent University, 2021)
The trend for multinational companies has been a preference to forum shop rather than to open insolvency proceedings in developing countries. The US and the UK are prime venues for such bankruptcy tourism enabled by long-arm jurisdiction through extraneous connection. At the same time, there has been a pattern in developing countries of insolvency law reforms which have been circumvented when multinational companies forum shop. Using doctrinal and comparative methodologies, this thesis examines how forum shopping and long-arm jurisdiction to the US and UK affect the efforts of developing countries to reform their insolvency laws and their possible effects on local stakeholders of multinational companies in developing countries. Additionally, the thesis proposes a longer-term strategy of dealing with forum shopping and long-arm jurisdiction by using the concept of centre of main interests ('COMI') as the basis for opening main insolvency proceedings. To ensure that the proposed insolvency procedural legal law is implemented uniformly, the thesis proposes the creation of a supranational court from which national courts, insolvency practitioners and multinational companies can request clarifications on the provisions of the proposed insolvency procedural legal framework. The thesis identified that developing countries require effective insolvency laws and institutions and highlighted key principles that should be included in the reforms. The hope is that developing countries can improve their insolvency laws and institutions to a global standard. Once the proposed insolvency procedural legal framework is implemented, multinational companies will be encouraged to utilise them once jurisdiction is identified through the COMI test rather than forum shopping.
https://irep.ntu.ac.uk/id/eprint/46506/

La publication des informations sociétales suivant les lois comptables revisées OHADA - Guimezap Épse Choukem, Claire (Revue Française d'Economie et de Gestion, 2021)
Dans un contexte marqué par le développement durable, le législateur OHADA n’a eu de cesse d’être accablé de toutes parts pour son statisme vis-à-vis de la montée des problématiques sociétales. Au lendemain des reformes du système comptable OHADA, les problématiques sociétales ont une fois de plus raté le rendez-vous de la normalisation. Toutefois, de nombreuses entreprises continuent à publier leurs informations sociétales parallèlement à leur communication financière. A cet effet, le problème que soulève cet article est celui de la compréhension des modes de production et de diffusion des informations extra-financières en l’absence d’une réglementation en la matière. Une étude empirique de nature descriptive est menée auprès d’un échantillon de 120 entreprises diffusant leurs informations sociétales au sein de l’espace OHADA. Il en ressort que le site internet et l’implication dans le développement de la communauté locale sont apparue respectivement comme support et thème de diffusion les plus utilisés dans l’espace OHADA en matière de reporting sociétal sous la pression de certaines parties prenantes notamment les associations consuméristes, les départements ministériels en charge de l’environnement, du travail et de la sécurité sociale. In a context marked by a widespread awareness of the needs of sustainable development, the OHADA legislator has been constantly burdened on all sides for its statism to the rise of societal problems. However, After the reform of the OHADA system, sustainability problems once more did not met up with the appointment of normalization. However, several enterprises continue to publish their societal information in parallel with their financial communication. As such, the problem raised by this article is that of understanding the mode of production and disclosure of non-financial information in the absence of a regulatory framework. A descriptive empirical analysis is carried out with a sample of 120 enterprises which propagate their societal information in the OHADA zone. It reveals that internet websites and implication in the development of the local community are respectively the medium and theme of the most used disclosures in the OHADA zone with regards to sustainability reporting under the pressure of some stakeholders especially consumer associations, ministerial departments in charge of the environment labor and social security.
Keywords: Accounting law; CSR; Corporate Social Responsibility; Droit comptable; Information sociétale; Parties-prenantes; RSE; Responsabilité Sociétale de l'Entreprise; Stakeholders

Corporate Social Responsibility, Corporate Governance and Banking Performance in the CEMAC Region - Fondem, Divine (Liberty University, 2021)
This researcher examined the effect of corporate governance (CG) and corporate social responsibility (CSR) on banking performance in the Central African Economic and Monetary Community (CEMAC) region. The data was obtained from the Worldwide Governance and the World Bank sovereign database from 2003 to 2018. This study employs the z-score to proxy the CSR factors such as labor force participation rate, population density, and renewable energy. The results reveal that the fixed effects model is superior to the pooled ordinary least square (OLS) and the random-effects model. The findings show that CSR has a significantly positive relationship, while CG has a positive but insignificant relation with banking performance in the CEMAC region. It suggests an ineffective implementation of CG strategies in the entire CEMAC region.
Keywords: Banking Performance; CEMAC; CSR; Central Africa Economic and Monetary Community; Corporate Social Responsibility; Corporate governance; RSE

Legal Challenges in the Enforcement of Foreign Arbitral Awards in Nigeria - Kudirat, Magaji (University of Ilorin, 2021)
Businessmen have a choice in the resolution of disputes, they may elect litigation or submit to arbitration. Delays, outrageous cost and undue technicalities associated with courts, makes commercial arbitration the preferred mode of settlement in the business world. However, the recalcitrance of an award-debtor to comply with the terms of the award necessitates the intervention of the courts. Nigeria has provisions for enforcement of foreign arbitral awards within her legal system. However, reliance on courts for enforcing foreign awards frequently frustrates the gains initially made by arbitration. Enforcement of arbitral awards via the courts has numerous legal challenges. This study is therefore aimed at analysing the challenges facing enforcement of foreign awards in Nigeria. The objectives of the study were to: (i) analyse the impact of extant legal regimes on the recognition and enforcement of foreign awards in Nigeria; (ii) examine the effects of the concepts of arbitrability and public policy exceptions on the enforcement of awards in Nigeria; (iii) examine the challenges inherent in judicial review on the enforcement of foreign awards in Nigeria; and (iv) examine the adequacy of the Arbitration and Conciliation Act 1988 (ACA 1988) in the recognition and enforcement of Islamic commercial arbitral awards. The study employed doctrinal methodology of legal research where primary and secondary of legal materials were subjected to descriptive and content analysis. The primary sources used were legislations, regulations, treaties, conventions and case laws, while secondary sources used were texts books, journals, internet materials, conferences and seminars papers. The findings of the study were that: i. the provisions of the laws regulating enforcement of foreign arbitral awards in Nigeria, particularly, Sections 51 and 54 of ACA 1988 have inherent and procedural defects, thus preventing the smooth enforcement of the award; ii. the narrow interpretation by the Nigerian courts on ‘arbitrability’ based on Sections 54 and 57 of ACA 1988 which restricts disputes to contractual and commercial disputes only, prevents the enforcement of foreign awards from jurisdictions with liberal interpretation. iii. the amorphous nature of the scope of public policy creates a challenge for the courts in Nigeria in determining whether a foreign award violates the country’s public policy or not; iv. the powers of the courts to set aside foreign awards based on grounds contained in Sections 29, 30 and 48 ACA 1988 are open-ended and allow the courts to examine the merit of the disputes rather than limit themselves to the validity of the award for enforcement; v. the provisions of ACA 1988 on enforcement of foreign arbitral awards do not consider the idiosyncrasies of awards from Islamic law jurisdictions, despite growing investors’ interests in Islamic commercial transactions. The study concluded that it is obvious that the various legal challenges identified showed that the existing legal frameworks on enforcement of foreign arbitral award in Nigeria are weak and ineffective. The study therefore recommended that the Nigerian arbitral laws in particular, the provisions on enforcement of arbitral awards under ACA 1988 should be amended.
Keywords: Enforcement; Foreign Arbitral Awards; Legal Challenges; Nigeria

The Role of Alternative Dispute Resolution (ADR) in Dispute Settlement of Logistics Activities - Quan, Gao (International Journal of Trend in Scientific Research and Development, 2021)
The Alternative Dispute Resolution (ADR) provides a non-litigation settlement mechanism for the parties of logistics activities. The advantages of ADR are highlighted in logistics dispute resolution due to the characteristics of logistics dispute and the difficulties faced in the litigation procedure. In the dispute resolution process, ADR means a simple, cost-efficient, and convenient method for the parties involved to settle disputes quickly, flexibly, and friendly. With its legitimacy and rationality, ADR should be the preferred choice for the parties involved in logistics dispute resolution.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitration; Dispute settlement; Litigation procedure; Logistics activities; MARD; Mediación; Mediation; Mediação; Médiation

The legal nature of debt securities in South African law - Beer, Johan Philip de (Stellenbosch University, 2021)
The problem statement of this thesis is ascertaining the legal nature of debt securities in furtherance of a consistent and coherent legal description of the South African positive law as it relates to this class of instruments. It focuses on four core issues: the legal history, legal nature, classification, and current legal issues relating to debt securities. Historical and analytic-systemic approaches to the problem statement make up Part 1 of the study. The historical approach shows an emergent commoditisation of debt, which is an important phenomenon in the analysis of securities law. It further shows a great deal of English influence in the development of the South African legal environment, most notably in terms of company law (as the primary driver of securities law) and the financial marketplace, its institutions and its regulation. Also highlighted is a notable scarcity of debt securities relative to equities, which materially impacted legislative developments. Finally, it points to an increase in the legal importance of the “securities” concept as a legal term to describe and govern debt and equity securities. Thereafter the analytic-systemic approach is used to identify a set of private law-rooted first principles applicable to South African registered securities, and herefore to debt securities as well. It posits that these securities should be understood conceptually as comprised two interdependent but functionally separate legal objects, rather than in terms of two different kinds of ownership (i.e. beneficial and registered). The first object is the "security instrument”, a locus for (holdership of) the incidents that flow from the entitlement of determination (beskikkingsbevoegdheid) over the underlying complex of rights and competencies of registered securities. These can be understood as incidents of execution. The second is the "security asset”, a locus for (holdership of) the incidents that flow from the entitlement of enjoyment (genotsbevoegdheid) over that underlying complex, and corresponds with the proprietary, patrimonial dimension of securities. These can be understood as incidents of enjoyment. This construction enables a more coherent understanding of the sui generis relationship of agency between beneficial owner and her nominee, as well as of the dynamics of ownership and quasi-possessio. These insights are then applied to the uncertificated environment, addressing a number of difficult and uncertain problems within the system that enables uncertificated securities and their holdership. Finally the particularly difficult issue of how to classify (and therefore identify) debt securities is dealt with. Here it is concluded that a typological approach is the only viable methodology to deal with this problem, and a number of necessary and thereafter possible classificatory indicia are outlined for this purpose. The functional-policy approach makes up Part 2 of the study. It is a policy-aware application of the theoretical framework developed to a select number of themes and legal issues of the current environment. Principally it shows that the reconceptualisation of registered securities has explanatory and problem-solving value, specifically relating to transfer, the granting of limited real interests, good faith acquisition, and the protection of holdership of certificated and uncertificated securities.
URI: http://hdl.handle.net/10019.1/110018
Keywords: Beneficial ownership; Debt and equity Securities; Securities; Securities industry; South Africa; Titre de créance

Mediation: Is There a More Promising Future? The Case of the Cairo Business Community - Soliman, Cherine (Arab Journal of Administration, 2021)
In an era of economic distress, some organizations have found refuge and growth potential in cooperation. Mediation, a highly recommended cooperative concept, has been enabled in certain countries but not all. Some applications lacked local cultural support making it, despite government efforts, a failure to launch. In this article, we investigate attempts to launch mediation in the Cairo Business Community (CBC). This study enabled us to revisit how Egyptian culture was prototyped by Hofstede and to question its representativeness. Hofstede has consistently described Egyptian culture as being highly cooperative / collectivist but our observations indicate that this culture is now more of an individualistic / competitive type, due to the tremendous economic difficulties that Egyptian society is going through. These difficulties and their impact on culture are at the heart of the explanation of the failure to launch mediation in the CBC.
Keywords: Cairo Business Society; Conflict Resolution; Culture; Egypt; Mediation

Combating insolvency and business recovery problems in the oil industry: proposal for improvement in Nigeria's insolvency and bankruptcy legal framework - Olujobi, Olusola Joshua (Heliyon, 2021)
Insolvency and business recovery laws in Nigeria have not evolved to incorporate reorganisation, reforming insolvent oil firms' operations to boost commercial oil firms' steadiness and economic suitability like other moderately developed countries. In Nigeria, liquidation is understood by many as the panacea to indebtedness. The research evaluates the Nigerian insolvency and business recovery legal regime to sustain indebted oil firms from economic shocks due to the global decline in the oil price to avert imminent business failures due to insufficient cash flows. The aim is to fill the gaps in Nigeria's insolvency and business recovery laws by recommending a model for the sustenance of oil firms and to suggest the reform of the gaps identified in the existing laws and the extant literature on the subject. The paper opted for conceptual legal review, comparative legal and policies analyses of solvency and business recovery legislations in Nigeria, Malaysia, India, South Africa, the United Kingdom and the United States. These nations were designated for this study because their insolvency and business recovery legal regime are business rescued driven, not winding up centred. The study is library research-based to address some of the flaws in Nigeria's insolvency and business recovery laws. The study finds that Nigerian legislation on insolvency is flawed in oil firms' salvage, improvement and rearrangement. It ends that, statutory bodies in the designated case study nations are efficient than those in Nigeria due to the strong political will of their governments in supporting insolvent oil firms for successful financial recovery, to safeguard jobs, to protect creditors and to enhance the wealth of their nations through sound business recovery policies and laws. The study, advocates, remodel of Nigeria's insolvency and business recovery legislations and policies in compliance with the international standards on insolvent oil firms salvaged and creditors focused policies for a robust economy. The study concludes with the recommendation for further study to consider quantitative analysis research methodology to project further scholarship on the subject.
Keywords: Creditor; Insolvency and business recovery laws; Nigeria; Oil firms

The impact of multilateral trade agreements on intra-regional trade : the case of SADC and ECOWAS - Osarumwense, Uwakata Yvonne (University of South Africa, 2021)
This study examines the comparative impact of multilateral trade agreements on intra-regional trade in the Southern African Development Community (SADC) and the Economic Community of West African States (ECOWAS) regions in Africa. Annual data was gathered from 2000 to 2018 and dynamic panel data and econometric techniques were used to control for individual country characteristics, endogeneity, serial correlation, heteroscedasticity and interdependencies between the countries in each region. Two estimations were done, one using the tariff measures of multilateral agreements, the second using non-tariff measures of multilateral agreement. The results of the empirical analysis show that the SADC region has a slight edge over ECOWAS in terms of technological progress and investment, especially in trade infrastructure. However, the ECOWAS levels of employment and economic growth are higher than those in the SADC region. These differences further translate into differences that drive intra-African trade in these regions, and how they relate to the role of multilateral agreements in intra-African trade in each of these regions. While technology and investment are key drivers and enhancers of intra-African trade in SADC countries, economic growth and employment stand out as key enhancers of intra-African trade in ECOWAS, especially where multilateral agreement is represented by tariff measures. This study reports that when non-tariff measures are used to represent multilateral agreements, export trade costs, in addition to investment and technology, are the key drivers of intra-African trade in SADC countries. For ECOWAS, under non-tariff measures of multilateral agreements, only economic growth drives intra-African trade.
Keywords: Commercial treaties; Customs unions; Institutional environment; Intra-African trade; Investments; Multilateral agreement; Panel data estimation; Tariff and non-tariff trade barriers

The Impact of Trade Openness and Foreign Direct Investment on Economic Welfare in sub-Saharan Africa - Adegboye, Folasade Bosede; Adesina, Olumide Sunday; Olokoyo, Felicia Omowunmi; Ojeka, Stephen Aanu; Akinjare, Victoria Abosede (International Journal of Financial Research, 2021)
The sub-Saharan African region is characterized by a high relative degree of openness to trade. The region is also identified with increased inflows of foreign investments with no significant welfare improvement. Economic development emphasizes that the lack of domestic investment in the developing economies could be boosted by trade openness and inflow of Foreign Direct Investment (FDI) for impactful enhancement of capital formation. In this article, the impact of trade openness and foreign capital inflow on economic welfare was examined on a sub-regional analysis for sub-Saharan Africa. The study also appraised the effect of openness to trade and FDI inflow on the region's economic welfare. The data for 30 countries from 2000 to 2018 were collected and analyzed, with the Generalized Least Square (GLS) technique to fit the model developed. The study showed that openness to trade has a significant impact on economic welfare for all sub-Saharan Africa regions, while FDI is only significant for the Western sub-region. Hence, the study recommends that the government of the countries in the sub-Saharan Africa region should boost trade openness to enhance efficiency in productivity, and improve industrial development.
Number: 2
Keywords: Economic Welfare; Foreign direct investment; Sub-Saharan Africa; generalized least square; sub-regional analysis; trade openness

The influence of capital structure and profitability on the solvency of nascent SMEs - Amoa-Gyarteng, Karikari (University of Johannesburg, 2021)
Even though small and medium enterprises contribute significantly to the growth of national economies, they are vulnerable in their early stages and may fail. Hence younger businesses are more likely to fail than more established ones because they face complex challenges that may limit their viability. This is a notion established in the liability of newness framework. According to the liability of newness concept, the precarious existence of emerging organisations is due to difficulties in managing relationships among strangers, not quickly assembling resources, and not coping with difficult environments, among other issues. All these elements notwithstanding, previous literature suggests that small businesses can, and sometimes do engage in techniques or approaches to help reduce the liability of newness, such as raising adequate capital. This study suggests that not only is adequate capital important but that the right mix of capital also results in higher solvency, thereby mitigating the liability of newness. Because the various funding forms have distinct advantages and disadvantages, an appropriate capital structure reduces the cost of financing while increasing the value of the firm. This study also advances the idea that profitable businesses are productive and financially strong, and thus nascent enterprises with high profitability can minimise the liability of newness. As a result, the study sought to examine the influence of capital structure and profitability on the solvency of nascent small and medium enterprises. To put the study's hypotheses to the test, 1106 nascent small and medium enterprises that are registered with the National Board for Small Scale Industries were sampled across three major cities in Ghana. Thus, data was gathered from every member of the population. Such data, gathered from the SMEs' financial statements, was submitted to preliminary screening as well as a number of statistical measurements. Operationally, the dependent variable, solvency, was defined as the solvency ratio, working capital ratio, and net worth. As a result, three distinct regression models were developed for robustness. The study's findings broadly indicate that capital structure and profitability have an influence on the solvency of nascent small and medium enterprises. The study also determined that emerging small and medium enterprises should follow the principles of the pecking order theory to reduce the liability of newness. These findings, if adopted by SME owners, can aid in the maturation of their fledgling businesses.
Keywords: Entrepreneurship; New business enterprises

Proceedings of 2021 UNCITRAL Working Group III inter-sessional meeting: the use of mediation in ISDS - Asian Academy of International Law Limited (AAIL) (Asian Academy of International Law Limited, 2021)
Contents: Opening remarks by Li Yongjie and Anna Joubin-Bret – Session 1: Presentation by the UNCITRAL Secretariat of the initial drafts on mediation and other forms of alternative dispute resolution (ADR) as possible reform option / C. Montineri, J. Knieper, J. S. Lee, p. 13-78 – Session 2: Sharing of views and experiences of international organisations, p. 79-117 – Session 3: Practical workshop: the use of mediation in ISDS - overcoming barriers and capacity building, p. 125-206 – Session 4: Summary of the inter-sessional meeting on ISDS reform submitted by the People's Republic of China, p. 215-232
Keywords: Dispute settlement; Investment disputes; MARD; Mediación; Mediation; Mediação; Médiation; UN Commission on International Trade Law; UN Convention on International Settlement Agreements resulting from Mediation (2018)

Securities regulation, enforcement and market integration in the development of sub-Saharan Africa's capital markets - Aziza, Onoriode Reginald (University of Oxford, 2021)
This thesis examines securities market development in sub-Saharan Africa, focusing on securities law, securities law enforcement and securities markets integration. Adopting a primarily comparative methodology, the thesis examines the continued relevance of securities markets in sub-Saharan Africa; the way selected countries in the region regulate their markets and enforce compliance with securities law; and the potential of market integration to promote market development. This thesis advances 4 main claims. First, empirical evidence supports the link between liquid securities markets and economic growth, independent of the level of banking development. In this sense, securities markets can act as good complements to banks in providing capital to the real economy. Second, at the minimum, there is an arguable preliminary case that rules of securities regulation can hinder market development in select countries in sub-Saharan Africa, by imposing high compliance costs and eligibility requirements, without commensurate benefits in greater liquidity or reduced cost of capital. Third, enforcement of securities regulation in sub-Saharan Africa is generally weak. Whilst public regulators often have formal powers, budgets and staff; actual enforcement activity is sometimes limited by inadequate market monitoring and reliance on criminal as opposed to administrative sanctions. Poor public enforcement, in turn, reinforces poor private enforcement, leading to reduced market participation, illiquidity, and ultimately market underdevelopment. Fourth, although increased market integration can go a long way in facilitating market development in the region, integration cannot be a short/medium term solution to market underdevelopment in sub-Saharan Africa, given the significant economic, political and socio-cultural barriers to integration initiatives in the region. Ultimately, to develop their securities markets, policymakers in sub-Saharan Africa must focus their attention on making and credibly enforcing market-friendly rules of securities regulation. The thesis explores some ways this may be realistically accomplished.
Keywords: Africa; Capital Markets; Capital market; Developing countries; Fintech; Going public (Securities); Market Integration; Securities; Securities Law; Securities Law Enforcement; Sub-Saharan Africa

A constitutional analysis of a differentiated tax treatment of residents and non-residents in respect of income deriving from immovable property in South Africa - Baines, Daniel (University of Pretoria, 2021)
A constitutional analysis of a differentiated tax treatment of residents and non-residents in respect of income deriving from immovable property in South Africa', Daniel Baines explores whether South African resident taxpayers' constitutional rights to equality and property are infringed by current laws which tax residents at higher rates than non-residents on rental income and proceeds from the disposal of fixed property. He aptly sets out what the right to equality and property entails and how these relate to taxpayers. He finds that the higher effective tax rates paid by residents violates their constitutional right to equality. The thesis provides valuable insight into a resident's right to equality and property in terms of current tax rates and illustrates how current tax rates are unconstitutional. The recommendations brought forward contribute toward the discussion of how tax rates should be altered in order to ensure that residents' constitutional rights are no longer violated.
URI: https://repository.up.ac.za/handle/2263/82750
Keywords: Immovable property; Income tax; South Africa; Tax treatment

A critical analysis of the effect of the moratorium on property owners - Beekarun, Yasthil (University of KwaZulu-Natal, 2021)
No abstract provided.
Keywords: Business rescue

Legal Translaboration for Effective Intercultural Communication - Bell Mandeng, Adrien (Scientific Annals of Alexandru Ioan Cuza University, 2021)
The European-inspired bilingualism and bi-legal system in Cameroon lead to an irregular profile and may be interesting for the European Union (EU) in its quest for preservation of intercultural processes through translation. The Organization for the Harmonization of Business Law in Africa (OHADA) of which Cameroon is part is only affiliated to Civil Law. However, the two legal systems employed in Cameroon (where both Civil Law and Common Law are used) are based on a balance in what concerns the conceptual, epistemic and stylistic representation. Intercultural dysfunction is the consequence of the lack of methodology in legal translation. Collaboration between legal translators and practitioners is key to adopt an agreed-upon model in multilingualism.
Keywords: Culture; History; Intercultural communication; Legal translaboration; OHADA

The arbitration of internal trust disputes in English law: Legal challenges and pathways - Clover Alcolea, Lucas (McGill University, 2021)
The arbitration of internal trust disputes has attracted significant attention in the arbitration and trust law communities in recent years with draft clauses and rules produced by arbitral institutions, several states undertaking legislative reform in order to provide such arbitrations with a statutory basis and numerous scholars as well as practitioners writing articles on the subject. Such enthusiasm is justified on the basis that arbitration has several advantages over litigation, such as confidentiality, international enforceability of judgments, the ability to choose one’s judge and the power to tailor the procedure. Notwithstanding these advantages, trust arbitration has failed to make any great inroad into trust disputes due to the many novel and complex points of legal practice and theory which it entails. For example, although arbitration does not typically involve minors or legally incapable parties’ trusts do, and thus trust arbitration raises numerous due process and human rights concerns. Similarly, court supervision and enforcement of trusts is sometimes considered essential to the very nature of trusts and questions therefore arise concerning the extent to which arbitral tribunals could supplant courts in that regard. Another complication is that trusts are not contracts and questions therefore arise about how to bind individuals to a trust arbitration agreement, particularly as regards beneficiaries who may be unascertained, minor or legally incompetent at the time the trust was created. The aim of this thesis is to analyse and present potential solutions to these complications from an English law perspective, although other common law legal systems will be analysed where relevant
Identifier: https://escholarship.mcgill.ca/concern/theses/x346d9718
Keywords: Arbitrage; Arbitragem; Arbitration; Internal trust disputes

Optimising regulatory responses to consumer disempowerment over personal data in the digital world - D'Amico, Alessia (European University Institute, 2021)
This thesis addresses the problem of individuals’ lack of control over personal data in the digital world. It sheds light on market and regulatory failures that lie behind the status quo and proposes a framework to improve regulatory responses. The two regulatory regimes that are at the core of this thesis are EU data protection regulation, which protects individuals’ fundamental rights over data, and EU competition law, which safeguards the sound functioning of the market and consumers’ economic interests. Despite the existence of these two regulatory regimes, individuals do not have sufficient control over personal data collected by digital firms, whose control over large datasets is a factor contributing to market monopolisation. The thesis argues that one reason for the shortcomings of today’s regulatory framework is that the market failure is composed of a combination of factors, which are currently addressed by the different regimes relatively independently. This dichotomy hinders the development of an effective strategy to tackle the market failure in its entirety. The approach taken in this thesis is that by integrating the two regimes, it might be possible to close the gaps deriving from a narrow perception of their regulatory spaces. Hence, the thesis formulates a holistic approach, encompassing data protection regulation and competition law, designed to increase the effectiveness of the regulatory framework as a whole. Different dimensions of the regimes’ interrelation are analysed, to uncover new ways to harness their complementarity and minimise their inconsistencies and overlaps. The thesis looks at how the regimes can incorporate elements from each other to inform their policies and application of their rules, as well as developing a complementary enforcement strategy. The holistic framework ultimately allows both regimes to better tailor their regulatory responses to the functioning of the digital market and take account of the diverse elements that constitute the market failure they seek to correct.
Accepted: 2021-07-07T10:12:30Z
Keywords: Data Protection; Personal data; Privacy

A comparative analysis between the Turkish Financial Reporting Standard for large and medium-sized entities and the OHADA accounting system - Diallo, Amadou Thierno (Sakarya Üniversitesi, 2021)
The rapidly growing bilateral and multilateral economic relationship between Turkey and African countries leads to the necessity of understanding each other's business and financial environment. Therefore, the accounting system as a fundamental tool for organizing and disseminating financial information should be accessible and understood by business actors and other stakeholders in these areas. Furthermore, the lack of study related to this subject has led us to carry out this comparative analysis between the two accounting systems by comparing financial statements prepared under each one and analyzing their main similarities and differences. The main purpose of this study is to highlight major differences and similarities between the SYSCOHADA and the FRS for LMSE. Also, the study is aimed to get a good understanding of both accounting sets and help practitioners and businessmen, and women operating in these places to have a good knowledge of the accounting regulations related to each country. On a topic basis and based on financial statements prepared following the SYSCOHADA rules and restated to be adapted to the FRS for LMSE, all main differences and similarities were thoroughly analyzed. Following the case study and the thematical analysis of different accounting topics, it can be understood that the two accounting sets differ to some extent due to philosophical approach on some topics such as the prudence principle where the SYSCOHADA, contrary to the FRS for LMSE, does not allow the recognition of potential profit resulting from currency translation gains related to receivable and payables until such profit becomes certain. However, these two sets also share some major similarities due to their proximity in some way to the IAS/IFRS. The effect of the main differences between the two sets can be noticed in the restated financial statements. The annual net income following the FRS for LMSE increased compared to the initial annual net income in the SYSCOHADA. Also, total assets and liabilities restated following the FRS for LMSE have decreased compared to the SYSCOHADA financial statements. Türkiye ile Afrika ülkeleri arasında hızla büyüyen ikili ve çok taraflı ekonomik ilişkiler, birbirlerinin iş ve finans ortamını anlama zorunluluğunu doğurmaktadır. Bu nedenle, finansal bilgilerin düzenlenmesi ve yayılması için temel bir araç olarak muhasebe sistemi, bu alanlardaki iş aktörleri ve diğer paydaşlar tarafından erişilebilir ve anlaşılabilir olmalıdır. Ayrıca bu konuyla ilgili çalışma eksikliği, iki muhasebe sistemi arasında bu karşılaştırmalı analizi, her biri altında hazırlanan finansal tabloları karşılaştırarak ve temel benzerlik ve farklılıklarını analiz ederek yapmaya yöneltmiştir. Bu çalışmanın temel amacı, SYSCOHADA ve BOBİ FRS arasındaki önemli farklılıkları ve benzerlikleri vurgulamaktır. Ayrıca, çalışma hem muhasebe standartları iyi anlamak hem de uygulayıcılara ve bu yerlerde faaliyet gösteren iş adamlarına her bir ülkeyle ilgili muhasebe düzenlemeleri hakkında iyi bilgi sahibi olmalarına yardımcı olmayı amaçlamaktadır. Konu bazında ve SYSCOHADA kurallarına göre hazırlanmış ve BOBİ FRS' ye uyarlanmak üzere yeniden düzenlenen mali tablolara dayalı olarak, tüm temel farklılıklar ve benzerlikler kapsamlı bir şekilde analiz edilmiştir. Vaka çalışması ve farklı muhasebe konularının tematik analizi sonucunda, iki muhasebe setinin bir ölçüde felsefi yaklaşım nedeniyle ihtiyat ilkesi gibi bazı konularda farklılık gösterdiğini anlaşılmaktadır. SYSCOHADA, BOBİ FRS'nin aksine alacak ve borçlara ilişkin kur farkı kazançları kaynaklanan potansiyel kârın kesinleşene kadar muhasebeleştirilmesine izin vermemektedir. Bununla birlikte, bu iki muhasebe seti, UFRS/UMS'ye bir şekilde yakın olmaları nedeniyle bazı önemli benzerlikleri de paylaşmaktadırlar. İki sistemin temel farkların etkisi, yeniden düzenlenen mali tablolarda fark edilebilir. BOBİ FRS'yi takiben yıllık net gelir, SYSCOHADA'daki yıllık net gelire kıyasla artmıştır. Ayrıca, BOBİ FRS'yi takiben yeniden düzenlenen toplam varlıklar ve yükümlülükler, SYSCOHADA finansal tablolarına kıyasla azalmıştır.
Keywords: Accounting standards; Accounting systems; Büyük ve orta boy işletmeler için finansal raporlama standardı; Comparative analysis; Financial reporting standard for large and medium size enterprises; Financial reporting standards; Finansal raporlama standartları; Karşılaştırmalı analiz; Muhasebe sistemleri; Muhasebe standartları; Turkish Financial Reporting Standards; Türkiye Finansal Raporlama Standardı

Transition from Local Accounting Standards to International Accounting Standards: A Comparison Between the OHADA Member Countries and Turkey - Diallo, Amadou Thierno; Çevi̇K, Zülküf (Yorum Yönetim Yöntem Uluslararası Yönetim Ekonomi ve Felsefe Dergisi, 2021)
This study tries to get a clear grasp of the factors that might play positively or negatively in a country’s convergence or adoption of the international financial reporting standards (IFRS). Through a comparative analysis between Turkey and the OHADA countries and based on the existing literature, the transition process towards the IFRS and challenges faced by each one is discussed from a historical perspective to the level of development. As a result, it is understood that the adoption or convergence towards the IFRS can be a challenging and a long-term process requiring multiple adjustments. Also, countries may differ in terms of historical past, level of development, cultural and socio-economic aspects which can all influence their transition. In addition, given the lack of study on the new adoption of the IFRS in the OHADA countries, this paper will contribute to filling the gap in the literature on the transition process. Furthermore, it will help countries which are in their early stage of the transition process to avoid some missteps and learn from others experience to get better prepared for a successful shift towards a fully IFRS compatible accounting system as has done Turkey. Bu çalışma, bir ülkenin uluslararası finansal raporlama standartlarına (IFRS) yakınsaması veya tam olarak benimsemesinde olumlu veya olumsuz rol oynayabilecek faktörleri tespit etmeyi amaçlamaktadır. Türkiye ile OHADA ülkeleri arasında karşılaştırmalı bir analiz yoluyla ve mevcut literatüre dayalı olarak, UFRS'e geçiş süreci ve bu süreçte karşılaşılan zorluklar, tarihsel bir perspektiften tartışılmaktadır. Sonuç olarak, IFRS’in benimsenmesi veya uyumlaştırılmasının zorlu ve birçok ayarlama gerektiren uzun vadeli bir süreç olduğu anlaşılmaktadır. Üstelik bu güçlükler, ülkelerin geçişlerini etkileyebilecek, tarihsel geçmiş, gelişmişlik düzeyi, kültürel ve sosyo-ekonomik yönler açısından farklılık gösterebilir. Buna ek olarak, OHADA ülkelerinde IFRS'in yeni benimsenmesine ilişkin çalışma eksikliği göz önüne alındığında, bu makale geçiş süreciyle ilgili literatürdeki boşluğun doldurulmasına katkıda bulunacaktır. Ayrıca, geçiş sürecinin erken aşamalarında olan ülkelere bazı yanlış adımlardan kaçınmalarına ve diğerlerinin deneyimlerinden öğrenerek, Türkiye'de olduğu gibi tamamen IFRS uyumlu bir muhasebe sistemine başarılı bir geçiş için daha iyi hazırlanmalarına yardımcı olacaktır.
Keywords: Accounting standards; Approche comparée; Comparison; Comptabilité; International Accounting Standards; Local Accounting Standard

Cryptocurrencies in an insolvent estate - Du Plessis, Shandi (University of Johannesburg, 2021)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Smart contracts : the Fourth Industrial Revolution and private international law - Dwamena, Elizabeth (University of Johannesburg, 2021)
Please refer to full text to view abstract. LL.M. (International Commercial Law)

The Contents of the Articles of Association as a Document used in the Creation of Companies in Cameroon under the OHADA Law - Eposi, Gladys Nku Tiku (International Journal of Science and Research, 2021)
This study unveils that the creation of companies in Cameroon is been regulated by the OHADA[1], law under the Uniform Act on Commercial Companies and Economic Interest Groups (UACCEIG) which says, every company must have its own Articles of Association [2]. The Articles of Association is a document that contains the internal regulation for the management of the company’s affairs. [3] The articles of association are the contracts between the shareholders and the company and among the shareholders themselves. [4] The questions raised are what are the requirements common in the Articles of Association of all companies under OHADA Law? What effect do the AOA has? The study adopted an analytical approach which has led to the finding that the AOA under OHADA, is similar to the MOA [5] in most English speaking countries, but a major difference in that UACCEIG has limited the life span of the company to 99years while under English company law, a company goes on for an indefinite period. [6] The life span of the company should not be limited due to the principle of perpetual succession. The UACC seem to have concurred with some aspects of the Common Law, making the UACC an applaudable law reform.
Keywords: Articles of association; Cameroon; Commercial companies; Notarised deed; OHADA Law

Experimenting with international commercial dispute resolution - Erie, Matthew S; Bookman, Pamela K (AJIL Unbound, 2021)
In this essay, we describe the overlapping phenomena of new legal hubs (NLHs), international commercial courts, and arbitral courts. We survey their impact on the law and geopolitics of international commercial dispute resolution, identifying key issues these new dispute resolution institutions raise. While the rise of international commercial courts spans authoritarian and liberal states, Western and Asian states, common law and civil law traditions, it also highlights and builds upon regional differences. We question the assumption that the establishment of new courts is always consistent with an increase in the rule of law, particularly in non-democratic states. We close with thoughts about the potential influence and future role of these institutions. Some of the procedural innovations discussed here may lead to shifts in international commercial dispute resolution for years to come, but the question of whether there is sufficient demand for these new institutions lingers.
Copyright © Pamela K. Bookman, Matthew S. Erie 2021. This is an Open Access article, distributed under the terms of the Creative Commons Attribution licence, which permits unrestricted re-use, distribution, and reproduction in any medium, provided the original work is properly cited.

Corporate social responsibility and management of oil related conflict in Host Communities of Niger Delta Region, Nigeria - Gbali, Kenneth Chisom; Weli, Vincent Ezikornwor; Mmom, Prince Chinedu (World Journal of Advanced Research and Reviews, 2021)
The study sought to examine the Corporate Social (CSR) and management of oil related conflicts in Host Communities of the Southern States. Corporate Social Responsibility is the commitment of businesses to contribute to sustainable economic development by working with employees, the local community and the society at large to improve their lives in ways that are good for business and for development. The study was guided by three research objectives, three research questions and three hypotheses. The design adopted for this study is exploratory and descriptive research design and was conducted in Bayelsa, Delta and Rivers State in Nigeria. The population of this study comprised of 15,245,247 residents in Bayelsa, Delta and Rivers State in Nigeria. The instrument for data collection was a set of structured questionnaire. Data derived from the field were analyzed using the Statistical Package for Social Sciences (SPSS) version 23.0. And statistical tools such as mean and standard deviation were used to respond to the research questions, while inferential statistical tool of independent sample T-test was used to test the hypotheses at 0.05 level of significance. Findings from the study showed that there is a significant difference in the mean ratings of male and female respondents on the level of relationship between IOC’s and hosts Communities in Niger Delta Region, Nigeria ((P=0.738>0.05), df (400) =. -0.49273, p=0.738); there is a significant difference in the mean ratings of male and female respondents on the on CSR programs carried out by IOCs in hosts Communities in Southern Nigeria (P=.117>0.05), df (400) = -401.618, p=.117); further findings showed that there is a significant difference in the mean ratings of male and female respondents on the Factors causing conflict between oil companies and host communities in Southern, Nigeria (P=0.775>0.05), df (400) =382.256 p=0.775). Based on the findings of the study, it was recommended that host communities should be integrated into the planning process, a paradigm shift from planning for to planning with the host Communities, amongst others.
Keywords: CSR; Corporate Social Responsibility; Host communities; Oil Related Conflict; Oil companies; Southern Nigeria

COVID-19 and Comparative Corporate Governance - Gelter, Martin; Puaschunder, Julia M. (The Journal of Corporation Law, 2021)
With the pandemic caused by the novel coronavirus SARS-CoV-2 raging around the world, many countries’ economies are at a crucial juncture. The COVID-19 external shock to the economy has the potential to affect corporate governance profoundly. This Article explores its possible impact on comparative corporate governance. For an economy to operate successfully, a society must first find a politically sustainable social equilibrium. In many countries, historical crises—such as the Great Depression and World War II—have resulted in a reconfiguration of corporate governance institutions that set the course for generations. While it is not yet clear whether COVID-19 will have a similar effect, it is possible that it will change patterns of what kind of firms are -from an evolutionary perspective- likely to survive, and which ones are not. We argue that to some extent, it will accelerate ongoing trends, whereas in other areas it put corporations on an entirely new course. We observe three trends, namely the need for resilience, a growth of nationalist policies in corporate law, and an increasing orientation toward “stakeholder” interests. First, firms will have to become resilient to the crisis and consequently long-term oriented. Corporations that are not operating merely on an arm’s length capital market basis but are integrated into a network, generated by core shareholders, state ownership, or bank lending may be more likely to survive. In addition, firms are beginning to interact with their workforce differently in their attempts to maintain what could be called “healthy human capital.” Second, we are likely to see a resurgence of nationalism in corporate governance to ensure that foreign ownership and interconnected supply chains do not put national security at risk. Third, the existing critiques of inequality but also climate change awareness will accelerate the trend toward a broadening of corporate purpose toward “stakeholderism” and public policy issues. As in the past years, institutional investors acting as “universal owners” will play a role in shaping this trend.
Keywords: Behavioral; COVID-19; Climate change; Corporate governance; Corporate law; Economic protectionism; Evolutionary theory; Free cash flow; Green New Deal; Human capital; Inequality; Nationalism; Ownership structure; Relational finance; Shareholder primacy; Stakeholder theory; Varieties of capitalism

Corporate Finance - Gherghina, Ştefan Cristian (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book comprises 19 papers published in the Special Issue entitled “Corporate Finance”, focused on capital structure (Kedzior et al., 2020; Ntoung et al., 2020; Vintilă et al., 2019), dividend policy (Dragotă and Delcea, 2019; Pinto and Rastogi, 2019) and open-market share repurchase announcements (Ding et al., 2020), risk management (Chen et al., 2020; Nguyen Thanh, 2019; Štefko et al., 2020), financial reporting (Fossung et al., 2020), corporate brand and innovation (Barros et al., 2020; Błach et al., 2020), and corporate governance (Aluchna and Kuszewski, 2020; Dragotă et al.,2020; Gruszczyński, 2020; Kjærland et al., 2020; Koji et al., 2020; Lukason and Camacho-Miñano, 2020; Rashid Khan et al., 2020). It covers a broad range of companies worldwide (Cameroon, China, Estonia, India, Japan, Norway, Poland, Romania, Slovakia, Spain, United States, Vietnam), as well as various industries (heat supply, high-tech, manufacturing).
Accepted: 2022-01-11T13:28:27Z

The impact of Covid-19 on labour law protection for Uber drivers - Gxabu, Mampho Aphelele (University of Johannesburg, 2021)
On 15 March 2020 the President of the Republic of South Africa announced a nationwide lockdown. The unpredicted pandemic dictated that extraordinary measures be put in place, which resulted in the country coming to a total standstill. Consequently, there was an alarming decline in economic activities and therefore government had to introduce measures to mitigate the impact of COVID-19 on employers and workers.

The Power of an Arbitral Tribunal to Determine Its Own Jurisdiction in International Commercial Arbitration - Kamanga, Patricia N. S. (Beijing Law Review, 2021)
Keywords: Arbitration Agreement; Competence-Competence; Jurisdiction; Party Autonomy; Power

The tax implications of intellectual property: an overview of the development of the law pertaining to deductions - Khan, Ilhaam (University of KwaZulu-Natal, 2021)
No abstract available.

Global Civil Procedure - King, Alyssa S. (SSRN Electronic Journal, 2021)
A “global” civil procedure has emerged and found its way into debates over procedural reform in both international and domestic arenas. Global civil procedure includes the procedural rules, practices, and social understandings that govern transnational litigation and arbitration. A global civil procedure norm is a norm adopted across courts or arbitration providers with the purpose of making that jurisdiction or provider more competitive in attracting transnational litigation or arbitration. Global civil procedure norms are at stake in multiple present trends and debates, including model laws in commercial arbitration, the procedure of international tribunals, the debate over investment dispute resolution, the rise of courts oriented towards international litigation, and sprawling litigation spanning multiple jurisdictions and fora. On a surface level, the values reflected in global civil procedure seem to be roughly the same across jurisdictions. A common language has emerged around competition for litigation business and procedure values such as efficiency, certainty, and impartiality. Yet different legal systems do not necessarily agree on the purpose of various shared elements of global civil procedure. For democracies, for instance, the purpose of procedural reforms might be to facilitate access to justice. Other countries may favor the same reforms because they facilitate top-down administrative control of judges. Surface agreement can submerge divergent logics that may ultimately lead to very different applications of harmonized rules. This Article begins by introducing the concept of global civil procedure, who uses it, and how. Next, it considers several examples of the phenomenon including conflicts of interest rules for adjudicators, aggrega tion, and discovery or disclosure rules. Finally, it considers the limits of global civil procedure. Although the rhetoric of procedural competition can be heard across systems, procedural values do not necessarily translate both in terms of enduring divisions between legal traditions and in terms of applications by current political regimes.

The conflict of jurisdiction between intra-EU BITs and European law: proposal for an EU investment court - Lewis, Krystle (Canterbury Christ Church University, 2021)
This work aims to find a practical solution to the problem that exists between intra-EU Bilateral Investment Treaties (BITs) and European Union (EU) law over conflict of jurisdiction issues. Currently, there is a problem as the EU Commission has rendered intra-EU BITs incompatible with EU law. This work argues that the current conflict of jurisdictional problems within investment agreements can be overcome by the creation of an EU investment court. The reliance on this court for the resolution of this conflict, as opposed to private law mechanisms, is important as it is the way forward in handling the conflict of jurisdiction issue at its best. This work argues that an EU investment court will be a panacea to the current problems concerning the conflict of jurisdiction. These problems will be presented through a positivist method where the law is analysed in its current form, highlighting its current weaknesses and resolving these weaknesses by proposing recommendations for such a court through a comparative examination of other international courts that fulfil a similar dispute resolution function, namely the Organisation for the Harmonisation of Business Law in Africa (OHADA) and the Unified Patent Court (UPC) and the World Trade Organisation (WTO). The purpose of this work is manifold. The work will provide an analytical examination of the relationship between EU law and international obligations within intra-EU BITs. It will further explore and assess the viability of a range of alternative solutions to intra EU BITs enforcement within the EU. It will additionally examine the operation of the OHADA, the UPC and the WTO to inform the proposal of an EU investment court. This is important as the outcome of these examinations will support the argument made in this thesis. It will also impact dispute resolution beyond academia by providing a practical solution to alleviate the current challenges with intra-EU BITs. The recommendations thus can inform changes for lex ferenda.
Permalink: https://repository.canterbury.ac.uk/item/94574/the-conflict-of-jurisdiction-between-intra-eu-bits-and-european-law-proposal-for-an-eu-investment-cour
Keywords: Bilateral Investment Treaties (BITs); Investissements; Investments

The job security of employees of financially distressed companies - Loubser, Mieka E.; Garbers, Christoph (South African Mercantile Law Journal, 2021)
This contribution considers the legislative regulation of the job security (which boils down to preservation of employment) of employees in case of financial distress of a company. It juxtaposes the legislative regulation of four interrelated processes a company may engage in where it finds itself in financial distress, namely a voluntary internal restructuring (especially retrenchment), the transfer of the business or part of the business, business rescue and winding up. The legislative endeavour to preserve the job security of employees in all these processes is described and analysed. The discussion shows that room exists for companies to circumvent this protection and, to the extent that the protection does apply, that it remains difficult for employees to ultimately challenge the substance of decisions negatively affecting their job security. The main protection for employees in all these processes is procedural in nature and to be found in their rights to be informed of and consulted prior to decisions negatively affecting them. In this regard, business rescue is the most employee-friendly process. Participation in this process by employees, however, requires a fine balance as it may be self-defeating and lead to winding up and the permanent loss of jobs.
Keywords: Business rescue; Dismissal; Insolvency; Job security; Labor laws and legislation; Liquidation; Merger; Operational requirements; Retrenchments; Transfer of a business

The tripartite free trade area: towards a comprehensive African economic community with a particular focus on SADC - Mabinza, Siqhamo (University of KwaZulu-Natal, 2021)
No abstract available.
Keywords: Africa; GATT; Multilateral trading systems; Regional Trade Agreements (RTAs); SADC; Southern African Development Community; WTO

COFOLA International 2021: International and National Arbitration: Challenges and Trends of the Present and Future - Malachta, Radovan; Provazník, Patrik (Masaryk University Press, 2021)
- Virtual Arbitration Hearings in Times of COVID-19 (And Beyond); - International Arbitration and Blockchain: Current State, Types, Characteristics and the Future Perspective; - Use of Artificial Intelligence in Arbitration; - The Impact of Brexit on the Arbitration Procedure in Great Britain; - May Misapplication of EU Law Give Rise to International Responsibility of the Member State ... Under Investment Treaties? - International Investment Court System: The Future of Investment Dispute Settlement? - EU and Its New Mechanism for the ISDS in the Protection of FDI – What the Future Holds? - (Un)Clean Hands in International Investment Arbitration: Some Cleaning Required? - Challenges of Arbitrators in Inter-State Cases: A Different Cattle of Fish? - “Rules of Law” and Lex Mercatoria Determination Under the Auspice of ICC Arbitration; - Sources of Transnational Public Policy in International Commercial Arbitration; - Regulation of Arbitration Agreements Under New York Convention; - Comfortable Satisfaction Before the Court of Arbitration for Sport: Consistency Despite Differences? - Comparison of ICC Expert Report vs. ICC Arbitration Award; - Analysis of Civil Law Consequences of Corruption Under the Czech Law... in the Light of International Commercial Arbitration; - The Crime of Bending the Law From the Point of View of the Arbitrator ... of the Court of Arbitration and Application Practice; - The Arbitration Convention as One of the Measures to Eliminate Double Taxation ... in the European Union and in Slovak Republic; - Possibility of Resolving Individual Labor Disputes in Croatian Law by Arbitration; - What We Know, We Don’t Know About Macao’s Arbitration Framework and the Way Forward.

The principle of party autonomy in the HAGUE principles on choice of law in International Commercial Contracts : lessons for Chinese, Russian and South African Private International Law - Manganye, Makhanani Annastesia (University of Johannesburg, 2021)
It is no secret that there has been an increase in international trade in recent decades. Natural and juristic persons have taken it upon themselves to trade both domestically and internationally. As international trade increases so too do the conclusion of international commercial contracts. When individuals enter into an international contract, one particularly important issue, and one that should be foremost in the minds of the contracting parties, is which legal system will govern their agreement? Therefore, a significant factor to any international commercial contract is whether the parties have the freedom to choose the law applicable to their agreement and to choose the court that will adjudicate upon their contractual disputes, and if so, to what extent may the parties exercise their freedom of choice?... LL.M. (International Commercial Law)
Keywords: Commercial policy; Commercial treaties; International trade

Optimising the legal regulation of circular labour migration between South Africa, Lesotho and Zimbabwe - Matete, P. (North-West University, 2021)
Circular labour migration is steadily gaining prominence the world over, primarily due to the benefits it offers to the migrants, to the sending country, and to the receiving country – the so-called "triple-win" benefits. In order to enhance the benefits of circular labour migration, both the International Labour Organisation and the International Organisation for Migration recommend that adequate instruments of governance should be utilised. From the outset, this thesis recognises bilateral labour arrangements as the ideal instruments for enhancing the potential benefits that circular labour migration offers to the stakeholders involved in the process. As far as could be established, there has been no comprehensive research that seeks to provide insights on how the selected countries in the Southern Africa Development Community (South Africa, Lesotho and Zimbabwe) could optimise the benefits of circular labour migration for all stakeholders, primarily through the use of bilateral labour arrangements. The need for these insights in Southern Africa is pertinent due to the absence of a contemporary and clear framework regulating circular labour migration in the region. Based on the foregoing, this thesis advances the proposition that the guidelines provided by international law and standards of labour migration, and the best practices in Spain and New Zealand, can provide significant insights on how South Africa, Lesotho and Zimbabwe can enhance the regulation of circular labour migration to provide optimised benefits for all stakeholders. Proceeding from the above premise, this thesis makes a number of findings. These include the affirmation that bilateral labour arrangements are indeed the key regulatory instruments for promoting the triple-win benefits that circular labour migration offers; that circular labour migration, if managed well, plays an instrumental role in development in both the sending countries and the receiving countries; and that three key areas should be addressed in bilateral labour arrangements in order to effectively promote triple-win benefits. The three key areas that need to be addressed in bilateral labour arrangements in order to enhance the benefits for all stakeholders are linking migration with development, migration governance, and the protection of the rights of migrant workers. This thesis outlines the various principles that are necessary to give effect to these three key areas. This thesis finds that, based on the guidelines provided by international law and standards, it is essential that bilateral labour arrangements, at the minimum, incorporate provisions that facilitate skills training, the return and reintegration of migrants, the transfer of remittances, and the promotion of human resources development. In this regard, this study finds that the bilateral labour arrangements between South Africa and its neighbours, Lesotho and Zimbabwe, fall short of the guidelines provided by international law and standards on labour migration and by the best practices in New Zealand and Spain. The original contribution of this study lies in it being the first study to comprehensively explore the legal measures that South Africa, Lesotho and Zimbabwe could utilise to optimise the regulation of circular labour migration to South Africa as the main receiving country in SADC. This study makes recommendations on how the labour migration legal framework between the three countries can be improved, based on lessons learned from international law and standards on labour migration and best practices from selected countries.
Keywords: Bilateral arrangements; Circular labour migration; Droit du travail; Labour law; Migrant workers; Remittances; Travailleur migrant

Challenges for Responsible Investment in the retirement benefits sector of Kenya - Mathenge, Elizabeth (Victoria University of Wellington, 2021)
Responsible investment (RI) is the investment strategy that incorporates environmental, social and governance (ESG) factors into the investment decision-making process (Hebb, Hawley, Hoepner, Neher, & Wood, 2015). RI has shifted from what was considered a niche market to become one of the fastest-growing areas of finance in many parts of the world (PRI, 2019b). However, a closer look at the development of RI and adoption rates in countries and regions reveals that RI is not commonly practised in sub-Sahara Africa (except for South Africa). This study explores the critical challenges for RI development in the retirement benefits sector of Kenya and, by engaging with a variety of key stakeholders, proposes how to overcome the identified challenges. It contributes to the literature on challenges for RI in a developing country by offering an in-depth case study of the retirement benefits sector.My study employs qualitative methods to collect and analyse data collected from semi-structured interviews with 22 participants (asset managers, regulators and capital market experts, and a council member of the Association of Retirement Benefits Schemes of Kenya) as well as a collection of published documents by government agencies in Kenya. Also, I analysed 10 annual reports to assess the kind of ESG information that is disclosed by listed companies. My study explores, in particular, how actors in the retirement benefits sector conceptualise RI. It identifies the leading ESG factors in Kenya and draws on the business-case approach to RI to explore whether the participants consider those factors as material risk factors that present both risks and opportunities to the investment decision-making process. Further, my study identifies the specific barriers for RI development and proposes how to overcome them. The findings show that participants define RI using several terminologies. This is consistent with the existing literature. My study finds that all participants consider corporate governance as a material risk factor that can impact the financial returns of a portfolio. However, most of the asset managers do not think that the environmental and social factors can present material risk factors to their investment decision-making process. Although over a third of the asset managers recognise that the environmental and social issues in Kenya present business opportunities to retirement benefits schemes, there is a shortage of well-structured assets in those areas. Further, this study identifies five specific barriers for RI development: diversification challenges; a lack of ESG data; a lack of demand/incentives; short-termism; and the demand for high financial returns and a lack of awareness and expert knowledge of RI practices. My study recommends that the National Treasury of Kenya develops RI policy for the entire finance sector. In addition, the findings support a recommendation for the Capital Markets Authority and the Retirement Benefits Authority to embark on capacity building programmes to educate the actors in the finance sector on RI strategies and to create awareness of the impact of ESG on financial returns in the long run.
Keywords: Investment and Risk Management; Kenya; Responsible investment; Retirement benefits schemes

Governance of non-bank systematically important financial institutions - Morbee, Katrien (University of Oxford, 2021)
This thesis identifies the circumstances under which corporate governance regulation can help gain traction to minimise systemic risk. Systemic risk is the risk that local losses spread through the financial system and badly affect the financial system and the real economy. Excessive risk-taking by financial institutions can contribute to such systemic risk. Prudential regulation and supervision of financial institutions leave corporate decision-makers with room for discretion to increase or decrease systemic risk. The incentives of these decision-makers are not necessarily aligned with minimising systemic risk. The thesis shows that this problem exists across different business models. More specifically, it identifies perverse incentives in the case of systemically important banks, CCPs, mutual funds, and hedge funds. The need for corporate governance regulation therefore lies in the inherent incompleteness of prudential regulation and supervision. Corporate governance regulation can help fill this gap by regulating the environment within which choices are made within these types of institutions. The analysis has three steps. First, it characterises the systemic importance of financial-sector activities carried on outside the context of ‘banks’. The governance literature so far has focused on the ‘systemic externalities’ created by banks. However, our analysis shows that other non-bank SIFIs generate similar systemic externalities with socially harmful consequences. These systemic externalities are not considered by SIFIs when taking business decisions. In a second step, the thesis shows that prudential regulation and supervision are incomplete and leave room for governance regulation to fill in the gaps. The final step shows that a corporate governance framework focused solely on the interests of shareholders will have negative consequences for systemic stability. Given such divergence between the decision-makers’ and society’s interests, corporate governance regulation can complement the traditional prudential framework.
Keywords: Asset managers; Central counterparties; Corporate governance; Finance; Non-bank financial institutions; Systemic risk

The impact of the Trade-Related Aspects of Intellectual Property Rights (TRIPS) on the right to health and the right to development: a study of the implementation of TRIPS in Zimbabwe - Munemo, Ropafadzo Blessing (University of KwaZulu-Natal, 2021)
The right to health and the right to development are intertwined socio-economic rights that affect the well being and growth of a country’s populace. Most developing and least developed countries face challenges in ensuring access to essential medicines vis a vis the realisation of the right to health and full potential of development. Patents, provided for under the TRIPS Agreement are partly to blame for the lack of access to essential medicines as they account for the excessive pricing of medicines. Zimbabwe being a developing country currently facing dire economic and political challenges but being obliged under the International and Regional Human Rights Conventions it subscribed to, has to ensure the progressive realisation of the right to health and development. However, as a member of the TRIPS Agreement, there are limitations to the country’s ability to ensure access to medicines and healthcare for developmental purposes. This thesis has outlined the problematic provisions of the TRIPS Agreement and Zimbabwe’s attempt to use the flexibilities provided to its advantage. Zimbabwe has only put into use the flexibility of compulsory licensing and parallel importation to a limited extent; hence the recommendation that even though the country has domesticated the Agreement to its advantage, the country needs to explore other flexibilities comprehensively and promote the realisation of the rights to health and development.
Keywords: Access to medicine; Health care costs; Intellectual property; Public health; TRIPs; Trade tariffs; Zimbabwe

An analysis of the consequences of a business rescue moratorium on legal proceedings on property owners - Ngubane, Samukelo Siyanda (University of KwaZulu-Natal, 2021)
It has been over a decade since the Companies Act 71 of 2008 introduced business rescue proceedings which provided for the rescue of financially distressed companies. This procedure replaced the then statutory procedure of judicial management under Companies Act 61 of 1973. The business rescue proceedings begin with the general moratorium or stay on legal proceedings against the company or its property. This has a consequence that any claims against the company may only be enforced with the consent of the business rescue practitioner or the leave of the court. However, the courts continue to grapple with the interpretation, effect, and application of the key elements of business rescue provisions while always striving to accord respect to the legislative intention of business rescue as set out in section 7(k) of the Companies Act 71 of 2008. After a decade since its introduction, it is an opportune time to ascertain whether the business rescue proceedings is an effective corporate rescue procedure suitable to the modern-day demands of the South African economy. The research analyses the effect and the consequences of the moratorium on the rights of property owners. The moratorium has the effect that companies are given temporary immunity to actions brought by creditors which would have been due and enforceable. In this regard, the property leased by the property owner remains occupied by the company during business rescue proceedings as the property owner is barred by the moratorium to institute legal proceedings against the company. Further, when the repossession of the property is not possible and the rental due or installment is not payable by the company, the business rescue proceedings encroaches on the right of the property owners. The purpose of the research is to highlight the effect of the moratorium on the lease agreement between the company and property owners and the possible protection of the property owners’ rights. The study includes a critical analysis of judicial decisions on the moratorium, together with a discussion of the legal position in comparable foreign jurisdictions. In my conclusion, based on the findings, the business rescue is not free from imperfection. Therefore, I recommended that the legislature amend some parts of Chapter 6 of the Companies Act 71 of 2008.
Keywords: Companies Act 71 of 2008; Corporate rescue procedure; Financially distressed companies; South Africa; Stay on legal proceedings

Regulatory measures to address bank failures in Zimbabwe - Nyaude, Ashley Batsirai (University of Pretoria, 2021)
The main rationale of prudential bank regulation and supervision of banks has traditionally been to ensure the safety and soundness of banks and protection of depositors. However, best practice standards in bank supervision acknowledge that it is impossible to completely prevent bank failures. Therefore, it is crucial to have regulatory measures in place to deal with banks that fail. Banks are core players in the financial system as the intermediaries between savers and users of capital. In addition, banks provide critical services to consumers, small and medium-sized businesses, large corporate entities and governments who rely on them to conduct their daily business, both at domestic and international level. Banks also fulfil a sui generis role that sets them apart from other financial institutions that are role players in the financial system because, inter alia, they hold “highly” liquid liabilities in the form of deposits that are repayable on demand; they extend long-term loans that may be difficult to sell or borrow against on short notice; they are the back-up source of liquidity to all other institutions (financial and non-financial); and, are also the transmission belt for monetary policy. Unlike other players in the financial system, banks are vulnerable to loss of public confidence and to liquidity risk. Liquidity risk being the risk that a bank will not have sufficient cash to meet short term obligations and the fact that a "run on the bank" by depositors can result in devastating liquidity drainage. Because banks play a special role in the economy and their failure may have a significant impact on financial stability, they need a special approach when they become insolvent or are likely to become insolvent. The 2008 Global Financial Crisis (“GFC”) demonstrated the importance of special resolution regimes for banks; and the need to balance the interests of shareholders, creditors and depositors, while promoting financial stability objectives. Given the critical role of banks in the economy the need is clear for a special resolution regime for banks that provides a legal framework for regulators that avails to them a suite of resolution tools which they can apply to resolve the bank in an orderly manner; to rescue those parts of the bank that may still be viable and to liquidate those parts that are not whilst avoiding a drain on public funds. In order to deal with bank failures in Zimbabwe, the Banking Act [Chapter 24:20] has provided for the mechanism of curatorship since 2000, as a rescue measure aimed at restoring failing banks to economic viability. Curatorship has over the years been applied with mixed success; consequently, Zimbabwe has undertaken a number of reforms which include the enactment of the Troubled Financial Institutions (Resolution) Act in 2005; and the introduction of the problem bank regime via the Banking Amendment Act of 2015. Throughout these reforms, Zimbabwe has elected to retain curatorship, which was once a standalone process in banking legislation to enable bank rescue; and assimilated it into a broader bank resolution framework. This study seeks to determine whether Zimbabwe’s resolution regime requires to be strengthened and if so, to recommend reforms that will align the resolution regime in Zimbabwe with international best practice. For such purpose it will draw upon the Financial Stability Board’s Key Attributes of Effective Resolution Regime as international best practice benchmark. It will further also consider guidance yielded by a comparative study of the resolution regimes in the United Kingdom and South Africa.
URI: https://repository.up.ac.za/handle/2263/80388
Keywords: Bank failure; Bank supervision; Zimbabwe

A Third World approach to the role of South Africa, Nigeria and Kenya in the multilateral trading system - Nzimande, Nosiphiwo (University of KwaZulu-Natal, 2021)
No abstract provided.
Keywords: GATT; General Agreement on Trade and Tariffs; International Trade; Kenya; Nigeria; Regional Trade Agreements (RTAs); South Africa; WTO; World Trade Organization; World trade

Allocating rights between nations: Legitimacy and justice in international tax policy - Ozawa Ozai, Ivan (McGill University, 2021)
Although extreme poverty has decreased in the last decades, we are a long way from eradicating global poverty. Similarly, the world has seen a considerable decrease in global inequality due to recent developments in emerging economies, but overall inequality between nations has risen in the last decades. International tax law may have a relevant role in improving or worsening global inequality. Extensive research has shown that the present international tax system was designed in a way that tends to benefit high-income economies. However, there has been no significant discussion about whether and how international tax law rules should be changed to address global inequality. The main goal of this thesis is to analyze the existing legitimacy and distributive justice issues that limit the ability of lower-income countries to raise tax revenues and consider what can be done to make the current international tax regime more aligned with global justice principles.The thesis builds on the contemporary literature in international political economy and global distributive justice and puts forth a normative framework for allocating the international tax base among states. First, it analyzes some of the legitimacy deficits of the present international tax system. In contrast to prevailing views about improving legitimacy, it demonstrates the shortcomings of focusing solely on making international tax policymaking processes more inclusive and argues for a greater focus on global distributive justice. It then analyzes the main tax theories that have defined international tax relations to date and demonstrates some of their limitations. The final part of the thesis puts forth normative principles that integrate distributive justice and considers the practical implications of the proposed normative framework for some of the most recent issues discussed in international tax policy
Identifier: https://escholarship.mcgill.ca/concern/theses/rf55zd52x
Keywords: International tax; International tax policy

Sensitivity analysis of a bond mutual fund to yield curve - Pigou, Leuyou; Fono, Louis Aimé (Institut International des Assurances (IIA), 2021)

Takeover and shareholders' agreements - Sabatini, Federico (LUISS Guido Carli, 2021)
The OPA. Notions of takeover bids. Recognising and distinguishing the various forms of control within a company. Type of takeover bid. Subsequent defence techniques. The US control market and details of M&A and tender offers. Bids and acquisitions in China. Comparative European case studies. Shaldeholders' agreements. Regulatory sources and definition of covenants. Concerted action. Takeover obligations arising from concerted action. Cases. The Fondiaria-Sai case. Unipol-BNL. Other case of exemption.

Harmonization (or rather Standardization) of Cooperative Law in the OHADA Zone: What is the Result after Ten Years of Implementation of the Uniform Act? - Tadjudje, Willy (CIRIEC - España. Revista jurídica de economía social y cooperativa, 2021)
The Uniform Act related cooperative societies (UA-COOP) is the main source of cooperative law in all the seventeen States parties to the OHADA founding Treaty. Ten years after its entry into force (2011-2021), the aim of this study is to assess the level of enforcement of this Act. More concretely, the aim is to compare the state of cooperative law at the time of the entry into force of the UA-COOP (2011) with the current situation (in 2021). Such a comparison should make it possible to assess the contribution of the UA-COOP to the development of cooperative law and strengthening of national cooperative movements in the OHADA zone.

UNCITRAL Expedited Arbitration Rules - UNCITRAL (United Nations, 2021)

Chapter II: The Arbitrator and the Arbitration Procedure, An Arbitrator’s Imperative – How to Avoid Disappointing the Parties, Preventing Surprises and Enabling Efficient and Progressive Arbitral Proceedings - Welser, Irene; Mimnagh, Samuel (Austrian Yearbook on International Arbitration, 2021)

Improving international investment law’s treatment of (anti-)corruption: Towards a more balanced approach - Yan, Yueming (McGill University, 2021)
In recent years, investment arbitration tribunals are increasingly confronted with allegations of corruption, mostly invoked by host States as a defense to investors’ claims. After an affirmative finding of an alleged corrupt act between the investor and a public official of the host State in the establishment or conduct of the investment, tribunals have adopted a binary approach to the issue – if they uphold allegations of corruption, they completely dismiss the investor’s submissions. This binary approach has resulted in an asymmetry of liability for the two parties to a corrupt act (i.e., investors and host States/host State officials), failing to take into account the inherent bilateralism of corruption and the fact that domestic laws and international norms have outlawed both the act of offering and of accepting bribes. In particular, public officials’ free participation in a corrupt act to advance investments is attributable to the host State and requires State responsibility under international law. Moreover, the increasingly prevalent practice of inserting anti-corruption provisions in investment treaties has reinforced this lop-sided feature, as well as offering only weak effectiveness in terms of deterring corruption. After a careful examination of the treatment of corruption issues in investment arbitration and investment treaties, this thesis proposes a paradigm shift from the current asymmetric approach to a more balanced approach. It calls on investment tribunals to take a dual-track approach that investigates both corruption and investors’ claims, and ensures that each party assumes responsibility for its own misconduct. It also proposes that treaty drafters include anti-corruption provisions that impose strong obligations of anti-corruption on both sides of corruption (i.e., investors and host States) rather than merely on a single party to it
https://escholarship.mcgill.ca/concern/theses/5q47rt984
Keywords: Anti-Corruption Law; Investment arbitration; Investment treaty; Investments

Legalization through adjudication: The case of investor-state dispute settlement - Yu, Chen (McGill University, 2021)
The reform of the Investor-State Dispute Settlement (ISDS) mechanism has provoked much debate among legal scholars and practitioners. The critiques of ISDS mainly arise from concerns regarding the legitimacy of the mechanism such as the perceived tolerance for the lack of impartiality and consistency. To allay these concerns, there have been proposals to reform ISDS by establishing investment courts with tenured judges and appellate tribunals. However, international adjudication systems like ISDS cannot be fully analogized to domestic courts in common law countries: ISDS falls into a broader international regime where there are neither hierarchical/centralized decision-making and enforcement authorities nor a multilateral investment treaty, and the rules and principles on foreign investment protection are fragmented in around three thousand Bilateral Investment Treaties (BITs). Against this backdrop, this thesis argues that, although there is a general agreement among the international community to further legalize international investment law, the process of legalization via the specific avenue of reforming the adjudication mechanism (i.e. ISDS) is subject to (1) the institutional constraint of international investment law, especially the lack of shared understanding among the international community regarding the treatment of foreign investments, and (2) the internal constraints of adjudication as a mode of social ordering. It further cautions that pursuing predictability while disregarding the low level of shared understandings regarding investment protection may cause more legitimacy problems than it solves
https://escholarship.mcgill.ca/concern/theses/2j62s986g
Keywords: Bilateral Investment Treaties (BITs); ISDS Reform; International Investment Law; Investments; Investor-State Dispute Settlement

Foreign Investments in Disputed Maritime Zones: Maritime Disputes as Events of Force Majeure in International Law and International Investment Contracts - Kassem, Hazem (BAU Journal - Journal of Legal Studies, 2020)
Sovereign rights in Exclusive economic zones and Continental shelves are functionally limited to the economic exploitation of these zones. Moreover, in the case of disputed maritime zones these sovereign rights are neither exclusive nor necessarily constant. Nevertheless, states are still expected to provide the investments established in these zones the same treatment they should provide in their territories where they exercise full and constant sovereignty. If a host state agrees to the establishment of an investment in a maritime zone that become later contested, do the occurrence of the contestation and the hazards arising from such contestation relief the host state from its contractual and treaty obligations toward the investment by virtue of the force majeure concept. This paper argues that a traditional interpretation of the force majeure concept in respect of investment agreements and contracts, hampers states ability to de-escalate their maritime disputes, diminishes its capacity to conclude delimitation agreements and reduces the promotion of the UNCLOS III as well as its mechanisms for disputes settlement. It proposes a contextualist interpretation of the force majeure concept that is adapted to the exploitation of disputed maritime zones and states obligations under the international law of the sea. First, it examines the concept of force majeure as a doc-trinal hypothesis and its applications in international contracts and international in-vestment agreements. Second, it analyzes the legal act of maritime contestation as a force majeure event according to the possible interpretations of the concept of “force majeure”. Finally, it examines the recurrent legal implications susceptible of arising out of a contestation; provisional orders and unfavorable delimitation and their qualifica-tion as a force majeure event in the realm of investment agreements and contract.
Keywords: BIT; Disputed maritime zones; Force majeure; Foreign investment; Investment contracts; Maritime contestation; Maritime delimitation; Provisional measures

Double taxation treaty interpretation : lessons from a case down under - Du Plessis, Izelle (Potchefstroom Electronic Law Journal, 2020)
In the Australian case of Bywater Investments Ltd v Commissioner of Taxation; Hua Wang Bank Berhad v Commissioner of Taxation (the Bywater case) the Australian High Court dealt with the question of whether certain companies were resident in Australia for income tax purposes. The majority answered this question by applying Australian domestic law. In a separate but concurring judgement, Gordon J also discussed the interpretation and application of the relevant double taxation treaty. This contribution analyses Gordon J's judgment to extract guidance from it for the South African courts on their interpretation of double taxation treaties. It is submitted that South African courts should also follow the "first step" proposed by Gordon J when interpreting double taxation treaties. South African courts may find Gordon J's judgment "instructive" when dealing with the interpretation of the "place of effective management" concept in both domestic law and double taxation treaties. In his judgment Gordon J favours the goal of common interpretation and it is argued that South African courts should follow this example and explicitly support this notion in applicable cases. From Gordon J's judgment and the judgement in Krok v Commissioner, South African Revenue Service, it is deduced that the positions in South Africa and Australia are similar in that the courts in both countries will be bound by the principles of Articles 31 and 32 of the Vienna Convention on the Law of Treaties when interpreting double taxation treaties. Moreover, Gordon J's judgment indicates that the domestic principles of interpretation should not be used in the interpretation of double taxation treaties. Recent South African cases have suggested that there are no differences between the South African domestic principles of interpretation and those contained in Articles 31 and 32 of the Vienna Convention on the Law of Treaties. This contribution submits that there are many similarities between the two, but that the rules are not exactly the same. South African courts should be aware of these differences and rather apply the rules of public international law, including those contained in the Vienna Convention on the Law of Treaties, when they interpret double taxation treaties. Gordon J specifically identifies the category of the Vienna Convention on the Law of Treaties in which he places the Commentary on the OECD Model Tax Convention, to rely on it for his interpretation of the relevant double taxation treaty. South African courts may well learn from this approach, to create more certainty in the process of interpreting a double taxation treaty.
http://hdl.handle.net/10019.1/124068

The Development of Accounting in Africa in the Era of International Financial Reporting Standards - Agyeman, Charles Gyamf (University of Westminster, 2020)
This thesis consists of two separate, but related studies on the development of accounting in Africa in the era of International Financial Reporting Standards. The first part of this thesis presents the first empirical test of a hypothetical classification of financial reporting in Africa based on de facto or actual practices as opposed to de jure rules. Three multivariate techniques (principal component analysis, cluster analysis, and multidimensional scaling) were used to analyse the accounting policies of large, listed companies in Africa that are required by law to adopt IFRS. It was found that there is a dichotomy between the IFRS policy choices of companies in Francophone and Lusophone countries, on the one hand, and those in common law jurisdictions, on the other, thus confirming the two-group classification schemes proposed by Elad (2015) and Nobes (1983). The results of this study extend previous research by demonstrating that international differences in financial reporting in Africa have survived in the era of IFRS and that pre-IFRS regulations enshrined in national and regional charts of account appear to have influenced IFRS policy choice. Furthermore, companies in common law countries tend to provide more extensive disclosures in their IFRS financial statements than their counterparts in code law countries. These findings have important policy implications, particularly in the context of recent recommendations of the World Bank, the International Monetary Fund, and the Pan-African Federation of Accountants that large entities in Africa adopt IFRS. The systematic differences in the choice of IFRS options between companies in civil law and common law jurisdictions suggest that it would be difficult to achieve internationalcomparability and consistency in financial reporting. The second part of the study uses semi structured telephone interviews to undertake interpretive accounting research (Baker and Bettner, 1997, p.293) to assess the perception of accounting professionals in relation to IFRS adoption and its use in Ghana. It concludes that despite the problems associated with its adoption and implementation, overall, International Financial Reporting Standards are viewed as necessary for the financial reporting needs of the country.
Keywords: Accounting classifications; CFA franc zone; IFRS practices; OHADA accounting system; Plan Comptable Général; SYSCOHADA

Economic Community of West African States at forty-five: a fool at forty-five a fool forever? - Nwosumba, Victor (African Journal of Politics and Administrative Studies, 2020)
Amid COVID-19 pandemic lockdown in the year 2020, Economic Community of West African States hereafter called ECOWAS quietly celebrated its forty-five years of establishment. Widely, much was not heard of or written about the community probably due to the challenges of the pandemic. However, the address of the President of ECOWAS Commission to the staff of ECOWAS institutions on the occasion of the commemoration of the community’s forty-fifth anniversary serves as a reminder that attention should also be given to this regional giant against all odds. Thus, the purpose of this paper is to celebrate ECOWAS at forty-five and then examine whether it is a fool at forty that is proverbially referred to as a fool forever. The paper, through thorough examination of the data collected from secondary sources finds that ECOWAS is still far from achieving its main mandate, its achievements as orchestrated by His Excellency, the President notwithstanding. The paper argues that the postponement of the establishment of ECO, a common currency for the region for the sixth time from 2020 to yet to be announced date, lack of realistic free movement of persons and goods among members and selfish interests of its leaders in the guise of national interest are enough reasons to conceive ECOWAS as a fool at forty-five. With the aid of constructivist theory,it concludes that even if ECOWAS at forty-five is still fooling around it has the chances of not being a fool forever if the leaders should turn a new leaf and pursue the attainment of the community’s mandate before its fiftieth anniversary.

Consumer protection in an electronic environment - Akhigbe, Iyen Joy (University of South Africa, 2020)
Consumer protection laws have not evolved on par with the development of electronic media. As a result, consumer protection laws do not address all major areas of legal concern that affect the electronic commerce (e-commerce) consumer. Furthermore, differing laws in the area of consumer protection make harmonised consumer protection neigh on impossible. Currently, there is a plethora of laws on the protection of consumers but most of these laws are within the sphere of conventional consumer protection legislation which does not adequately address the legal challenges posed by the proliferation of electronic transactions (e-transactions). Specific e-transaction laws are now to be found in certain international and regional documents emanating from organisations including: the United Nations (UN); the Council of Europe; the Organisation for Economic Cooperation and Development (OECD); the African Union (AU); the Economic Community of West African States (ECOWAS); the Southern African Development Community (SADC); the Common Market for Eastern and Southern Africa (COMESA); and the East African Community (ECA). These legal instruments have already been implemented in certain states’ national legislation, while other countries have yet to accede to them. Despite these legal instruments, e-commerce consumers are faced with inadequate or obsolete legislative provisions and are yet to enjoy full protection equivalent to that accorded to the “traditional” consumer. Furthermore, given the trans-national nature of the internet, divergent laws will inevitably prove to provide inadequate protection to e-commerce consumers. In this research, international and regional legislative instruments, as well as the national laws of selected countries such as the United States (US), the United Kingdom (UK), the Republic of South Africa (South Africa), the Federal Republic of Nigeria (Nigeria), and the Commonwealth of Australia (Australia) are examined. The strengths and gaps in each of these instruments and laws are identified with the aim of harmonising the principles they espouse in a single, cogent, and comprehensive body of rules which could take the form of an international convention. An international convention should be based on national and international best practices. The national adoption of the minimum standards espoused in the proposed Convention will ultimately, promote harmonisation.
Keywords: Borderless jurisdiction; Cooling-off; Cyberspace; E-agent; E-commerce consumer rights; Electronic transferable record; Hidden charges; Information; Keystroke error; M-commerce; Shrinkwrap; Single window facility; Terms and conditions; Transaction; Web-wrap; Wireless Application Protocol

Historical and comparative perspectives on trade union regulation with specific emphasis on the accountability of trade unions to their members - Greenhalgh, Bradley Paul (Stellenbosch University, 2020)
How do members hold their own trade unions accountable in South Africa? What legal mechanisms, if any, are available to assist union members in receiving adequate representation and service from their unions? This study approaches these questions through a comparative and historical examination of the regulation of the union member relationship in the UK, USA and the RSA. The study commences with an examination of what unions do, how they function and what benefits potentially accrue to their members, while the role played by unions in utilising collectivisation to offset the bargaining power of employers is demonstrated. The need for organised labour, by society in general, but South Africa specifically, is brought into sharp relief. This is, however, offset by the examination of 25 constitutions of broadly representative South African trade unions, where the lack of proper regulation of the union-member relationship is brought to the fore. This already means the common law and current judicial approach that is so reliant on the interpretation and implementation of trade union constitutions to address union-member disputes is unsuitable, certainly in those instances where the constitution is either silent or ambiguous, or where the nature of the relationship between the union and its member(s) mimics that of the constantly present imbalance of power and influence between employers and employees. The comparative examination of union accountability is undertaken against the backdrop of the common historical phases of proscription, acknowledgement/assimilation, and readjustment of and towards trade unions. The historical and contemporary regulation of the union-member relationship in South Africa is examined in the same way. The study demonstrates that purely statutory regulation of the union member relationship by means of punitive provisions and inter-union self-regulation measures are not feasible. A series of possible legal mechanisms – that draw from the comparative examination – are suggested, even though they are to be utilised in a collective (rather than individual) way. Even these suggestions, however, are subject to the challenges of cost-effectiveness, accessibility and efficiency of enforcement by (the) average union member(s). Three proposals are made to foster improved union member accountability: Firstly, the use of section 103A of the LRA by the Registrar so as to place unions that meet the appropriate criteria under administration, in order to restore accountable functioning and elevate the interests of the member(s) over that of the officials of the union; secondly, the introduction of a duty of fair representation – to be administered by the CCMA – to hold both union and employer accountable to members, and; thirdly, in conjunction with the first two proposals, the use of a package of further measures (and an associated information campaign), such as bolstering the financial/institutional capacity of the Registrar’s office, compelling the inclusion of accountability clauses within union constitutions, and minor amendments to the LRA with regard to balloting, reporting/transparency (and the enforcement thereof). If implemented, the expected outcomes are improved labour relations, increased accountability and professionalisation of trade union administration, a realignment of the employer-union divide and elevating the awareness of union member rights and concomitant obligations on trade unions – all of which are of critical importance in South Africa’s post-Marikana society.
URI: http://hdl.handle.net/10019.1/109343
Keywords: Labor union members; South Africa; Trade union accountability; Union security

Decompilation and copyright in ideas - the protection of non-literal elements of computer software and the idea/expression dichotomy - Jooste, Jacobus Petrus (Stellenbosch University, 2020)
The maxim, that copyright law does not protect ideas, is frequently challenged when the established principles are tested against new forms of expression or exploitation of a work. The evolution of computer programs, its unique characteristics and the increasing value of software as a commodity have resulted in a strained relationship between copyright law and the public interest regarding access to the underlying ideas in a computer program. This work examines the misalliance between copyright principles and the technical nature of computer programming, with a specific focus on the act of decompiling an existing program where it is undertaken in order to understand the underlying ideas and techniques. The impetus for this analysis is the sui generis classification of computer programs in South African copyright law and the potential this offers for development of domestic law in pursuit of national policy goals. This work conducts a normative analysis of the law and the technical reality of decompilation, from the perspective that copyright law must maintain a clear separation between the idea and the expression. The review of national and foreign copyright law is, throughout, conducted with a perspective on the effect of protection and a critical examination of the degree to which the law maintains an adequate balance between the private and public interests in the protection of software. In this respect, the current legal position is evaluated and a different, normative and prodevelopmental perspective regarding decompilation is proposed. It is submitted that are balancing of interests is justified and essential in order to establish an appropriate level of fairness and, at the same time, stimulate progress in this industry. It is argued that the act of using computer code to discover its meaning should not amount to infringement in the form of reproduction or adaptation of the work. It is found that the perception of decompilation, as a form of infringement, relies on an analogy to literary work. This view, it is argued, is ill suited to the nature of computer programs, at odds with the sui generis classification in SA copyright law, causes overbroad protection and violates the idea/expression separation. In light of the technical review of decompilation, it is found that the legal basis for prohibiting decompilation as a form of infringement is narrower than commonly assumed and that copyright law principles should be reinterpreted purposefully to permit decompilation. This work advocates that decompilation must be permissible and that an exemption, in SA copyright law, which is limited to decompilation for interoperability alone, is not appropriate in light of the national developmental agenda. Therefore, an alternative exemption is proposed which accommodates the technical reality of decompilation, the public interest in access to ideas and the commercial interests of copyright owners. This approach is supported by an analysis of international copyright law and is based on the inherent flexibilities of the three-step test. The justification for the findings of this work and the proposed departure from foreign precedent is supported by a close examination of the effect of a limited decompilation exception in foreign law and the impact of legislative measures to restrict circumvention of technological protection measures.
URI: http://hdl.handle.net/10019.1/109088
Keywords: Copyright; Copyright infringement; Decompilation; Intellectual property; International Copyright

Commercialization of Microfinance in Cameroon : How can Microfinance Institutions manage their dual social and commercial goals? - Singhe, Steffi Sandra (Université de Nantes, 2020)
La commercialisation de la microfinance a mis au premier plan la performance financière des I MF, les IMF adoptant désormais une logique commerciale de rentabilité en plus de leur logique sociale établie de lutte contre la pauvreté. Cela pose un défi de gestion crucial pour les IMF pour équilibrer l'aspect social et commercial de leur mission. Cette thèse vise à analyser comment les IMF surmontent leurs défis pour atteindre leur double objectif social et commercial. Elle s'appuie sur le concept de bricolage comme perspective théorique et sur une approche méthodologique abductive, exploratoire et qualitative. La thèse vise également à fournir une meilleure compréhension du secteur de la microfinance camerounaise, en termes de son histoire et évolution, et des défis spécifiques au secteur. L'étude identifie diverses pratiques de bricolage que les IMF utilisent pour faire avancer la réalisation de leur double mission. Les résultats suggèrent l'utilisation de ces pratiques de bricolage par les IMF pour mobiliser des ressources, renforcer la légitimité et accroître leur ou/reach, dans un contexte caractérisé par des contraintes de ressources. Ces trois résultats de bricolage se renforcent mutuellement pour faciliter la réalisation du double objectif des IMF. Cette recherche a également mis en évidence les quatre phases d'évolution du secteur de la microfinance camerounaise et les cinq principaux défis auxquels sont confrontées les IMF du secteur. Cette thèse contribue à la littérature sur la microfinance. Elle propose un nouvel regard sur la gestion de la double mission des IMF en montrant comment les IMF mobilisent les stratégies de bricolage pour faire avancer leurs objectifs sociaux et commerciaux. Elle met en lumière le lien entre la littérature sur la microfinance et le bricolage. The commercialization of microfinance has brought to the forefront the financial performance of MF!s, with MF!s now adopting a commercial logic of profitability in addition to their established social logic of poverty alleviation. This poses a crucial management challenge for the MF!s in terms of balancing the social and commercial aspect of their mission. The main aim of this thesis is to understand how MFls overcome their challenges so as to achieve their dual social and commercial goals. lt draws on the bricolage concept as a theoretical perspective and on an abductive, exploratory and qualitative research approach. The thesis also aimed to provide a better understanding of the Cameroonian microfinance sector, in terms of its history and evolution, and the challenges specific to the sector. The study identifies various bricolage practices that the MF!s use to advance the fulfilment of their dual mission. The findings suggest the use of these bricolage practices by the MF!s to mobilize resources, build legitimacy, and increase outreach, in a context characterized by resource constraints. These three bricolage outcomes reinforce each other, and they all strengthen the achievement of the MF!s' dual goals. This research also highlighted the four phases of evolution of the Cameroonian microfinance sector and the five main challenges faced by MF!s in the sector. This thesis contributes to the microfinance literature. lt offers a new perspective on MF! dual-mission management by showing how MF!s mobilize bricolage practices to advance their dual social and commercial goals. lt brings light on the link between the literature on microfinance and bricolage.
Keywords: CSR; Cameroun; Microfinance; RSE; Responsabilité sociétale; Régulation (théorie)

Tax Competition: Global but Virgin under Rwandan Law - Habimana, Pie (Recht in Afrika, 2020)
This paper’s foundation is the global character of (harmful) tax competition. While this phenomenon’s global existence is widely recognised alongside the…

International Commercial Arbitration - Kizi, Boratova Ziyoda Sobir (International Journal of Trend in Scientific Research and Development, 2020)
This article is devoted to the complex analysis of the English legislation of the international commercial arbitration. The author analyzed the commercial disputes and the bodies that proceed these disputes in England as well as main statutes regulating the international commercial arbitrations of England. The international commercial practices of the London International Court of Arbitration are described. Moreover, the author represents the main conclusions formed on the basis of the provisions of the national legislation on commercial arbitration and the regulations of the most well-known international arbitrations in England.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration Act 1996; Arbitration institution; Commercial disputes; International commercial arbitration; The LCIA Rules; The London International Court of Arbitration (LCIA)

The intersection of Public Procurement Law and Policy, and International Investment Law - Dagbanja, Dominic Npoanlari (Transnational Corporations Journal, 2020)
There is substantial scholarship on the limitations that international investment agreements (IIAs) place on States’ authority to regulate in the public interest. An area of fundamental importance that has not received scholarly attention in connection with IIAs is public procurement regulation. Given that public procurement is about the needs of States and their citizens, States would want to retain their authority within municipal public procurement laws to decide with whom to contract to meet those needs, and to pursue socioeconomic and industrial policies through procurement. However, most States are parties to IIAs, which impose obligations on them with respect to the protection of foreign investment. This article explores this seminal issue of whether IIAs stand to limit the authority of States in the implementation of procurement legislation and policies. Based on textual analysis and arbitral case study, it argues that treaty-based standards of investment protection can limit States’ authority on the implementation of methods of procurement (such as national competitive tendering or restricted tendering) and socioeconomic policies in procurement. A question that needs fuller engagement is the extent of conflict between specific IIAs and public procurement laws and policies, either regionally or globally, and how to reconcile conflicting obligations to promote foreign investment and sustainable development. This article provides the foundation for such future research.
http://hdl.handle.net/10019.1/124422
Keywords: Foreign (International law); Investments; Methods of procurement; Socioeconomic policies; Sustainable development

Relationship between corporate social responsibility practice and its effects on the botton-line - Tandoh, Isaac; Aovare, Ayishetu (International Journal of Innovation and Scientific Research, 2020)
The study comparatively evaluates the relationship between Corporate Social Responsibility and Profitability in the fuel and gas sectors in Ghana. The descriptive survey design and quantitative methods was adopted to find a relationship between innovations in strategic stakeholder engagement with corporate profitability or bottom-line, with the mediating role of strategic stakeholder engagement leading to a firm’s bottom-line. An analysis of strategic stakeholder engagement and bottom-line of selected fuel and gas companies in the Kumasi Metropolitan, Asokore Mampong, Oforikrom and Ejisu Municipalities was provided.A five point closed ended Likert Scale self-administrable structured questionnaire and researcher guide to aid participants answer relevant questions was used to confirm that innovations in strategic stakeholder engagement fueled increases in corporate bottom-line of selected companies. The four major steps of analysing data collected from Atkinson’s (2002) categories of quantitative data analysis was used, following which the primary data/information gathered and coded was analysed using the Statistical Package for Social Sciences to guarantee validity and reliability of the various investigations conducted. The hierarchical multiple regression of the Baron and Kenny’s (1986) procedure was also adopted to analyse for study the mediating effect of innovation on the relationship between strategic stakeholder engagement and corporate bottom-line.The study opines the involvement of key stakeholder participation in the siting and general operations of fuel and gas companies given the divergent viewpoints of operators and stakeholders (O’Riordan, 2017). A discovery of a statistically significant positive influence of perceptions of CSR towards customers on an organization’s image in general intensifies the suggestion that mangers of fuel and gas sectors take special interest in innovative ways of engaging strategic stakeholders due to its influence and ripple mediating effect on corporate bottom-line to improve the performance of the business or induces increases in profit.
Keywords: Brand; Corporate Social Responsibility; Employees; Image; Perception; Strategic Stakeholder

Transition to the Revised OHADA Law on Accounting and Financial Reporting: Corporate Perceptions of Costs and Benefits - Fossung, Micheal Forzeh; Ntoung, Lious Agbor Tabot; Santos de Oliveira, Helena Maria; Pereira, Cláudia Maria Ferreira; Bastos, Susana Adelina Moreira Carvalho; Pimentel, Liliana Marques (Journal of Risk and Financial Management, 2020)
This paper examines the ongoing transition to the revised Organisation for the Harmonisation of Business Law in Africa Act on Accounting and Financial Reporting for companies in general and to the International Financial Reporting Standards for listed and group companies with a particular focus on recent institutional developments and corporate concerns. The study used 80 professional accountants, most of whom were members of the Institute of Chartered Accountants of Cameroon and academics. Using the descriptive statistics, the study shows that the transition to the revised OHADA brings about a high level of comparability and transparency of the financial statements, that the International Financial Reporting Standards can be implemented in Cameroon (but not fully), and that the benefit of the transition exceeds the cost.
Number: 8
Keywords: Comparability; IFRS; OHADA accounting; perception; transition

The dispute board in international construction contracts - Nunziata, Martina (LUISS Guido Carli, 2020)
The dispute board as an alternative dispute resolution mechanism in international construction contracts. The functioning of the dispute board. Issues related to the legal nature and the enforcement of the final determination. Evaluation and familiarity with the mechanism of the dispute board. The Italian case and the distrust towards the development of "private justice systems".

The Changing Paradigm of International Tax Dispute Settlement: What Are the Promises and Challenges of Mandatory Arbitration for China? - Ji, Xueliang (Oregon Review of International Law, 2020)
Through comparing dispute resolution methods under bilateral investment treaties (BITs) and bilateral tax treaties, this Article critically discusses the advantages of incorporating mandatory arbitration in bilateral tax treaties and demonstrates that national sovereignty will not be decreased by it. As a result, the Article argues that it would, in fact, be beneficial for China to adopt the mandatory arbitration method, which would further strengthen the global reform initiated by the OECD.
Keywords: China; Dispute resolution; International tax law

An economic and legal analysis of trade measures against illegal, unreported and unregulated fishing - Ma, Xuechan (Marine Policy, 2020)
Illegal, unreported and unregulated (IUU) fishing threatens the ability of the aquatic systems to continue providing vital ecosystem services and essential food resources. Most of the existing economic analysis on IUU fishing is conducted from the perspective of IUU fishing vessels rather than that of States. This paper seeks to fill this gap and concludes that trade measures against IUU fishing are cost-effective for the international community, as the IUU fishing has reached such a substantial scale that the total harm or loss caused is estimated to be greater than the total abatement costs required. Meanwhile, from a legal point of view, trade measures against IUU fishing might have more tensions with international trade law than with the international law of the sea. This paper draws on relevant GATT and WTO jurisprudence for guidance to eliminate such tensions. Two other comprehensive solutions to ensure legal compliance of trade measures against IUU fishing include taking such measures on a cooperative basis and making use of the standard-setting process through competent international organizations or conferences such as the FAO.
Keywords: Economic analysis; IUU fishing; International trade law; The law of the sea; Trade measures

A review of the Libyan insolvency and restructuring laws informed by insolvency law theory and international benchmarks - Hosen, Emad-edden Rajab A. (Nottingham Trent University, 2020)
The research aims to evaluate the adequacy of the insolvency system in Libya to support the national desires and objectives identified in the country to enhance the national economy and to maintain social stability. The thesis considers the need for reform in the current business insolvency and rescue framework taking into account the country’s domestic circumstances. To conduct this evaluation, the research reviews the Libyan insolvency law by examining the theoretical approaches to corporate insolvency laws in order to understand the role that should be played, or the goal that should be reached, by the insolvency law. This is important to identify whether the insolvency and rescue laws should be concerned only about maximising economic interests or should be concerned also about wider societal interests and objectives. The study also undertakes an in depth evaluation of the current business insolvency and rescue framework by using the international benchmarks with particular reference to the UNCITRAL Legislative Guide on Insolvency Law. The thesis establishes that the current insolvency law is insufficient to promote the economic and social goals of the country because of both the deficiency of the legislative framework and inefficient institutions. The investigation reveals also that an application of the social justice theory as traditionally perceived by the Civil Code 1953 (as manifested in property law and contract law) that is primarily designed to achieve social goals (for example, the priority given to the wide-ranging category of privileged creditors over secured creditors) prevents the insolvency law from achieving the sought-after objectives leaving much to be desired for a reform. The research builds on these foundations to identify challenges and impediments to the development of the insolvency and rescue regime of Libya.
https://irep.ntu.ac.uk/id/eprint/41433/
Keywords: Company law; Corporate law; Insolvabilité; Insolvency; Libya; Procédures collectives; Restructuration; Restructuring law

Reimagining the Framework for Resolving Intra-African Commercial Disputes in the Context of the African Continental Free Trade Area Agreement - Onyema, Emilia (World Trade Review, 2020)
This article examines the effectiveness of the framework for the resolution of intra-African cross-border commercial disputes, arising from the projected increase in intra-African trade in goods, services, and investments under the African Continental Free Trade Area. It examines the peculiar nature of intra-African trade and of the participating entities to provide the context to discuss the three major processes adopted in commercial dispute resolution (litigation, mediation, and arbitration) in Africa. It then argues for the promotion of arbitration as the dispute resolution process of choice for such disputes. It reimagined the framework for arbitration at the continental level and made two proposals targeted at the greater efficiency of the process: the designation of Regional Arbitration Centres across the African Union's eight recognized Regional Economic Communities, to administer such references; and the establishment of an African Commercial Court as a one-stop court for the enforcement or annulment of the final award.
Number: 3
Keywords: AfCFTA; Arbitrage; Arbitragem; Arbitration; Commercial dispute; Dispute Resolution; Litigation

The Impact of Employee Board Representation on the Firm’s CSR Engagement : evidence from the French Context - Boukadhaba, Amal (Le Mans Université, 2020)
Cette thèse propose d’examiner la relation entre la représentation des salariés dans le conseil d’administration et l’engagement RSE de l’entreprise. En particulier, nous étudions comment les investisseurs perçoivent-ils le reporting RSE et laperformance ESG lorsque les salariés sont représentés au sein du conseil d’administration. En utilisant un échantillon de sociétés françaises appartenant à l’indice SBF 120 sur deux périodesdifférentes de 2001 à 2011 et de 2007 à 2017, nos résultats montrent que la présence des administrateurs salariés modère positivement la perception du reporting RSE et négativement la perception de la performance ESG par les investisseurs. Un examin plus détaillé montre que les administrateurs élus par les salariés par leur droit de travail améliorent exclusivement la performance sociale et modèrent négativement la perception des investisseurs vis-à-vis de la performance ESG. Au contraire, les administrateurs élus par les salariés actionnaires renforcent la performance ESG globale ainsi que les performances environnementale et de gouvernance et modèrent positivement la perception de la performance ESG par les investisseurs. Nos résultats mettent en évidence un conflit d’intérêts entre les actionnaires et les administrateurs salariés, notamment avec les représentants des travailleurs. Cette thèse couvre plusieurs disciplines à savoir la comptabilité, la gouvernance d’entreprise et lagestion des ressources humaines. En conséquence, elle intérèsse vivement les législateurs, les investisseurs, les managers et les actionnaires.
Impact de la représentation des salariés au sein du conseil d’administration sur l’engagement RSE de l’entreprise : Etude du contexte français
Keywords: Actionnariat du personnel; Administrateurs salariés; CSR reporting; ESG performance; Employee board representation; Firm market value; Gouvernement d'entreprise; Performance ESG; Performance boursière; Personnel – Participation à la gestion; Relations avec les actionnaires; Reporting RSE; Responsabilité environnementale; Responsabilité sociétale; Sociétés

The Applicability of Mediation as an Alternative Dispute Resolution Mechanism under OHADA Law - Leinyuy, Kifemmabuh Antonia (Scholars International Journal of Law Crime and Justice, 2020)
Almost 20 years after it adopted the Uniform Act on Arbitration, OHADA revised its Uniform Act on Arbitration and adopted a new Uniform Act on Mediation along with the fresh set of arbitration rules of the Common Court of Justice and Arbitration in Abidjan. These three texts were revised with the assistance of consultants. Among other changes, with the 2018 Uniform Act on Mediation, a solid platform for the use of mediation in the region is now in place. The ability of mediators to carry out their adjudication function with judicial intervention remains a major challenge by parties under the OHADA zones. In this light, the worry which this article seeks to uncover is how the new mediation law is applicable and facilitates the amicable settlement of investment disputes. The article also highlights the legal basis regulating the mediation process as a whole. In attaining these objectives, we employ doctrinal research methodology. The article conclude with vigorous recommendations which if effectively implemented will go a long way to enhance business (investment) security.
OpenAlex: https://openalex.org/W3035045968
Keywords: ADR; Alternative dispute resolution; Applicability; Dispute resolution mechanism; MARD; Mediación; Mediation; Mediação; Médiation; OHADA Uniform Act

The Effectiveness of the Harmonization Tool Adopted Under the Ohada Regime - Ceesay, Buba (Social Science Research Network, 2020)
The Organization for the Harmonization of Business Law in Africa, OHADA, is a regional entity whose primary objective is to harmonize the Business Law of its members. It has adopted legislative measures and institutional setups to ensure the realization of this object. This paper critically examined the effectiveness of the harmonization tool adopted under OHADA. The paper first gives a brief overview of OHADA setups, then the advantages and shortcomings of the harmonization tool adopted under the OHADA regime and finally concluded that though OHADA is a major step towards the attainment of harmonization of business law and Integration with the view of fostering development and business activities, its harmonization tool is lacking full efficacy towards the attainment of the objectives of the organization due to prevailing limitations and challenges.
Keywords: SSRN

The African Continental Free Trade Area: Toward a New Legal Model for Trade and Development - Kuhlmann, Katrin; Agutu, Akinyi Lisa (Georgetown Journal of International Law, 2020)
International trade law is at a turning point, and the rules as we know them are being broken, rewritten, and reshaped at all levels. At the same time that institutions like the World Trade Organization (WTO) face significant change and a global pandemic challenges the rules of the market, Africa’s new mega-regional trade agreement, the African Continental Free Trade Area (AfCFTA), is emerging as a promising framework for redesigning international economic law. As this Article will argue, the AfCFTA presents a new normative approach to trade and development that is positioned to rewrite the rules in a more inclusive and equitable way and, over time, possibly affect global trade well beyond the African continent.Historically, trade and development have been linked through the framework of Special and Differential Treatment (S&D), which has been a central feature of the WTO and is increasingly shaping regional trade agreements (RTAs) as well. Although the connection between trade and development is more important than ever before, traditional S&D is not positioned to deliver on broader priorities of social and economic development in the current international climate. Fortunately, as this Article will argue, Africa’s approach under the new AfCFTA sets the stage for a needed refresh of S&D. While the AfCFTA incorporates traditional aspects of S&D, it also includes elements of a forward-looking, rules-based approach to further economic and social development, advancing the Sustainable Development Goals (SDGs). This new dimension of S&D holds great potential for promoting integration through trade, representing the needs of a diverse group of countries in the rulemaking process, and reshaping international economic law more broadly to generate positive development outcomes. This Article begins with an assessment of the AfCFTA as an alternative model for trade and development law, evaluating the agreement in the historical and evolving context of S&D and examining its role in shaping a new normative approach to S&D. The AfCFTA, we argue, represents a shift from using S&D as a largely defensive trade approach to one that positions S&D as an affirmative tool for achieving sustainable development through the design and implementation of the rules of trade themselves, while still maintaining flexibility for countries that need it. This new approach may finally replace the old trade paradigm of the ”haves and have nots” with a system in which trade rules can be designed to benefit all. Although the AfCFTA is still at an early stage and will have to overcome formidable challenges, this Article provides an initial assessment of the AfCFTA’s proactive new model in the context of the substantive areas of law identified as next-stage (Phase II) negotiating priorities: intellectual property rights (IPR), investment, and competition law. The Article’s comparative assessment draws upon the laws of African nations, African and international RTAs, and other proposals for international legal reform. Finally, the Article looks to the future, positing that the AfCFTA could be the best legal instrument available to break the stalemate in international rulemaking, design new trade law approaches to pressing issues like global health and food security, and close the loop between trade rules and development goals, including the seventeen SDGs. As the AfCFTA is rolled out and implemented, it could have a profound impact on trade and development law, reshaping the rules for Africa and perhaps the world as well.
Keywords: AfCFTA; African Continental Free Trade Area; International Economic Law; International Trade

International Investment Law in African Courts - Mbengue, Makane Moïse; Schacherer, Stefanie (International Investment Law: An Analysis of Major Decisions, 2020)
This chapter identifies major categories of situations, events and institutions in which or through which questions of international investment law have been dealt with before African courts. The chapter is selective in nature and aims at showing tendencies instead of exhaustivity. A noteworthy tendency that becomes apparent through the chapter’s analysis is that the prevailing narrative of bypassing African courts and tribunals seems declining in importance as an increasing number of national investment law instruments foresee African judicial and arbitral institutions for the settlement of investment disputes.
Keywords: African national courts; Apartheid; EAC; ECOWAS; Investment arbitration; Land reform; National investment law; OHADA

Trade in Services in the African Continental Free Trade Area: Prospects, Challenges and WTO Compatibility - Simo, Regis Yann (Journal of International Economic Law, 2020)
This article engages with the recently adopted agreement for the African Continental Free Trade Area (AfCFTA) in the area of services. While services trade had heretofore stood at the queue of African trade pacts, the AfCFTA breaks new grounds by negotiating goods and services concurrently, signalling a paradigm shift and a commitment to a deeper integration of the continent. Upon Members’ implementation of the Protocol on Trade in Services, whose aim is to establish a single market in services, the region will be the largest economic integration agreement ever concluded since the birth of the World Trade Organization (WTO). This paper sets out to analyse the provisions of the Protocol and how they contribute to achieving the objective of attaining a single market where services (alongside goods, people and capital) move unrestricted.

State aid to state owned enterprises in South Africa : the need for a comprehensive State aid policy : a competition law inquiry - Afrika, Sasha-Lee Stephanie (Stellenbosch University, 2020)
The Competition Act 89 of 1998 applies equally to all firms with regard to anti-competitive behaviour regardless whether it is privately or publicly owned. Therefore it applies to stateowned enterprises (SOEs) if their actions fall short of the Act. There is however one aspect relating to SOEs which is not covered by the application of the Competition Act but may have a significant impact on free and fair competition and can be of big concern for private competitors of SOEs. Since discriminatory policies during Apartheid have created a huge inequality gap in post-Apartheid South Africa, the government has to be actively involved in the economy to address the inequality. Therefore the government uses SOEs as vehicles to achieve its developmental goals. As a result SOEs in South Africa which are active market participants may always rely on the financial support of the state. They may do so purely because of their crucial governmental mandates regardless of financial mismanagement, poor corporate governance and deep seated corruption in almost every SOE. Even though the fundamental need for the existence of SOEs in South Africa is acknowledge, it is argued that state financial aid could qualify as a state-initiated constraint on competition in South Africa as it creates an uneven playing field between SOEs and their private competitors, which is always skewed in favour of the SOEs. It may create warped incentives and SOEs may not compete efficiently if they know that they are protected by a state sponsored safety net. This dissertation asks the question whether the time has not arrived in South Africa for state aid to SOEs to be subjected to a certain degree of scrutiny in order to bring about a level playing field between SOEs and their private competitors. It is recognised that privatisation of SOEs is not always the better option as it could threaten the delivery of basic services and goods to poorer South Africans. Hence, the dissertation investigates whether a state aid control model, based on the European Union state aid rules, is not perhaps a solution to address the potential distortion of free and fair competition by state financial aid. It proposes a customised state aid control regime for South Africa which provides for an active role by the competition authorities in state aid decisions and it presents draft legislation which could be used as a basis for the implementation in South Africa of a regulated system of state financial aid to SOEs (and even private enterprises where applicable).
URI: http://hdl.handle.net/10019.1/108193
Keywords: Government business enterprises; South Africa; State aid; State-owned enterprises; Unfair competition

The Opportunity for Convergence of SYSCOHADA towards IFRS Standards: An Effect of Coercitive and Mimetic Isomorphism - Souleymanou, Kadouamaï; Mouafo, Cédrick Nzokouo (Journal of Modern Accounting and Auditing, 2020)
The last few years have been marked by the increase in power of IFRS international accounting standards. From the full or partial adoption to the gradual convergence, many countries have displayed a strong preference for these standards. Meanwhile, the implementation of International Financial Reporting Standards (IFRS standard) in the context of developing countries is not trivial. We are witnessing an unprecedented clash between the authors who support the interest of these standards for developing countries, and those who conversely demonstrate that these norms are not well adapted to the context of those countries. Falling within this problematic, this thesis analyses the issues and determinants of the convergence of the Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) accounting system towards IFRS international accounting standards in view of the reforms introduced by the last revision. From a sample of 10 companies, among which two local firms, two international firms, three publicly traded companies, and three not listed other companies, we show that the current convergence towards international accounting standards follows an effect of coercitive and mimetic isomorphism. In so doing, the timely implementation of these standards in the context of Cameroon is contingent with a number of structural and environmental factors that call their pertinence into question.
Keywords: Convergence; Developing countries; IFRS; SYSCOHADA; Système Comptable OHADA

The Effect of EU State Aid Law on the Future of EU Investment Policy - Finckenberg-Broman, Pamela (Griffith University, 2020)
On 1 July 2017, the Commission of the European Union (Commission) announced that investor state dispute settlement (ISDS) was dead. Apart from the fundamental public distrust of ISDS, its rejection by the European Union (EU) is a symptom of several underlying causes, the foremost of which is the need to protect the autonomy of the EU legal order and its right to regulate public policy objectives, as well as to avoid jurisdictional conflicts. With this backdrop EU state aid law, which enjoys public policy status, has emerged as a major example of the conflict between investor protection and the right to regulate. As state aid law imposes measures on the EU Member States that conflict with these states’ international obligations to foreign investors under bilateral investment treaties (BITs), they have become subject to claims and substantial liabilities. This dilemma can arise in any setting that involves the EU or one or more of its Member States. It also includes relations with non-EU countries, as the web of international investment agreements (IIAs) operates, in different forms, on an international scale. Therefore, this dilemma and the EU’s responses to it is analysed through the different forms in which EU state aid law appears, dependent on the EU investment policy aspect utilised as a platform for analysis. Utilising a doctrinal analysis by studying, discussing and analysing the impact of EU state aid law on the EU Member States’ BITs and EU Trade Agreements, this dissertation provides an insight into the function and logic behind international treaties involving the EU’s competition and investment policy. This is done by utilising the research question: How does the European Union (EU) state aid law affect the future of EU investment policy in a global context? Further, this thesis puts forward three arguments in which EU state aid law is affecting the future of EU investment policy in a global context. First, state aid law applies in the EU’s incorporation of clauses promoting fair competition and state aid policy in international trade agreements. Second, state aid law and policy has contributed to recent EU internal development, which led the EU Member States to terminate their bilateral agreements with each other (intra-EU BITs) by the end of 2019. Third, the EU has been working towards replacing the existing BITs between the EU’s Member States and third countries (extra-EU BITs) with the EU’s own trade agreements, which are aligned with EU legislation. Essentially, this thesis golden thread is a debate on who gets to decide on the scope of state aid law now and in the future. In other words, is it the EU that sets the borders and the status of state aid law and policy law regarding investment protection or the international investment tribunals by their legal practice? Hence, this thesis offers a glimpse of a conceivable future of EU investment policy in a global context. An analysis of the relevant literature, and observation of recent policy changes on its subject matter, as reflected in the Commission’s policy documents, the EU’s international agreements and declarations by the Member States, leads to the findings of this dissertation. A conflict situation that originated from legal conflicts within the EU, the EU experience of investment protection and state aid regarding intra-EU BITs, provided some lessons to learn for the EU organs. These lessons learned have found expression on a global scale. By incorporating fair competition and state aid policy in international trade the EU is reasserting that it is the EU that decides on state aid law and policy law regarding investment protection. Indeed, the EU is attempting to tame investment protection in such a way that fair competition and investment protection can peacefully coexist in international trade. Ultimately, the interplay of state aid and the EU’s investment policy within the internal market reflects on the external trade relations of both the Member States and the EU through this practice. Thus, state aid law affects and will continue to affect the future of EU investment policy in a global context.
Keywords: EU; European Union; Investment protection; Investments; Policy Law; State aid law

The Standards for Proving Damages and Its Amount: A Comparative Study under Transnational Instruments and International Arbitration Awards - Shoarian, Ebrahim; Sahebjam, Sara (Public Law Researsh, 2020)
Defining the applicable standards for proving and measurement of damages constitute one of the most significant issues under the law of damages. In principle, an aggrieved party, who claims compensation for damages based on contractual liability is responsible for showing the existence and the amount of losses suffered or to be suffered. Due to great importance of the issue, transnational instruments of contract law, such as UNIDROIT Principles of International Commercial Contracts (UPICC), Principles of European Contract Law (PECL) and Draft Common Frame of Reference (DCFR) have set out, explicitly or implicitly, special standards such as reasonable certainty, reasonably likely to occur and so on for proving damages; By contrast, the Iranian laws and regulations including the Civil Code do not set out such standards. The legal scholarship and jurisprudence have also failed to address the issue. Therefore, a comparative study of the issue with particular look at international instruments and arbitral awards could provide a reliable source of guidance. This paper analyzes the general and specific standards for proving damages and those situations that fall outside of ambit of the standards such as late payment damages. By doing so, the paper tries to open the debate in Iranian law. یکی از موضوعات قابل توجه در حوزه حقوق خسارت، تعیین استانداردهای قابل اعمال برای اثبات خسارات و میزان آنها است. علی القاعده، زیان‌دیدهای که به استناد مسئولیت قراردادی برای مطالبه خسارت اقامه دعوی میکند، بایستی اصل و میزان خسارتی را که متحمل شده یا خواهد شد، به اثبات برساند. نظر به اهمیت موضوع، اسناد فراملی مربوط به حقوق قراردادها از جمله اصول قراردادهای تجاری بینالمللی، اصول حقوق قراردادهای اروپا و پیشنویس طرح مشترک مرجع، به صورت صریح یا ضمنی، استانداردهای مشخصی مانند قطعیت متعارف، وقوع محتمل متعارف و غیره را برای اثبات خسارت پیشبینی کردهاند. در مقابل، مقررات موضوعه ایران از جمله قانون مدنی؛ چنین استانداردهایی را تنظیم ننموده و موضوع نیز مورد بررسی حقوقدانان و رویه قضایی قرار نگرفته است. بنابراین، مطالعه تطبیقی موضوع با نگاهی ویژه بر اسناد بینالمللی و آرای داوری می‌تواند منبع قابل اتکایی برای طرح بحث باشد. این مقاله، استانداردهای عام و خاص اثبات اصل خسارت و میزان آن و نیز مواردی مثل خسارت تأخیر تأدیه را که خارج از قلمرو شمول این استانداردها هستند، مورد تحلیل قرار میدهد و در نهایت تلاش دارد تا باب بحث را در حقوق ایران بگشاید.
Keywords: Arbitral Awards; Reasonable Certainty; Reasonably Likely to Occur; Standard for Proving Damages; Transnational Instruments; آرای داوری; استاندارد اثبات خسارت; اسناد فراملی; قطعیت متعارف; وقوع محتمل متعارف

Corporate Social Responsibility and Organizational Performance of Oil Companies in Southern Nigeria - Daubry, Powei Martin (Walden University, 2020)
In this study, the relationship between corporate social responsibility (CSR) activities and organizational performance (OP) of international oil companies (IOCs) operating within the Niger Delta Region of Nigeria was investigated. Grounded on the stakeholder theory, the problem being investigated involved the extent to which dimensions of CSR in terms of centrality, visibility, and voluntary contributions impact measures of OP (relational capital and employees’ commitment) specifically within the oil industry in Nigeria. Data for the study were obtained through a quantitative survey instrument from a sample of a population of individuals (N=270) living in host communities who are impacted by IOC activities in Rivers, Delta, and Bayelsa States. The results of the multiple regression analysis indicated a predictive model F (1, 268) = 774, p < 0.05, and R 2 = .742, which indicated that CSR was positively and significantly correlated with OP. In addition, centrality and voluntary contributions significantly affected OP. Also, centrality and voluntary contributions significantly correlated with employees’ commitment while only voluntary contributions significantly correlated with relational capital. The results of the study corroborated the need for CSR practitioners in the oil industry within the Niger Delta to operate in a socially responsible manner. The implications for positive social change include the potential for policy makers to use the findings to create mutually beneficial relationships that could contribute to resolving persistent adverse issues involving oil exploration and production in the Niger Delta Region by improving the socioeconomic dynamics of the host population, not only in the region, but also throughout Nigeria and similar countries.
Keywords: CSR; Corporate Social Responsibility; Nigeria; Oil companies; Organizational performance

Fall of Last Safeguard in Global Dejudicialization: The Problem of Protecting Public Policy in Private Business Disputes - Ghodoosi, Farshad (Oregon Review of International Law, 2020)
The importance of courts is shrinking. This is largely due to global dejudicialization: the process of outsourcing disputes to private dispute resolution. In the last several decades, along with the triumph of neoliberalism, privatization of the resolution of disputes has become the gospel of modern judiciaries. Courts have been pushed to the tail end of the private adjudication process and are used only as the last resort. The courts’ warm embrace of this structure along with practitioners’ push has led to a staggering expansion of private dispute resolution. The world therefore has witnessed an unprecedented growth of arbitration—the primary mode of private dispute resolution.
Keywords: Business law; Dejudicialization; Dispute resolution; Déjudiciarisation; Privatization; Public policy

The OHADA Structure as a Possible Model for the Development of a Commercial Law Structure in the Southern African Development Community (SADC) - Leno, Ngaundje Doris (International Journal of Social Sciences and Management Review, 2020)
The Southern African Development Community's (SADC) colonial legacy which introduced foreign legal traditions and the consequences of the diversity heighten the urgency for unified commercial legislation to deal with cross-border disputes.Thus, the issue is whether the Organisation for the Harmonisation of Business Law in Africa (OHADA) structure can serve as a possible model for the development of a uniform commercial law structure in the SADC .Despite the success of the OHADA, the author submits that the OHADA can only serve as a source of inspiration, or roadmap, providing guidance to the SADC drafters.The paper aims at demonstrating that the OHADA provides practical lessons for the development of a uniform commercial law structure in the SADC.The significance of this paper lies in the contributions it makes to the development of a commercial law structure in the SADC.
OpenAlex: https://openalex.org/W3124748692
Keywords: Development; Integration; Model; OHADA; SADC

Capital market effects of adoption of IFRS - Opare, Solomon (Victoria University of Wellington, 2020)
This thesis examines the impact of adoption of IFRS (International Financial Reporting Standards) on two aspects of the operation of capital markets. Firstly, the impact of adoption of IFRS on financial reporting comparability, market liquidity, and cost of capital. Secondly, the impact of adoption of IFRS on seasoned equity offering (SEO) underperformance. To examine the impact of adoption of IFRS on financial reporting comparability, market liquidity, and cost of capital, the study used meta-analysis of empirical studies published since 2000. Meta-analysis provides an objective view of the empirical results, in contrast to narrative reviews, which offer subjective conclusions. From meta-analysis of 55 empirical studies with 1,259 effect sizes, the study finds that IFRS adoption has increased financial reporting comparability, market liquidity, and reduced cost of equity. For cost of debt, a decrease is observed only for voluntary adoption. The meta-regression analysis shows how the results differ across mandatory and voluntary adoption of IFRS and that the measurement choices, type of control variables, study design, and strength of empirical results explain the variation in the observed effect of adoption of IFRS. To examine the impact of adoption of IFRS on SEO underperformance the study analyses a large sample of SEOs from 51 countries over the period 1992-2017. Given that the empirical literature on SEOs has established that information asymmetry contributes to SEO underperformance, it is important to assess whether adoption of IFRS has reduced the uncertainties surrounding SEOs and, thus, subsequent underperformance. The study employs a control sample of non-IFRS adoption countries and applies a difference-in-difference (DiD) design to test for the incremental change for IFRS adoption countries over non-IFRS adoption countries. The study finds that SEO underperformance reduces for IFRS adopters relative to non-IFRS adopters in the post-adoption period. The reduction in SEO underperformance is influenced by increased disclosure, increased comparability, and number of accounting changes. The study also finds that the impact of adoption of IFRS on SEO underperformance exists only for firms in countries with strong enforcement, and is conditional on the implementation credibility of countries. The findings are robust to the application of a different measure of SEO underperformance. Overall, the study suggests that IFRS has had a positive impact on capital markets. However, increased disclosure, comparability, and credible implementation play important roles in realising the benefits of adoption of IFRS. Thus, policymakers of weak enforcement countries are encouraged to strengthen their institutional environment in order to reap the benefits that adoption of IFRS can provide to their capital market.
Keywords: Cost of debt; Cost of equity; Enforcement; Financial reporting comparability; IFRS adoption; Market liquidity; Meta-analysis; SEO underperformance; Seasoned equity offering

Protecting the Industrial Designs of Today and the Future - Samoylov, Vladimir (Victoria University of Wellington, 2020)
This study examines and critiques New Zealand intellectual property protection for industrial designs, taking into account that many New Zealand industrial design owners outsource manufacture of their designs to China. Industrial design, which refers to improving the aesthetics of products to increase their marketability, is evolving conceptually and practically. In New Zealand, copyright and registered design laws each protect, respectively, the visual expression and the “eye appeal” of an original design. As design practices evolve with advances in technology however, it is increasingly evident that industrial design is about more than just visual expression or “eye appeal”. Many designers are not focusing solely on product stylisation and decoration, but on the provision of a more holistic product experience for the consumer. The development process of industrial designs from concept to marketable product is also changing, with many New Zealand industrial design owners employing increasingly efficient design development strategies. The fast-paced, cost-effective infrastructure of China is often utilised by New Zealand businesses for the manufacture of industrial designs. This study therefore sought to determine how to appropriately protect New Zealand industrial designs, in light of: a. foreseeable advances in technology; and b. the fact that many New Zealand industrial designs are manufactured in China. To answer these questions, this study examined and analysed New Zealand’s copyright and registered design laws, taking into account not only existing protections, but also factors that are likely to be of significant relevance in the future, such as the impact on industrial design from developments in 3D printing and virtual reality. The Chinese intellectual property regime for industrial designs was also examined because China is a major trading partner and often, as noted, the locus of manufacture. The study included an empirical investigation, in the form of interviews with designers and design academics as well as legal practitioners specialising in intellectual property law. The input of the interviewees, together with the legal analysis, informed a series of suggestions and recommendations for New Zealand policy and its law-makers regarding how industrial design protection can be improved. A key finding of this study was that existing legal protections do not appropriately protect increasingly holistic designs, as well as new types of designs emerging from developing fields such as virtual reality. In assessing the appropriateness of protection, the interests of industrial design owners were balanced against the public interest in protecting the public domain. It is suggested that to achieve equilibrium copyright law should be expanded to protect design expressions for all senses. Moreover, new categories of copyright protected works should be introduced to accommodate emerging design. The definition of design in registered design law should also be reconceptualised in order to acknowledge new types of designs and evolving design practices. Industrial design owners who outsource manufacturing to China can protect their designs via copyright as well as design patent. However, enforcement of intellectual property protection is unsatisfactory in many areas of China. Therefore, New Zealand industrial design owners should also employ non-legal protection strategies. Interviews with successful businesses, in the course of the empirical investigation for this study, revealed that the leveraging of existing relationships of those with already established operations in China, and intentionally splitting an industrial design’s component parts for manufacture among several factories in different locations, are useful strategies to employ.
Keywords: 3D printing; Artistic Craftsmanship; China; Copyright; Doing business in China; Intellectual property; Multisensory Designs; Propriedade intelectual; Propriété intellectuelle; Registered design; Spare Parts; Virtual Designs; Virtual Reality

The Distributional Effects of Value-Added Taxes in OECD Countries - Thomas, Alastair (Victoria University of Wellington, 2020)
Most OECD countries’ value-added tax (VAT) systems apply reduced VAT rates to a selection of expenditure items in order to achieve distributional goals, and – to a lesser extent – social, cultural and employment-related goals. This thesis investigates the distributional effects of the VAT in OECD countries, and the merits of using reduced VAT rates to achieve distributional goals. The research adopts a microsimulation modelling approach that draws on household expenditure microdata from household budget surveys for an unprecedented 27 OECD countries. A consistent microsimulation methodology is adopted to ensure cross-country comparability of results. Non-behavioural VAT microsimulation models are first built to examine the overall distributional impact of the current VAT systems in each country. The research assesses the competing methodological approaches used in previous studies, highlighting the misleading effect of savings patterns on cross-sectional analysis when VAT burdens are measured relative to income. Measuring VAT burdens relative to expenditure – thereby removing the influence of savings – is found to provide a more reliable picture of the distributional impact of the VAT. On this basis, the VAT is found to be either roughly proportional or slightly progressive in most of the 27 OECD countries examined. Nevertheless, results for a small number of countries (Chile, Hungary, Latvia and New Zealand) highlight that broad-based VAT systems that have few reduced VAT rates or exemptions can produce a small degree of regressivity. Results also show that even a roughly proportional VAT can still have significant equity implications for the poor – potentially pushing some households into poverty. Behavioural VAT microsimulation models are then built for 23 OECD countries to investigate whether reduced VAT rates are an effective way to support poorer households, and whether the use of targeted cash transfers would be more effective. The behavioural microsimulation methodology follows the Linear Expenditure System based approach of Creedy and Sleeman (2006). Complementing this approach, a Quadratic Almost Ideal Demand System (QUAIDS) is estimated specifically for New Zealand, thereby providing the first estimates of a QUAIDS model based on New Zealand data. Simulation results show that, as a whole, the reduced VAT rates present in most OECD countries tend to have a small progressive impact. However, despite this progressivity, reduced VAT rates are shown to be a highly ineffective mechanism for targeting support to poorer households: not only do rich households benefit from reduced rates, but they benefit more in aggregate terms than poor households do. When looking at reduced VAT rates applied to specific products, results are found to vary considerably. Reduced VAT rates specifically introduced to support the poor (such as reduced rates on food consumed at home and domestic utilities) are generally found to have a progressive impact, though rich households still receive a larger aggregate benefit than poor households. In contrast, reduced VAT rates introduced to address non-distributional goals (such as reduced rates on restaurants, hotels, and cultural and social expenditure) often have a regressive impact. Additional simulation results show that an income-tested cash transfer will better target support to poorer households than reduced VAT rates in all countries. Furthermore, even a universal cash transfer is found to better target poorer households than reduced VAT rates. However, results also show that it is very difficult for an income-tested cash transfer to fully compensate all poor households for the removal of reduced VAT rates. This is due to the significant variation in the underlying consumption patterns across households. While a small number of poor households lose out from replacing reduced VAT rates with targeted cash transfers, those that receive support are instead determined by income and family characteristics as opposed to consumption tastes – thereby increasing horizontal equity. Furthermore, many households are lifted out of poverty as revenue previously transferred to richer households is now transferred to poorer households. These results empirically confirm the theoretical expectation that, where available, direct mechanisms (whether via the income tax or benefit system) will better achieve distributional goals than reduced VAT rates. Countries that currently employ reduced VAT rates to achieve distributional goals should therefore consider removing these reduced rates and adjusting their income tax or benefit systems to achieve these distributional goals instead. Countries should also consider removing reduced VAT rates aimed at non-distributional goals where a more effective instrument is available to achieve the particular policy goal. At a minimum, the merits of these reduced VAT rates should be reassessed in light of their negative distributional impact.

Chinese Investment in Ethiopia: Contribution, Challenges, Opportunities and Policy Recommendations - Gebrehiwot, Berihu Assefa; Gebreeyesus, Mulu; Weldesilassie, Alebel Bayrau (PSI Research Report, 2020)
Recognizing the immense potential for greater Chinese investment promotion and its contribution to Ethiopia’s industrialization and acknowledging the gaps, this paper aims to conduct a rigorous research through analysis of secondary sources and qualitative survey of Chinese enterprise doing business in Ethiopia in various sectors. In this regard, the key policy questions that this study tries to answer are ‘the involvement in and the contribution to Ethiopia’s industrialization and the challenges and opportunities they face. Hence, the overall objective of this research will be to (i) assess the trends in Chinese enterprises involvement in Ethiopia’s industrialization for the last decade, (ii) inform both the Chinese government and Ethiopian government on key business barriers and market failures that are constraining Chinese business entry and growth in Ethiopia; (iii) investigate the immense untapped investment potential from China that can be attracted and opportunities that Ethiopia could offer to Chinese investors; and (iv) propose policy options on how to address the challenges and thereby maximize the opportunities to enhance Chinese investment towards Ethiopia’s industrialization.

Selected legal aspects of liability insurance - Jacobs, Wenette (University of South Africa, 2020)
Liability insurance concerns an insured’s insurance of its legal liability towards a third party for the latter’s loss. This specialised type of insurance is rather neglected in South African insurance law. There is a lack of understanding of the intricacies of liability insurance and its unique challenges. This flows primarily from its complex nature as third-party insurance, which involves legal obligations between multiple parties, and a lack of statutory regulation of the distinctive contractual aspects of liability insurance. Furthermore, limited authority exists on contentious legal aspects as a result of the relatively small number of judicial decisions in this field of law. It is also evident that liability insurance constantly evolves as new grounds of liability emerge and new insurance products develop in response to the changing demands of society. The rise of consumerism and the increase in third-party claims amplify the economic significance of the law of liability insurance in South Africa. A substantial knowledge gap remains in our jurisprudence, irrespective of the recent introduction of new statutory instruments aimed at regulating insurance practice in general. These reforms have not as yet been applied critically to liability insurance, and no specialised legislation in South Africa regulates aspects of this branch of insurance as is the case with microinsurance. The focus in this thesis is on two main issues: the insurer’s duty effectively to indemnify the insured, and the insurer’s defence and settlement of third-party claims brought against the insured. As a subsidiary theme, this thesis analyses legal uncertainties that may persist during pre-contractual negotiations, the liability insurance contract lifecycle, and even after the expiry of the contract. Legal challenges can be addressed by novel and creative application of the national law. Potential solutions can be gleaned from the other progressive jurisdictions reviewed – English and Belgian law. It is evident that this research may prompt Parliament to develop specific rules and regulations for liability insurance contract law. This thesis includes a check list of some of the most important disclosure duties for procuring liability insurance cover, its operation, and claims processes.
Keywords: Claims-made policy; Duty to indemnify; Indemnity insurance; Liability insurance; Liability insurer; Third-party insurance

The choice of non-state law in international commercial contracts - Abdullah, Humaira (University of Johannesburg, 2020)
When a dispute arises in relation to an act, person or property that is connected to more than one country, such dispute is governed by the rules of private international law, more commonly referred to as the “conflict of laws”.1 The term conflict of laws essentially means that the dispute in question will be governed by the national law of a country while having a connection to a foreign country,2 and is relevant to this discussion as the election of non-state law is an important aspect found within private international law. In order to determine whether or not such laws may be applied, courts usually look at the conflict of laws rules of that particular country... LL.M. (International Commercial Law)
Keywords: Commercial law; Conflict of laws; Contracts (International law)

Investor-state arbitration and African states: a proposal for a Pan-African investment court - Ama, Obiajunwa (Canterbury Christ Church University, 2020)
This thesis proposed for the reform of Africa’s Investor-State Dispute Settlement (ISDS) landscape through the establishment of a Pan-African Investment Court (PAIC) as a mechanism for the resolution of Investor-State Disputes. This proposal is influenced by the findings of my investigation on the functioning of Investor-State Dispute Settlement (ISDS) through the deployment of Investor-State Arbitration to resolve Investor-State Disputes between African states and foreign investors. This research is motivated by the criticisms of the Arbitration mechanism by a broad spectrum of constituencies within international investment law. These criticisms are primarily anchored on the legitimacy crises of ISDS, a dissatisfactory notion that denounces the deployment of the private mechanism and privity of contract ingrained investment arbitration framework to resolve publicly-inclined investor-state disputes. Ancillary to this critical holy grail are further dissatisfactions on the practical functionality of investment arbitration in aspects of high volume of cases against developing states, lack of diversity in the appointment of arbitrators and curtailment of sovereignty of host states through the intrusion of provisions of International Investment Agreements on legitimate internal decision-making powers. Consequently, this thesis investigated the practical functioning of ISDS in African states. After the study of the experiences of Egypt, South Africa and Tanzania; it was found that the legitimacy crises of ISDS also impacts on African states, and does not support their socio-economic and sustainable developmental aspirations. As a remedy, I proposed for a reform to an Investment Court System (ICS) through the establishment of a Pan-African Investment Court (PAIC). An evaluation of this recommendation was conducted that evidenced potential challenges that may mitigate its feasibility, thus leading to the advancement of two secondary reform alternatives vis the reform and retention of the current investor-state arbitration framework and engagement in innovative treaty-making practices by African states. To the best of my knowledge, this thesis has not been previously submitted in any higher institution or published by another person. The contents of this thesis are my ideas. Where the materials of others were used, due acknowledgement and reference was provided. Acknowledgements
Permalink: https://repository.canterbury.ac.uk/item/90873/investor-state-arbitration-and-african-states-a-proposal-for-a-pan-african-investment-court
Keywords: Arbitration; Investment Court System; Investments; Investor-State Dispute Settlement; Investor-state arbitration

Critical reflections on the development of integrated reporting: Are integrated reporting and IFRS competing frameworks? - Barker, R.; Teixeira, A. (The Routledge Handbook of Integrated Reporting, 2020)
Although integrated reporting emphasizes the contemporaneous relationship between financial and non-financial capitals, its primary purpose is to explain how an organization creates value over time. This is similar to the purpose of management commentary, which is part of a general-purpose financial report. We compare and contrast the information requirements of an integrated report with the type of information that supplements the primary financial information in general purpose financial reports, prepared in accordance with International Financial Reporting Standards (IFRS). We examine whether the information in those reports is intended to be forward-looking and predictive, whether non-financial capitals can (and should) be monetized in order to facilitate integration, and whether the reporting boundary should be drawn in different ways to serve different purposes. We find that the International Integrated Reporting Framework and IFRS do not serve different purposes or apply different approaches, but that – in essence – they are competing frameworks. While IFRS has highly developed standards for reporting financial capital, neither has a well-developed approach for reporting any other capital.

The development of the parol evidence rule and its impact on the interpretation and drafting of contracts - Dhlamini, Tshogofatso Elisa (University of Johannesburg, 2020)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Rights on news : expanding copyright on the internet - Furgal, Urszula (European University Institute, 2020)
The internet and digital technologies have irreversibly changed the way we find and consume news. Legacy news organisations, publishers of newspapers, have moved to the internet. In the online news environment, however, they are no longer the exclusive suppliers of news. New digital intermediaries have emerged, search engines and news aggregators in particular. They select and display links and fragments of press publishers’ content as a part of their services, without seeking the news organisations’ prior consent. To shield themselves from exploitation by digital intermediaries, press publishers have begun to seek legal protection, and called for the introduction of a new right under the umbrella of copyright and related rights. Following these calls, the press publishers’ right was introduced into the EU copyright framework by the Directive on Copyright in the Digital Single Market in 2019.
Accepted: 2020-02-20T11:26:15Z
Keywords: Copyright; Digital media; Electronic information resources; Intellectual property; Internet; Propriedade intelectual; Propriété intellectuelle

A critical discussion of the affected parties in business rescue proceedings - Gayadin, Kashmita (University of KwaZulu-Natal, 2020)
Abstract available in PDF.
Keywords: Companies Act 71 of 2008; Creditors; Financially distressed companies; Shareholders

Re-integration, rehabilitation and return-to-work of disabled workers : a comparative legal enquiry - Gresse, E. (North-West University, 2020)
There are many employment positions in the labour market that could be filled by the disabled of whom most, given the right environment, could be productive in the workplace. However, there are employers who still labour under the misconception that Persons with Disabilities (PWDs) are unqualified and unproductive although their participation in the workplace could contribute to the national economy, while restoring their dignity and social integration. The United Nations Convention on the Rights of Persons with Disabilities (CRPD) entered into force on 3 May 2008. The CRPD is the first international legally binding treaty aimed specifically at protecting the rights of PWDs. It is expected of ratifying States Parties to either amend their domestic existing laws or to enact new legislation in order to meet their obligations, as set out in the CRPD. In 2008, South Africa ratified the CRPD and the Optional Protocol, thus committing itself to the provisions relating to, inter alia, workplace integration. Article 26 of the Convention mandates States Parties to take effective and appropriate measures to enable PWDs to attain and maintain maximum independence, physical, mental, social and vocational ability, and to ensure their social inclusion. Article 27 stipulates, inter alia, that States Parties shall safeguard and promote the realisation of the right to work, including those who incur a disability during the course of employment. Legislation should make provision for, inter alia the following: • enable PWDs to have effective access to general technical and vocational guidance programmes; • placement services and continued vocational training; • promote employment opportunities and career advancement; • assistance in sourcing, obtaining, maintaining and returning to work; and • reasonable accommodation in the workplace as well as vocational and professional rehabilitation. Although the Compensation for Occupational Injuries and Diseases Act 130 of 1993 was amended recently to include rehabilitation, re-integration and return to work (RTW) as part of its objectives, it will be argued that South Africa needs to initiate targeted legislation and policies that make disability management functions mandatory. Employers’ obligations need to be set out clearly in the Act, because, as it stands, the following lacunae exist: • There is no obligation to appoint Case Managers; • Dismissal protection is not provided for; • The regulation of negative incentives to assist with RTW compliance is lacking; and • The roles of different stakeholders in the RTW process require clarification. Without South Africa having an appropriate and detailed RTW framework, ill or injured employees stand the risk of losing their jobs and becoming dependent on family members and/or disability grants. Against this background, a comparative analysis of international and regional law and the RTW practices of two foreign jurisdictions were made. This enabled the author to devise recommendations and identify the roles of the government, employers, employees and Case Managers. The primary objective of this thesis is to determine how and to what extent regional and international standards and RTW programmes in other countries could assist in developing and amending the current legislative and policy framework in South Africa to promote the RTW of disabled employees.
Keywords: Disability management; Persons with Disabilities; Re-integration; Rehabilitation; Return to work

Political business cycles, bank pricing behaviour and financial inclusion in Africa - Iddrisu, Abdul Ganiyu; Turkson, Festus Ebo (Cogent Economics & Finance, 2020)
This paper analyses financial inclusion in Africa focusing on the role of political business cycles and pricing behaviour of banks. We employ a sample of 330 banks operating in 29 African countries to test for two related hypotheses. Panel fixed and random effects were estimated for the period 2002 to 2013. The regression results that ensued suggests first that loan price increases in pre-election and election years. Building on this result and employing various specifications of financial inclusion, the second results suggest that, high bank loan prices in election years tend to increase financial access more, compared to non-election years, and that, high deposit price reduces financial usage but increases financial access in election years, compared to non-election years. By extension, these results have important policy implications for policymakers.
Publisher: Abingdon: Taylor & Francis https://www.econstor.eu/handle/10419/245317
Keywords: Africa; Banks' pricing behaviour; Election; Financial inclusion; Political business cycles

Protection of Intellectual Property Rights in International Trade - Indradewi, Anak Agung Sagung Ngurah (International Journal of Social Sciences, 2020)
That intellectual property is the creation of ideas in the form of new discoveries, literary works, and works of art, symbols, names and images used in trade. Of course, intellectual property is closely related to the world of commerce because its emergence is triggered by the desires of the members of the World Intellectual Property Organization who want to protect their economies in the era of free trade. In this case how the form of protection of intellectual property rights in the perspective of international trade, it can be seen that basically the laws and or regulations in every country in the world are different and each country has the right to implement its own legal rules in the jurisdiction of their country.
Keywords: Intellectual property; Intellectual property rights; International Trade; Legal rules

The effectiveness of the adopted OECD transfer pricing dispute resolution mechanisms in an African context - Kekana, Nelson Doctor (University of Pretoria, 2020)
With the developments happening globally that are aimed at curbing base erosion and profit shifting by multinationals, improving the resolution of transfer pricing disputes has been identified as one of the key issues. This thesis investigates the challenges uniquely faced by African countries that militate against the use of the OECD transfer pricing dispute resolution mechanisms. The thesis starts by reflecting on the effect of transfer pricing manipulation by multinational enterprises in Africa in particular. Transfer pricing manipulation is one of the causes of the so-called tax gap, which is, the gap between anticipated and actual revenue collection. The aggression by revenue authorities against transfer pricing manipulation in order to close this gap has triggered a lot of transfer pricing adjustments. These adjustments have resulted in multiple transfer pricing disputes. In the analysis of the adopted OECD dispute resolution mechanisms, the thesis focuses on the effectiveness of the mutual agreement procedure (MAP), the advance pricing arrangement (APA) and the mandatory binding arbitration (MBA). It identifies the problems that result in the failure of or the delay in the resolution of many transfer pricing disputes by analysing the domestic frameworks that exist in four African countries namely: South Africa, Kenya, Uganda and Ghana. The thesis identifies problems such as the absence of a tax treaty network within the African continent, the use of underdeveloped double tax agreements and the lack of commitment from African countries to subscribe to and ratify multilateral conventions. These problems delay or stifle the resolution of tax treaty disputes. They also cause uncertainty for taxpayers and lead to continued tax avoidance by multinational enterprises that essentially avoid paying tax in African countries where the economic activities of these enterprises take place. The thesis also identifies the importance of other OECD supporting tools such as the exchange of tax information in the resolution of transfer pricing disputes. It focuses on tools such as country by country reports, the master file, the local file and simultaneous tax examination as covered by the Multilateral Convention on Mutual Administrative Assistance in Tax Matters. The thesis contributes to the resolution of the identified problems with transfer pricing dispute resolution in Africa by recommending certain improvements that can be effected. These recommendations entail, regarding the MAP, the expansion of tax treaty networks by African countries and the establishment of a Tax Treaty Dispute Resolution Committee by ATAF. Regarding the APA, it is recommended that African countries should sign the multilateral instrument (MLI) and make use of advance tax rulings (ATRs) as alternatives. With respect to the MBA, this thesis recommends that African countries should use optional arbitration by effectively using article 25(4) of the OECD Model tax convention (MTC). It also recommends that African countries must enhance their tax transparency by ratifying multilateral conventions that seek to address international tax co-operation and to improve compliance with transfer pricing documentation requirements in order to make the resolution of transfer pricing disputes more effective.
https://repository.up.ac.za/handle/2263/80889
Keywords: Dispute resolution; Model Tax Convention; OECD; Transfer pricing

The law applicable to liability arising from the use of selfdriving cars in the wake of the Fourth Industrial Revolution : a global comparative analysis - Kyeremateng, Joshua Godwin (University of Johannesburg, 2020)
This study explores the liability associated with the use of autonomous vehicles. With the increase in efforts by automobile industries to manufacture driverless cars, the issue of liability occupies the front seat of the discussion. A major benefit of autonomous and connected vehicles is their potential to ameliorate, if not eradicate, avoidable accidents on roads. Currently, it is estimated that 90% of road accidents are caused by human error. The epoch of driverless vehicles, where the narrative will drastically change, is upon us. This means a shift away from human liability to machine liability, since these technologies have in-built algorithms to ensure autonomous decisions by the vehicle. Product liability becomes crucial in the wake of driverless cars. The gradual and ultimate shift of liability from the traditional human driver to the machine ‘driver’ coupled with the cross-border sale of driverless vehicles provide justification for scholarly attention. Accidents may now be attributed to technological error and not human mistake. Conflict of law issues become central in instances where manufacturers and users live in different parts of the world... LL.M. (International Commercial Law)
Keywords: Automated vehicles; Commercial law; International law; Products liability

Algeria and the African Union - between security and economic integration: a neofunctionalist and regionalist reading - Lamri, Amel (Canterbuy Christ Church University, 2020)
This thesis investigates the process of integration in the African Union (AU), and the reasons behind the slow progress of the AU to achieve the goal of deeper economic integration. In the research I explore the role of an AU member state in the process of African integration: Algeria. The research scrutinises the development of Algerian foreign policy towards the AU and highlights any changes in the Algerian FP attitudes and the reasons behind these changes. Similarly, the research unveils the reality of the decision-making process in this country, and the different agents that influence it. To achieve the main goals of the research, different theoretical choices were elaborated. This resulted in researching European integration theories; Neofunctionalism was, then, selected to study the Algerian development in the making of its foreign policy in general and towards the African Union specifically. Some concepts within the Neofunctionalist thinking were used including the principle of the shift of loyalties, the socialisation process, the spillover system, and the role of interest groups in the process of integration. Moreover, the theory of Regionalism was used to examine the process of integration in the AU discovering new reasons that led to the slow development of economic integration in Africa. Consequently, the research highlights the current obstacles and challenges that have hindered the process of economic integration in the AU, including the poverty of most of the AU member states, the limited financial budget of the Union and the instability of the majority of African countries. Furthermore, the research unveiled the lack of political will towards AU economic integration plans. Hence, this contribution extends beyond the traditional models of explanation, and discusses the situation in AU member states (in this case Algeria) and points to other factors as well such as the weakness of the lobbyist activities and business groups in Algeria specifically and Africa more generally. The thesis, then, focusses on Algeria’s supportive and active status in the AU security sector, highlighting how Algeria has been successful in pushing its own security and antiterrorism agenda to the AU level, thereby demonstrating that integration into the AU is possible, if it is backed by influential member states, and wider coalitions can be built to promote integration and cooperation.
Permalink: https://repository.canterbury.ac.uk/item/8y60y/algeria-and-the-african-union-between-security-and-economic-integration-a-neofunctionalist-and-regionalist-reading
Keywords: Africa Union; Algeria; Intégration régionale

An Empirical Analysis of Private Equity Investment Affecting Enterprise Value - Li, Jianhong (Université de Genève, 2020)
The lack of long-term and stable financial support for SMEs is the fundamental reason why enterprises cannot develop for a long time. At present, the situation of financing difficulties for SMEs is becoming more and more serious. Private equity (PE) investment has emerged as an important financing method. Private equity investment, while broadening the financing channels of SME capital markets, brings advanced management experience to enterprises, which helps enterprises to develop rapidly and effectively. According to the statistics of the Zero2IPO Research Center, the active investment institutions in China's equity market have grown from more than 200 in 2000 to more than 14,000 in 2018, with a total asset under management over RMB 9 trillion. Great progress has been realized in the scale and development of the industry. In addition, with the launch of the GEM in 2009, PE investment industry met new opportunities of development and became popular. At present, the development of China's PE investment business is still at an early stage. Neither relevant policies, laws and regulations nor supporting mechanisms are mature enough. Therefore, researches on China's PE investment business needs to be carried out. In this context, more and more scholars are beginning to focus on the field of PE investment. This paper focuses on whether PE investments can fundamentally increase the enterprise value. The basic theory is sorted out to serve as the theoretical basis for this study. Through a systematic analysis, this paper draws out 4paths of PE investment affecting enterprises, which are the influence on technological innovation, corporate governance activities, dividend distribution decision and earnings management, respectively. And through empirical analysis, it finds the empirical basis of the impact of PE investment on enterprise value, and investigates how PE investments affect enterprise value based on the difference in investment characteristics such as investment duration and whether the investment is joint or not. This paper conducts an empirical test by selecting the listed companies of the Shenzhen Stock Exchange GEM in 2015-2018 as sample. The results show that the investment of PE firm will significantly increase the value of the target enterprise. This paper makes a detailed analysis of sample data. The conclusion of the study is that private equity investment will have a significant impact on the value of target enterprises. Private equity investment plays an important role in the modern governance structure of small and medium-sized enterprises in China This paper enriches the existing literature and provides constructive suggestions for the health development of the PE investment market. 中小企业缺乏长期稳定的资金来源是企业无法长久发展的根本性原因，目前 中小企业融资难的形势越来越严峻，私募股权投资作为一种重要的融资手段应运 而生。私募股权投资在拓宽中小企业资本市场融资渠道的同时，给企业带来先进的 管理经验，有助于企业快速并有效的发展。据清科研究中心的统计数据显示，中国 股权市场活跃的投资机构已由 2000 年的 200 多家发展到 2018 年的 1.4 万多家，管 理资本量超过 9 万亿人民币，行业规模和发展实现了质的飞跃。此外，随着 2009 年创业板的推出，私募股权投资行业的发展业迎来了新的希望和契机，私募股权投 资业务开始盛行。目前，我国私募股权投资业务的发展还处于早期阶段，无论是从 政策还是法律法规再到配套机制，都还不够健全。因此，对我国私募股权投资业务 的研究亟需开展，在此背景下，越来越多的学者开始关注私募股权投资这一领域。 本文研究的重点是私募股权投资是否能够根本上提升企业价值。本文首先对 基础理论进行了梳理，以此作为研究的理论依据，而后论述了私募股权投资对被投 资企业价值影响的理论分析，。本文通过系统的理论分析得出了私募股权投资影响 企业的路径，并通过实证分析，得到私募股权投资对企业价值的影响的实证依据， 并且从投资期限和是否联合投资等投资特征的差异性，深入研究私募股权投资对 企业价值的影响方式。本文通过选取深圳证券交易所创业板 2015-2018 年的上市企 业作为样本，进行了实证检验，并得出以下研究结论:私募股权投资的参与会显著 提升目标企业的价值，同时，私募股权投资的期限越长、联合投资机构的数量越多， 目标企业的价值也会越高。 本文基于理论又结合实际，对样本数据进行了分析，研究的结论是私募股权投 资会对被投资企业的价值产生显著影响。私募股权投资对于我国中小企业的现代 化治理结构起到了完善作用。本文的研究结果丰富了现有文献，对私募股权投资市 场健康发展提出了建设性的建议。
Keywords: Enterprise Value; Investment Term; PE Investment

Corporate social responsibility and executive personality - Li, Xin (Simon Fraser University, 2020)
My dissertation investigates two streams of managerial accounting literature; specifically, corporate social responsibility (CSR) and executive personality. Paper 1 focuses on whether companies strategically engage in CSR practices to retain employees. Using a difference-in-differences design, I find that an increase in the enforcement of non compete agreements (which enhances a firm’s ability to retain employees) deteriorates CSR performance. Paper 2 extends prior literature and links managerial risk tolerance and firms’ CSR performance. The empirical result of Paper 2 shows that pilot CEOs are less likely to exhibit better CSR performance. Paper 3 examines the spillover effect of managerial risk tolerance along the supply chain. Specifically, I follow Paper 2 to use the pilot status of CEOs to proxy for the customers’ risk tolerance level. Overall, the results support a negative association between customer risk tolerance and supplier investment efficiency, and customer companies ran by pilot CEOs leads to supplier investment inefficiency. Each chapter is designed to be self-contained and provides a more detailed discussion of the research question and contribution.
Keywords: CEO; CSR performance; Corporate Social Responsibility; Non-compete enforceability; Pilot; RSE; Risk tolerance; Supplier investment efficiency

The regulation of international commercial arbitrators - Loreto Ilhao Moreira, João (University of Oxford, 2020)
International commercial arbitration has established itself as the main dispute resolution mechanism for international commercial disputes. This increased visibility has drawn attention to arbitrators’ public role, leading to a well-established general perception that arbitrators are bound to special obligations, such as the duty to be independent and impartial or the obligation to assure that arbitral proceedings are not abused to achieve nefarious goals. Despite this general acknowledgement, little attention has been paid to the mechanisms that ensure that arbitrators adhere to these obligations. In particular, there has been limited analysis of the underlying mechanisms that incentivise the production and enforcement of professional norms in this field. This thesis argues that the particulars of the arbitration market largely explains why the evolution of the regulation of international arbitrators has not matched those of other professions. At the same time, it will argue that those same particularities create incentives for several actors, most notably the arbitral community itself, to step in and occupy this regulatory vacuum. In particular, it explores the notion that the market strategies employed by arbitrators, arbitral institutions and other members of the arbitral community have the production of professional norms as a by-product. It further explores how the arbitral market tends to create an environment where compliance with professional norms is rewarded, leading, at the same time, the arbitral community to work as a network that promotes adherence to professional norms through mostly informal sanctions.
https://ora.ox.ac.uk/objects/uuid:c2dd717f-e53b-4ab6-b848-c089b70adec2
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration (international law); Arbitration market; Dispute Resolution; International commercial arbitrators; Regulation

The role of the Southern African Development Community (SADC) and the Economic Community of West African States (ECOWAS) in facilitating continental integration - Luthuli, Isaac (University of KwaZulu-Natal, 2020)
The dissertation examines the role the Southern African Development Community (SADC) and the Economic Community of West African States (ECOWAS) can play in facilitating the political and economic convergence of the African Union (AU) member states. The developmental challenges facing Africa in spite of its wealth of human and natural resources is poignant. The genesis of this problem can be traced to the history of colonialism and the wave of independence in the continent in the late 1950s. Arguments have been put forward to suggest that one of the most viable ways of promoting Africa’s development is by developing and promoting intra-continental trade which can be possible through continental integration. The specific areas reviewed are regional stability and how intra-regional trade and investment is used to promote economic convergence. Africa's need for political and economic integration at a continental level is further sustained by the assumption that neocolonialism can be blamed for the weakness of structures in African states. Some scholars agree on the idea that regionalisation is often seen to offer a possibility to respond to the challenges of globalization. This impact nevertheless is dependent on the relation between globalisation and regional sentiment. Regional integration implies a form of interdependence among nation-states. Such interdependence leads to an establishment of regional integration arrangements between sovereign states within a geographical space. These agreements are shaped formally and there is a commitment to work together in order to realise political and socio-economic benefits. This study maintains that in order to achieve effective integration of the continent, Nigeria and South Africa as case studies, as continental giants have a key role to play to this end and as members of ECOWAS and SADC respectively. It is argued here that both the SADC and ECOWAS as sub-continental blocks have made some notable and commendable progress in developing policies for trade liberalization and economic integration, this, however, is not enough as such policies are also pertinent at a continental level. The study found that SADC and ECOWAS as regional blocks can play a role in aiding the continent to achieve a trade liberalization to achieve continental economic development.
https://researchspace.ukzn.ac.za/handle/10413/18708
Keywords: African integration; ECOWAS; Economic Development; Economic convergence; Integration; Intra-continental trade; SADC

The role of the locus contractus as a connecting factor in common-law private international law of contract - Madziwa, Cuthbert Simbarashe (University of Johannesburg, 2020)
Global trade has consistently been on an upward trajectory over the past few decades. In 2001, the International Monetary Fund (IMF) estimated that over the course of the previous twenty (20) years world trade had grown at an average rate of six (6) percent per annum, double as fast as world output.1 A substantial component of global trade consists of cross-border transactions. It was projected that between 2010 and 2022, the number of global transactions would double from three (3) to six (6) trillion per year.2 These volumes of global trade naturally entail an enormous number of cross-border commercial contracts, which often result in disputes over defective goods or services, payment or, delays... LL.M. (International Commercial Law)
Keywords: Commercial Law; International law

Portability of social security benefits of circular migrant workers in selected SADC member states - Masoebe, P. (North-West University, 2020)
The issue of portability of social security benefits is a daunting issue facing migrant workers in both Southern Africa and the world in general. In the Southern African Development Community region migration seems to be driven mainly by the need to attain economic freedom. The fact of the matter is that migrant workers from Lesotho and Swaziland who work and have worked in South Africa do play a major role in boosting these countries’ economies. Another issue that cannot be ignored is the fact that circular migration as a phenomenon is unlikely to come to an end any time soon in this part of the world. This means that social security benefits of migrant workers and its portability should be an issue that is dealt with cautiously and speedily, especially in terms of looking at the millions of unclaimed social security benefits reported each year by social security funds and schemes in South Africa. While examining the extent to which selected SADC member states, namely Lesotho, Swaziland and South Africa, have undertaken to combat this issue, international and regional instruments that have a bearing on social security rights are analysed and the realisation is that in as much as these do provide for social security rights and portability of benefits thereof, a lack of ratification and implementation play a vital role in achieving efficient portability of these rights. Although South Africa, as the largest migrant-receiving country in the SADC region, does provide for the right to social security in its Constitution, the fragmented nature of its social security framework, together with other factors such lack of information, exploitation by employers, distances travelled to lay claims and a non-existent social security adjudication system means that migrant workers are normally left with lack of redress when their contracts of employment reach an end. On the other hand, Swaziland and Lesotho, as migrant-sending countries, do not even have provisions in their constitutions that specifically deal with the right to social security. This means that citizens who work abroad do not have sufficient social security coverage in either country, as well as in South Africa as a host country. Consequently, multilateral and bilateral agreements on social security are pivotal in addressing this issue of unclaimed social security benefits as they go a long way in making sure that migrant workers are provided with adequate social security protection and coverage as a whole. Migrant sending countries also need to undertake unilateral initiatives to guarantee that their citizens are adequately protected in this specific sphere of social security. Examples are further drawn from the best practices of different regions in the world, namely the Southeast Asian Nations Region, Caribbean Community and Common Market and the Southern Common Market. The above-mentioned regions have established multilateral social security agreements that seek social security protection for migrant workers who play an undeniable role in their economies. Bilateral social security agreements between Zambia and Malawi, together with the one between Sweden and Philippines, are taken into consideration as best practices that Lesotho, Swaziland and South Africa may draw examples from when drawing up and concluding their own bilateral social security agreements. The Philippines’ unilateral initiatives are also discussed and hailed as the best practices that migrant-sending countries such as Lesotho and Swaziland may further draw examples from. The Philippines has developed strategies aimed at guaranteeing social protection for its migrant workers abroad and further makes sure that it enters into bilateral agreements with any country that receives services from its citizens. While the need to conclude multilateral and bilateral agreements on social security cannot be denied, there is also a need for migrant-sending countries to come up with unilateral initiatives to lessen the burden on migrant-receiving countries in this social security domain. Sectors such as the mining sector should also have mining-specific agreements that specifically deal with issues related to migrant mine workers. Lack of statistics of migrant workers moving in and out of South Africa has also been labelled as one of the reasons halting access and portability of social security benefits; hence there is a need to develop a data-base aimed at keeping track of all migrant workers, retired and otherwise. Migrant workers who seek redress regarding access of their unclaimed or unpaid social security benefits also have to be provided with comprehensive protection from the courts of law. This therefore means that an adjudication system should be established to deal with social security woes so that those seeking redress have adequate legal support.
Keywords: Labour and social protection; Migrant workers; Multilateral agreements; SADC; SADEC; Social protection; Social security; Sécurité sociale; Travailleur migrant

Balancing the rights of creditors and consumers when a home is sold in execution: what procedures should be followed? - Mazubane, Zamanguni Sithabile (University of KwaZulu-Natal, 2020)
The sale in execution of theprimary residence of a consumer has numerous implications. This is especially in light of section 26 of the Constitution of the Republic of South Africa, 1996(‘Constitution’) which gives people the right to adequate housing and to not be arbitrarily evicted from their homes. The enactment of the National Credit Act 34 of 2005(‘NCA’) which aimsto balance the rights of creditors and consumers also impacted the procedure to sell homes in execution. In particular, section 129 of the NCA has pre-enforcement procedures whilst section 130 allows credit agreements to be reinstated if consumers can pay the overdue amounts and other costs in full. In addition, amendments were made tothe Magistrates’Court Rules and the Uniform Rules of Court regarding the sale of consumers’homes.The new requirements introduced by the NCA and procedures introduced by thecourt rules resulted in a great deal of confusion with different courts and judges adopting different approaches. Eventually, several matters which sought to sell consumers’homes in execution were heard in Absa Bank v Mokebe and Related Matters 2018 (6) SA 492 (GJ)(‘Mokebe case’). Van der Linde Jofthe Gauteng Local Division of the High Court, used the power granted in section 14(1)(b) of the Superior Courts Act 10 of 2013 to, in consultation with the Judge President, discontinue the hearing of the matters before him and refer the mattersto the full bench of the Division.In essence, the court held that a uniform approach must be taken by the judges of this Division regarding how they handle foreclosure matters. This thesis investigates the procedure that creditors should follow before they are entitled to sell consumers’ homesin execution. In order to do this, this thesis will examinethe Constitution, NCA, court rules, practice notesand case law. More specifically, the persons that are the focusof the investigation are creditors that have a security right in the form of a mortgage bond over the home,versus consumers who have become overindebted and are no longer able to meet their obligations under the loan agreement that was entered into with the creditors. There cent landmark Mokebe case is examined in depth to determine what the current law is and how it can be improved.Furthermore, the effect of the Mokebe case inother High Court Divisions in the country will be briefly discussed.Lastly, this thesis sets out what consumers can do to prevent their homes being sold on publicauction especially after they default in their payments. This thesis will show that the procedure to sell homes in execution has drastically changed from the pre-constitutional to the current constitutional dispensation. However, it is submitted that the procedures can still be improved upon. This is because the right to adequate housing is an important socio-economic right which has been undervalued and overlooked. The courts have previously allowed execution of homes without considering the circumstances of consumers. The court rules allowed for this as the contractual rights of creditors were held at a higher standard than the socio-economic rights of consumers. It is argued that in the light of the NCA and its aims, there must be an appropriate balancing of the rights of creditors and consumers to create just outcomes. If we are to truly create a society based on ‘human dignity, the achievement of equality and the advancement of human rights and freedoms’ as expressed in the founding values of South Africa’s Constitution and reiterated to a large extent in the NCA; foreclosure laws must also reflect that vision.
Keywords: Consumers; Creditors; Execution; Foreclosure; Human dignity; Mortgage bond; National Credit Act 34 of 2005

IFRS compliance, corporate governance and financial reporting quality of GSE-listed nonfinancial firms - Mbir, Deborah Esi Gyanba; Agyemang, Otuo Serebour; Tackie, George; Abeka, Mac Junior (Cogent Business & Management, 2020)
The adoption of International financial reporting standards (IFRS) has been presented in several empirical literature as a factor that could improve the quality of financial reports. However, Ghana has not attained the desired levels of financial reporting quality after the adoption of IFRS. Literature reveals that lack of proper enforcement of these high-quality standards may result in limited compliance and will undermine the effectiveness of these standards in terms of attaining high-quality financial reports. This study therefore argues that the relationship between IFRS compliance and reporting quality revolves around some enforcement mechanisms like corporate governance structures. In view of that, by using random effect estimation technique, this study examined the role of corporate governance in the relationship between IFRS compliance and the reporting quality of firms listed on the Ghana Stock Exchange (GSE). The study found that the right corporate governance mechanisms will enhance the positive effect of IFRS compliance on reporting quality. This study further recommends that to gain an appreciable level of public confidence in the annual reports of firms listed on the GSE, the audit committee’s independence and the board’s independence should be strengthened to ensure that management does not only adopt IFRS, but that the standards are actually complied with.
Keywords: Compliance; Corporate governance; IFRS; Reporting quality

A critical analysis of the subcontractor’s builder’s lien - Mdletshe, Sithandiwe Samukelisiwe (University of KwaZulu-Natal, 2020)
This research paper looks at the South African common law right to lien as it currently stands as the only compensatory remedy for a construction subcontractor in the event of non-payment by the main contractor. The nature and scope of the builder’s lien in this regard will be analysed and its limitations will be highlighted. Accordingly, having critically considered a potential alternative remedy, an unjustified enrichment claim, for the subcontractor, this research paper will illustrate that there is insufficient protection for an unpaid subcontractor in our legal system. Hence, there is a need for our common law builder’s lien to be developed into a statutory builder’s lien. An analysis of foreign jurisdictions legal position, in particular Canadian law, with regard to the construction subcontractor and the right to lien as a remedy has a commendable statutory measure in place to assist a subcontractor by attempting to prevent such a financial predicament and if it nonetheless still occurs, that in the event of non-payment, the subcontractor is adequately protected. This research project proposes that our legal system should take influence from the Canadian legal system and be developed in accordance with our legal framework in order for construction subcontractors to also have sufficient and effective protection under our legal system.
Keywords: Builder’s lien; Contract; Liability; Subcontractor; Unjustified enrichment

The Effect of IFRS Adoption on Foreign Direct Investment in Africa - Musah, Alhassan; Adjei, Eunice; Ahmed, Ibrahim Anyass (Journal of Applied Accounting and Taxation, 2020)
Adoption of International Financial Reporting Standards (IFRS) is supposed to help enhance comparability of financial statement, improve the quality of financial reporting and accounting information of businesses in a country. This is expected to help improve Foreign Direct Investment (FDI) in the adopting countries. This study examined the effect of IFRS adoption on FDI inflows in Africa. Unlike previous studies that sample both adopting and non-adopting countries, this study sampled only Africa countries that have adopted IFRS to determine whether the adoption has improved FDI inflows. To achieve this objective, 20 African countries that have adopted IFRS were sampled covering a period 1980 to 2015. Data was sourced from The World Bank financial and Economic Data. Control variables such as GDP growth, openness of the economy, government debt and population growth were included in the model. The correlation and regression analysis showed that IFRS adoption has a positive and significant influence on FDI inflows in Africa. On the other hand, open economy, government debt and population growth had a positive and significant association with FDI. Overall, the results show that African countries that want to improve FDI inflows must improve the quality of their reporting environment by adopting IFRS.
Keywords: Africa; FDI; Foreign direct investment; IFRS; IFRS adoption; Investments; Macroeconomic variables

The impact of cryptocurrencies on the general powers and duties of insolvency practitioners - Naidoo, Sidasha (University of Johannesburg, 2020)
Please refer to full text to view abstract. LL.M. (Commercial Law)

Fiscal Potential and Political and Institutional Constraints to Increasing Domestic Revenues - Niang, Birahim Bouna; Mbaye, Ahmadou Aly (Center for Global Development, 2020)

Arbitration related lessons: Insights from the supreme courts around the world - Nigmatullina, Dilyara; Vanlerberghe, Beatrix (b-Arbitra : Belgisch tijdschrift voor arbitrage, 2020)
In international arbitration, arbitrators have procedural powers that allow them to manage and conduct the arbitration proceedings in a fair and efficient manner. These powers are typically set out in the arbitration rules that the parties have agreed to, such as the International Chamber of Commerce (ICC) rules or the United Nations Commission on International Trade Law (UNCITRAL) rules. Arbitrators have the authority to determine the procedure to be followed in the arbitration, including the admissibility, relevance, materiality, and weight of the evidence presented. They can also decide on the language to be used in the arbitration and the location of the hearings. In addition, arbitrators can issue orders and directions as needed to ensure the fair and efficient conduct of the proceedings. This may include ordering the production of documents or witness testimony, or setting time limits for the submission of evidence. The present paper critically examines the lex arbitri, the law that governs the arbitral proceedings, and makes out a case that lex arbitri cannot be challenged in court, as the parties to the arbitration have agreed to resolve their disputes through arbitration rather than through the courts. However, if the tribunal exceeds its powers or acts in a manner that is inconsistent with the lex arbitri, the parties may have grounds to challenge the tribunal's decision on the grounds of lack of jurisdiction or due process. The paper summarises some key judgments in which Courts have upheld or quashed the Tribunals procedural orders. It will be concluded that the procedural powers of arbitrators in international arbitration are real and not perfunctory, though bounded within powers extended by Parties to the arbitral tribunal.
Place: Brussel
Keywords: Arbitrage; Arbitragem; Arbitration

The implication of the moratorium on lease agreements in business rescue - Nqwata, Sibahle (University of Johannesburg, 2020)
The purpose of the Companies Act1 is, amongst others, to “provide for the efficient rescue and recovery of financially distressed companies, in a manner that balances the rights and interests of all relevant stakeholders.”2 Business rescue means facilitating the rehabilitation of a financially distressed company by providing temporary supervision of the company, a temporary moratorium on legal proceedings against the company in business rescue and the development and implementation of the business rescue plan.3 As a result of the moratorium, the legal proceedings against the company may only be instituted with the consent of the business rescue practitioner or with the leave of the court.4 Thus, the moratorium is the cornerstone of business rescue as it provides a company with an opportunity to operate on a solvent basis.
Keywords: Contracts; South Africa; commercial law

A critical assessment of freedom of choice of law in international commercial contracts - Raissa, Kalenga Kalubi (University of Johannesburg, 2020)
Please refer to full text to view abstract. LL.M. (International Commercial Law)
Keywords: Commercial law; Contracts (International law); Foreign trade regulation

How will the information regulator manage and control advancements in technology to minimise its adverse effects on the protection of personal information? - Ramcharan, Sarika (University of KwaZulu-Natal, 2020)
No abstract provided.
Keywords: Data protection; POPIA; Personal information; Privacy infringements; Privacy protection; Protection of Personal Information Act; Right to privacy; Technology and privacy

The liquidation process and unsecured creditors: using the resulting trust to restore the balance - Stubbins, Matthew (Canterbury Christ Church University, 2020)
Ever since the formation of limited companies became permissible, unsecured creditors have faced a Sisyphean struggle to regularly recover substantial levels of the debts owed to them should corporate creditors enter insolvency. These low recovery rates result in many issues for lenders, including large losses, and in some cases, the insolvency of the lender themselves. The causes of these low return rates are long established and clearly demarcated. They consist of the existence and widespread use of security interests - which remove the majority of the company’s assets upon insolvency occurring - and the statutory priority of distribution, which ensures that parties other than the unsecured creditors have their debts discharged first by the liquidator from the already insufficiently resourced asset pool. English insolvency law has sought to provide some protection to the unsecured creditors through the anti-deprivation and personal liability provisions of the Insolvency Act 1986, which are intended to protect the integrity of the insolvent company’s asset pool. However, as concluded by this thesis, these provisions fail to afford adequate protection as a consequence of their substantive, evidential and remedial limitations, potentially resulting in the distributable assets being misappropriated and out of the reach of unsecured creditors. This thesis therefore analyses the limitations of the existing anti-deprivation and personal liability provisions before concluding as to how and why they fail to adequately protect unsecured creditors. This is done through a doctrinal and theoretical analysis of the provisions, before these conclusions are then tested empirically in two case studies. Given the inadequate protection provided by the Insolvency Act, this thesis then analyses the resulting trust – on which little analysis has been conducted in the context of insolvency – to determine whether it is capable of assisting unsecured creditors to increase their liquidation return rates. This increase is achieved through returning assets beneficially owned by the company to the company, or by preventing parties from becoming unsecured creditors in the first place by removing assets beneficially owned by them from the company. This analysis too will adopt a doctrinal and theoretical methodology, and it is concluded that the resulting trust is able to assist should the requisite factual matrices occur.
Permalink: https://repository.canterbury.ac.uk/item/8z4x2/the-liquidation-process-and-unsecured-creditors-using-the-resulting-trust-to-restore-the-balance
Keywords: Insolvabilité; Insolvency; Insolvência; Liquidation

Promoting financial inclusion through mobile money while introducing regulatory solutions to reduce and control money laundering in Lesotho - Taole, T. E. (North-West University, 2020)
Mobile money services have considerable potential in modern economies. They have the potential to increase financial inclusion for poor people and people excluded from formal financial services. This is because mobile money services can be accessed simply using a mobile cellular phone and the majority of people nowadays own mobile phones, including people living in the rural areas. Mobile money can therefore solve the problem of financial exclusion because even the people who live in the rural areas without access to formal financial services can now access financial services thorough mobile money services. Financial inclusion, on the other hand, is simply defined as a situation where every member of the society has access to and is able to use financial services offered by formal financial services institutions, such as banks and insurance companies. Financial inclusion has many benefits, the main benefit being the stimulation of the economy of a country. For mobile money services to operate smoothly and financial inclusion to be achieved, there must be enabling regulation. Regulation must not be so strict as to prevent mobile money service providers from operating. Regulation must allow for innovation and at the same time maintain financial integrity and stability by ensuring that financial crimes, such as money laundering, do not affect mobile money services. Although mobile money services can increase financial inclusion, regulators must be vigilant to ensure that they stop criminals from using mobile money services to commit money laundering offences. This research focuses mainly on mobile money services in the Kingdom of Lesotho. The aim is to find out how regulation can be improved to ensure that mobile money services can help to increase financial inclusion. The aim is also to find out how regulation can help to ensure that mobile money services operate smoothly, and that the crime of money laundering is prevented from affecting mobile money services. To achieve this aim, the research is divided into different chapters and in each chapter the aim is to find ways in which the main aim can be achieved. In the research, mobile money and financial inclusion will be defined and their importance in modern economies will be demonstrated in greater detail. Furthermore, the issues of money laundering will be discussed. The threat of the crime of money laundering will be highlighted. An analysis of the legal regulatory framework of mobile money services and money laundering in Lesotho will be undertaken to determine the extent to which these regulatory frameworks can help realise financial inclusion and promote mobile money services in Lesotho. The same discussion is made in respect of other African countries. The legal regulatory framework of Lesotho will be compared to the framework of other African countries to ascertain how mobile money services and money laundering and financial inclusion issues are regulated in those countries. The countries discussed in this research are South Africa, Malawi, Kenya, Nigeria, Uganda, Tanzania, and Ghana. Based on these discussions, some shortcomings in the legal regulatory framework of mobile money services and money laundering in Lesotho will be identified and the conclusion will be drawn that the two frameworks have to be revisited to ensure that mobile money services will operate smoothly in the Kingdom of Lesotho. Furthermore, recommendations will be made to address the legal shortcomings identified in the framework.
Keywords: Financial inclusion; Lesotho; Mobile money services; Regulatory framework

The Trajectory of Illicit Waste Trade in Africa: Implications for Human Rights and Sustainable Development - Umenze, Nnamdi Stanislaus (Journal of Law, Society and Development, 2020)
As globalisation intensifies, the environmental burden of economic development is being shifted to poor countries. This development manifests in waste trade involving the transboundary shipment of toxic waste from developed to developing countries. This article evaluates the strategies with which waste trade is being perpetuated to the detriment of sustainable development and human rights values in Sub-Sahara Africa. It argues that capitalism has influenced massive generation and commodification of waste, especially in industrialised countries. It has also established that globalisation has made the transboundary shipment of waste easy. Moreover, foreign investments in the waste industry in developing countries appear to be a means by developed countries to perpetuate waste shipment to developing countries, which helps waste traders to avoid stringent regulations and high costs of waste management in developed countries. Therefore, such investments in developing countries should not always be viewed as a breakthrough in attracting foreign investments. The findings made include that despite the existence of the Basel and Bamako Conventions at global and regional levels, respectively, waste trade has continued in different forms in Africa, where waste merchants exploit the low-cost facilities, cheap labour and weak regulatory frameworks. The trend includes the reckless dumping of hazardous industrial waste, electronic waste as well as ostensible investment in “dirty industries” in some African countries. It concludes by urging the states to individually establish robust mechanisms that protect the environment and enforce environmental rights. These measures will help complement the collective efforts they have made in multilateral and regional agreements.
Keywords: Africa; electronic waste; globalisation; human rights; sustainable development; toxic waste trade

The Use of Mediation in ISDS - UNCITRAL Working Group III Virtual Pre-Intersessional Meeting (Asian Academy of International Law Limited, 2020)
Keywords: ISDS; Investor-State Dispute Settlement; Mediation; Médiation

The adaptation of China’s maritime arbitration system to international legal norms and practice - Xuan, Yan (The University of Queensland, 2020)
Maritime transport is essential to the world’s economy and maritime arbitration plays a crucial role in maritime dispute resolution. Nowadays, many coastal jurisdictions have set up their own maritime arbitration institutions such as those in the US, the UK, Germany, Australia, China, Japan, Hong Kong, and Singapore. Building a national world-advanced maritime arbitration system as soon as possible to suit China’s rapid developments in shipping and international trading does not permit of any delay. How should China improve her laws, rules and institutions, including those for the enforcement of maritime arbitration awards, having regard to leading international maritime arbitration systems? It is posited that selective adaptation from the successful experience of other maritime arbitration systems is the most convenient and effective way to achieve such a goal. This adaptation will follow from a comprehensive and comparative study of the maritime arbitration laws, rules and the maritime arbitration institutions, including the laws relating to the enforcement of maritime arbitration awards, from these main global maritime arbitration centres in order to make China’s maritime arbitration more competitive at the international level. This thesis does not purport to cover every research field relating to maritime arbitration. Instead, as previously stated, it will focus only on the comparative study of some selected key issues of international commercial arbitration among the selected jurisdictions. A comprehensive study of international commercial arbitration or international maritime law is not the subject of this thesis. It should be noted further that this research basically concentrates on the practical problems of maritime arbitration practices, rather than taking an overly theoretical approach. The thesis selects the UK, the US, Singapore and Hong Kong as the target jurisdictions for comparison. Through selective comparative analysis of the key issues of maritime arbitration systems in the selected jurisdictions, which are internationally recognised as significant by many arbitration scholars, this thesis proposes that all these issues could conveniently be categorised into four key criteria; namely, fairness, confidentiality, efficiency and enforceability. It follows that the adaptations of the Chinese maritime arbitration system should mainly focus on these four criteria, as these are the most critical factors for the development of Chinese maritime arbitration system. Moreover, these four criteria should also have significance for other underdeveloped maritime arbitration systems. Also, based on these four key criteria, the thesis provides some specific suggestions on how the Chinese maritime arbitration system can be adapted to reflect other selected jurisdictions in the respects of some key issues of international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Confidentiality; Droit maritime; Efficiency; Enforceability; Fairness; Maritime arbitration

What drives individual decision-making of Foreign Direct Investments (FDI) to Sub-Saharan Africa - Yusuf, Mukhtar Abubakar (Case Western Reserve University, 2020)
This dissertation examines a multiplicity of factors that influence at the microeconomic level the level of Foreign Direct Investment (FDI). The main objective of the dissertation is to empirically explore and validate the effect of a select set of individual-level perceptual factors on FDI decisions. Given the paucity of research on the topic in comparison to macroeconomic studies of investment inflows between regions and countries, we conduct the study as a mixed-method study. The study consists of three interconnected empirical studies. The first seeks to identify the presence of factors that shape an individual’s decisions on FDI inflows. The two following ones seek to validate the effects of these factors on the individual decision maker's propensity to invest in a specific country. The first study belongs to a qualitative strand and answers the following research question: What are the investor’s critical perceptual factors and experiences that influence their FDI decisions? The study participants consisted of 30 foreign investors, the government’s Ministries, Departments, and Agencies (MDAs), and the Nigerian investors in the diaspora. The paper finds that on the supply side, several key FDI perception factors influence decision-making. On the demand side, there are four attractors and four repellents that influence potential investors' decisions. In the quantitative strand of the study, we offer the following questions: (1) To what extent do investment decision perception impact foreign direct investment (FDI) inflows? And (2) To what extent do the investors from Europe and North America and investors from Asia and Africa (the West and the East) influence what factors matter in foreign direct investment (FDI) decisions? The samples consist of 269 individuals from the private sector, both in Nigeria and in the diaspora that participated in the survey. I use structural equation modeling to find that Return on Investment (ROI), Security/Personal Safety, and Investment Facilitation Services have a significant direct effect on the FDI decisions. A post hoc exploratory analysis indicates positive relationships between Ease of Doing Business and Investment Promotion and FDI are significant for investors from the investors from Europe and North America as well as the negative impact of Corruption. In contrast, the positive relationship between Return-On-Investment and FDI is more substantial for investors from East Asia and Africa. The next part of the quantitative strand investigates (1) to what extent investment promotion services and Investment Facilitation effects in the receiving country shape positive investment decision outcomes, and (2) to what extent investment perceptions and related decisions vary across industry groups facing different investment horizons and risk levels. The analysis indicates that the Investment Promotion services significantly mediate Corruption Perceptions and Investment Facilitation services. And Investment Facilitation does moderate the effect of Investment Promotion. The exploratory industry-level analysis reveals that the effects of Return On Investment to FDI decisions and Security to FDI decisions significantly differ across Infrastructure-Mining/Services, Services/Agriculture-Manufacturing, and Agriculture-Manufacturing/Infrastructure-Mining industries suggesting significant Industry-level effects. Generally, these findings reveal much more refined and complex dynamics of FDI inflows and how individual investor’s perceptions shape them. Specifically, the results provide deeper insights into the investor’s risk perceptions that arise in a particular country. This depends on holistic perceptions of the country’s economic, political, and social environment, and also the investor’s time horizon and risk preferences signaling significant individual and situational differences in how decision-makers approach FDI.
Keywords: Corruption; Ease-of-doing-business; FDI; FDI attractors; Foreign direct investment; Investment decision-making; Investments; Nigerian Investment Promotion Commission; Perception; ROI; Return on investment; Security

The enforceability of interim measures granted by an emergency arbitrator in international commercial arbitration - Zhang, Junmin (ProefschriftMaken, 2020)
The emergency arbitrator mechanism makes interim measures possible for parties involved in international commercial arbitration before the constitution of arbitral tribunals under urgent situations. However, with the development of the emergency arbitrator mechanism, the enforceability of interim measures made by an emergency arbitrator is questioned. This uncertainty leads to the hesitation of legal practitioners to apply the emergency arbitrator mechanism in practice. The research conducted two comparisons between different arbitration rules and between arbitration laws in jurisdictions. After discussing the legal status of an emergency arbitrator, the legal criteria to render interim measures, the potential barriers for the enforceability, and possible harmonization, it concluded that the interim measures granted by an emergency arbitrator in international commercial arbitration should be enforced and even harmonized through mandatory and non-mandatory methods.
Keywords: Arbitrage; Arbitragem; Arbitral Tribunal; Arbitration; Arbitration Law; Arbitrator; Commercial Arbitration; Emergency arbitrator; Enforceability; Interim measures; International commercial arbitration